Reconstructing two decades of spatiotemporal change in estuarine ecological condition - Orlando Lam-Gordillo; Bruce D. Dudley; Emily J. Douglas; David Plew; Melanie Hayden; Arman Haddadchi; Rachel Hale; Andrew M. Lohrer (Marine Pollution Bulletin, 2026)

Acute thermal stress alters sperm swimming activity, viability, and gene expression in blue catfish, Ictalurus furcatus - Kaylan M. Price; Brian G. Bosworth; Samitha S.N. Liyanage; Jason W. Abernathy; Benjamin H. Beck; Luke A. Roy; Timothy J. Bruce; Rex A. Dunham; Ian A.E. Butts (Theriogenology, 2026)

Rapid changes in transcription during a feast-famine event - Paul Dijkstra; Bruce A. Hungate; Jennifer Pett-Ridge; Steven J. Blazewicz; Javier A. Ceja-Navarro; Ember M. Morrissey; Peter F. Chuckran; Egbert Schwartz (Soil Biology and Biochemistry, 2026)

Threshold responses of soil microbial communities and functions to 18O-H2O enrichment - Fangying Qu; Lingrui Qu; Yue Liu; Mike Manefield; Bruce A. Hungate; Ember M. Morrissey; Jian Wang; Yi Yang; Juan Piñeiro; Edith Bai; Chao Wang (Soil Biology and Biochemistry, 2026)

Epidemiological status of bovine viral diarrhea virus in water buffalo (Bubalus bubalis): A global systematic review and meta-analysis - Eaftekhar Ahmed Rana; Md. Saiful Islam; Belayet Hossain; Mieghan Bruce; Subir Sarker; Jully Gogoi-Tiwari; Jasim M. Uddin (Research in Veterinary Science, 2026)

Impact of light intensity and tank color on growth and development of largemouth bass, Micropterus nigricans, during early life history - Anneleen Swanepoel; Nelson S. Parajuli; Kaylan Martin; Kyle R. Wood; Josh Sakmar; Allen Nicholls; Anita M. Kelly; Luke A. Roy; Timothy J. Bruce; D. Allen Davis; Ian A.E. Butts (Aquaculture, 2026)

Measurement of tyre-related chemicals in roadside retention ponds using the Chemcatcher passive sampler: An ex-situ calibration and in-situ monitoring study - Katie McKenzie; Alfonso Fernández-García; Francisco José Díaz-Galiano; Sam M. Walker; Angela Pllu; Iain Campbell; Oliver Hughes; Gary R. Fones; Graham A. Mills; Juan F. García-Reyes; Linda A. Lawton; Bruce Petrie (Journal of Hazardous Materials, 2026)

Per- and polyfluoroalkyl substances, vitamin D, and risk of preterm birth in a Canadian cohort - Mandy Fisher; James Owen; Leonora Marro; Beth Potter; Hope A. Weiler; Gillian England-Mason; Michael M. Borghese; Mark Walker; Linda Dodds; Michael Helewa; Tye E. Arbuckle; Bruce Lanphear; et al. (Environmental Research, 2026)

Which soil health indicators best track diversification benefits in tropical agroecosystems? - Anna M. Visscher; Simon Fonteyne; Mirjam Pulleman; Anna Alekseeva; Martin Hartmann; Jose M. Rodriguez-Castellanos; Pankaj Trivedi; Rodolfo Vilchis-Ramos; Sergio Zapata-Martínez; Bruce G. Ferguson; Helda Morales; Steven Vanek; et al. (Applied Soil Ecology, 2026)

A new sustainability paradigm beyond the organic brand - Joe M. Roberts; Angharad M.R. Gatehouse; Toby J.A. Bruce (Trends in Plant Science, 2026)

Integrated modelling reveals widespread distribution of invasive wild pigs across Australia - Matthew W. Rees; David J. Mitchell; Katherina Ng; Sandra K. Parsons; Kirstin M. Proft; Scott D. Foster; David Peel; Zachary Amir; Tom Bruce; Matthew S. Luskin; Jens G. Froese (Biological Conservation, 2026)

Methoxyacetic acid exposure in rats induces N-butyrylglycinuria consistent with beta-oxidation impairment - Samuele Sala; Janonna Kadyrov; Andres Bernal; Andres M. Castillo; Preechaya Naraprasertkul; Nadia Paesalasakul; Proud Bekanan; Issariya Dhitsuwon; Thanaporn Kulthawatsiri; Reika Masuda; Manthan Sharma; Jutarop Phetcharaburanin; et al. (Archives of Toxicology, 2026)

Improving the use of expert opinion in disease risk analysis for conservation translocations - John G. Ewen; Stefano Canessa; Caitlin E. Andrews; Katie M. Beckmann; Irene Bueno; Deidre K. Fontenot; Caio Kenup; Suzanne Medina; Axel Moehrenschlager; Francesco Origgi; Bruce Rideout; Anthony W. Sainsbury; et al. (Conservation Biology, 2026)
Conservation translocations are subject to considerable uncertainty and risk, of which disease is one of the most recognized. To address disease risks, several protocols for qualitative disease risk analysis (qDRA) exist and are used for responsible conservation translocation planning. Existing qDRA protocols usually rely on expert judgment, but they lack quantitative aggregation of elicited estimates, transparent treatment of uncertainty, and explicit comparison of alternative disease risk management pathways. We added these factors to a qDRA for translocation of a charismatic species that is extinct in the wild, the sihek (Guam kingfisher) ( Todiramphus cinnamominus ). We asked a panel of seven independent experts to quantify their judgment of risks of pathogen release, exposure, and consequences for seven pathogen hazards under three translocation management scenarios. Experts suggested that implementing a full biosecurity protocol would reduce risk for several pathogen hazards but would have variable effectiveness (11–65% depending on the hazard). There was substantial uncertainty associated with individual experts and noise among different experts, showing the potential for error if decisions are based on single‐point judgments (i.e., providing judgment of a central tendency without accounting for uncertainty) from one expert or on collaborative consensus of multiple experts, as is current practice.

Efficacy of an Inactivated Bacterin Vaccine Against Emerging Streptococcus dysgalactiae in Channel Catfish ( Ictalurus punctatus ) - Brent M. Vuglar; Krishna P. Singha; Craig A. Shoemaker; Benjamin H. Beck; Taylor I. Heckman; Jason W. Abernathy; Julio C. García; Eric Peatman; Timothy J. Bruce (Journal of Fish Diseases, 2026)
Lancefield Group C Streptococcus dysgalactiae recently emerged as a catfish pathogen in the US. Reports from hatcheries suggest S. dysgalactiae causes substantial broodfish loss. We aimed to develop a challenge model and evaluate vaccine efficacy against S. dysgalactiae in juvenile channel catfish ( Ictalurus punctatus ). Three S. dysgalactiae (14–1, 14–24 and 14–25) isolates were tested for virulence. Intracoelomic (IC) injection demonstrated S. dysgalactiae 14–1 was the most virulent. Reisolated 14–1 was used to develop a formalin‐killed cell (FKC) vaccine. Catfish (200) were immunized via IC injection of 100 μL FKC with adjuvant (1:1 v/v), and another 200 catfish were sham vaccinated. Five fish from each group were bled for antibody titre every 14 days. At 28 and 56 days post‐vaccination (dpv), subsets of both groups were challenged with S. dysgalactiae via IC injection (200 μL/fish) in triplicate (20 fish/tank). Cumulative percent mortality was significantly ( p S. dysgalactiae bacterin induced humoral immunity and protected juvenile catfish. Future studies are planned to evaluate this bacterin in broodfish.

The Effects of Peracetic Acid on Post‐Larvae and Juvenile Pacific White Shrimp ( Litopenaeus vannamei ) and Seven Vibrio Species Isolates at Two Salinities - James T. Tuttle; Timothy J. Bruce; Luke A. Roy; Hisham A. Abdelrahman; Julio C. García; Benjamin H. Beck; David L. Straus; Anita M. Kelly (Journal of Fish Diseases, 2026)
Pacific white shrimp ( Litopenaeus vannamei ) are among the most important aquaculture species but are highly susceptible to Vibrio infections. Novel disease management strategies are necessary. Previous studies have reported that peracetic acid (PAA) is an effective disinfectant, but its application in shrimp aquaculture remains underexplored. This study aimed to determine the median lethal concentration (LC 50 ) of PAA at two life stages of L. vannamei under two salinities and assess its in vitro growth‐inhibitory effects against Vibrio spp. Two groups of 180 juveniles (~5 g) and post‐larvae (maintained at either 4 or 30 g L −1 ) were exposed to six geometrically increasing concentrations of PAA to determine 24‐h LC 50 estimates. Representative juvenile shrimp tissues were histologically assessed. Seven isolates of Vibrio spp. inocula were exposed to PAA and enumerated to determine growth inhibition. The LC 50 estimates varied from 29.09 to 82.40 mg L −1 of PAA. Gill and hepatopancreas tissues were notably damaged at 40.5 and 75 mg L −1 of PAA at 4 and 30 g L −1 , respectively. Growth of all Vibrio spp. was inhibited at the lowest PAA dose tested, that being 0.03125 mg L −1 after 45 min. These findings will help progress the further application of peracetic acid in shrimp aquaculture.

Bridging the Scale Gap: Regional Refinement of National Mineral Prospectivity Models for Nunavut, Canada - Julie E. Bourdeau; Mohammad Parsa; Christopher J. M. Lawley; Steve R. Beyer; Bruce Kjarsgaard; Tommy Tremblay (Natural Resources Research, 2026)
Mineral exploration in the Arctic is challenging, resulting in decreased survey and mineral discovery rates. Data-driven mineral prospectivity mapping is intended to reduce exploration risk by delineating promising areas. However, data sparsity, especially of deposit locations, is a critical bottleneck. In this study, we developed and tested a method to conduct data-driven mineral prospectivity mapping in regions where annotated data are too sparse. Our method is predicated on the existence of large-scale mineral prospectivity frameworks (data, models and methods), which are fine-tuned using regional ground truth to produce locally refined predictions. This is possible because the spatial transferability of trained machine learning models is incomplete. We explicitly tested the hypothesis of limited spatial transferability. To within limitations of our experimental design, our results are supportive of our hypothesis that the incorporation of new positive samples into an existing training dataset preferentially influences the local outcome. Using a suite of critical minerals combined with published data and models in Canada, we demonstrated that by treating large-scale mineral prospectivity frameworks as foundational, it is productive to fine-tune trained models using regional data. Although national-scale maps exist prior to this study, they did not incorporate a substantial amount of ground truth from Nunavut. Therefore, through regional refinement, we produced the inaugural version of a set of pan-Canadian mineral prospectivity maps that are specifically refined for Nunavut for: (1) flake graphite; (2) magmatic Ni (±Cu ±Co ±PGE); and (3) Mississippi Valley-type Pb–Zn. The regional refinement method is a perspectivist and federated approach to MPM that extracts additional value from large-scale mineral prospectivity frameworks and provides an interoperable method for national, regional and inter-regional mineral exploration.

A conservation behaviour approach to the mitigation hierarchy for anthropogenic stressors - Kathleen D.W. Church; Brett M. Seymoure; Shannon Crossen; Kasey D. Fowler-Finn; Matthew K. LeFauve; Jennifer N. Phillips; Bruce A. Schulte (Animal Behaviour, 2026)

Longitudinal wastewater-based surveillance of vancomycin-resistant Enterococci in tertiary-care hospitals - Emily Au; Nicole Acosta; Barbara J. Waddell; Jangwoo Lee; Kristine Du; R. Benson Weyant; Maria Bautista; Janine McCalder; Jennifer Van Doorn; Kashtin Low; September Stefani; Gail Visser; et al. (Science of The Total Environment, 2026)

Association between gestational and childhood exposures to organophosphate esters and social skill, problem behavior among adolescents - Jagadeesh Puvvula; Joseph M. Braun; Kimberly Yolton; Kim M. Cecil; Antonia M. Calafat; Maria Ospina; Whitney Fitts; Kelli M. Williams; Weili Yang; Ann M. Vuong; Zana Percy; Bruce Lanphear; et al. (Environmental Research, 2026)

Identifying associations and key early life exposure windows for organophosphate esters and adolescent brain morphometry in the HOME study - Zheng Ren; Aimin Chen; Jagadeesh Puvvula; Yingying Xu; Ethan Bouche; Antonia M. Calafat; Alex D. Edmondson; Kristin A. Linn; Russell T. Shinohara; Maria Ospina; Zana Percy; Ann M. Vuong; et al. (Environmental Research, 2026)

Haemodynamic adaptations to isometric handgrip versus isometric wall squat exercise training: a randomised crossover study - Jamie J. Edwards; Andy Galbraith; Stewart Bruce-Low; Rajan Sharma; Jamie M. O’Driscoll (European Journal of Applied Physiology, 2026)

Combining ability and identification of novel sources of fall armyworm resistance in tropical mid-altitude maize - Wilber Wambi; Dan Makumbi; Godfrey Asea; Habtamu Zeleke; Anani Y. Bruce; Mulatu Wakgari; Boddupalli M. Prasanna (Euphytica, 2026)

Growth, Foraging, and Health Effects of Turbidity on Captive, Juvenile-subadult Delta Smelt - Bruce G. Hammock; Meghan M. Holst; Nathan Bryant; Khiet H. Huynh; Wendie H. Vang; Phoebe Fitzmaurice-Shean; Kimberly I. Stauffer; Tien-Chieh Hung; Yi-Jiun Tsai; Luke Ellison; Swee J. Teh (Estuaries and Coasts, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Evaluation of rapid evaporative ionization mass spectrometry (REIMS) relationships with biochemical markers of tenderness in beef Longissimus lumborum steaks - Kaitlyn R. Loomas; Dale R. Woerner; Ben M. Bohrer; Tyson R. Brown; Heather L. Bruce; Marcio S. Duarte; Bimol C. Roy; Yifei Wang; Katie Pedgerachny; Jerrad F. Legako (Meat Science, 2026)

Serum PFAS concentrations and neuromorphometry in adolescents: The HOME Study - Jasmine Haraburda; Jonathan Dudley; Kimberly Yolton; Yingying Xu; Joseph M. Braun; Aimin Chen; Bruce P. Lanphear; Kim M. Cecil (Environmental Research, 2026)

Optimization of a high-throughput single spore DNA extraction protocol for the model species of arbuscular mycorrhizal fungi, Rhizophagus irregularis - Selina A. Spence; Brontë R. Shelton; Diego Yusta Belsham; Joana Larrere; Cassandra E. Bruce; Olivia J. Regush; Miranda M. Hart (Mycorrhiza, 2026)

Acoustic evidence for topographic blocking on a steep submarine canyon wall - Astrid B. Leitner; Chad M. Waluk; Kim R. Reisenbichler; Rob E. Sherlock; Bruce H. Robison; Kelly J. Benoit‐Bird (Limnology and Oceanography, 2026)
Diel vertical migration (DVM) is the largest mass‐movement of animals on Earth, with profound ecological and biogeochemical consequences. DVM has mostly been studied in the open ocean; however, at steep slopes, pelagic animals including vertical migrators must contend with the seafloor, emphasizing the importance of understanding DVM in these prevalent, critical habitats. Here we used active acoustics in combination with video to conduct a detailed study of the interactions of vertical migrators with the steep wall of a submarine canyon during their sunrise descent. We found regular and frequent, high‐density sunrise aggregations of animals consistent with seafloor blocking of descending vertical migrators across all seasons. While topographic blocking was thought to be primarily caused by nighttime advection of migrators over shallows by prevailing currents, here the occurrence of this phenomenon was observed to be largely independent of oceanographic drivers including advection as measured by an ADCP, providing evidence that behavior plays an important role. Advection, season, upwelling, and other environmental factors were found to impact specific characteristics of sunrise aggregations but not likelihood of occurrence. Given its intensity and prevalence, topographic blocking likely creates high‐quality, predictable foraging opportunities for a large diversity of predators and influences the abundance and habitat use of predators in the area. The steep slopes of this canyon, as with any abrupt bathymetry, juxtapose the deep and the shallow, the benthic and the pelagic, and the offshore and nearshore. Thus, topographic blocking may be prevalent in other steep canyons and at steep bathymetry more generally.

Detection of the eruption of the East Epi submarine volcano, Vanuatu, and its subsequent tsunami on 31 January 2023 - Jean H. M. Roger; Aditya R. Gusman; Bruce E. O. Thomas; Janine B. Krippner; Salman Ashraf; Jelle D. Assink; Xiaoming Wang; Bernard Pelletier; Philipson Bani; Jean-Claude Kali (Bulletin of Volcanology, 2026)
Between the 25th and the 31st of January 2023 an eruption occurred several kilometres East of Epi Island, Vanuatu, an area known to host a submarine volcanic zone including several cones. The largest cone (Epi B) entered regularly in activity in the last century, and images of daily monitoring satellites confirmed its responsibility for the January 2023 eruption. The eruption evolved to Surtseyan on the 31st, producing ash and gas columns reaching more than 100 m above sea level and small pyroclastic surge moving across the water, with subsequent pumice rafts and water discolouration. The eruptive activity is visible on satellite imagery and was well recorded on seismic, hydroacoustic and infrasound stations that are part of the Comprehensive Nuclear-Test-Ban Treaty Organization (CTBTO) International Monitoring System (IMS). Although this had no apparent consequences on the nearby communities, a small tsunami was however reported by locals and recorded on the coastal tide gauges of Port Vila ~ 125 km to the south and Luganville ~ 175 km to the north showing maximum amplitude of ~ 5 cm. This data is used to validate the location and timing of the eruption and tentatively propose a tsunami mechanism. As a large part of the Vanuatu population is living in coastal areas, understanding tsunami mechanisms and assessing tsunami hazards associated with submarine eruptions is of main concern. Ultimately, this study aims to bring scientists and risk managers’ attention to a potentially hazardous volcano, through satellite and seismo-acoustic data analysis, numerical simulations of tsunami, and GIS mapping.

Increases in plastic bottles washing ashore on sub-Antarctic Marion Island - Peter G. Ryan; Azwianewi B. Makhado; Thando Cebekhulu; Robert J.M. Crawford; Bruce M. Dyer; Makhudu J. Masotla; Vonica Perold; Maelle Connan (Marine Pollution Bulletin, 2026)

The association of gestational phthalate exposure with social skills and problem behaviors in adolescents - Whitney Fitts; Jagadeesh Puvvula; Joseph M. Braun; Bruce P. Lanphear; Antonia M. Calafat; Yingying Xu; Kim M. Cecil; Kimberly Yolton; Aimin Chen (Science of The Total Environment, 2026)

Alteration minerals and their formation environments in intrusion-related hydrothermal systems at Mt. Ruapehu (New Zealand) – New insights from mass balance, thermodynamic modelling and stable isotopes - Antonio M. Álvarez-Valero; Gabor Kereszturi; Rachelle Sánchez; David Benavente; Cristina Pérez-Coca; Mercedes Suárez; Bruce Christenson; Takumi Imura; Masao Ban (Journal of Volcanology and Geothermal Research, 2026)

Pregnancy exposure to environmental phenols and breastfeeding duration in the HOME Study - Zaya Gerili; Joseph M. Braun; Kimberly Yolton; Bruce Lanphear; Megan E. Romano; Janne Tolstrup; Amalie Timmermann (International Journal of Hygiene and Environmental Health, 2026)

No-till in rice systems: A global meta-analysis of key agronomic practices impacting yields - Mia Godbey; Ignacio Macedo; Cameron M. Pittelkow; Bruce Linquist (Field Crops Research, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Predator and prey density effects on early life-history performance of largemouth bass (Micropterus nigricans) in an indoor recirculating aquaculture system - Nelson S. Parajuli; Josh Sakmar; Allen Nicholls; Anita M. Kelly; Luke A. Roy; D. Allen Davis; Timothy J. Bruce; Matthew K. Litvak; Ian A.E. Butts (Aquaculture, 2026)

Selective detoxification of digesta revealed how cold-pressed apple fractions modulate transepithelial glucose transport and stimulate GLP-1 secretion - Ivan M. Lopez-Rodulfo; Martin K. Rasmussen; Bruce Hamaker; Mario M. Martinez (Food Chemistry, 2026)

Genetic analysis of Aspergillus flavus infection and aflatoxin accumulation in tropical yellow maize - Julius Pyton Sserumaga; Dan Makumbi; Tonny Obua; Fredrick Nganga; Catherine Ziyomo; Bright M. Jumbo; Anani Y. Bruce; Dan Jeffers; Spencer Smith; Marilyn L. Warburton (Phytoparasitica, 2026)

Associations between air pollution and markers of neuroinflammation, synaptic dysfunction and core Alzheimer’s disease pathology vary by APOE genotype - Kana Kimura; Ira Driscoll; Noah Cook; Sonia Shahzad; Tobey J. Betthauser; Sterling C. Johnson; Sanjay Asthana; Catherine L. Gallagher; Bruce P. Hermann; Mark A. Sager; Kaj Blennow; Henrik Zetterberg; et al. (Neurotoxicity Research, 2026)
To determine whether long-term residential air pollution [AP; ozone (O₃) and fine particulate matter (PM₂.₅)] is associated with (1) incident mild cognitive impairment (MCI) or Alzheimer’s disease (AD), (2) biomarkers of core and AD-relevant pathology, and (3) whether these relationships are moderated by APOE4+/- (carrier/non-carrier of one or both ε4 alleles) status or mediated by neuroinflammation. Sample included 795 participants (Mage 68.7 ± 7.9; 68% female) from the Wisconsin Alzheimer’s Disease Research Center and Wisconsin Registry for Alzheimer’s Prevention parent studies, both enriched for AD risk at enrollment based on parental AD history. Residential zip code and 2009–2021 EPA-based annual AP reports were used to estimate individual exposure. Cox proportional hazards models assessed MCI/AD risk. Linear regressions examined the relationships between AP exposure and biomarkers of core and AD-relevant pathology, with and without APOE4 + stratification. Causal mediation analysis examined whether markers of inflammation mediated the AP-AD pathology relationships. Neither O₃ nor PM₂.₅ exposure predicted MCI/AD incidence nor core AD pathology (Ps > 0.05). Higher PM₂.₅ was associated with higher CSF GFAP levels ( P = 0.003). APOE4 + with higher levels of PM₂.₅ exposure had higher CSF levels of tTau ( P = 0.01), pTau₁₈₁ ( P = 0.01) and neurogranin ( P = 0.02). These relationships were not mediated by neuroinflammation (Ps > 0.05). In this AD-risk enriched cohort, AP was not associated with MCI/AD incidence. However, higher PM₂.₅ exposure was associated with astrocytic activation, and in APOE4+, AD pathology, neurodegeneration, and synaptic dysfunction. Our findings suggest AP as an environmental risk factor contributing to AD-relevant pathology, particularly among genetically at-risk individuals.

Dysregulation of the BRD2-FGF17 Signal Pathway Induces Abnormal Forebrain Development Associated with Schizophrenia - Xiao Yu; Jiacheng Du; Chenger Zhou; Yongheng Huang; Huijuan Li; Bruce M. Cohen; Sangmi Chung; Zhicheng Shao (Neuroscience Bulletin, 2026)

Hormonal and behavioral variation during release from reproductive suppression in an extreme cooperative breeder - Phoebe D. Edwards; Juweriah Munir; Ilapreet Toor; Bruce D. Goldman; Rudy Boonstra; Rupert Palme; Gabriela F. Mastromonaco; Melissa M. Holmes (Mammalian Biology, 2026)

Validity of an open-source mobile app to measure fractal correlation properties of heart rate variability during exercise - Bruce Rogers; Juan M. Murias; Pablo R. Fleitas-Paniagua (European Journal of Applied Physiology, 2026)

Correction: Causal Networks to Inform Decisions for Ecological Restoration - Christopher J. Kotalik; Freya E. Rowland; Bruce G. Marcot; Kristin E. Skrabis; David M. Walters; Jo Ellen Hinck; William H. Clements; Eric E. Richer; John P. Isanhart (Environmental Management, 2026)

Gestational PBDE concentrations and functional connectivity in adolescents: The HOME Study - Jonathan Dudley; Kimberly Yolton; Alex D. Edmondson; Yingying Xu; Aimin Chen; Jeffrey R. Strawn; Joseph M. Braun; Andreas Sjodin; Bruce P. Lanphear; Kim M. Cecil (International Journal of Hygiene and Environmental Health, 2026)

Maternal serum polybrominated diphenyl ether concentrations during pregnancy and adolescent bone mineral density at age 12 years - Katherine M. Marquess; Jordan R. Kuiper; Bruce P. Lanphear; Antonia M. Calafat; Andreas Sjodin; Maria Ospina; Lesliam Quirós-Alcalá; Kim M. Cecil; Halley Wasserman; Yingying Xu; Kimberly Yolton; Heidi J. Kalkwarf; et al. (International Journal of Hygiene and Environmental Health, 2026)

Interlaboratory clinical chemistry parameter variation in seven-day acute hydrazine toxicity studies in the Sprague-Dawley rat - Janonna Kadyrov; Samuele Sala; Lucy Grigoroff; Reika Masuda; Samantha Lodge; Timothy M. Ebbels; Michael D. Reily; Donald Robertson; Lois Lehman-McKeeman; John Shockcor; Bruce D. Car; Craig Thomas; et al. (Archives of Toxicology, 2026)
Clinical chemistry retains its position as a cornerstone of toxicological assessment, yet inter-laboratory variability in baseline values remains a challenge for the integration and interpretation of multisite datasets. This study leveraged a publicly available clinical chemistry database to assess the impact of inter-laboratory variability in response to hydrazine-induced steatosis. Seventeen clinical chemistry and physico-chemical parameters were evaluated in response to a single dose of hydrazine (at 30 mg/kg or 90 mg/kg) administered to Sprague-Dawley rats ( n = 83) across five different pharmaceutical companies and compared with sham-dosed control animals. Hydrazine exposure produced a distinct and consistent biochemical signature at 48 h post-dose across the combined sample set from all laboratory sites, characterised by increased serum bilirubin and BUN and decreased serum protein concentrations, alongside atypical reductions in ALT and AST due to transaminase inhibition. Despite sizable inter-laboratory differences in response when considering single assays, multivariate analysis of the complete dataset was able to extract a core pathological response signature. Early changes at 24 h post-dose in AST, ALT, total protein, and calcium demonstrated strong predictive value for 48-h toxicity profiles (AUROC 0.98), underscoring the translational potential of early biomarkers. This study highlights both the robustness and contextual limitations of clinical chemistry data in toxicological studies. It underscores the importance of matched-control designs and multivariate approaches for multisite studies and advocates for the integration of early predictive modelling to optimise study design and align with the principles of the Replace, Reduce, and Refine initiative.

Drought Reduces Formation, but Enhances Persistence, of Mineral‐Associated Organic Matter in a Grassland Soil - Noah W. Sokol; Megan M. Foley; Steven J. Blazewicz; Nicole DiDonato; Katerina Estera‐Molina; Mary Firestone; Alex Greenlon; Bruce A. Hungate; William Kew; Ljiljana Paša‐Tolić; Eric Slessarev; Jennifer Pett‐Ridge (Global Change Biology, 2026)
Drought effects are pervasive in terrestrial ecosystems, yet there is limited understanding of how drought impacts the transformation of plant carbon (C) inputs to mineral‐associated organic matter (MAOM)—the largest and slowest‐cycling pool of soil organic carbon (SOC). In a 12‐week 13 C‐CO 2 greenhouse labeling experiment, we tracked the formation of MAOM derived from the two dominant sources of plant C input to the mineral soil—living root inputs ( 13 C‐rhizodeposits) and decaying root inputs ( 13 C‐root detritus)—under normal moisture and droughted conditions in a semiarid grassland soil. At the end of the 12‐week period, we also measured the persistence of 13 C‐MAOM formed from rhizodeposits versus root detritus via a subsequent persistence assay. Drought reduced the formation of MAOM derived from living roots by decreasing rhizodeposits, reducing microbial growth rates, and altering the composition of organic matter, lipids, and metabolites. Drought initially delayed the formation of MAOM derived from root detritus by slowing the early stages of root litter decomposition (week 4–8), but did not decrease total MAOM formation by the end of the 12‐week period. Notably, drought enhanced the persistence of MAOM derived from root detritus, but did not influence the persistence of MAOM derived from rhizodeposits. Our results provide some of the first direct evidence that drought can reduce the formation of MAOM in a grassland soil, but may enhance its persistence, based on the source of plant input from which MAOM is derived.

Clarifying space use concepts in ecology: Range vs. occurrence distributions - Jesse M. Alston; Christen H. Fleming; Michael J. Noonan; Marlee A. Tucker; Inês Silva; Cody Folta; Thomas S. B. Akre; Abdullahi H. Ali; Jerrold L. Belant; Dean Beyer; Niels Blaum; Katrin Böhning‐Gaese; et al. (Ecology, 2026)
Quantifying animal movements is necessary for answering a wide array of research questions in ecology and conservation biology. Consequently, ecologists have made considerable efforts to identify the best way to estimate an animal's home range, and many methods of estimating home ranges have arisen over the past half a century. Most of these methods fall into two distinct categories of estimators that have only recently been described in statistical detail: those that measure range distributions (methods such as kernel density estimation that quantify the long‐run behavior of a movement process that features restricted space use) and those that measure occurrence distributions (methods such as Brownian bridge movement models and the Correlated Random Walk Library that quantify uncertainty in an animal movement path during a specific period of observation). In this paper, we use theory, simulations, and empirical analysis to demonstrate the importance of appropriately using these two categories of distributions and their estimators. Conflating range and occurrence distributions can have serious consequences for ecological inference and conservation practice. For example, in most situations, home ranges estimated using estimators of occurrence distributions are too small, and this problem is exacerbated by ongoing improvements in tracking technology that enable more frequent and more accurate data on animal movements. We encourage researchers to use estimators of range distributions to quantify home ranges and estimators of occurrence distributions to answer other questions in movement ecology, such as when and where an animal crossed a linear feature, visited a location of interest, or interacted with other animals.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

PTUPB improves cognitive function in Alzheimer’s disease associated with enhancing cerebral vascular myogenic response and attenuating vascular remodeling - Gilbert C. Morgan; Andrew Gregory; Chengyun Tang; Sung Hee Hwang; Jane J. Border; Jing Xu; Yedan Liu; Shan Bai; Tae Jin Lee; Cameron Cantwell; David Bunn; Karen M. Wagner; et al. (GeroScience, 2026)

Disentangling the visual cues of an evolutionary trap for aquatic insects - Nathan W. Forgan; Camila M. Cohen Suárez; Willow S. Lovecky; Patrick W. Crumrine; Bruce A. Robertson; Kyle J. Haynes (Evolutionary Ecology, 2026)
Aquatic insects use polarized light as a reliable visual cue for locating water surfaces given their need to locate sites for oviposition. However, many man-made surfaces polarize light more strongly than natural waterbodies creating an evolutionary trap in which many species preferentially lay their eggs on these polarizing artificial surfaces. Previous work has shown that the attractiveness of artificial surfaces to aquatic insects is diminished by adding non-polarizing gridlines to these surfaces. However, it is unknown how this mitigation affects aquatic insect preferences. We tested two alternative hypotheses about how aquatic insects judge the quality of potential oviposition sites. The visual averaging hypothesis states that insects judge the quality of a surface based on the percent area of the surface that is polarizing. An alternative hypothesis is that the quality of a polarizing surface is judged by the degree to which it is fragmented by non-polarizing elements. This experiment was conducted using oil tray traps as artificial polarizers whose percentage of polarizing area and the presence/absence of fragmentation was manipulated. Only Diptera were captured in sufficient numbers to test the hypotheses. Our findings for the dominant family in our captures, Dolichopodidae, were consistent with the visual averaging hypothesis – increasing the percent area that was non-polarizing significantly decreased captures, but the fragmentation of a polarizing surface had no significant effect on the number captured. For the other families of aquatic Diptera combined, however, there was a complex interactive effect of percent area of a surface that was polarizing and its fragmentation by non-polarizing gridlines. For the conservation of aquatic insects, these findings support the effectiveness of reducing the attractiveness of artificial polarizing surfaces such as solar panels by adding non-polarizing elements, but also show that for some aquatic insects, it is important to consider if the non-polarizing elements fragment the surface.

Circadian rhythm of amyloid-β in the olfactory bulb and cerebellum of wild-type and APPxPS1 knock-in mice indicates a loss of rhythmicity in regions more vulnerable to amyloid pathology - Valeria A. Buzinova; Carrie E. Johnson; Savannah M. Turton; Sarah E. Barth; Samantha Padgett; M. Tyler Maisel; Katharina Kohler; Haleigh R. Whitlock; Adam D. Bachstetter; Sridhar Sunderam; Bruce F. O’Hara; Marilyn J. Duncan; et al. (Biogerontology, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

A history of the collaborative group of the Americas on inherited gastrointestinal cancer (CGA-IGC): 1995–2025 - Beth Dudley; Bruce M. Boman; Marc S. Greenblatt; Steven H. Erdman; Paul E. Wise; Randall E. Brand; Carol A. Burke; Jose G. Guillem; Michael J. Hall; Heather Hampel; Brandie Heald; Matthew F. Kalady; et al. (Familial Cancer, 2026)

Validating shipping noise simulations for the Red Sea using field measurements - Rihab Larayedh; Michelle N. Havlik; Bruce D. Cornuelle; George Krokos; Carlos M. Duarte; Ibrahim Hoteit (Marine Pollution Bulletin, 2026)

Effects of different soybean protein sources on growth performance, feed utilization efficiency, intestinal histology, and physiological gene expression of Pacific white shrimp (Litopenaeus vannamei) in green water and indoor biofloc system. - Khanh Q. Nguyen; Aya S. Hussain; Adela N. Araujo; Leila M. Strebel; Trenton L. Corby; Melanie A. Rhodes; Timothy J. Bruce; Jorge Cuéllar-Anjel; D. Allen Davis (Aquaculture, 2026)

Gestational and early childhood air pollution exposure and neurodevelopmental outcomes in early childhood - Christina Berninger; Yingying Xu; Patrick Ryan; Kim M. Cecil; Bruce P. Lanphear; Aimée Vester; Kimberly Yolton (Neurotoxicology and Teratology, 2026)

The history of Martian water during the Hesperian and Amazonian epochs - Bruce M. Jakosky; Noora R. Alsaeed; Eryn M. Cangi; Michael S. Chaffin; Justin Deighan; Margaret E. Landis; Michael T. Mellon; Edward M.B. Thiemann (Icarus, 2026)

Associations of endocrine disrupting chemical biomarkers and their mixture with vitamin D biomarker concentrations in childhood: The HOME Study - Katherine M. Marquess; Jordan R. Kuiper; Taylor M. Etzel; Bruce P. Lanphear; Andrew N. Hoofnagle; Antonia M. Calafat; Julianne Cook Botelho; Maria Ospina; Andreas Sjodin; Lesliam Quirós-Alcalá; Kim M. Cecil; Aimin Chen; et al. (Environmental Research, 2026)

Causal Networks to Inform Decisions for Ecological Restoration - Christopher J. Kotalik; Freya E. Rowland; Bruce G. Marcot; Kristin E. Skrabis; David M. Walters; Jo Ellen Hinck; William H. Clements; Eric E. Richer; John P. Isanhart (Environmental Management, 2026)
The release of contaminants into the environment can occur from anthropogenic activities, such as oil extraction and transportation, mining, and industrial processes. Remediation associated with reducing contaminant concentrations, and restoration that improves animals and supporting habitat, are often needed to restore ecosystems to their pre-release, baseline condition. We demonstrated the application of Bayesian Decision Networks (BDNs) with two Natural Resource Damage Assessment and Restoration (NRDAR) case studies. We use a stylized case study of riparian restoration following the remediation of a mine-impacted site to evaluate proposed restoration actions aimed at restoring Song Sparrow ( Melospiza melodia ) populations to baseline conditions. We then use a settled NRDAR case with implemented restoration in the Upper Arkansas River (UAR, Colorado, USA) to demonstrate the application of BDNs to evaluate and forecast restoration effectiveness for Brown Trout ( Salmo trutta ) (i.e., restoration effectiveness assessment). The riparian restoration model showed differences in the effects of restoration actions on Song Sparrow populations, with the time to reach baseline generally reduced with increased restoration costs, indicating trade-offs between costs and expected recovery. The UAR model showed recovery of Brown Trout populations (i.e., uplift) in response to improved instream habitat restoration, along with forecasted improvements. While the BDNs we developed were specific to two case studies, the structure is adaptable to a diversity of sites, resources, and actions. We suggest that causal network modeling can provide restoration practitioners with a decision advisory tool useful for a wide range of projects.

Evaluation of phytogenic product supplementation on the growth performance, immune function, and gut microbiota composition in fingerling channel catfish (Ictalurus punctatus) - Ishini A. Appuhami; D. Allen Davis; Yoonhang Lee; Abdulmalik A. Oladipupo; Brent M. Vuglar; Fernando Y. Yamamoto; Mark Farmer; Timothy J. Bruce (Animal Feed Science and Technology, 2026)

Genomic Architecture of Inbreeding Depression Associated With Hatching Failure in an Endangered Parrot - Yasmin Foster; Stefanie Grosser; Brodie J. Foster; Nicolas Dussex; Aimee Stubbs; Ludovic Dutoit; Theo Atkinson; Fiona Robertson; Ken G. Dodds; Rudiger Brauning; Jeanne M. E. Jacobs; John C. McEwan; et al. (Molecular Ecology, 2026)
Conservation management of endangered species increasingly relies on genomic approaches to understand how long‐term small population sizes affect the fitness of extant individuals. However, despite the growing investment in genomic resources by conservation programmes, the impact that sequencing methods have on the ability to detect inbreeding‐related phenomena has been largely overlooked. Here, we compare the use of whole‐genome and reduced‐representation sequencing approaches in 148 individuals of the critically endangered parrot, the kākāpō ( Strigops habroptilus ), to assess inbreeding and its effects on female reproductive success. We explore how sequencing choice influences the identification of long stretches of homozygosity across the genome (runs of homozygosity, ROH), and compare the conservation implications of the results produced by each method. Both whole‐genome and reduced‐representation sequencing approaches provided comparable estimates of genome‐wide inbreeding ( F ROH ) and revealed consistent effects on egg hatching success, suggesting that reduced‐representation sequencing is capable of detecting inbreeding depression in wild populations under certain conditions. Whole‐genome sequencing enabled chromosome‐level inbreeding analyses, which revealed no strong evidence of chromosome‐specific effects beyond the genome‐wide signal. These results suggest that inbreeding depression in kākāpō reflects small effects across many chromosomes rather than strong effects on only a few, and that the primary benefit of whole‐genome sequencing lies in improving the precision of genome‐wide inbreeding estimates rather than identifying chromosome‐specific effects. Our findings highlight the distinct benefits of each sequencing approach in conservation, particularly within the context of resource limitations.

Corrigendum to Toward a near-lossless image compression strategy for the NASA/USGS Landsat Next mission Remote Sensing of Environment Volume 329, 1 November 2025, 114929 - Rehman S. Eon; Craig De Groot; Jeffrey A. Pedelty; Aaron Gerace; Matthew Montanaro; Richard K. Covington; Amy S. DeLisa; Wen-Ting Hsieh; Joy M. Henegar-leon; Douglas J. Daniels; Christopher Engebretson; Christopher J. Crawford; et al. (Remote Sensing of Environment, 2025)

Comparative characterization and interaction mechanism of zein-enhanced plant protein blends in a food model with soy, pea, chickpea, rice, and pumpkin seed proteins - Oguz K. Ozturk; Andres M. Salgado; Osvaldo H. Campanella; Bruce R. Hamaker (Food Hydrocolloids, 2025)

Associations between gestational polybrominated diphenyl ether (PBDE) serum concentrations and child sleep outcomes from ages 2–8 years - Kelli Williams; Jagadeesh Puvvula; John H. Holmes; Wei Yang; Sigrid Veasey; Jianghong Liu; Kimberly Yolton; Kim M. Cecil; Yingying Xu; Joseph M. Braun; Bruce P. Lanphear; Clara Sears; et al. (Environmental Research, 2025)

Thirty years of arboreal wildlife trends in an African rainforest under evolving threats and researchers' presence - Bastien Dehaudt; Ruksan Bose; Jean Jacques Avoto; Stephanie Brittain; Tom Bruce; Emily K. Chen; Francis A. Forzi; Britta D. Hardesty; Kimberly M. Holbrook; Aaron M. Lamperti; V. Thomas Parker; John R. Poulsen; et al. (Biological Conservation, 2025)

Personalized nutrition: perspectives on challenges, opportunities, and guiding principles for data use and fusion - Sharon M. Donovan; Mariette Abrahams; Joshua C. Anthony; Ying Bao; Maribel Barragan; Kate M. Bermingham; Gil Blander; Anna-Sigrid Keck; Bruce Y. Lee; Kristin M. Nieman; Jose M. Ordovas; Victor Penev; et al. (Critical Reviews in Food Science and Nutrition, 2025)

Leveraging animal behaviour can improve translocation success in the face of anthropogenic stressors - Elizabeth K. Peterson; M. Elsbeth McPhee; Rachel Y. Chock; Bruce A. Schulte; Julie K. Young (Animal Behaviour, 2025)

Toward a near-lossless image compression strategy for the NASA/USGS Landsat Next mission - Rehman S. Eon; Craig De Groot; Jeffrey A. Pedelty; Aaron Gerace; Matthew Montanaro; Richard K. Covington; Amy S. DeLisa; Wen-Ting Hsieh; Joy M. Henegar-leon; Douglas J. Daniels; Christopher Engebretson; Christopher J. Crawford; et al. (Remote Sensing of Environment, 2025)

The estimation of consumer scores for lamb longissimus lumborum muscle juiciness using pressed juice percentage values - Benjamin W.B. Holman; Shawn R. McGrath; M. Bruce Allworth; Emma E.M. Lynch; Damian Collins (Meat Science, 2025)

A standardized nontargeted metabolomics method for cross-laboratory comparison of food profiles - Melanie T. Odenkirk; Cole Michel; Katrina A. Doenges; Katrina L. Leaptrot; Stacy D. Sherrod; Jody C. May; Margaret L. Read; Jacqueline M. Chaparro; Nathan Montgomery; Sarah Brinkley; Arpana Vaniya; Susan B. Mitchell; et al. (Food Chemistry, 2025)

Paired megacrystic zircon (U-Th)/He and U/Pb dating reveals kimberlite eruption ages, protracted emplacement histories, and insights into megacryst genesis - Spencer D. Zeigler; Rebecca M. Flowers; D. Graham Pearson; Liam Courtney-Davies; Bruce A. Kjarsgaard; Stephen H. Richardson; Kaden Berkhahn; James R. Metcalf; Izaac Cabral-Neto (Chemical Geology, 2025)

Bringing soil sulfur to the forefront: How long-term cropping impacts sulfur speciation in soil organic matter fractions - Meghan Barnard; Ram C. Dalal; Brigid A. McKenna; Jeremy L. Wykes; Bruce C.C. Cowie; Peter M. Kopittke (Agriculture, Ecosystems & Environment, 2025)

The submarine Cowal Igneous Complex, New South Wales, Australia: embryonic arc volcanism and 20 m.y. of basin evolution at East Gondwana’s Cambro-Ordovician margin - M. Ila’ava; M. Jutzeler; R. Cas; S. Meffre; M. Bruce; R. Carey (Australian Journal of Earth Sciences, 2025)

Establishing scientific confidence in a two-chamber co-culture system to evaluate androgenic response in the presence of hepatic metabolism - Tessa C.A. van Tongeren; Susan J. Hall; Samantha J. Madnick; Blanche C. Ip; Paul L. Carmichael; Hequn Li; Wei Chen; Lori A. Breitweiser; Heather E. Pence; David M. Ames; Andrew J. Bowling; Kamin J. Johnson; et al. (Toxicology Letters, 2025)

Solubility of anhydrite in supercritical water from 380 ˚C to 625 ˚C and 220 bar to 270 bar - Pedro M. Rendel; Bruce W. Mountain; Lucjan Sajkowski (Geochimica et Cosmochimica Acta, 2025)

Depression of intracranial self-stimulation in male and female rats by intraperitoneal lactic acid: effects of morphine, ketoprofen, and interactions with G-protein biased kappa opioid agonists - Thomas J. Martin; Conner W. Martin; Kevin J. Frankowski; Bruce E. Blough; Jeffrey Aubé; Laura M. Bohn; Sara R. Jones (Psychopharmacology, 2025)
Introduction Numerous pharmacological classes of compounds have been explored as novel and efficacious alternatives to standard mu opioid agonist analgesics. We and others have described G-protein biased kappa opioid agonists as having potential utility as analgesics due to a lower propensity to produce sedation and dysphoria, which are thought to be mediated in large part through beta-arrestin signaling. Methods Here we compare two G-protein biased kappa agonists that differ in their basic chemical scaffold, triazole 1.1 (Tr1.1) and isoquinolinone 2.1 (Iso2.1), for alteration of intracranial self-stimulation (ICSS) in male and female rats. Lactic acid (LA) was given i.p. at a concentration sufficient to produce moderate to severe depression of ICSS. Results Neither Tr1.1 nor Iso2.2 reversed the effects of lactic acid at concentrations that produced significant depression of ICSS in either sex. Neither drug altered ICSS in the absence of lactic acid administration. In both males and females, morphine reversed the effects of i.p. lactic acid on ICSS and co-administration of Tr1.1 did not alter the dose–effect curve for morphine in either sex. Similar effects were observed for ketoprofen. Ketoprofen also reversed the effects of i.p. lactic acid on ICSS in both sexes in a dose-dependent manner, and co-administration of neither Tr1.1 nor Iso2.1 altered the ketoprofen dose–effect curve. Conclusions These data suggest that these G-protein biased kappa agonists may lack sufficient efficacy or potency to alter the effects of opioids or NSAIDs against moderate to severe antinociceptive stimuli in rats, and development of more potent or efficacious compounds may be required to demonstrate efficacy in rat models of moderate to severe nociception.

DNA barcode assessment of Xanthium section Xanthium cockle burrs in Australia - David Gopurenko; Xiaocheng Zhu; R. M. S. P. Rathnayake; Hanwen Wu; Bruce A. Auld; James Hereward; Heather Smith; Stephen B. Johnson; Karen A. Kirkby; Graham W. Charles (Plant Systematics and Evolution, 2025)
Xanthium cockle burrs are invasive weeds in many countries, affecting local ecosystems and agriculture. All Xanthium in Australia are naturalised weeds from multiple overseas sources, but their taxonomic identities are contentious. In particular, species identities of four burr varieties or “complexes” under Xanthium section Xanthium in Australia are unclear. These complexes, commonly referred to as “Noogoora”, “Californian”, “Hunter”, and “South American” burr, are regarded as either varieties of a single species ( Xanthium strumarium ) or four separate species in the section. To genetically determine the species identities of these complexes in Australia, we compared their chloroplast DNA barcodes to reference sequences of vouchered Xanthium species reported by Tomasello (2018). We barcoded 173 plants from 26 sites consisting of single complex burrs and 175 plants from sites containing mixed burr complexes. Single complex sites contained either of two DNA barcode clades. One clade consisting of Noogoora and Californian burrs matched reference sequences of X. chinense . The second clade consisting of Hunter and South American burrs matched X. orientale . Genetic exchange between these two species in Australia was partially evident at some sites containing sympatric complexes or putative hybrids. Reference X. strumarium sequences were unmatched to the DNA barcodes of specimens sampled in Australia, and subsequently, we advise against future claims to a historical presence of this species in Australia. Our findings are significant for taxonomic treatment of Xanthium species in Australia and for consideration of source-specific biological controls of these weeds.

Limited Evidence of Native Woody Plant Recovery and Changes in Millipede and Earthworm Communities Following Herbicide Applications on Callery Pear (Pyrus calleryana) - Joseph M. McGee; James T. Vogt; Bruce A. Snyder (Forest Science, 2025)

Unraveling microclimate effects on pollinator foraging and crop yield in lowbush blueberry - Garrett Sisk; Anaís Ostroski; Travis Dillard; Bruce Hall; Sarah C. Goslee; Christina M. Grozinger; Vikas Khanna; Heather Grab (Agriculture, Ecosystems & Environment, 2025)

Benefits and tradeoffs of diversifying rice-based cropping systems: Impacts on soil health, productivity, and agroecosystem multifunctionality - Sara Rosenberg; Amélie C.M. Gaudin; Tommy L.D. Fenster; Whitney Brim-DeForest; Bruce Linquist; Michelle M. Leinfelder-Miles; Luis Espino; Kassim Al-Khatib; Cameron M. Pittelkow (Agriculture, Ecosystems & Environment, 2025)

Molecular Footprints of Quaternary Climate Fluctuations in the Circumpolar Tundra Shrub Dwarf Birch - Maria Dance; Erin E. Saupe; James Borrell; Pernille Bronken Eidesen; Daniel Ackerman; Jakob Assmann; Bruce C. Forbes; Marina Gurskaya; Toke T. Høye; Stein R. Karlsen; Timo Kumpula; Mariusz Lamentowicz; et al. (Molecular Ecology, 2025)
The Arctic tundra biome is undergoing rapid shrub expansion (‘shrubification’) in response to anthropogenic climate change. During the previous ~2.6 million years, glacial cycles caused substantial shifts in Arctic vegetation, leading to changes in species' distributions, abundance and connectivity, which have left lasting impacts on the genetic structure of modern populations. Examining how shrubs responded to past climate change through genetic data reveals the demographic dynamics that shaped their current diversity and distribution and sheds light on the resilience of Arctic shrubs. Here we test scenarios of Quaternary demographic history of dwarf birch species ( Betula nana L. and Betula Glandulosa Michx.) using Single Nucleotide Polymorphism (SNP) markers obtained from RAD sequencing and approximate Bayesian computation. We compare the timings of modelled population events with ice sheet reconstructions and other paleoenvironmental information to untangle the impacts of alternating cold and warm periods on dwarf birch. Our best supported model suggested that the species diverged in the Mid‐Pleistocene Transition as glaciations intensified. We found support for a complex history of inter‐ and intraspecific divergences and gene flow, and secondary contact occurred during both ice sheet expansion and retreat. Our spatiotemporal analysis suggests that the modern genetic structure of dwarf birch results from transitions in climate between glacials and interglacials, with ice sheets acting alternatively as a barrier or an enabler of population mixing. Tundra shrubs may have had more nuanced responses to past climatic changes than phylogeographic analyses have often suggested, with implications for future eco‐evolutionary responses to anthropogenic climate change.

Evaluating Seasonal vs. Spatial Extrapolation for Cetacean Distribution Models in the California Current - Elizabeth A. Becker; Karin A. Forney; Bruce J. Thayre; Katherine Whitaker; Ryan Hoopes; Joshua M. Jones; John A. Hildebrand; Jeff Moore (Marine Mammal Science, 2025)
Species distribution models (SDMs) have been developed for multiple cetacean species within the California Current Ecosystem (CCE) from shipboard survey data collected by the Southwest Fisheries Science Center (SWFSC) in summer and fall, thus limiting the ability to inform management decisions in cool seasons when abundance and distribution patterns are substantially different. Winter and spring SDMs have been developed for a few species using California Cooperative Oceanic Fisheries Investigations (CalCOFI) shipboard survey data, but model predictions are limited to the waters off southern and central California. In this study, winter and spring density estimates for the entire CCE study area were made from SWFSC summer and fall model predictions (temporal extrapolation) and CalCOFI winter and spring model predictions (spatial extrapolation) for short‐beaked common dolphin ( Delphinus delphis delphis ), Pacific white‐sided dolphin ( Lagenorhynchus obliquidens ), Dall's porpoise ( Phocoenoides dalli ), and fin whale ( Balaenoptera physalus ). The performance of the models was compared based on available abundance estimates and documented distribution patterns in the cool seasons. Results reveal species‐specific ecological factors to consider when extrapolating model predictions temporally or spatially, including whether a given study area includes a species “core habitat”, and whether static variables should be included when a species exhibits temporal distribution shifts.

Composition, Growth, Succession, and Function in the Cladophora Microbiome: Insights From Quantitative Stable Isotope Probing and NanoSIMS Imaging - Raina M. Fitzpatrick; Bruce A. Hungate; Mary Power; Megan Foley; Ty Samo; Egbert Schwartz; Micheala Hayer; Peter K. Weber; Jennifer Pett‐Ridge; Jane C. Marks (Environmental Microbiology, 2025)
The branching green macroalga Cladophora glomerata and its epiphytic microbiome dominate summer biomass in the Eel River, a Northern California river under Mediterranean (summer drought, winter rain) seasonality. Green Cladophora streamers proliferate in early summer, then change to yellow and then red‐brown as epiphyte loads increase. We characterised successional changes in epiphytic bacteria on Cladophora , examining both community composition and growth rates, using quantitative Stable Isotope Probing (qSIP) and 16S rRNA gene amplicon sequencing. The number of bacterial taxa increased with succession while growth rates peaked in the middle stage. NanoSIMS imaging confirmed high sulphur (S) concentrations in Cladophora cell walls relative to surrounding biomass, coinciding with a bloom of sulphur bacteria (bacteria that reduce or oxidise sulphur/sulphates). In general, relative abundances and growth rates were independent, indicating that either metric alone is insufficient for understanding how taxonomy and functional groups affect ecosystem processes. For instance, the relative abundance of nitrogen fixers peaked in the late summer when their relative growth rates were slowest. Such patterns may be driven by space competition limiting growth. Together, changes in abundance and relative growth rates suggest different limiting factors for different functional groups in the Cladophora microbiome at multiple successional stages.

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Smartphone-integrated visual inspection for enhancing agricultural product quality and safety: a review - Lingyuan Xu; A. M. Abd El-Aty; Peipei Li; Jia Li; Jing Zhao; Xingmei Lei; Song Gao; Yun Zhao; Yongxin She; Fen Jin; Jing Wang; Shuting Wang; et al. (Critical Reviews in Food Science and Nutrition, 2025)

Novel Correlations Between Lung Function and Gut Microbial-Produced VOCs in the Exhaled Breath of Ultramarathon Runners: Insights from the 2019 Ultra-Trail du Mont Blanc - Hsuan Chou; Amy Craster; Kayleigh Arthur; Billy Boyle; Max Allsworth; Eli F. Kelley; Glenn M. Stewart; Courtney M. Wheatley-Guy; Jesse Schwartz; Caitlin C. Fermoyle; Briana L. Ziegler; Kay A. Johnson; et al. (Journal of Science in Sport and Exercise, 2025)

Epigenome-wide association study of gestational exposure to organophosphate esters and replacement brominated flame retardants with newborn DNA methylation - Angelico Mendy; Zana Percy; Joseph M. Braun; Bruce Lanphear; Mark J. La Guardia; Robert C. Hale; Scott Langevin; Karl Kelsey; Aimin Chen; Kimberly Yolton (Science of The Total Environment, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Hempseed cell wall polysaccharides are dominated by linear xylans and cellulose: Comprehensive structural profiling of ten cultivars of industrial hemp, Cannabis sativa L. - Prakash Raj Pandeya; Ian M. Black; Steven D. Karlen; Christian Heiss; Yen-Chang Tseng; A. Bruce Downie; Parastoo Azadi; Rachel R. Schendel (Carbohydrate Polymers, 2025)

Whole Transcriptome RNA-Seq Reveals Drivers of Pathological Dysfunction in a Transgenic Model of Alzheimer’s Disease - Nikita Potemkin; Sophie M. F. Cawood; Diane Guévremont; Bruce Mockett; Jackson Treece; Jo-Ann L. Stanton; Joanna M. Williams (Molecular Neurobiology, 2025)
Alzheimer’s disease (AD) affects more than 55 million people worldwide, yet current theories cannot fully explain its aetiology. Accordingly, gene expression profiling has been used to provide a holistic view of the biology underpinning AD. Focusing primarily on protein-coding genes, such approaches have highlighted a critical involvement of microglia-related inflammatory processes. Simultaneous investigation of transcriptional regulators and noncoding RNA (ncRNA) can offer further insight into AD biology and inform the development of disease-modifying therapies. We previously described a method for whole transcriptome sampling to simultaneously investigate protein-coding genes and ncRNA. Here, we use this technique to explore transcriptional changes in a murine model of AD (15-month-old APP/PS1 mice). We confirmed the extensive involvement of microglia-associated genes and gene networks, consistent with literature. We also report a wealth of differentially-expressed non-coding RNA — including microRNA, long non-coding RNA, small nuclear and small nucleolar RNA, and pseudogenes — many of which have been overlooked previously. Transcription factor analysis determined that six transcription factors likely regulate gene expression changes in this model ( Irf8 , Junb , c-Fos , Lmo2 , Runx1 , and Nfe2l2 ). We then utilised validated miRNA-target interactions, finding 60 interactions between 15 miRNA and 42 mRNA (messenger RNA) with largely consistent directionality. Furthermore, we found that eight transcription factors ( Clock , Lmo2 , Runx1 , Nfe2l2 , Egr2 , c-Fos , Junb , and Nr4a1 ) are likely responsible for the regulation of miRNA expression. Taken together, these data indicate a complex interplay of coding and non-coding RNA, driven by a small number of specific transcription factors, contributing to transcriptional changes in 15-month-old APP/PS1 mice.

An Overview of Vaccine Development Strategies for Columnaris‐Causing Bacteria in Cultured Fish - Courtney E. Harrison; Benjamin R. LaFrentz; Craig A. Shoemaker; Miles D. Lange; Mark R. Liles; Haitham H. Mohammed; Benjamin H. Beck; Emily M. Churchman; Eric Peatman; Timothy J. Bruce (Journal of Fish Diseases, 2025)
Columnaris disease, caused by columnaris‐causing bacteria (CCB), affects cultured and wild freshwater fish worldwide. Belonging to the phylum Bacteroidota and the family Flavobacteriaceae, CCB are gram‐negative, yellow‐pigmented bacteria that are presumed ubiquitous in freshwater habitats. Since the first report of the disease in 1922, growth and survival, pathogenesis, and transmission of these pathogens have been intensely researched, aiding in a greater understanding of host‐pathogen interactions. Recent classification of Flavobacterium columnare into four distinct species based on genetic similarity, including F. columnare , F. covae , F. davisii , and F. oreochromis , along with their host associations is critical to understanding disease dynamics and prevention strategies. Outbreaks of the disease typically follow stressful events where CCB colonise external tissues, such as skin and gill. Vaccination against columnaris disease was practiced as early as the 1970's. Since then, many different vaccine types have been under development, including killed, live‐attenuated, recombinant, and micro‐ and nano‐particle vaccines. Among the different CCB vaccine types, immune responses and level of protection have been variable. However, some vaccines have been reported to offer moderate‐significant protection in some fish species. This review synthesises the current knowledge of CCB taxonomy, genetic diversity, virulence, and immunity in various aquaculture species, with the goal of identifying knowledge gaps to be addressed for future CCB vaccine development. The development of an efficacious columnaris vaccine remains a challenge, with promising results in the laboratory that have yet to be reflected under production settings. This highlights the need for improved strategies tailored to the species of CCB most appropriate for the target host species.

Coinfection of channel catfish ( Ictalurus punctatus ) with virulent Aeromonas hydrophila and Flavobacterium covae exacerbates mortality - Allison L. Wise; Benjamin R. LaFrentz; Anita M. Kelly; Mark R. Liles; Matt J. Griffin; Benjamin H. Beck; Timothy J. Bruce (Journal of Fish Diseases, 2025)
Flavobacterium covae and virulent Aeromonas hydrophila are prevalent bacterial pathogens within the US catfish industry that can cause high mortality in production ponds. An assessment of in vivo bacterial coinfection with virulent A. hydrophila (ML09‐119) and F. covae (ALG‐00‐530) was conducted in juvenile channel catfish ( Ictalurus punctatus ). Catfish were divided into seven treatments: (1) mock control; (2) and (3) high and low doses of virulent A. hydrophila ; (4) and (5) high and low doses of F. covae ; (6) and (7) simultaneous challenge with high and low doses of virulent A. hydrophila and F. covae . In addition to the mortality assessment, anterior kidney and spleen were collected to evaluate immune gene expression, as well as quantify bacterial load by qPCR. At 96 h post‐challenge (hpc), the high dose of virulent A. hydrophila infection (immersed in 2.3 × 10 7 CFU mL −1 ) resulted in cumulative percent mortality (CPM) of 28.3 ± 9.5%, while the high dose of F. covae (immersed in 5.2 × 10 6 CFU mL −1 ) yielded CPM of 23.3 ± 12.9%. When these pathogens were delivered in combination, CPM significantly increased for both the high‐ (98.3 ± 1.36%) and low‐dose combinations (76.7 ± 17.05%) ( p tnfα , il8 , il1b ) demonstrated increased expression levels at 48 hpc. These results demonstrate the additive effects on mortality when these two pathogens are combined. The synthesis of these mortality and health metrics advances our understanding of coinfections of these two important catfish pathogens and will aid fish health diagnosticians and channel catfish producers in developing therapeutants and prevention methods to control bacterial coinfections.

Investigation of dietary exogenous protease and humic substance on growth, disease resistance to Flavobacterium covae and immune responses in juvenile channel catfish ( Ictalurus punctatus ) - Abdulmalik A. Oladipupo; Anita M. Kelly; D. Allen Davis; Timothy J. Bruce (Journal of Fish Diseases, 2025)
Many bacterial pathogens impact the US catfish industry, and disease control can be challenging for producers. Columnaris disease in channel catfish, Ictalurus punctatus , is primarily caused by Flavobacterium covae (formerly F. columnare ). Immunostimulants may enhance nonspecific immune responses and offer an alternative to antibiotic treatments in catfish. Furthermore, dietary protein sources and inclusions are also essential to fish health and nutrition and may enhance overall fish performance in pond culture. The current project evaluated two immunostimulants: a protease complex (PC) and a humic substance (HS) derived from a reed‐sedge peat product. A 60‐day trial examined the effects of five diets on growth performance, immune response and resistance to experimental F. covae infection in channel catfish. Diets included a high‐quality fishmeal diet (32%; CF32), a high‐protein soy‐based diet (32%; C32), a low‐protein soy‐based diet (28%; C28; predominately used in industry), a low‐protein soy diet supplemented with C28 + PC at 175 g metric ton −1 and C28 + HS in a low‐protein diet at 23 g metric ton −1 . Following feeding for 60 d, juvenile channel catfish were sampled for growth performance and baseline health indicators ( n = 3; body mucus, blood for sera, kidney and spleen). A subset of fish was then subjected to an immersion‐based in vivo challenge trial with F. covae (ALG‐00‐530; 10 6 CFU mL −1 exposure). At 60d post‐initiation, there were no dietary differences in the relative growth rate ( p = .063) or thermal growth coefficient ( p = .055), but the 32% diets generally appeared to perform best. Post‐challenge, the C32 group's mortality was higher than the C28 + PC ( p = .006) and C28 + HS diets ( p = .005). Although not significant, the C28 and CF32 groups also demonstrated higher mortality compared to both PC and HS diets. Sera lysozyme concentration was found to increase following pathogen challenge ( p p il‐1β , il‐8 , tnf‐α and tgf‐β ) were observed at trial midpoint and post‐infection when compared to 60d. The C28 treatment was found to have lower tnf‐α expression than the C28 + PC ( p = .042) and C28 + HS ( p = .042) groups following exposure to F. covae . These challenge data suggest that the immunostimulants (PC and HS) in plant‐based protein may be beneficial in protecting against F. covae when offered in low‐protein channel catfish diets.

From concept to reality: the journey of establishing the Australian companion animal registry of cancers (ACARCinom) - C. Palmieri; P. Bennett; M. Bruce; M. Krockenberger; P. McLaren; T. Meiring; K. Mengersen; A. Peaston; A. Roach; G. Rossi; A. Stent; R. Soares-Magalhaes (Journal of Comparative Pathology, 2025)

Systematics of helium diffusion sinks in apatite demonstrated by 4He/3He degassing experiments and modeling - Hongcheng Guo; Marissa M. Tremblay; Peter K. Zeitler; Bruce D. Idleman; Annia K. Fayon (Geochimica et Cosmochimica Acta, 2025)

Combining ability for resistance to fall armyworm, Spodoptera frugiperda in tropical maize inbred lines - Ovide Nuambote-Yobila; Anani Y. Bruce; Dan Makumbi; Gerphas O. Ogola; Charles Marangu; Yoseph Beyene; Nzola-Meso Mahungu; Boddupalli M. Prasanna; Frédéric Marion-Poll; Paul-André Calatayud (Phytoparasitica, 2025)

Influence of dietary fermented yeast products (Saccharomyces cerevisiae) on performance, health and microbiome of Nile tilapia (Oreochromis niloticus) and the influence of discharge water in the production of romaine lettuce (Lactuca sativa) - Uthpala M. Padeniya; D. Allen Davis; Daniel E. Wells; Courtney E. Harrison; Benjamin R. LaFrentz; Benjamin H. Beck; Luke A. Roy; Mark Farmer; Timothy J. Bruce (Animal Feed Science and Technology, 2025)

Resource quantity and quality co‐limit consumer production in forest streams - Lee M. Demi; Phillip M. Bumpers; Wyatt F. Cross; Susan L. Eggert; John S. Kominoski; David W. P. Manning; Amy D. Rosemond; J. Bruce Wallace; Seth J. Wenger; Jonathan P. Benstead (Ecology, 2025)
Ecological theory predicts that consumers should be co‐limited by resource quantity and quality, given widespread consumer‐resource nutritional imbalances. We used 25 estimates of annual community secondary production (ACSP) of stream macroinvertebrates to assess the relative roles of basal resource quantity (leaf litter standing stock [LLSS]) and quality (% nitrogen and % phosphorus of leaf litter) in modulating patterns of production in forest streams. We also tested the effects of hypothesized indirect drivers (stream discharge and inorganic nutrient concentrations) on basal resource quality and quantity and secondary production. In the top model for ACSP, LLSS, and %P together explained 59% of its variation, providing strong evidence of co‐limitation by both resource quantity and quality. Mean annual stream discharge and stream water P concentration explained 75% and 43% of variation in LLSS and %P, respectively. Together, stream discharge and stream water P concentration explained 77% of the variation in ACSP, demonstrating a critical link between hypothesized indirect and direct (basal resources) drivers and ACSP. Our results are the first to demonstrate co‐limitation of ACSP and highlight several mechanisms by which drivers of anthropogenic global change, such as altered precipitation (stream discharge) and eutrophication, influence the productivity of animal communities in stream ecosystems.

Onset and evolution of summit lava fountaining during the Mauna Loa 2022 eruption - Natália G. Pasqualon; Bruce F. Houghton; Matthew R. Patrick; Edward W. Llewellin; Caroline M. Tisdale (Bulletin of Volcanology, 2025)

Examining the effect of intensive seismic surveys on abundance and behaviour of groundfish species along a continental slope of Newfoundland and Labrador, Canada - Khanh Q. Nguyen; Jacqueline M. Hanlon; Bruce S. Martin; Pablo Borys; Dustin Schornagel; Corey J. Morris (Marine Pollution Bulletin, 2025)

Next generation Arctic vegetation maps: Aboveground plant biomass and woody dominance mapped at 30 m resolution across the tundra biome - Kathleen M. Orndahl; Logan T. Berner; Matthew J. Macander; Marie F. Arndal; Heather D. Alexander; Elyn R. Humphreys; Michael M. Loranty; Sarah M. Ludwig; Johanna Nyman; Sari Juutinen; Mika Aurela; Juha Mikola; et al. (Remote Sensing of Environment, 2025)

Prenatal PFAS exposures and cardiometabolic health in middle childhood in the MIREC cohort - Alan J. Fossa; Amber M. Hall; George D. Papandonatos; Tye E. Arbuckle; Jillian Ashley-Martin; Michael M. Borghese; Jenny Bruin; Aimin Chen; Mandy Fisher; John E. Krzeczkowski; Bruce P. Lanphear; Amanda J. MacFarlane; et al. (Environmental Research, 2025)

Impacts of geographic variability and geologic history on the distribution of post-settlement alluvium (PSA) across the upper Midwest, USA - Alison M. Anders; Bruce L. Rhoads (CATENA, 2025)

Fractal correlation properties of heart rate variability and respiratory frequency as measures of endurance exercise durability - Bruce Rogers; Pablo R. Fleitas-Paniagua; Mackenzie Trpcic; Alessandro M. Zagatto; Juan M. Murias (European Journal of Applied Physiology, 2025)

The caatinga dry tropical forest: A highly efficient carbon sink in South America - Keila R. Mendes; Pablo E.S. Oliveira; José Romualdo S. Lima; Magna S.B. Moura; Eduardo S. Souza; Aldrin M. Perez-Marin; John Elton B.L. Cunha; Pedro R. Mutti; Gabriel B. Costa; Thales N. Martins de Sá; Paula A.A. Araujo; Rosaria R. Ferreira; et al. (Agricultural and Forest Meteorology, 2025)

A clinical chemical atlas of xenobiotic toxicity for the Sprague–Dawley rat - Janonna Kadyrov; Samuele Sala; Lucy Grigoroff; Novia Minaee; Reika Masuda; Samantha Lodge; Timothy M. Ebbels; Michael D. Reily; Donald Robertson; Lois Lehman-McKeeman; John Shockcor; Bruce D. Car; et al. (Archives of Toxicology, 2025)
The Consortium for Metabonomic Toxicology (COMET) studies was designed to model metabolic responses to organ- and mechanism-specific toxins to predict acute drug toxicity in rats. A range of clinical chemical parameters were measured in 7-day toxicology studies for 86 toxins eliciting a range of organ- and mechanism-specific effects. Additionally, 21 surgical or physiological stressors were evaluated to identify physiological or metabolic responses that might confound the interpretation of observed toxicity profiles. From these studies on a total of 3473 rats measured at six pharmaceutical companies, we provide a set of 12 serum and 5 urine physical and clinical chemistry parameters. Samples were collected at 24 h, 48 h and 168 h post-dose for each animal and are presented as a downloadable database file. We also summarise the main observations based on the group response at the level of the individual toxin. We demonstrate that correlations between parameters, such as serum bilirubin and aspartate aminotransferase (AST), provide a more nuanced profile of organ-specific toxicity than consideration of individual parameters alone. In addition, we highlight the variability in the measured parameters across the dataset attributable to inter-laboratory differences, and the heterogeneity of metabolic responses to particular compounds or differences in temporal patterns of response. This clinical chemistry atlas of toxicity serves as a valuable reference tool for evaluating the potential toxicity of novel drug candidates.

Correction to: Putting biomonitors to work: native moss as a screening tool for solid waste incineration - Sarah Jovan; Eleonore Jacobson; Jason M. Unrine; Nasser Jalili-Jahani; Bruce McCune (Environmental Monitoring and Assessment, 2025)

Quantifying explosive processes of the 2022 Meradalir eruption of the Fagradalsfjall Fires, Iceland - Caroline M. Tisdale; Bruce F. Houghton; Thorvaldur Thorsdarson; Edward W. Llewellin; Jóna S. Pálmadóttir (Bulletin of Volcanology, 2025)

Gestational PBDE concentrations and executive function in adolescents with self- and caregiver-report: The HOME study - Kim M. Cecil; Yingying Xu; Aimin Chen; Joseph M. Braun; Andreas Sjodin; Bruce P. Lanphear; Ann M. Vuong; Kimberly Yolton (Environmental Research, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Evaluation of rapid evaporative ionization mass spectrometry (REIMS) for the prediction of slice shear force and quality grades in beef longissimus lumborum steaks - Kaitlyn R. Loomas; Dale R. Woerner; Ben M. Bohrer; Tyson R. Brown; Heather L. Bruce; Marcio S. Duarte; Bimol C. Roy; Yifei Wang; Katie Pedgerachny; Jerrad F. Legako (Meat Science, 2025)

Flood frequency and amplitude analysis under changing climate scenarios in the Mono River Basin, West Africa - Djanna Koubodana Houteta; Moustapha Tall; Rodric M. Nonki; Nilanchal Patel; Mouhamadou B. Sylla; Koffi Djaman; Kossi Atchonouglo; Bruce Hewitson (Sustainable Water Resources Management, 2025)
This study examined the flood frequencies and amplitudes of annual maximum precipitation and discharge within the Mono River Basin (MRB) in Togo, West Africa. We scrutinized daily historical data from 1961 to 2020, alongside Shared Socio-economic Pathway SSP5-8.5 scenario derived from the Coupled Model Intercomparison Project phase 6 (CMIP6) data for 2035 to 2094. The observational data were initially evaluated in conjunction with innovative CMIP6 data collected between 1985 and 2014, and employing the Pearson correlation (r), Percent of Bias (PBIAS), Standardized Root Mean Square Error (RSR), Kling–Gupta efficiency (KGE) validation statistical metrics. Subsequently, Generalized Extreme Value (GEV) probability distributions were utilized to predict flood amplitudes and frequencies, leveraging annual maximum precipitation, discharge, and return period values. The findings revealed new insights regarding flood amplitudes for discharge and precipitation; categorized as moderate, limited, or critical. This classification depended on whether the amplitude fell below or exceeded the specified thresholds under various climate conditions. However, it’s essential to note the intricacies involved in this classification process, as it reflects the complex nature of climate impacts. Our investigation uncovered strong statistical metrics between observation and CMIP6 multi-model ensemble datasets, with acceptable RSR, KGE, and r values above 0.70, and PBIAS lower than − 20%. We determined that the Gumbel probability distribution is the most accurate model for annual maximums at a 95% confidence level. Flood amplitudes were initially categorized into three distinct classes: limited, moderate, or critical (based on their amplitude). This classification was applied to the northern, central, and southern regions. However, the frequency of return periods was observed to be below 25 years for more likely floods across all locations, but they exceeded 25 years for less probable floods in certain regions and scenarios. Although this analysis provides insightful data, it also reveals complexities that warrant further exploration. We projected an increase in less severe floods in the MRB over the next 25 years, with changing flood amplitudes and increased frequencies for most south regions from past to future periods. These results highlight the pressing need to enhance early warning systems and strengthen societal resilience through sustainable policies and governance.

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Differential Responses of the Egg-Larval Parasitoid Chelonus Bifoveolatus To Fall Armyworm-Induced and Constitutive Volatiles of Diverse Maize Genotypes - Collins O. Onjura; Emmanuel Peter; George O. Asudi; Michael M. Gicheru; Samira A. Mohamed; Toby J. A. Bruce; Amanuel Tamiru (Journal of Chemical Ecology, 2025)
The fall armyworm (FAW), Spodoptera frugiperda , is a serious invasive crop pest and threat to food security. Conventional pest control approaches using chemical pesticides can lead to adverse environmental and human health problems calling for safer alternative pest management options. Volatile organic compounds (VOCs) released by plants constitutively and in response to herbivory have been shown to enhance ecologically benign biocontrol alternatives to chemical insecticides for pest management. However, genotypic variations in VOC emissions have also been reported for plant species including maize ( Zea mays ). Hence, a better insight into the variations in odor profiles of different maize varieties and their corresponding role in recruiting pests’ natural enemies are crucial for developing a sustainable biocontrol strategy. Our present study assessed the behavioral responses of the FAW egg-larval parasitoid, Chelonus bifoveolatus (Braconidae: Hymenoptera), to constitutive and induced volatiles from different maize landraces (Jowi Red, Nyamula) and hybrids (SC Duma, DK 777) grown in Kenya and compared their volatile profiles. In a four-arm olfactometer, female parasitoid wasps were significantly attracted to FAW oviposition-induced VOCs from SC Duma and Nyamula. Chemical analysis of test plant volatiles revealed significant variation in the quantity and quality of key bioactive VOCs such as ( E )-2-hexenal, α-pinene, ( Z )-3-hexenyl acetate, ( E )-4,8-dimethyl-1,3,7-nonatriene, α-copaene, ( E) -β-farnesene and ( E , E )-4,8,12-trimethyl-1,3,7,11-tridecatetraene. Our findings provide more insights into genetic variation in VOCs emission across maize genotypes and the corresponding differences in attraction of pest natural enemies that provide indirect defense. As such, these traits could be exploited to enhance ecologically sustainable pest management strategies.

Can agricultural systems facing climate change benefit from a deeper understanding of invasive plant species? - Artur Nosalewicz; Ali A. Bajwa; Dana M. Blumenthal; David Edwards; Marcel G.C. França; Ülo Niinemets; Bruce A. Osborne; Lewis H. Ziska (Agriculture, Ecosystems & Environment, 2025)

Molecular characterization of a polymycovirus in Leptosphaeria biglobosa - Nesma M. Samir; Jacob Locke-Gotel; Syun-Ichi Urayama; Adel A. El-Morsi; Ghada A. El-Sherbeny; Yongju Huang; Bruce D. L. Fitt; Hiromitsu Moriyama; Robert H. A. Coutts; Ioly Kotta-Loizou (Archives of Virology, 2025)
Leptosphaeria biglobosa is a phytopathogenic ascomycete of Brassica napus that causes phoma stem canker/blackleg. A new double-stranded RNA (dsRNA) mycovirus from this fungus has been fully characterized. The virus genome has five dsRNA segments, ranging in length from 1,180 bp to 2,402 bp. Each dsRNA has a single open reading frame flanked by 5′ and 3′ untranslated regions. The proteins encoded by dsRNAs 1 and 3, an RNA-dependent RNA polymerase (RdRP) and a methyltransferase, respectively, have significant similarity to those of Plasmopara viticola lesion associated polymycovirus 1. The proline-alanine-serine-rich protein encoded by dsRNA 5 is similar to that of Erysiphe necator associated polymycovirus 1. The proteins encoded by dsRNAs 2 and 4 have significant similarity to those of a mycovirus identified in Alternaria sp. FA0703. Phylogenetic analysis based on RdRP sequences showed that this virus clusters with members of the family Polymycoviridae . Based on these observations, this virus, which we have named "Leptosphaeria biglobosa polymycovirus 1", should be classified as a member of the family Polymycoviridae . This is the first report of a polymycovirus in L. biglobosa.

Marine strontium isotopes preserved in fossil shark teeth calibrate Neogene land mammal evolution - Stephanie R. Killingsworth; Sean M. Moran; Bruce J. MacFadden; Victor J. Perez; Jeanette Pirlo; Michael J. Ziegler (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Triangulating habitat suitability for the locally extirpated California grizzly bear - Alex McInturff; Peter S. Alagona; Scott D. Cooper; Kaitlyn M. Gaynor; Sarah E. Anderson; Elizabeth S. Forbes; Robert Heilmayr; Elizabeth H.T. Hiroyasu; Bruce E. Kendall; Alexis M. Mychajliw; Molly Hardesty-Moore (Biological Conservation, 2025)

Routine large-scale movements of the yelloweye rockfish (Sebastes ruberrimus) - Leif K. Rasmuson; Matthew T. O. Blume; Kelly A. Lawrence; Bruce M. Laughlin; Christopher A. Edwards; Mark R. Terwilliger; A. Camille Ayrea; Alexandra G. McInturf; Bryan J. Legare; Taylor K. Chapple (Frontiers in Marine Science, 2025)
Of the seven species of Pacific rockfish declared overfished in the California Current in 2008, yelloweye rockfish ( Sebastes ruberrimus ) is the only remaining overfished rockfish species. Part of the original rebuilding plan included designation of a yelloweye rockfish conservation area, a rocky reef closed off the Central Coast of Oregon that is closed to bottom fishing. The yelloweye rockfish conservation area’s ability to help rebuild the population, is predicated on the theory that demersal rockfishes are relatively sedentary. However, in the years since being declared overfished, acoustic tagging studies suggested yelloweye rockfish did not remain in the yelloweye rockfish conservation area. However, where they went remained a mystery. In this paper we describe the use of pop-off satellite tags to conduct a mark-recapture study of 11 yelloweye rockfish tagged within the Stonewall Bank Yelloweye Rockfish Conservation Area. We used back-in-time particle tracking coupled with an ocean circulation model in an attempt to increase the precision in the location at which each tag shed off the fish, and further validated that location by associating it to the underlying seafloor habitat type. Ten out of eleven tags were shed from the fish while it was outside the Stonewall Bank Yelloweye Rockfish Conservation Area’s boundary. While most fish remained within 50 km of the Stonewall Bank Yelloweye Rockfish Conservation Area, one tagged fish swam to an offshore reef off Central Washington (~40 km from the shore). Backtracked locations were more likely over rock than the initial satellite transmission, indicating the method was effective at identifying tag shed locations. We found no relationship between days at large, fish sex or length and the distance between release site and shed location. Our work supports a growing body of work that suggests yelloweye rockfish have less site fidelity than previously hypothesized.

Inhibition of soluble epoxide hydrolase ameliorates cerebral blood flow autoregulation and cognition in alzheimer's disease and diabetes-related dementia rat models - Chengyun Tang; Jane J. Border; Huawei Zhang; Andrew Gregory; Shan Bai; Xing Fang; Yedan Liu; Shaoxun Wang; Sung Hee Hwang; Wenjun Gao; Gilbert C. Morgan; Jhania Smith; et al. (GeroScience, 2025)

Prenatal and postnatal exposure to organophosphate esters and replacement flame retardant mixtures and childhood respiratory outcomes - Angelico Mendy; Zana Percy; Joseph M. Braun; Bruce Lanphear; Mark J. La Guardia; Robert C Hale; Kimberly Yolton; Aimin Chen (Environmental Research, 2025)

Corrigendum to “Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes” [Biol. Conserv. 300 (2024), 110843] - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2025)

Declines in greater bilby (Macrotis lagotis) geographic range and realised niche are best explained by the invasive red fox (Vulpes vulpes) - Hayley M. Geyle; Alys R. Young; Brett P. Murphy; Chris R. Dickman; Christine Schlesinger; Kelly M. Dixon; Harry Moore; Sarah Legge; Jennifer Silcock; Naomi Indigo; Martin Dziminski; Bruce Greatwich; et al. (Biological Conservation, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Demonstrating a biobased concept for the production of sustainable bacterial cellulose from mixed textile, agricultural and municipal wastes - Alexandra Lanot; Shivam Tiwari; Philip Purnell; Abdalla M. Omar; Miriam Ribul; Daniel J. Upton; Heather Eastmond; Ishrat J. Badruddin; Hannah F. Walker; Angharad Gatenby; Sharon Baurley; Paulo J.D.S. Bartolo; et al. (Journal of Cleaner Production, 2025)

Prenatal exposure to PFAS and the association with neurobehavioral and social development during childhood - Trisha Saha; M. Corinaud J. Gbemavo; Linda Booij; Tye E. Arbuckle; Jillian Ashley-Martin; Mandy Fisher; Gina Muckle; Bruce Lanphear; Elizabeth Asztalos; Jean Séguin; Maryse F. Bouchard (International Journal of Hygiene and Environmental Health, 2025)

Occurrence, characterization, and ecological risk analysis of petroleum hydrocarbons in water and sediments following large-scale field simulated oil spills at the experimental lakes area, Northwestern Ontario, Canada - Zeyu Yang; Keval Shah; Bruce Hollebone; Sonia Laforest; Madison MacGillivray; Diane Dey; Jose Luis Rodriguez; Benoit Lalonde; Chun Yang; Vanessa Beaulac; Jules M. Blais; Mark Hanson; et al. (Marine Pollution Bulletin, 2024)

Disrupted development in fathead minnow embryos exposed to wetland waters from the Athabasca Oil Sands Region, Alberta, Canada - Joanne L. Parrott; Danna M. Schock; Ian J. Vander Meulen; Lukas Mundy; Bruce Pauli; Kerry Peru; John V. Headley (Science of The Total Environment, 2024)

Comparing efficiencies of population control methods for responding to introductions of transboundary animal diseases in wild pigs - Nathan P. Snow; Benjamin Smith; Michael J. Lavelle; Michael P. Glow; Kayleigh Chalkowski; Bruce R. Leland; Sarah Sherburne; Justin W. Fischer; Keely J. Kohen; Seth M. Cook; Hatton Smith; Kurt C. VerCauteren; et al. (Preventive Veterinary Medicine, 2024)

Sequence stratigraphy and metre-scale cyclicity of Neoarchean dolomite strata at Bushy Park, Griqualand West Basin, Transvaal, South Africa - William Baugaard; Jay M. Gregg; Bruce A. Ahler (Journal of African Earth Sciences, 2024)

Gestational organophosphate esters (OPEs) and executive function in adolescence: The HOME Study - Ann M. Vuong; Zana Percy; Weili Yang; Amruta M. Godbole; Maria Ospina; Antonia M. Calafat; Kim M. Cecil; Bruce P. Lanphear; Joseph M. Braun; Kimberly Yolton; Aimin Chen (Environmental Research, 2024)

Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2024)

Comparison of the reinforcing, antinociceptive, and respiratory depressant effects of prototypical and G-protein biased mu-opioid receptor agonists in male and female Sprague–Dawley rats - C. Austin Zamarripa; Tanya Pareek; Loc M. Pham; Bruce E. Blough; Hayley M. Schrock; Eric J. Vallender; Kenneth J. Sufka; Kevin B. Freeman (Psychopharmacology, 2024)

Putting biomonitors to work: native moss as a screening tool for solid waste incineration - Sarah Jovan; Eleonore Jacobson; Jason M. Unrine; Nasser Jalili-Jahani; Bruce McCune (Environmental Monitoring and Assessment, 2024)
Solid waste incineration (SWI) can release numerous air pollutants although the geographic reach of emissions is not routinely monitored. While many studies use moss and lichens for biomonitoring trace elements, including around SWIs, few investigate the complex, multi-element footprint expected from SWI emissions. This study develops using native moss as a screening tool for SWI while also informing community concerns about an aging incinerator in rural Oregon, USA. Trained community volunteers helped collect 36 composite samples of epiphytic moss ( Orthotrichum s.l.) along a 32-km transect from the SWI. We used ICP-MS to measure 40 elements in moss, including 14 rare earth elements (REEs) previously unexplored for SWI. We compared the elemental signatures of samples with an emissions profile for SWI and modeled relationships between element concentrations and distance from the facility using nonparametric regression. The chemical signatures in moss pointed to SWI as a source, potentially through both stack and fugitive dust emissions. The strongest models described farther-dispersing elements, including mercury and cadmium (xR 2 = 0.65 and 0.62, respectively), and suggested most deposition occurs within 5 to 10 km of the facility. Elements often associated with soil and dust, like arsenic and chromium, exhibited localized peaks within 0.2 km of the incinerator (xR 2 = 0.14–0.3). Three novel elements—cesium and REEs europium and gadolinium—also showed promise as atmospheric tracers for SWI. Gadolinium, a contrast reagent for MRIs, could reflect medical waste incineration by the facility. We include additional analysis and discussion to help stakeholders use results effectively.

Blue and fin whale residence time and occupancy in Navy training and testing areas off the U.S. West Coast - Barbara A. Lagerquist; Ladd M. Irvine; Thomas M. Follett; Kristen Ampela; Erin A. Falcone; Gregory S. Schorr; Bruce R. Mate; Daniel M. Palacios (Frontiers in Marine Science, 2024)
Blue ( Balaenoptera musculus ) and fin ( B. physalus) whales are prominent species in the California Current Ecosystem (CCE) using the area for migration and foraging. Blue whales migrate between tropical wintering grounds and higher latitude foraging grounds in the CCE, whereas fin whales may remain there year-round. We used Argos tracks of 182 blue (mean duration: 78 days) and 98 fin (mean duration: 35 days) whales tagged from 1994-2018 along the U.S. West Coast to examine residence time and occupancy in U.S. Navy training and testing areas. Bayesian hierarchical switching state-space model locations calculated from Argos tracks were used to provide residence time and proportion of tracking duration within each Navy area. We also calculated relative occupancy isopleths from the state space models, for both directed and non-directed movement, to assess spatial use of Navy areas. We then used generalized linear mixed models and beta regression to examine relationships between Navy area use and covariates, including six climate indices. Point Mugu Sea Range (PMSR) was the most heavily used Navy area by both species in terms of whale numbers, followed by the Southern California Range Complex (SOCAL). Residence time was longest in PMSR for blue whales and in the Northwest Training and Testing Study Area (NWTT) for fin whales. Blue whale use in PMSR was greater in summer versus autumn and for whales tagged in Southern versus Central California. Proportion of tracking duration decreased in all areas with increasing values of the Oceanic Niño Index (ONI), and in PMSR, with increasing values of the North Pacific Gyre Oscillation. Fin whale residence time was longer in PMSR during summer than winter or spring and decreased with increasing values of Habitat Compression Index and ONI. Proportion of tracking duration for fin whales was greatest in summer in PMSR and in winter in SOCAL and NWTT. Overlap of directed and non-directed movement was greatest in PMSR for both species. This assessment of blue and fin whale residence time and occupancy in Navy areas improves our understanding of potential threats these animals face, not only from military activities in Navy areas, but throughout the CCE.

Long-distance Southern Ocean environmental DNA (eDNA) transect provides insights into spatial marine biota and invasion pathways for non-native species - Georgia M. Nester; Leonie Suter; John A. Kitchener; Michael Bunce; Andrea M. Polanowski; Johan Wasserman; Bruce Deagle (Science of The Total Environment, 2024)

Threat assessment for Pacific sand lance (Ammodytes personatus) in the Salish Sea - Jacqueline R. Huard; Victoria Hemming; Matthew R. Baker; Jennifer Blancard; Ian Bruce; Sarah Cook; Gail K. Davoren; Phillip Dionne; Virginia East; J. Mark Hipfner; Nicola R. Houtman; Brian A. Koval; et al. (Frontiers in Marine Science, 2024)
Like many forage fish species, Pacific sand lance ( Ammodytes personatus ) play a key role in nearshore marine ecosystems as an important prey source for a diverse array of predators in the northeastern Pacific. However, the primary threats to Pacific sand lance and their habitat are poorly defined due to a lack of systematic data. Crucial information needed to assess their population status is also lacking including basic knowledge of their local and regional abundance and distribution. Sand lance are currently listed as ‘not evaluated’ under the IUCN red list and they have not been assessed by US and Canadian agencies. This hampers management and policy efforts focused on their conservation. To address this knowledge gap, we conducted a three-part, structured expert elicitation to assess the vulnerability of Salish Sea sand lance populations. Experts were asked to list and rank key threats to Salish Sea sand lance and/or their habitat, to further quantify the vulnerability of sand lance to identified threats using a vulnerability matrix, and to predict the population trajectory in 25 years from today. Impacts associated with climate change (e.g. sea level rise, sea temperature rise, ocean acidification, and extreme weather) consistently ranked high as threats of concern in the ranking exercise and quantified vulnerability scores. Nearly every expert predicted the population will have declined from current levels in 25 years. These results suggest sand lance face numerous threats and may be in decline under current conditions. This research provides vital information about which threats pose the greatest risk to the long-term health of sand lance populations and their habitat. Managers can use this information to prioritize which threats to address. Future research to reliably quantify population size, better understand the roles of natural and anthropogenic impacts, and to identify the most cost-effective actions to mitigate multiple threats, is recommended.

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Crystal mush interaction controls eruptive style during the 2018 Kīlauea fissure eruption - Arianna Soldati; Daniel Weidendorfer; Corrado Cimarelli; Ulrich Kueppers; Bruce F. Houghton; Caroline M. Tisdale; Donald B. Dingwell (Journal of Volcanology and Geothermal Research, 2024)

Mule deer selection of fuel reductions is restricted by site fidelity and structured by circadian and seasonal patterns - Tavis D. Forrester; Derek B. Spitz; Jennifer L. Merems; Michael J. Wisdom; Mary M. Rowland; Bruce K. Johnson; Joshua B. Smith; Taal Levi; Ryan A. Long; Darren A. Clark (Forest Ecology and Management, 2024)

Accelerating and standardising IUCN Red List assessments with sRedList - Victor Cazalis; Moreno Di Marco; Alexander Zizka; Stuart H.M. Butchart; Manuela González-Suárez; Monika Böhm; Steven P. Bachman; Michael Hoffmann; Ilaria Rosati; Francesco De Leo; Martin Jung; Ana Benítez-López; et al. (Biological Conservation, 2024)

The effects of four hours of normobaric hypoxia on the vestibular control of balance - M. I. B. Debenham; C. B. Bruce; C. J. McNeil; B. H. Dalton (Experimental Brain Research, 2024)

Correction: Introduced mice influence the large-bodied alpine invertebrate community - Aaron Bertoia; Tara J. Murray; Bruce C. Robertson; Joanne M. Monks (Biological Invasions, 2024)

Introduced mice influence the large-bodied alpine invertebrate community - Aaron Bertoia; Tara J. Murray; Bruce C. Robertson; Joanne M. Monks (Biological Invasions, 2024)
Invasive mammalian predators are a key threat to native fauna globally. Island ecosystems that developed in isolation from mammals are particularly threatened by introduced mammalian predators. This is the case in New Zealand, where introduced mammalian predators have caused the decline of native birds, lizards, and invertebrates. In alpine areas of New Zealand, predator control targets stoats, rats, and cats as they are recognised as the key threats to native birds. Mice, which are known predators of invertebrates at lower elevations, are not actively controlled. As a result, alpine invertebrates in New Zealand represent an ideal focus for a natural experiment to understand the effects of predator control efforts and invasive mice on native invertebrates that evolved in isolation from mammals. In the Fiordland region of New Zealand, we assessed the large-bodied alpine invertebrate community at eight different sites that vary in their occurrence of mice and control of higher-order predators. We found that the recent presence of mice influenced the invertebrate community: wētā (a group of native orthopterans) were less common at sites where mice were present, and the mean body size of invertebrates collected in pitfall traps was larger at sites where mice were absent compared to sites where they were present. Control of other predators (specifically rats and mustelids) did not influence invertebrate body size, abundance, or community composition. Our findings suggest that, as in lowland environments, mice are an important predator of large-bodied invertebrates in the alpine zone and should be incorporated into future predator management programmes.

Divergent seed dispersal outcomes: Interactions between seed, disperser, and forest traits - Bastien Dehaudt; Tom Bruce; Vincent Deblauwe; António Ferraz; Brett Gardner; Tafon Godwin ‘Babs’ Bibila; Matthew LeBreton; Gaston Mempong; Kevin Njabo; Standly Nkemnyi Nkengbeza; Elsa M. Ordway; Lucas Pavan; et al. (Ecology, 2024)
Animals disperse seeds in various ways that affect seed deposition sites and seed survival, ultimately shaping plant species distribution, community composition, and ecosystem structure. Some animal species can disperse seeds through multiple pathways (e.g., defecation, regurgitation, epizoochory), each likely producing distinct seed dispersal outcomes. We studied how seed traits (size and toughness) interact with disperser species to influence seed dispersal pathway and how this ultimately shapes the proportion of seeds deposited in various habitat types. We focused on three frugivorous species of duikers (African forest antelopes) in the Dja Faunal Reserve, a tropical rainforest in southern Cameroon. Duikers can both defecate and regurgitate seeds, the latter predominantly occurring during rumination at their bedding sites (or “nests”). We located duiker nests and dungs along 18 linear 1‐km‐transects to assess: (1) how seed traits affect the likelihood of dispersal via defecation versus regurgitation, (2) if defecated versus regurgitated seeds are deposited at different rates in different forest types (assessed by indigenous Baka), microhabitats, and forest structural attributes (measured by drone lidar), and (3) if these differ between three duiker species that vary in size and diel activity patterns. We found that duikers predominantly defecated small seeds ( 10 mm length), the latter including 25 different plant species. The three duiker species varied in their nesting habits, with nocturnal bay duikers ( Cephalophus dorsalis ) nesting in dense understory vegetation at proportions 3–4 times higher than Peter's and yellow‐backed duikers ( Cephalophus callipygus and Cephalophus silvicultor ). As a result, bay duikers deposited larger regurgitated seeds at a higher rate in habitats with denser understory where lianas and palms predominate and near fallen trees. This directed regurgitation seed deposition likely plays an important and unique role in forest succession and structure. This study highlights the importance of ungulate seed dispersal by regurgitation, a vastly understudied process that could impact many ecosystems given the prevalence of ruminating ungulates worldwide.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Mesoscale Brain Mapping: Bridging Scales and Modalities in Neuroimaging – A Symposium Review - Joshua K. Marchant; Natalie G. Ferris; Diana Grass; Magdelena S. Allen; Vivek Gopalakrishnan; Mark Olchanyi; Devang Sehgal; Maxina Sheft; Amelia Strom; Berkin Bilgic; Brian Edlow; Elizabeth M. C. Hillman; et al. (Neuroinformatics, 2024)
Advances in the spatiotemporal resolution and field-of-view of neuroimaging tools are driving mesoscale studies for translational neuroscience. On October 10, 2023, the Center for Mesoscale Mapping (CMM) at the Massachusetts General Hospital (MGH) Athinoula A. Martinos Center for Biomedical Imaging and the Massachusetts Institute of Technology (MIT) Health Sciences Technology based Neuroimaging Training Program (NTP) hosted a symposium exploring the state-of-the-art in this rapidly growing area of research. “Mesoscale Brain Mapping: Bridging Scales and Modalities in Neuroimaging” brought together researchers who use a broad range of imaging techniques to study brain structure and function at the convergence of the microscopic and macroscopic scales. The day-long event centered on areas in which the CMM has established expertise, including the development of emerging technologies and their application to clinical translational needs and basic neuroscience questions. The in-person symposium welcomed more than 150 attendees, including 57 faculty members, 61 postdoctoral fellows, 35 students, and four industry professionals, who represented institutions at the local, regional, and international levels. The symposium also served the training goals of both the CMM and the NTP. The event content, organization, and format were planned collaboratively by the faculty and trainees. Many CMM faculty presented or participated in a panel discussion, thus contributing to the dissemination of both the technologies they have developed under the auspices of the CMM and the findings they have obtained using those technologies. NTP trainees who benefited from the symposium included those who helped to organize the symposium and/or presented posters and gave “flash” oral presentations. In addition to gaining experience from presenting their work, they had opportunities throughout the day to engage in one-on-one discussions with visiting scientists and other faculty, potentially opening the door to future collaborations. The symposium presentations provided a deep exploration of the many technological advances enabling progress in structural and functional mesoscale brain imaging. Finally, students worked closely with the presenting faculty to develop this report summarizing the content of the symposium and putting it in the broader context of the current state of the field to share with the scientific community. We note that the references cited here include conference abstracts corresponding to the symposium poster presentations.

Phosphorus attenuation and mobilization in sand filters treating onsite wastewater - Mian Wang; Fanjian Zeng; Siwei Chen; Laura M. Wehrmann; Stuart Waugh; Bruce J. Brownawell; Christopher J. Gobler; Xinwei Mao (Chemosphere, 2024)

MRO overview: Sixteen years in Mars orbit - Richard Zurek; Leslie Tamppari; M. Dan Johnston; Scott Murchie; Alfred McEwen; Shane Byrne; Roberto Seu; Nathaniel Putzig; David Kass; Michael Malin; Bruce Cantor (Icarus, 2024)

Three-dimensional imaging of martian glaciated terrain using Mars Reconnaissance Orbiter Shallow Radar (SHARAD) observations - Matthew R. Perry; Aaron T. Russell; Megan B. Russell; Frederick J. Foss; Frank C. Chuang; Gareth A. Morgan; Zachary M. Bain; Bruce A. Campbell; Nathaniel E. Putzig (Icarus, 2024)

Critical assessment of nitrogen use efficiency indicators: Bridging new and old paradigms to improve sustainable nitrogen management - Santiago Tamagno; Tai McClellan Maaz; Chris van Kessel; Bruce A. Linquist; Jagdish Kumar Ladha; Mark E. Lundy; Fidel Maureira; Cameron M. Pittelkow (European Journal of Agronomy, 2024)

Coupled atmosphere-ocean response of the southwest Pacific to deglacial changes in Atlantic meridional overturning circulation - Shaun R. Eaves; Andrew N. Mackintosh; Joel B. Pedro; Helen C. Bostock; Matthew T. Ryan; Kevin P. Norton; Bruce W. Hayward; Brian M. Anderson; Feng He; Richard S. Jones; Andrew M. Lorrey; Rewi M. Newnham; et al. (Earth and Planetary Science Letters, 2024)

The new kid on the block in insect pest management: sprayable RNAi goes commercial - Junjie Yan; Ralf Nauen; Stuart Reitz; Andrei Alyokhin; Jiang Zhang; David Mota-Sanchez; Yonggyun Kim; Subba Reddy Palli; Silvia I. Rondon; Brian A. Nault; Juan Luis Jurat-Fuentes; Michael S. Crossley; et al. (Science China Life Sciences, 2024)

A longitudinal behavioral analysis of aquarium whale sharks (Rhincodon typus): insights into anticipatory cues, individual variation, and social interaction - Connor G. Gallimore; Celeste Walton; Richard Nugent; Maury Fradkin; Laurie Poppell; Christian Schreiber; Christopher Coco; Matthew Grober; Bruce Carlson; Alistair D. M. Dove; Michael P. Black (Frontiers in Marine Science, 2024)
Rhincodon typus , or the whale shark, is the largest extant fish in the world and is classified as endangered on the IUCN’s Red List. Due to their enormous size and conservation status, whale sharks are rarely housed in aquaria. Here we present a behavioral analysis culminating from a large effort by 89 observers from 2008–2012 to study four R. typus (ID codes: AL, TA, TR, YU) longitudinally in an aquarium setting. We found that relatively simple behavioral metrics such as swim speed, depth occupation, swimming direction, and lead-follow interactions demonstrated R. typus individual variation and responses to habitat changes. All sharks displayed increased swim speeds 30-minutes before regimented feed times, when there was scent of food being fed to other animals in the habitat. Consistently in the habitat, one male shark (YU) was recorded swimming more at depth, faster, almost exclusively clockwise, and engaged in fewer close proximity interactions with others than expected by chance. In contrast, a larger female shark (AL) was observed swimming the slowest, at the surface more than others, led other sharks more than she followed, and had strong lead-follow interactions with another shark of the opposite sex (TA). TA and TR did not differ from each other in depth profiles or speed, but did differ in their proclivity to lead or follow. Depth preferences and lead-follow interactions suggest some partitioning of the habitat and the possibility of social hierarchy in this species. These results represent the first longitudinal behavioral analysis of aquarium R. typus , offering meaningful similarities and contrasts to field observations.

Gestational PBDE concentrations, persistent externalizing, and emerging internalizing behaviors in adolescents: The HOME study - Kim M. Cecil; Yingying Xu; Aimin Chen; Jane Khoury; Mekibib Altaye; Joseph M. Braun; Andreas Sjodin; Bruce P. Lanphear; Nicholas Newman; Jeffrey R. Strawn; Ann M. Vuong; Kimberly Yolton (Environmental Research, 2024)

Per- and polyfluoroalkyl substances and bone mineral content in early adolescence: Modification by diet and physical activity - Jessie P. Buckley; Junyi Zhou; Katherine M. Marquess; Bruce P. Lanphear; Kim M. Cecil; Aimin Chen; Clara G. Sears; Yingying Xu; Kimberly Yolton; Heidi J. Kalkwarf; Joseph M. Braun; Jordan R. Kuiper (Environmental Research, 2024)

A Great Tsunami Earthquake Component of the 1957 Aleutian Islands Earthquake - Yoshiki Yamazaki; Thorne Lay; Kwok Fai Cheung; Robert C. Witter; SeanPaul M. La Selle; Bruce E. Jaffe (Earth and Planetary Science Letters, 2024)

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Improved resilience and proteostasis mediate longevity upon DAF-2 degradation in old age - Adrian Molière; Ji Young Cecilia Park; Anita Goyala; Elena M. Vayndorf; Bruce Zhang; Kuei Ching Hsiung; Yoonji Jung; Sujeong Kwon; Cyril Statzer; David Meyer; Richard Nguyen; Joseph Chadwick; et al. (GeroScience, 2024)
Little is known about the possibility of reversing age-related biological changes when they have already occurred. To explore this, we have characterized the effects of reducing insulin/IGF-1 signaling (IIS) during old age. Reduction of IIS throughout life slows age-related decline in diverse species, most strikingly in the nematode Caenorhabditis elegans . Here we show that even at advanced ages, auxin-induced degradation of DAF-2 in single tissues, including neurons and the intestine, is still able to markedly increase C. elegans lifespan. We describe how reversibility varies among senescent changes. While senescent pathologies that develop in mid-life were not reversed, there was a rejuvenation of the proteostasis network, manifesting as a restoration of the capacity to eliminate otherwise intractable protein aggregates that accumulate with age. Moreover, resistance to several stressors was restored. These results support several new conclusions. (1) Loss of resilience is not solely a consequence of pathologies that develop in earlier life. (2) Restoration of proteostasis and resilience by inhibiting IIS is a plausible cause of the increase in lifespan. And (3), most interestingly, some aspects of the age-related transition from resilience to frailty can be reversed to a certain extent. This raises the possibility that the effect of IIS and related pathways on resilience and frailty during aging in higher animals might possess some degree of reversibility.

The path from root input to mineral-associated soil carbon is dictated by habitat-specific microbial traits and soil moisture - Noah W. Sokol; Megan M. Foley; Steven J. Blazewicz; Amrita Bhattacharyya; Nicole DiDonato; Katerina Estera-Molina; Mary Firestone; Alex Greenlon; Bruce A. Hungate; Jeffrey Kimbrel; Jose Liquet; Marissa Lafler; et al. (Soil Biology and Biochemistry, 2024)

Neurophysiological and other features of working memory in older adults at risk for dementia - Rachel A. Patterson; Heather Brooks; Mina Mirjalili; Neda Rashidi-Ranjbar; Reza Zomorrodi; Daniel M. Blumberger; Corinne E. Fischer; Alastair J. Flint; Ariel Graff-Guerrero; Nathan Herrmann; James L. Kennedy; Sanjeev Kumar; et al. (Cognitive Neurodynamics, 2024)

Managing carbon dioxide mass transfer in photobioreactors for enhancing microalgal biomass productivity - Nima Hajinajaf; Alireza Fallahi; Everett Eustance; Aditya Sarnaik; Anis Askari; Mahsa Najafi; Ryan W. Davis; Bruce E. Rittmann; Arul M. Varman (Algal Research, 2024)

Climatic, oceanic, freshwater, and local environmental drivers of New Zealand estuarine macroinvertebrates - Orlando Lam-Gordillo; Judi E. Hewitt; Emily J. Douglas; Bruce D. Dudley; Steven J. Holmes; Sarah Hailes; Kelly Carter; Barry Greenfield; Tarn Drylie; Andrew M. Lohrer (Marine Environmental Research, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Cryptic corals thriving in dynamic environments may hold key insights into future coral reef habitats - Ashleigh M. Epps; Morgan N. Bruce; Maryssa Dailey; Keisha D. Bahr (Estuarine, Coastal and Shelf Science, 2024)

Proliferation and anatoxin production of benthic cyanobacteria associated with canine mortalities along a stream-lake continuum - Lindsay H. Johnston; Yannan Huang; Tessa D. Bermarija; Cheryl Rafuse; Lydia Zamlynny; Meghann R. Bruce; Catherine Graham; André M. Comeau; Cecilio Valadez-Cano; Janice E. Lawrence; Daniel G. Beach; Rob C. Jamieson (Science of The Total Environment, 2024)

Effects of endocrine disrupting chemicals and their interactions with genetic risk scores on cardiometabolic traits - Xueling Lu; Tian Xie; Martijn van Faassen; Ido P. Kema; André P. van Beek; Xijin Xu; Xia Huo; Bruce H.R. Wolffenbuttel; Jana V. van Vliet-Ostaptchouk; Ilja M. Nolte; Harold Snieder (Science of The Total Environment, 2024)

The U.S. PFAS exposure burden calculator for 2017–2018: Application to the HOME Study, with comparison of epidemiological findings from NHANES - Shelley H. Liu; Yitong Chen; Leah Feuerstahler; Aimin Chen; Anne Starling; Dana Dabelea; Xiaobin Wang; Kim Cecil; Bruce Lanphear; Kimberly Yolton; Joseph M. Braun; Jessie P. Buckley (Neurotoxicology and Teratology, 2024)

Mars' atmosphere, volatiles, and climate as the sun heats up over the next 6 billion years - Bruce M. Jakosky (Icarus, 2024)

(1 → 3),(1 → 6) and (1 → 3)-β-D-glucan physico-chemical features drive their fermentation profile by the human gut microbiota - Matheus Zavadinack; Thaisa M. Cantu-Jungles; Hellen Abreu; Oguz K. Ozturk; Lucimara M.C. Cordeiro; Rilton A. de Freitas; Bruce R. Hamaker; Marcello Iacomini (Carbohydrate Polymers, 2024)

Sensitivity of a meandering lowland river to intensive landscape management: Lateral migration rates before and after watershed-scale agricultural development - Bruce L. Rhoads; Alison M. Anders; Poushalee Banerjee; David A. Grimley; Andrew Stumpf; Neal E. Blair (Anthropocene, 2024)

Optimization of the IntraVascular Oxygenator Catheter Using Angular Oscillation - Stewart Farling; Bruce Klitzman; Travis P. Vesel; Ira M. Cheifetz; Tobias L. Straube; Marc A. Deshusses (Annals of Biomedical Engineering, 2024)

A case study of epizootic ulcerative syndrome ( EUS ) caused by Aphanomyces invadans in eastern mosquitofish ( Gambusia holbrooki ) from the headwaters of Charleston Harbor, South Carolina - Timothy J. Bruce; Carl C. Trettin; Zachary A. Noel; Alex T. Chow; Kylie Warden; Craig Roghair; Troy M. Farmer (Journal of Fish Diseases, 2024)

Growing smaller fish for inclusive markets? Increasing stocking density and shortening the production cycle of Nile tilapia in cages on Lake Victoria - Alexander M. Kaminski; Alexandra M. Pounds; Bruce McAdam; John Bostock; Mary A. Opiyo; David C. Little (Aquaculture, 2024)

Freshwater mussel glochidia infesting anadromous Gaspereau below a hydroelectric generating station: implications for mussel conservation - K. D. R. Dobbs; T. J. Lynn; M. R. Bruce; A. Reyes-Prieto; K. M. Samways; R. A. Curry; M. S. Duffy (Hydrobiologia, 2024)

Opportunities for mitigating net system greenhouse gas emissions in Southeast Asian rice production: A systematic review - Zhenglin Zhang; Ignacio Macedo; Bruce A. Linquist; Bjoern Ole Sander; Cameron M. Pittelkow (Agriculture, Ecosystems & Environment, 2024)

Ancient mitochondrial genomes unveil the origins and evolutionary history of New Zealand's enigmatic takahē and moho - Alexander J. F. Verry; Eduard Mas‐Carrió; Gillian C. Gibb; Ludovic Dutoit; Bruce C. Robertson; Jonathan M. Waters; Nicolas J. Rawlence (Molecular Ecology, 2024)
Many avian species endemic to Aotearoa New Zealand were driven to extinction or reduced to relict populations following successive waves of human arrival, due to hunting, habitat destruction and the introduction of mammalian predators. Among the affected species were the large flightless South Island takahē ( Porphyrio hochstetteri ) and the moho (North Island takahē; P. mantelli ), with the latter rendered extinct and the former reduced to a single relictual population. Little is known about the evolutionary history of these species prior to their decline and/or extinction. Here we sequenced mitochondrial genomes from takahē and moho subfossils (12 takahē and 4 moho) and retrieved comparable sequence data from takahē museum skins ( n = 5) and contemporary individuals ( n = 17) to examine the phylogeny and recent evolutionary history of these species. Our analyses suggest that prehistoric takahē populations lacked deep phylogeographic structure, in contrast to moho, which exhibited significant spatial genetic structure, albeit based on limited sample sizes ( n = 4). Temporal genetic comparisons show that takahē have lost much of their mitochondrial genetic diversity, likely due to a sudden demographic decline soon after human arrival (~750 years ago). Time‐calibrated phylogenetic analyses strongly support a sister species relationship between takahē and moho, suggesting these flightless taxa diverged around 1.5 million years ago, following a single colonisation of New Zealand by a flighted Porphyrio ancestor approximately 4 million years ago. This study highlights the utility of palaeogenetic approaches for informing the conservation and systematic understanding of endangered species whose ranges have been severely restricted by anthropogenic impacts.

Need and vision for global medium-resolution Landsat and Sentinel-2 data products - Volker C. Radeloff; David P. Roy; Michael A. Wulder; Martha Anderson; Bruce Cook; Christopher J. Crawford; Mark Friedl; Feng Gao; Noel Gorelick; Matthew Hansen; Sean Healey; Patrick Hostert; et al. (Remote Sensing of Environment, 2024)

Specific dietary fibers prevent heavy metal disruption of the human gut microbiota in vitro - Yony Román-Ochoa; Thaisa M. Cantu-Jungles; Grethel Teresa Choque Delgado; Nuseybe Bulut; Teresa R. Tejada; Harry R. Yucra; Antonio E. Duran; Bruce R. Hamaker (Food Research International, 2024)

Bioactive peptides in hydrolysates of bovine and camel milk proteins: A review of studies on peptides that reduce blood pressure, improve glucose homeostasis, and inhibit pathogen adhesion - Rami M. Althnaibat; Heather L. Bruce; Jianping Wu; Michael G. Gänzle (Food Research International, 2024)

Prenatal exposure to replacement flame retardants and organophosphate esters and childhood adverse respiratory outcomes - Angelico Mendy; Zana Percy; Joseph M. Braun; Bruce Lanphear; Mark J. La Guardia; Robert C. Hale; Kimberly Yolton; Aimin Chen (Environmental Research, 2024)

A geospatial assessment of soil properties to identify the potential for crop rotation in rice systems - Luke A. Salvato; Cameron M. Pittelkow; Anthony T. O’Geen; Bruce A. Linquist (Agriculture, Ecosystems & Environment, 2024)

Observations of tissue healing around an implanted “C” tag in a Pacific Coast Feeding Group gray whale ( Eschrichtius robustus ) - P. Dawn Goley; John Calambokidis; Pádraig Duignan; Frances M. D. Gulland; Barbie Halaska; Allison Lui; Margaret Martinez; Bruce Mate (Marine Mammal Science, 2024)

Modeling forest canopy surface retrievals using very high-resolution spaceborne stereogrammetry: (II) optimizing acquisition configurations - Tiangang Yin; Paul M. Montesano; Bruce D. Cook; Eric Chavanon; Christopher S.R. Neigh; David Shean; Dongju Peng; Nicolas Lauret; Ameni Mkaouar; Omar Regaieg; Zhijun Zhen; Rongjun Qin; et al. (Remote Sensing of Environment, 2023)

Modeling forest canopy surface retrievals using very high-resolution spaceborne stereogrammetry: (I) methods and comparisons with actual data - Tiangang Yin; Paul M. Montesano; Bruce D. Cook; Eric Chavanon; Christopher S.R. Neigh; David Shean; Dongju Peng; Nicolas Lauret; Ameni Mkaouar; Douglas C. Morton; Omar Regaieg; Zhijun Zhen; et al. (Remote Sensing of Environment, 2023)

Evaluation of biosorbents as an alternative for mercury cyanide removal from aqueous solution - Paula Aliprandini; Amilton Barbosa Botelho; Marcello M. Veiga; Bruce G. Marshall; Tatiana Scarazzato; Denise Crocce Romano Espinosa (Minerals Engineering, 2023)

Thirty years of regional groundwater-quality trend studies in the United States: Major findings and lessons learned - Bruce D. Lindsey; Brandon J. Fleming; Phillip J. Goodling; Amanda M. Dondero (Journal of Hydrology, 2023)

Normobaric hypoxia does not influence the sural nerve cutaneous reflex during standing - Mathew I. B. Debenham; Christina D. Bruce; Juliana M. Rancier; Chris J. McNeil; Brian H. Dalton (Experimental Brain Research, 2023)

Early Eocene Arctic volcanism from carbonate-metasomatized mantle - James M. D. Day; D. Graham Pearson; Bruce A. Kjarsgaard; Abigail K. Barker; Geoff M. Nowell; Nancy Joyce; David Lowry; Chiranjeeb Sarkar; Christopher Harrison (Contributions to Mineralogy and Petrology, 2023)
Melilitite, nephelinite, basanite, and alkali basalt, along with phonolite differentiates, form the Freemans Cove Complex (FCC) in the south-eastern extremity of Bathurst Island (Nunavut, Canada). New 40 Ar/ 39 Ar chronology indicates their emplacement between ~ 56 and ~ 54 million years ago within a localized extensional structure. Melilitites and nephelinites, along with phonolite differentiates, likely relate to the beginning and end phases of extension, whereas alkali basalts were emplaced during a main extensional episode at ~ 55 Ma. The melilitites, nephelinites, and alkali basalts show no strong evidence for significant assimilation of crust, in contrast to some phonolites. Partial melting occurred within both the garnet- and spinel-facies mantle and sampled sources with He, O, Nd, Hf, and Os isotope characteristics indicative of peridotite with two distinct components. The first, expressed in higher degree partial melts, represents a relatively depleted component (“A”; 3 He/ 4 He ~ 8 R A , ε Nd i ~ + 3 ε Hf i ~ + 7, γ Os i ~ 0). The second was an enriched component (“B” 3 He/ 4 He < 3 R A , ε Nd i < – 1 ε Hf i < + 3, γ Os i > + 70) sampled by the lowest degree partial melts and represents carbonate-metasomatized peridotite. Magmatism in the FCC shows that rifting extended from the Labrador Sea to Bathurst Island and reached a zenith at ~ 55 Ma, during the Eurekan orogeny. The incompatible trace-element abundances and isotopic signatures of FCC rocks indicate melt generation occurred at the base of relatively thin lithosphere at the margin of a thick craton, with no mantle plume influence. FCC melt compositions are distinct from other continental rift magmatic provinces worldwide, and their metasomatized mantle source was plausibly formed synchronously with emplacement of Cretaceous kimberlites. The FCC illustrates that the range of isotopic compositions preserved in continental rift magmas are likely to be dominated by temporal changes in the extent of partial melting, as well as by the timing and degree of metasomatism recorded in the underlying continental lithosphere.

Prioritizing the reassessment of data‐deficient species on the IUCN Red List - Victor Cazalis; Luca Santini; Pablo M. Lucas; Manuela González‐Suárez; Michael Hoffmann; Ana Benítez‐López; Michela Pacifici; Aafke M. Schipper; Monika Böhm; Alexander Zizka; Viola Clausnitzer; Carsten Meyer; et al. (Conservation Biology, 2023)
Despite being central to the implementation of conservation policies, the usefulness of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species is hampered by the 14% of species classified as data‐deficient (DD) because information to evaluate these species’ extinction risk was lacking when they were last assessed or because assessors did not appropriately account for uncertainty. Robust methods are needed to identify which DD species are more likely to be reclassified in one of the data‐sufficient IUCN Red List categories. We devised a reproducible method to help red‐list assessors prioritize reassessment of DD species and tested it with 6887 DD species of mammals, reptiles, amphibians, fishes, and Odonata (dragonflies and damselflies). For each DD species in these groups, we calculated its probability of being classified in a data‐sufficient category if reassessed today from covariates measuring available knowledge (e.g., number of occurrence records or published articles available), knowledge proxies (e.g., remoteness of the range), and species characteristics (e.g., nocturnality); calculated change in such probability since last assessment from the increase in available knowledge (e.g., new occurrence records); and determined whether the species might qualify as threatened based on recent rate of habitat loss determined from global land‐cover maps. We identified 1907 species with a probability of being reassessed in a data‐sufficient category of >0.5; 624 species for which this probability increased by >0.25 since last assessment; and 77 species that could be reassessed as near threatened or threatened based on habitat loss. Combining these 3 elements, our results provided a list of species likely to be data‐sufficient such that the comprehensiveness and representativeness of the IUCN Red List can be improved.

Ultraconserved elements resolve phylogenetic relationships and biogeographic history of African-Malagasy bent-winged bats (Miniopterus) - Terrence C. Demos; Paul W. Webala; Steven M. Goodman; Julian C. Kerbis Peterhans; Holly L. Lutz; Bernard R. Agwanda; Natalia Cortés-Delgado; Stefania Briones; Richard H. Ree; Bruce D. Patterson (Molecular Phylogenetics and Evolution, 2023)

A novel approach to estimate product-specific greenhouse gas emissions for 23,550 Australian packaged foods and beverages - Allison M. Gaines; Tazman Davies; Maria Shahid; Fraser Taylor; Jason HY. Wu; Michalis Hadjikakou; Simone Pettigrew; Paraskevi Seferidi; Bruce Neal (Journal of Cleaner Production, 2023)

Effects of short-chain per- and polyfluoroalkyl substances (PFAS) on toxicologically relevant gene expression profiles in a liver-on-a-chip model - Megan E. Solan; Bennett Schackmuth; Erica D. Bruce; Sahar Pradhan; Christie M. Sayes; Ramon Lavado (Environmental Pollution, 2023)

Juvenile Brown Shrimp (Farfantepenaeus aztecus) Use of Salt Marsh Intertidal Creeks as Nursery Habitat - Kaitlin M. Glover; Matthew E. Kimball; Bruce W. Pfirrmann; Mary Margaret Pelton; Robert P. Dunn (Estuaries and Coasts, 2023)

Distribution and structure of deep-sea demersal fish assemblages across the central and western Pacific Ocean using data from undersea imagery - Gina M. Selig; Jeffrey C. Drazen; Peter J. Auster; Bruce C. Mundy; Christopher D. Kelley (Frontiers in Marine Science, 2023)
Demersal deep-sea fish assemblages from islands and seamounts are poorly described, even in the Hawaiian archipelago. Knowledge across all depths, in similar settings, is even sparser for other archipelagos in the central and western Pacific. However, recent remotely operated vehicle (ROV) explorations and archived video from human-occupied submersible dives conducted by the Hawai`i Undersea Research Laboratory (HURL) provide an opportunity to explore the structure of these assemblages. Here we describe demersal fish assemblages across the central and western Pacific, including in four Marine National Monuments, and examine the relationship of the assemblages to depth and environmental conditions. We used data collected from 227 underwater vehicle dives resulting in the identification of 24,837 individuals belonging to 89 families and 175 genera. The most frequently occurring genera at depths of 250-500 m were Epigonus , Setarches , Polymixia , and Antigonia , between 500-1000 m were Chlorophthalmus , Aldrovandia , and Neocyttus , and between 1000-3000 m were Synaphobranchus , Kumba , Halosaurus , Ilyophis , and Ipnops . There are strong changes in the fish assemblages with depth and region, and assemblages become more similar between regions with greater depth. Depth and region explained the most variance in assemblage structure followed by seafloor particulate organic carbon flux (a food supply proxy), concentrations of dissolved oxygen, and salinity. The Line Islands and Tokelau Ridge had the highest values of seafloor particulate organic carbon flux for all depth zones investigated (250-3000 m) and the highest abundance of fishes at 250-500 m and 500-1000 m, respectively. Taxon accumulation curves indicated that diversity at the genus level within all regions and depth bins (except 1000-2000 m and 2000-3000 m) had not been reached with the existing sampling effort. However, when combining samples from all regions, diversity generally appeared to decrease with depth. Overall, this study demonstrates that there are significant regional differences in the composition of the deep-sea fish fauna as well as differences across depth. Such distribution patterns suggest that the four Marine National Monuments (Papahānaumokuākea, Marianas Trench, Pacific Remote Islands, and Rose Atoll Marine National Monuments, encompassing an area of 3,063,223 km 2 ) are not replicates of diversity, but complementary components of the regional fauna.

Child Care Feeding Programs Associated With Food Security and Health for Young Children From Families With Low Incomes - Stephanie Ettinger de Cuba; Allison Bovell-Ammon; Nayab Ahmad; Charlotte Bruce; Ana Poblacion; Lindsey J. Rateau; Sharon M. Coleman; Maureen M. Black; Deborah A. Frank; Félice Lê-Scherban; Geraldine Henchy; Eduardo Ochoa; et al. (Journal of the Academy of Nutrition and Dietetics, 2023)

Simulations of hydrate reformation in the water production line of the second offshore methane hydrate production test in Japan’s Nankai trough - Shunsuke Sakurai; Zachary M. Aman; Tomoya Nonoue; Takuya Nagaoka; Motohiro Omori; Joel Choi; Eric F. May; Bruce W.E. Norris (Fuel, 2023)

Exposure to dust organophosphate and replacement brominated flame retardants during infancy and risk of subsequent adverse respiratory outcomes - Angelico Mendy; Zana Percy; Joseph M. Braun; Bruce Lanphear; Mark J. La Guardia; Robert Hale; Kimberly Yolton; Aimin Chen (Environmental Research, 2023)

Pitfall trapping outperforms other methods for surveying ground-dwelling large-bodied alpine invertebrates - Aaron Bertoia; Tara Murray; Bruce C. Robertson; Joanne M. Monks (Journal of Insect Conservation, 2023)
Appropriate sampling methods are essential for monitoring and managing all wildlife. There is limited information on how to monitor ground-dwelling invertebrates in the alpine zone compared to more commonly studied lower-elevation habitats. We aim to understand the strengths, weaknesses, and cost-effectiveness of invertebrate survey methods when deployed in the alpine zone. We tested four methods on the South Island of New Zealand (Aotearoa): pitfall traps, tracking tunnels, visual surveys, and trail cameras. We focused on methods for ground-dwelling large-bodied invertebrates, a group most likely to be impacted by introduced mammalian predators. Pitfall traps and trail cameras were practical methods for surveying alpine invertebrates. Tracking tunnels only reliably detected large wētā (Orthoptera: Anostostomatidae), as other invertebrates were too light to leave distinguishable tracks. Visual surveys did not generate enough observations to be considered a successful method. We found no difference in the total abundance or easily recognised taxonomic groups detected by pitfall traps and trail cameras. Trail cameras detected fewer wētā compared to tracking tunnels and pitfall traps. Of the successful methods, pitfall traps were the most cost-effective, followed by tracking tunnels and trail cameras. Tracking tunnels were the fastest to install and required the least processing time, followed by pitfall traps and trail cameras. We recommend using pitfall traps to survey large-bodied alpine ground-dwelling invertebrates to better understand population trends or community composition. This method was consistent across all alpine habitat types and has the potential to be an effective method to inform conservation monitoring and management programmes. Implications for insect conservation Monitoring is vital to understand how invertebrates respond to change and evaluate conservation management program outcomes. This study provides practical information on potential monitoring tools for invertebrates in the alpine zone and recommends pitfall traps to survey large-bodied alpine invertebrates.

Multi intercalators FRET enhanced detection of minute amounts of DNA - Luca Ceresa; Jose Chavez; Magdalena M. Bus; Bruce Budowle; Emma Kitchner; Joseph Kimball; Ignacy Gryczynski; Zygmunt Gryczynski (European Biophysics Journal, 2023)

Germline whole genome sequencing in adults with multiple primary tumors - Yiming Wang; Qiliang Ding; Stephenie Prokopec; Kirsten M. Farncombe; Jeffrey Bruce; Selina Casalino; Jeanna McCuaig; Marta Szybowska; Kalene van Engelen; Jordan Lerner-Ellis; Trevor J. Pugh; Raymond H. Kim (Familial Cancer, 2023)

Four challenges to an effective national nature assessment - Carlos Carroll; Reed F. Noss; Lindsay M. Dreiss; Healy Hamilton; Bruce A. Stein (Conservation Biology, 2023)
Comprehensive biodiversity assessments play an essential role in strengthening global and national conservation strategies. The recently announced first U.S. National Nature Assessment (NNA) provides an unparalleled opportunity to comprehensively review status and trends of biodiversity at all levels. This broad context can help in the coordination of actions to conserve individual species and ecosystems. The scientific assessments that informed the Kunming–Montreal Global Biodiversity Framework adopted at the 2022 Convention on Biological Diversity (CBD) conference of parties provide models for synthesizing information on trends at multiple levels of biodiversity, including decline in abundance and distribution of species, loss of populations and genetic diversity, and degradation and loss of ecosystems and their services. The assessments then relate these trends to data on drivers of biodiversity loss and pathways to their mitigation. The U.S. NNA can augment such global analyses and avoid the pitfalls encountered by previous U.S. efforts by ensuring policy‐relevant design, data accessibility, and inclusivity in process and product and by incorporating spatial data relevant to national and subnational audiences. Although the United States is not formally a CBD party, an effective NNA should take full advantage of the global context by including indicators adopted at the 2022 meeting and incorporating an independent review mechanism that supports periodic stocktaking and ratcheting up of ambition in response to identified shortfalls in stemming biodiversity loss. The challenges to design of an effective U.S. assessment are relevant globally as nations develop assessments and reporting to support the new global biodiversity framework's targets. By considering and incorporating the diverse ways in which society values and benefits from nature, such assessments can help bridge the gap between research and conservation practice and communicate the extent of the biodiversity crisis to the public, fostering broad‐based support for transformative change in humanity's relationship to the natural world.

Making waves: Integrating wastewater surveillance with dynamic modeling to track and predict viral outbreaks - Tin Phan; Samantha Brozak; Bruce Pell; Jeremiah Oghuan; Anna Gitter; Tao Hu; Ruy M. Ribeiro; Ruian Ke; Kristina D. Mena; Alan S. Perelson; Yang Kuang; Fuqing Wu (Water Research, 2023)

Associations of prenatal and postnatal exposure to perfluoroalkyl substances with pubertal development and reproductive hormones in females and males: The HOME study - Yun Liu; Antonia M. Calafat; Aimin Chen; Bruce P. Lanphear; Nana-Hawa Yayah Jones; Kim M. Cecil; Susan R. Rose; Kimberly Yolton; Jessie P. Buckley; Joseph M. Braun (Science of The Total Environment, 2023)

Mars volatile inventory and outgassing history - Bruce M. Jakosky; Allan H. Treiman (Icarus, 2023)

Site-specific spatiotemporal occurrence and molecular congener distributions of naphthenic acids in Athabasca oil sands wetlands of Alberta, Canada - Ian J. Vander Meulen; Danna M. Schock; Fardausi Akhter; Lukas J. Mundy; Kristin M. Eccles; Catherine Soos; Kerry M. Peru; Dena W. McMartin; John V. Headley; Bruce D. Pauli (Environmental Pollution, 2023)

Identifying areas of high drought risk in southwest Western Australia - Amanda R. Bourne; John Bruce; Meredith M. Guthrie; Li-Ann Koh; Kaylene Parker; Stanley Mastrantonis; Igor Veljanoski (Natural Hazards, 2023)

Long‐term elevated precipitation induces grassland soil carbon loss via microbe‐plant–soil interplay - Mengmeng Wang; Xin Sun; Baichuan Cao; Nona R. Chiariello; Kathryn M. Docherty; Christopher B. Field; Qun Gao; Jessica L. M. Gutknecht; Xue Guo; Genhe He; Bruce A. Hungate; Jiesi Lei; et al. (Global Change Biology, 2023)
Global climate models predict that the frequency and intensity of precipitation events will increase in many regions across the world. However, the biosphere‐climate feedback to elevated precipitation (eP) remains elusive. Here, we report a study on one of the longest field experiments assessing the effects of eP, alone or in combination with other climate change drivers such as elevated CO 2 (eCO 2 ), warming and nitrogen deposition. Soil total carbon (C) decreased after a decade of eP treatment, while plant root production decreased after 2 years. To explain this asynchrony, we found that the relative abundances of fungal genes associated with chitin and protein degradation increased and were positively correlated with bacteriophage genes, suggesting a potential viral shunt in C degradation. In addition, eP increased the relative abundances of microbial stress tolerance genes, which are essential for coping with environmental stressors. Microbial responses to eP were phylogenetically conserved. The effects of eP on soil total C, root production, and microbes were interactively affected by eCO 2 . Collectively, we demonstrate that long‐term eP induces soil C loss, owing to changes in microbial community composition, functional traits, root production, and soil moisture. Our study unveils an important, previously unknown biosphere‐climate feedback in Mediterranean‐type water‐limited ecosystems, namely how eP induces soil C loss via microbe‐plant–soil interplay.

Giants of the Amazon: How does environmental variation drive the diversity patterns of large trees? - Robson Borges de Lima; Eric Bastos Görgens; Diego Armando S. da Silva; Cinthia Pereira de Oliveira; Anderson Pedro B. Batista; Rinaldo L. Caraciolo Ferreira; Flavia R. C. Costa; Renato A. Ferreira de Lima; Perseu da Silva Aparício; Jadson Coelho de Abreu; José Antônio Aleixo da Silva; Aretha Franklin Guimaraes; et al. (Global Change Biology, 2023)
For more than three decades, major efforts in sampling and analyzing tree diversity in South America have focused almost exclusively on trees with stems of at least 10 and 2.5 cm diameter, showing highest species diversity in the wetter western and northern Amazon forests. By contrast, little attention has been paid to patterns and drivers of diversity in the largest canopy and emergent trees, which is surprising given these have dominant ecological functions. Here, we use a machine learning approach to quantify the importance of environmental factors and apply it to generate spatial predictions of the species diversity of all trees (dbh ≥ 10 cm) and for very large trees (dbh ≥ 70 cm) using data from 243 forest plots (108,450 trees and 2832 species) distributed across different forest types and biogeographic regions of the Brazilian Amazon. The diversity of large trees and of all trees was significantly associated with three environmental factors, but in contrasting ways across regions and forest types. Environmental variables associated with disturbances, for example, the lightning flash rate and wind speed, as well as the fraction of photosynthetically active radiation, tend to govern the diversity of large trees. Upland rainforests in the Guiana Shield and Roraima regions had a high diversity of large trees. By contrast, variables associated with resources tend to govern tree diversity in general. Places such as the province of Imeri and the northern portion of the province of Madeira stand out for their high diversity of species in general. Climatic and topographic stability and functional adaptation mechanisms promote ideal conditions for species diversity. Finally, we mapped general patterns of tree species diversity in the Brazilian Amazon, which differ substantially depending on size class.

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Crustal basement terranes under the Taupō Volcanic Zone, New Zealand: Context for hydrothermal and magmatic processes - Nick Mortimer; Bruce L.A. Charlier; Shane M. Rooyakkers; Rose E. Turnbull; Colin J.N. Wilson; Marianne Negrini; Stephen Bannister; Sarah D. Milicich; Isabelle Chambefort; Craig A. Miller; Geoff Kilgour (Journal of Volcanology and Geothermal Research, 2023)

Absence of low-δ18O magmas despite widespread assimilation of altered crust in a large magmatic and hydrothermal province - Shane M. Rooyakkers; Isabelle Chambefort; Kevin Faure; Colin J.N. Wilson; Simon J. Barker; Nick Mortimer; Hannah C. Elms; Juliana Troch; Bruce L.A. Charlier; Graham S. Leonard; David Farsky (Geochimica et Cosmochimica Acta, 2023)

Dietary per- and polyfluoroalkyl substance (PFAS) exposure in adolescents: The HOME study - Harry Sultan; Jessie P. Buckley; Heidi J. Kalkwarf; Kim M. Cecil; Aimin Chen; Bruce P. Lanphear; Kimberly Yolton; Joseph M. Braun (Environmental Research, 2023)

Non-asbestiform elongate mineral particles and mesothelioma risk: Human and experimental evidence - Julie E. Goodman; Michael J. Becich; David M. Bernstein; Bruce W. Case; Jeffrey H. Mandel; Andre E. Nel; Robert Nolan; Nnaemeka U. Odo; Steven R. Smith; Emanuela Taioli; Graham Gibbs (Environmental Research, 2023)

Editorial: The discovery of the unknown planet: the ocean - Paolo Favali; Juan José Dañobeitia; Bruce M. Howe; Henry A. Ruhl (Frontiers in Marine Science, 2023)

Radio- and stable carbon isotope analysis reveals minimal assimilation of petrogenic carbon into an oligotrophic freshwater food web after experimental spills of diluted bitumen - Stephanie D. Graves; Johanna J. Mason; Jose Luis Rodriguez-Gil; Jonathan Y. Séguin; Jules M. Blais; Mark L. Hanson; Bruce P. Hollebone; Vince P. Palace; Ian Clark; Leah Cundall; Daniel Layton-Matthews; Matthew I. Leybourne; et al. (Chemosphere, 2023)

Evolutionary genomics of oceanic island radiations - José Cerca; Darko D. Cotoras; Vanessa C. Bieker; Rishi De-Kayne; Pablo Vargas; Mario Fernández-Mazuecos; Julia López-Delgado; Oliver White; Martin Stervander; Anthony J. Geneva; Juan Ernesto Guevara Andino; Joana Isabel Meier; et al. (Trends in Ecology & Evolution, 2023)

Cultural and regulatory factors influence distribution and trajectory of invasive species in the United States: A wild pig case study - Andrew L. Smith; Bronson K. Strickland; Bruce D. Leopold; James L. Cummins; John J. Mayer; Garrett M. Street (Journal of Environmental Management, 2023)

Air pollution exposure and social responsiveness in childhood: The cincinnati combined childhood cohorts - Nidhi Iyanna; Kimberly Yolton; Grace LeMasters; Bruce P. Lanphear; Kim M. Cecil; Joel Schwartz; Cole Brokamp; Erika Rasnick; Yingying Xu; Melinda C. MacDougall; Patrick H. Ryan (International Journal of Hygiene and Environmental Health, 2023)

Identification of peptides from camel milk that inhibit starch digestion - Rami M. Althnaibat; Heather L. Bruce; Michael G. Gӓnzle (International Dairy Journal, 2023)

Solar wind driven influences on the Martian oxygen corona: Constraints on atmospheric sputtering from a synthesis of MAVEN measurements during solar minimum - Robin Ramstad; David A. Brain; Yaxue Dong; Jasper S. Halekas; James M. McFadden; David L. Mitchell; Jared Espley; Francis G. Eparvier; Bruce M. Jakosky (Icarus, 2023)

Development of a monoclonal antibody specific to burbot (Lota lota) IgM and optimization of an ELISA to measure anti-Aeromonas sp. antibody titers following pathogen challenge - Luke P. Oliver; Timothy J. Bruce; Jie Ma; Evan M. Jones; Kenneth D. Cain (Fish & Shellfish Immunology, 2023)

Characterization of maternal immunity following vaccination of broodstock against IHNV or Flavobacterium psychrophilum in rainbow trout (Oncorhynchus mykiss) - Jie Ma; Jesse T. Trushenski; Evan M. Jones; Timothy J. Bruce; Doug G. McKenney; Gael Kurath; Kenneth D. Cain (Fish & Shellfish Immunology, 2023)

Liver and cardiometabolic markers and conditions in a cross-sectional study of three Australian communities living with environmental per- and polyfluoroalkyl substances contamination - Nina Lazarevic; Kayla S. Smurthwaite; Catherine D'Este; Robyn M. Lucas; Bruce Armstrong; Archie CA. Clements; Susan M. Trevenar; Imogen Gad; Rose Hosking; Hsei Di Law; Jochen Mueller; Jennifer Bräunig; et al. (Environmental Research, 2023)

Subsurface damage detection via noncontact laser based surface level strain sensing smart skin with carbon nanotubes - Ashish Pal; Wei Meng; Sergei M. Bachilo; R. Bruce Weisman; Satish Nagarajaiah (Engineering Structures, 2023)

Assessing Antigen-Adjuvant Complex Stability Against Physical Stresses By wNMR - Marc B. Taraban; Katharine T. Briggs; Yihua Bruce Yu; Michael T. Jones; Lindsey Rosner; Akhilesh Bhambhani; Donna M. Williams; Christopher Farrell; Mikhail Reibarkh; Yongchao Su (Pharmaceutical Research, 2023)

Decoupled Patterns of Diversity and Disparity Characterize an Ecologically Specialized Lineage of Neotropical Cricetids - Rafaela V. Missagia; Daniel M. Casali; Bruce D. Patterson; Fernando A. Perini (Evolutionary Biology, 2023)

Combining multiple lines of evidence to elucidate the origin and introduction pathway of bitou bush (Chrysanthemoides monilifera subsp. rotundata) in Australia - Amanda M. Emmett; John K. Scott; Bruce L. Webber; Anita A. Severn-Ellis; Karen L. Bell (Biological Invasions, 2023)
Understanding the historical context of biological invasions can improve weed management outcomes. In this study, we aim to identify the introduction pathway of bitou bush ( Chrysanthemoides monilifera subsp. rotundata ) into Australia and its biogeographical origin in southern Africa by combining multiple lines of evidence from genomic tools and historical documentation. Geographic structure of genomic diversity based on SNPs supported the previous analysis of the invasion pathway of bitou bush between the two countries and within Australia, namely that all Australian material originated from the southern part of the South African distribution. Our synthesis of historical records points to the introduction of this plant into eastern Australia in Newcastle, New South Wales, from its native range in South Africa, via dry shipping ballast in about 1900. Variation in the chloroplast genome was also informative as to the biogeographical origin of Australian material and the context of the introduction. Ten unique haplotypes were discovered in South Africa with only one occurring throughout Australia, indicating an introduction from a single source population to eastern Australia. The matching haplotype was from East London, a port in South Africa with documented shipping connections to Newcastle in eastern Australia, where the weed was first recorded. Historical records suggest that the most plausible explanation for the origins of the isolated bitou bush population in Western Australia is via the shipping of steel billets or landscape plantings associated with shipping companies. The most likely introduction pathway linked the eastern Australian steel processing ports of Newcastle or Port Kembla to the Western Australian port of Kwinana in 1995. Discovering the origin and pathway of bitou bush invasions in Australia opens new opportunities for sourcing biological control agents with a higher chance of impact as well as identifying additional quarantine measures to improve outcomes and reduce long-term costs to management.

1,4-Dioxane removal in nitrifying sand filters treating domestic wastewater: Influence of water matrix and microbial inhibitors - Cheng-Shiuan Lee; Mian Wang; Patricia M. Clyde; Xinwei Mao; Bruce J. Brownawell; Arjun K. Venkatesan (Chemosphere, 2023)

Effects of temperature and subspecies during critical early life history stages of largemouth bass (Micropterus salmoides) - Gavin L. Aguilar; Josh Sakmar; Allen Nicholls; Matthew K. Litvak; Hana N. Hess; Timothy J. Bruce; Helen R. Montague; Anita M. Kelly; Luke A. Roy; Moisés A. Bernal; Sebastian N. Politis; Ian A.E. Butts (Aquaculture, 2023)

Uptake of polycyclic aromatic hydrocarbons via high-energy water accommodated fraction (HEWAF) by beach hoppers (Amphipoda, Talitridae) using different sandy beach exposure pathways - Bryand M. Duke; Kyle A. Emery; Jenifer E. Dugan; David M. Hubbard; Bruce M. Joab (Marine Pollution Bulletin, 2023)

Early-life exposure to a mixture of organophosphate esters and child behavior - Zana Percy; Aimin Chen; Heidi Sucharew; Weili Yang; Ann M. Vuong; Joseph M. Braun; Bruce Lanphear; Maria Ospina; Antonia M. Calafat; Kim M. Cecil; Yingying Xu; Kimberly Yolton (International Journal of Hygiene and Environmental Health, 2023)

Pre- and postnatal exposure to secondhand tobacco smoke and cardiometabolic risk at 12 years: Periods of susceptibility - Nerea Mourino; Mónica Pérez-Ríos; Kimberly Yolton; Bruce P. Lanphear; Aimin Chen; Jessie P. Buckley; Heidi J. Kalkwarf; Kim M. Cecil; Joseph M. Braun (Environmental Research, 2023)

A Numerical Study of SMART Cables Potential in Marine Hazard Early Warning for the Sumatra and Java Regions - Amir Salaree; Bruce M. Howe; Yihe Huang; Stuart A. Weinstein; Andi Eka Sakya (Pure and Applied Geophysics, 2023)

Intertidal Creek Pool Nekton Assemblages: Long-term Patterns in Diversity and Abundance in a Warm-Temperate Estuary - Matthew E. Kimball; Bruce W. Pfirrmann; Dennis M. Allen; Virginia Ogburn-Matthews; Paul D. Kenny (Estuaries and Coasts, 2023)

Acute ecotoxicological effects of Hg(CN)2 in Danio rerio (zebrafish) - Henrique Alencar Meira da Silva; Daniele Kasper; Bruce G. Marshall; Marcello M. Veiga; Jean Remy Davée Guimaraes (Ecotoxicology, 2023)

Investigating the influence of ultrasound parameters on ibuprofen drug release from hydrogels - Svenja Meissner; Jhansi H. Akepogu; Samantha M. Arnet; Mohammed Z. Dean; Jessie Ji; Grace Wright; Bruce Harland; Brad Raos; Darren Svirskis; Sachin S. Thakur (Drug Delivery and Translational Research, 2023)

Coordinating science during an eruption: lessons from the 2020–2021 Kīlauea volcanic eruption - Kari M. Cooper; Kyle Anderson; Kathy Cashman; Michelle Coombs; Hannah Dietterich; Tobias Fischer; Bruce Houghton; Ingrid Johanson; Kendra J. Lynn; Michael Manga; Christelle Wauthier (Bulletin of Volcanology, 2023)

Matching textural properties of commercial meat and cheese products using zein as the viscoelastic agent and calcium hydroxide as the textural modifier in plant-based formulations - Andres M. Salgado; Oguz K. Ozturk; Bruce R. Hamaker; Osvaldo H. Campanella (Food Hydrocolloids, 2023)

When increasing vegetable production may worsen food availability gaps: A simulation model in India - Marie L. Spiker; Joel Welling; Daniel Hertenstein; Suvankar Mishra; Krishna Mishra; Kristen M. Hurley; Roni A. Neff; Jess Fanzo; Bruce Y. Lee (Food Policy, 2023)

Multi-sectoral analysis of smarter urban nitrogen metabolism: A case study of Suzhou, China - M Bruce Beck; Chen Chen; Rodrigo Villarroel Walker; Zongguo Wen; Jiangxue Han (Ecological Modelling, 2023)

Associations of early life phthalate exposures with adolescent lipid levels and insulin resistance: The HOME Study - Taylor M. Etzel; Jordan R. Kuiper; Xiaobin Wang; Noel T. Mueller; Antonia M. Calafat; Kim M. Cecil; Aimin Chen; Bruce P. Lanphear; Kimberly Yolton; Heidi J. Kalkwarf; Joseph M. Braun; Jessie P. Buckley (International Journal of Hygiene and Environmental Health, 2023)

Associations of maternal gestational urinary environmental phenols concentrations with bone mineral density among 12-year-old children in the HOME Study - Jordan R. Kuiper; Shudi Pan; Bruce P. Lanphear; Antonia M. Calafat; Aimin Chen; Kim M. Cecil; Yingying Xu; Kimberly Yolton; Heidi J. Kalkwarf; Joseph M. Braun; Jessie P. Buckley (International Journal of Hygiene and Environmental Health, 2023)

The Mars upper atmosphere at solar minimum - Bruce M. Jakosky; David A. Brain; Francis G. Eparvier (Icarus, 2023)

Drought stress impact on agronomic, shoot, physiological, canning and nutritional quality traits of navy beans (Phaseolus vulgaris L.) under field conditions in Zimbabwe - Bruce Mutari; Julia Sibiya; Prince M. Matova; Edmore Gasura; Kennedy Simango (Field Crops Research, 2023)

Designing an expert-led Bayesian network to understand interactions between policy instruments for adoption of eco-friendly farming practices - Helen J. Mayfield; Rachel Eberhard; Christopher Baker; Umberto Baresi; Michael Bode; Anthea Coggan; Angela J. Dean; Felicity Deane; Evan Hamman; Diane Jarvis; Barton Loechel; Bruce M. Taylor; et al. (Environmental Science & Policy, 2023)

Carbon acquisition ecological strategies to connect soil microbial biodiversity and carbon cycling - Ember M. Morrissey; Jennifer Kane; Binu M. Tripathi; Md Shafiul Islam Rion; Bruce A. Hungate; Rima Franklin; Chris Walter; Benjamin Sulman; Edward Brzostek (Soil Biology and Biochemistry, 2023)

Active populations and growth of soil microorganisms are framed by mean annual precipitation in three California annual grasslands - Megan M. Foley; Steven J. Blazewicz; Karis J. McFarlane; Alex Greenlon; Michaela Hayer; Jeffrey A. Kimbrel; Benjamin J. Koch; Victoria L. Monsaint-Queeney; Keith Morrison; Ember Morrissey; Bruce A. Hungate; Jennifer Pett-Ridge (Soil Biology and Biochemistry, 2023)

Adamantyl-ureas with pyrazoles substituted by fluoroalkanes as soluble epoxide hydrolase inhibitors - Vladimir V. Burmistrov; Christophe Morisseau; Tatyana K. Shkineva; Dmitry V. Danilov; Boris Gladkikh; Gennady M. Butov; Robert R. Fayzullin; Tatyana Ya. Dutova; Bruce D. Hammock; Igor L. Dalinger (Journal of Fluorine Chemistry, 2023)

Experimental laboratory tests of short-term habitat selection by hatchery-reared juvenile red drum (Sciaenops ocellatus) - Bruce W. Pfirrmann; Robert P. Dunn; Matthew E. Kimball; Erin M. Levesque (Journal of Experimental Marine Biology and Ecology, 2023)

Gestational exposure to organophosphate esters and infant anthropometric measures in the first 4 weeks after birth - Weili Yang; Joseph M. Braun; Ann M. Vuong; Zana Percy; Yingying Xu; Changchun Xie; Ranjan Deka; Antonia M. Calafat; Maria Ospina; Heather H. Burris; Kimberly Yolton; Kim M. Cecil; et al. (Science of The Total Environment, 2023)

Dispersion of zein into pea protein with alkaline agents imparts cohesive and viscoelastic properties for plant-based food analogues - Oguz K. Ozturk; Andres M. Salgado; David R. Holding; Osvaldo H. Campanella; Bruce R. Hamaker (Food Hydrocolloids, 2023)

Impacts of industrial microwave and infrared drying approaches on hemp (Cannabis sativa L.) quality and chemical components - Abass A. Oduola; Rebecca M. Bruce; Soraya Shafiekhani; Griffiths G. Atungulu (Food and Bioproducts Processing, 2023)

Urinary concentrations and determinants of glyphosate and glufosinate in pregnant Canadian participants in the MIREC study - Jillian Ashley-Martin; Rong Huang; Susan MacPherson; Orly Brion; James Owen; Eric Gaudreau; Jean-Francois Bienvenu; Mandy Fisher; Michael M. Borghese; Maryse F. Bouchard; Bruce Lanphear; Warren G. Foster; et al. (Environmental Research, 2023)

Associations of gestational exposure to organophosphate esters with gestational age and neonatal anthropometric measures: The HOME study - Weili Yang; Joseph M. Braun; Ann M. Vuong; Zana Percy; Yingying Xu; Changchun Xie; Ranjan Deka; Antonia M. Calafat; Maria Ospina; Heather H. Burris; Kimberly Yolton; Kim M. Cecil; et al. (Environmental Pollution, 2023)

Evaluations of Lagrangian egg drift models: From a laboratory flume to large channelized rivers - Geng Li; Caroline M. Elliott; Bruce C. Call; Duane C. Chapman; Robert B. Jacobson; Binbin Wang (Ecological Modelling, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

The detection of African trypanosomes in goats reared in tsetse infested villages of Eastern Zambia - Gloria M. Mulenga; Bruce Gummow (Tropical Animal Health and Production, 2022)
Control programmes for African animal trypanosomiasis (AAT) in livestock have been mainly focused on cattle with very little focus on goats, an important reservoir for the disease. Using the polymerase chain reaction (PCR), this study investigated trypanosome infection in village goats in Mambwe, a rural District in Eastern Zambia . Filter paper blood spots were collected from 326 goats and tested for infection with Trypanosoma congolense , Trypanosoma vivax and Trypanosoma brucei s.l . using ribosomal RNA internal transcribed spacers (ITS)-PCR. The frequency of trypanosomes from the sampled goats was 4.6% (95% CI = 2.3–6.8). Results indicated significantly high infections with Trypanosoma vivax (4.0%; 95% CI = 1.9–6.1) than T. congolense (0.6%; 95% CI = − 0.2 to 1.5) , and T. brucei (0.0%), P = 0.04. Findings show the circulation of trypanosomes that causes AAT in goats and that they may pose serious threats to not only goats but also to other livestock reared alongside goats.

Postmortem Human Dura Mater Cells Exhibit Phenotypic, Transcriptomic and Genetic Abnormalities that Impact their Use for Disease Modeling - Andrea R. Argouarch; Nina Schultz; Andrew C. Yang; Yeongjun Jang; Kristle Garcia; Celica G. Cosme; Christian I. Corrales; Alissa L. Nana; Anna M. Karydas; Salvatore Spina; Lea T. Grinberg; Bruce Miller; et al. (Stem Cell Reviews and Reports, 2022)
Patient-derived cells hold great promise for precision medicine approaches in human health. Human dermal fibroblasts have been a major source of cells for reprogramming and differentiating into specific cell types for disease modeling. Postmortem human dura mater has been suggested as a primary source of fibroblasts for in vitro modeling of neurodegenerative diseases. Although fibroblast-like cells from human and mouse dura mater have been previously described, their utility for reprogramming and direct differentiation protocols has not been fully established. In this study, cells derived from postmortem dura mater are directly compared to those from dermal biopsies of living subjects. In two instances, we have isolated and compared dermal and dural cell lines from the same subject. Notably, striking differences were observed between cells of dermal and dural origin. Compared to dermal fibroblasts, postmortem dura mater-derived cells demonstrated different morphology, slower growth rates, and a higher rate of karyotype abnormality. Dura mater-derived cells also failed to express fibroblast protein markers. When dermal fibroblasts and dura mater-derived cells from the same subject were compared, they exhibited highly divergent gene expression profiles that suggest dura mater cells originated from a mixed mural lineage. Given their postmortem origin, somatic mutation signatures of dura mater-derived cells were assessed and suggest defective DNA damage repair. This study argues for rigorous karyotyping of postmortem derived cell lines and highlights limitations of postmortem human dura mater-derived cells for modeling normal biology or disease-associated pathobiology. Graphical abstract

Probing the nature of soil organic matter - Zhe (Han) Weng; Johannes Lehmann; Lukas Van Zwieten; Stephen Joseph; Braulio S. Archanjo; Bruce Cowie; Lars Thomsen; Mark J. Tobin; Jitraporn Vongsvivut; Annaleise Klein; Casey L. Doolette; Helen Hou; et al. (Critical Reviews in Environmental Science and Technology, 2022)

Host plant resistance for fall armyworm management in maize: relevance, status and prospects in Africa and Asia - Boddupalli M. Prasanna; Anani Bruce; Yoseph Beyene; Dan Makumbi; Manje Gowda; Muhammad Asim; Samuel Martinelli; Graham P. Head; Srinivas Parimi (Theoretical and Applied Genetics, 2022)
Key message Sustainable control of fall armyworm (FAW) requires implementation of effective integrated pest management (IPM) strategies, with host plant resistance as a key component. Significant opportunities exist for developing and deploying elite maize cultivars with native genetic resistance and/or transgenic resistance for FAW control in both Africa and Asia. Abstract The fall armyworm [ Spodoptera frugiperda (J.E. Smith); FAW] has emerged as a serious pest since 2016 in Africa, and since 2018 in Asia, affecting the food security and livelihoods of millions of smallholder farmers, especially those growing maize. Sustainable control of FAW requires implementation of integrated pest management strategies, in which host plant resistance is one of the key components. Significant strides have been made in breeding elite maize lines and hybrids with native genetic resistance to FAW in Africa, based on the strong foundation of insect-resistant tropical germplasm developed at the International Maize and Wheat Improvement Center, Mexico. These efforts are further intensified to develop and deploy elite maize cultivars with native FAW tolerance/resistance and farmer-preferred traits suitable for diverse agro-ecologies in Africa and Asia. Independently, genetically modified Bt maize with resistance to FAW is already commercialized in South Africa, and in a few countries in Asia (Philippines and Vietnam), while efforts are being made to commercialize Bt maize events in additional countries in both Africa and Asia. In countries where Bt maize is commercialized, it is important to implement a robust insect resistance management strategy. Combinations of native genetic resistance and Bt maize also need to be explored as a path to more effective and sustainable host plant resistance options. We also highlight the critical gaps and priorities for host plant resistance research and development in maize, particularly in the context of sustainable FAW management in Africa and Asia.

Enhanced conditioned “liking” of novel visual cues paired with alcohol or non-alcohol beverage container images among individuals at higher risk for alcohol use disorder - Roberto U. Cofresí; Thomas M. Piasecki; Bruce D. Bartholow; Todd R. Schachtman (Psychopharmacology, 2022)

Non-antibiotic antimicrobial polydopamine surface coating to prevent stable biofilm formation on satellite telemetry tags used in cetacean conservation applications - Ariana Smies; Jeremy Wales; Maureen Hennenfent; Laura Lyons; Caleigh Dunn; Jooke Robbins; Bruce P. Lee; Alexandre Zerbini; Rupak M. Rajachar (Frontiers in Marine Science, 2022)
Satellite telemetry tags, used to monitor the migratory behavior of cetaceans, have the potential to be a vehicle for infection due to their invasive nature. Antibiotic coatings have been previously employed to reduce the chances of infection via the formation of a stable biofilm on the surface of the tags. However, increased use of antibiotics has the potential to lead to the development of antibiotic-resistant pathogens. To prevent the formation of antibiotic-resistant pathogens, a polydopamine surface coating that, when exposed to oxygen, releases low doses (~40-100µM) of hydrogen peroxide over a prolonged period (>24 hours) can be used to replace current antibiotic coatings used in the field. These pDA coatings can reduce bacterial adhesion from model bacteria from the two most common genotypes found on the skin of cetaceans ( Psychrobacter and Tenacibaculum ). The adhesion of Psychrobacter bacteria was reduced by 80% (p<0.01) while Tenacibaculum was reduced by 70% (p<0.001). When the bacteria were dosed with a non-lethal quantity of hydrogen peroxide (200µM) prior to being exposed to pDA surface coatings, there was no decrease in the efficacy of the coatings. This indicates a resistance to hydrogen peroxide will not be formed quickly. Overall, the polydopamine surface coatings were able to reduce the adhesion of model bacteria strains on the surface of medical grade stainless steel, which could increase the functional tag service life while reducing the chances of infection.

A sulfur and halogen budget for the large magmatic system beneath Taupō volcano - Max S. Sharpe; Simon J. Barker; Shane M. Rooyakkers; Colin J. N. Wilson; Isabelle Chambefort; Michael C. Rowe; C. Ian Schipper; Bruce L. A. Charlier (Contributions to Mineralogy and Petrology, 2022)
The transport and degassing pathways of volatiles through large silicic magmatic systems are central to understanding geothermal fluid compositions, ore deposit genesis, and volcanic eruption dynamics and impacts. Here, we document sulfur (S), chlorine (Cl), and fluorine (F) concentrations in a range of host materials in eruptive deposits from Taupō volcano (New Zealand). Materials analysed are groundmass glass, silicic melt inclusions, and microphenocrystic apatite that equilibrated in shallow melt-dominant magma bodies; silicic melt and apatite inclusions within crystal cores inferred to be sourced from deeper crystal mush; and olivine-hosted basaltic melt inclusions from mafic enclaves that represent the most primitive feedstock magmas. Sulfur and halogen concentrations each follow distinct concentration pathways during magma differentiation in response to changing pressures, temperatures, oxygen fugacities, crystallising mineral phases, the effects of volatile saturation, and the presence of an aqueous fluid phase. Sulfur contents in the basaltic melt inclusions (~ 2000 ppm) are typical for arc-type magmas, but drop to near detection limits by dacitic compositions, reflecting pyrrhotite crystallisation at ~ 60 wt. % SiO 2 during the onset of magnetite crystallisation. In contrast, Cl increases from ~ 500 ppm in basalts to ~ 2500 ppm in dacitic compositions, due to incompatibility in the crystallising phases. Fluorine contents are similar between mafic and silicic compositions (< 1200 ppm) and are primarily controlled by the onset of apatite and/or amphibole crystallisation and then destabilisation. Sulfur and Cl partition strongly into an aqueous fluid and/or vapour phase in the shallow silicic system. Sulfur contents in the rhyolite melts are low, yet the Oruanui supereruption is associated with a major sulfate peak in ice core records in Antarctica and Greenland, implying that excess S was derived from a pre-eruptive gas phase, mafic magma recharge, and/or disintegration of a hydrothermal system. We estimate that the 25.5 ka Oruanui eruption ejected > 130 Tg of S (390 Tg sulfate) and up to ~ 1800 Tg of Cl, with potentially global impacts on climate and stratospheric ozone.

Use of a multi‐metric macroalgal index to document severe eutrophication in a New Zealand estuary - Leigh M. Stevens; Barrie M. Forrest; Bruce D. Dudley; David R. Plew; John R. Zeldis; Ude Shankar; Arman Haddadchi; Keryn L. Roberts (New Zealand Journal of Marine and Freshwater Research, 2022)
Environmental indicators that reliably describe estuary trophic response to nutrient loading are required for the effective management of New Zealand estuaries. A common estuary eutrophication response is frequent, extensive and persistent opportunistic macroalgae blooms. This study explores the utility of the Opportunistic Macroalgal Blooming Tool (OMBT) in the New River Estuary (∼4600 ha), a shallow intertidal‐dominated system within a pastoral farming catchment in Southland, New Zealand. Total nitrogen (TN) loads increased from 3206 T y −1 in 2000 to 5143 T y −1 in 2020. Concomitantly, areas of opportunistic macroalgae, measured using the OMBT, expanded across the available intertidal habitat (AIH) from 34.9 ha or 1.4% of the AIH to 1383 ha or 47.6% of the AIH, and the average wet weight biomass increased from 19.3 g m −2 to a peak of 1326 g m −2 in 2019. We hypothesise that opportunistic macroalgae expanded rapidly in direct response to temporal increases in TN load, with increases disproportionately contributed by expansion and intensification of dairy farming in the catchment. This study confirmed that the OMBT predictably responded to changes in TN concentration and may therefore be useful in defining estuary‐specific TN concentration thresholds to inform likely load reductions required to achieve improved environmental outcomes.

Water chemistry of rivers and streams from the Jaú and Uatumã basins in central Brazilian Amazon - Eduardo Antonio Ríos-Villamizar; Aline Lopes; Maria do Socorro Rocha da Silva; Nilyan Adria Santarém dos Santos; Regison Oliveira; Robson M. Calazães; Maria Teresa Fernandez Piedade; Jochen Schöngart; Bruce R. Forsberg; Florian Wittmann; Wolfgang J. Junk (Sustainable Water Resources Management, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Cognitive control, interference inhibition, and ordering of information during working memory in younger and older healthy adults - Mina Mirjalili; Reza Zomorrodi; Zafiris J. Daskalakis; Sean L. Hill; Sanjeev Kumar; Daniel M. Blumberger; Corinne E. Fischer; Alastair J. Flint; Nathan Herrmann; Krista L. Lanctôt; Linda Mah; Benoit H. Mulsant; et al. (GeroScience, 2022)

Mismatches in scale between highly mobile marine megafauna and marine protected areas - Melinda G. Conners; Nicholas B. Sisson; Pierre D. Agamboue; Philip W. Atkinson; Alastair M. M. Baylis; Scott R. Benson; Barbara A. Block; Steven J. Bograd; Pablo Bordino; W. D. Bowen; Paul Brickle; Ignacio M. Bruno; et al. (Frontiers in Marine Science, 2022)
Marine protected areas (MPAs), particularly large MPAs, are increasing in number and size around the globe in part to facilitate the conservation of marine megafauna under the assumption that large-scale MPAs better align with vagile life histories; however, this alignment is not well established. Using a global tracking dataset from 36 species across five taxa, chosen to reflect the span of home range size in highly mobile marine megafauna, we show most MPAs are too small to encompass complete home ranges of most species. Based on size alone, 40% of existing MPAs could encompass the home ranges of the smallest ranged species, while only < 1% of existing MPAs could encompass those of the largest ranged species. Further, where home ranges and MPAs overlapped in real geographic space, MPAs encompassed < 5% of core areas used by all species. Despite most home ranges of mobile marine megafauna being much larger than existing MPAs, we demonstrate how benefits from MPAs are still likely to accrue by targeting seasonal aggregations and critical life history stages and through other management techniques.

The Colombian geochronological database (CGD) - Andres F. Rodriguez-Corcho; Yamirka Rojas-Agramonte; Johana A. Barrera-Gonzalez; Maria P. Marroquin-Gomez; Sarah Bonilla-Correa; David Izquierdo-Camacho; Sofia M. Delgado-Balaguera; David Cartwright-Buitrago; Maria D. Muñoz-Granados; William G. Carantón-Mateus; Alejandro Corrales-García; Andrés F. Laverde-Martinez; et al. (International Geology Review, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Investigating the contribution of white matter hyperintensities and cortical thickness to empathy in neurodegenerative and cerebrovascular diseases - Miracle Ozzoude; Brenda Varriano; Derek Beaton; Joel Ramirez; Melissa F. Holmes; Christopher J. M. Scott; Fuqiang Gao; Kelly M. Sunderland; Paula McLaughlin; Jennifer Rabin; Maged Goubran; Donna Kwan; et al. (GeroScience, 2022)

Comments on “Quantifiable urine glyphosate levels detected in 99% of the French population, with higher values in men, in younger people, and in farmers” - William Reeves; John L. Vicini; John T. Swarthout; Bruce M. Young; Pamela K. Jensen (Environmental Science and Pollution Research, 2022)

Genetic analysis of grain yield and yield-attributing traits in navy bean (Phaseolus vulgaris L.) under drought stress - Bruce Mutari; Julia Sibiya; Edmore Gasura; Prince M. Matova; Kennedy Simango; Aleck Kondwakwenda (Euphytica, 2022)

Expert range maps of global mammal distributions harmonised to three taxonomic authorities - Charles J. Marsh; Yanina V. Sica; Connor J. Burgin; Wendy A. Dorman; Robert C. Anderson; Isabel del Toro Mijares; Jessica G. Vigneron; Vijay Barve; Victoria L. Dombrowik; Michelle Duong; Robert Guralnick; Julie A. Hart; et al. (Journal of Biogeography, 2022)
Aim Comprehensive, global information on species' occurrences is an essential biodiversity variable and central to a range of applications in ecology, evolution, biogeography and conservation. Expert range maps often represent a species' only available distributional information and play an increasing role in conservation assessments and macroecology. We provide global range maps for the native ranges of all extant mammal species harmonised to the taxonomy of the Mammal Diversity Database (MDD) mobilised from two sources, the Handbook of the Mammals of the World (HMW) and the Illustrated Checklist of the Mammals of the World (CMW). Location Global. Taxon All extant mammal species. Methods Range maps were digitally interpreted, georeferenced, error‐checked and subsequently taxonomically aligned between the HMW (6253 species), the CMW (6431 species) and the MDD taxonomies (6362 species). Results Range maps can be evaluated and visualised in an online map browser at Map of Life ( mol.org ) and accessed for individual or batch download for non‐commercial use. Main conclusion Expert maps of species' global distributions are limited in their spatial detail and temporal specificity, but form a useful basis for broad‐scale characterizations and model‐based integration with other data. We provide georeferenced range maps for the native ranges of all extant mammal species as shapefiles, with species‐level metadata and source information packaged together in geodatabase format. Across the three taxonomic sources our maps entail, there are 1784 taxonomic name differences compared to the maps currently available on the IUCN Red List website. The expert maps provided here are harmonised to the MDD taxonomic authority and linked to a community of online tools that will enable transparent future updates and version control.

Biogeography of Southern Ocean prokaryotes: a comparison of the Indian and Pacific sectors - Swan L. S. Sow; Mark V. Brown; Laurence J. Clarke; Andrew Bissett; Jodie van de Kamp; Thomas W. Trull; Eric J. Raes; Justin R. Seymour; Anna R. Bramucci; Martin Ostrowski; Philip W. Boyd; Bruce E. Deagle; et al. (Environmental Microbiology, 2022)
Summary We investigated the Southern Ocean (SO) prokaryote community structure via zero‐radius operational taxonomic unit (zOTU) libraries generated from 16S rRNA gene sequencing of 223 full water column profiles. Samples reveal the prokaryote diversity trend between discrete water masses across multiple depths and latitudes in Indian (71–99°E, summer) and Pacific (170–174°W, autumn‐winter) sectors of the SO. At higher taxonomic levels (phylum‐family) we observed water masses to harbour distinct communities across both sectors, but observed sectorial variations at lower taxonomic levels (genus‐zOTU) and relative abundance shifts for key taxa such as Flavobacteria, SAR324/Marinimicrobia, Nitrosopumilus and Nitrosopelagicus at both epi‐ and bathy‐abyssopelagic water masses. Common surface bacteria were abundant in several deep‐water masses and vice‐versa suggesting connectivity between surface and deep‐water microbial assemblages. Bacteria from same‐sector Antarctic Bottom Water samples showed patchy, high beta‐diversity which did not correlate well with measured environmental parameters or geographical distance. Unconventional depth distribution patterns were observed for key archaeal groups: Crenarchaeota was found across all depths in the water column and persistent high relative abundances of common epipelagic archaeon Nitrosopelagicus was observed in deep‐water masses. Our findings reveal substantial regional variability of SO prokaryote assemblages that we argue should be considered in wide‐scale SO ecosystem microbial modelling.

Atlantic Sturgeon Status and Movement Ecology in an Extremely Small Spawning Habitat: The Nanticoke River-Marshyhope Creek, Chesapeake Bay - D. H. Secor; M. H. P. O’Brien; N. Coleman; A. Horne; I. Park; D. C. Kazyak; D. G. Bruce; C. Stence (Reviews in Fisheries Science & Aquaculture, 2022)

Genetic analysis of sucrose concentration in soybean seeds using a historical soybean genomic panel - Alexandra Ficht; Robert Bruce; Davoud Torkamaneh; Christopher M. Grainger; Milad Eskandari; Istvan Rajcan (Theoretical and Applied Genetics, 2022)

Rifting and recharge as triggers of the mixed basalt–rhyolite Halarauður ignimbrite eruption (Krafla, Iceland) - Shane M. Rooyakkers; John Stix; Kim Berlo; Daniele Morgavi; Maurizio Petrelli; Monika K. Rusiecka; Simon J. Barker; Bruce L. A. Charlier; David A. Neave; Francesco P. Vetere; Diego Perugini (Contributions to Mineralogy and Petrology, 2022)

TitaniQ revisited: expanded and improved Ti-in-quartz solubility model for thermobarometry - Zach R. Osborne; Jay B. Thomas; William O. Nachlas; Ross J. Angel; Christopher M. Hoff; E. Bruce Watson (Contributions to Mineralogy and Petrology, 2022)

The emergence of marine recreational drone fishing: Regional trends and emerging concerns - Alexander C. Winkler; Edward C. Butler; Colin G. Attwood; Bruce Q. Mann; Warren M. Potts (Ambio, 2022)

Understanding the economic activity generated by recreational fishing in South Africa provides insights on the role of recreational fisheries for social development - Warren M. Potts; Melville Saayman; Andrea Saayman; Bruce Q. Mann; Peet Van der Merwe; Peter Britz; Christopher S. Bova (Fisheries Management and Ecology, 2022)
While the economic activity associated with recreational fishing is well assessed in the developed world, substantially less is known in developing countries. South Africa is a unique microcosm for applying economic evaluation frameworks as its dualist economy shares characteristics of both the developed and developing world. Understanding participation levels and the role of dualism in economic activity linked to recreational fisheries is a crucial step towards leveraging the sector for economic development. A total of 1320 face‐to‐face and online questionnaires were used to estimate annual economic spend by recreational fishers, and the economic activity associated with this spend was modelled using Social Accounting Matrix analysis. Recreational fishing participation estimates totalled 1,327,633, which contributed ZAR 32.6 billion (US$2.2 billion) per year to economic activity and sustained 94,070 full‐time jobs. However, less than 10% of the economic activity benefitted lower income households, suggesting that the “first” and “second” economies of this dualist economy are disconnected. This is likely similar in other developing nations with international tourism‐driven recreational fisheries. To reduce this disconnect, changes in tourism policies to focus on local development, the identification of recreational fisheries tourism hotspots and the development of local education, skills and appropriate infrastructure through public–private partnerships will be necessary.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Decreased growth of wild soil microbes after 15 years of transplant‐induced warming in a montane meadow - Alicia M. Purcell; Michaela Hayer; Benjamin J. Koch; Rebecca L. Mau; Steven J. Blazewicz; Paul Dijkstra; Michelle C. Mack; Jane C. Marks; Ember M. Morrissey; Jennifer Pett‐Ridge; Rachel L. Rubin; Egbert Schwartz; et al. (Global Change Biology, 2022)
The carbon stored in soil exceeds that of plant biomass and atmospheric carbon and its stability can impact global climate. Growth of decomposer microorganisms mediates both the accrual and loss of soil carbon. Growth is sensitive to temperature and given the vast biological diversity of soil microorganisms, the response of decomposer growth rates to warming may be strongly idiosyncratic, varying among taxa, making ecosystem predictions difficult. Here, we show that 15 years of warming by transplanting plant–soil mesocosms down in elevation, strongly reduced the growth rates of soil microorganisms, measured in the field using undisturbed soil. The magnitude of the response to warming varied among microbial taxa. However, the direction of the response—reduced growth—was universal and warming explained twofold more variation than did the sum of taxonomic identity and its interaction with warming. For this ecosystem, most of the growth responses to warming could be explained without taxon‐specific information, suggesting that in some cases microbial responses measured in aggregate may be adequate for climate modeling. Long‐term experimental warming also reduced soil carbon content, likely a consequence of a warming‐induced increase in decomposition, as warming‐induced changes in plant productivity were negligible. The loss of soil carbon and decreased microbial biomass with warming may explain the reduced growth of the microbial community, more than the direct effects of temperature on growth. These findings show that direct and indirect effects of long‐term warming can reduce growth rates of soil microbes, which may have important feedbacks to global warming.

The CO 2 record at the Amazon Tall Tower Observatory: A new opportunity to study processes on seasonal and inter‐annual scales - Santiago Botía; Shujiro Komiya; Julia Marshall; Thomas Koch; Michał Gałkowski; Jost Lavric; Eliane Gomes‐Alves; David Walter; Gilberto Fisch; Davieliton M. Pinho; Bruce W. Nelson; Giordane Martins; et al. (Global Change Biology, 2022)
High‐quality atmospheric CO 2 measurements are sparse in Amazonia, but can provide critical insights into the spatial and temporal variability of sources and sinks of CO 2 . In this study, we present the first 6 years (2014–2019) of continuous, high‐precision measurements of atmospheric CO 2 at the Amazon Tall Tower Observatory (ATTO, 2.1°S, 58.9°W). After subtracting the simulated background concentrations from our observational record, we define a CO 2 regional signal ( ) that has a marked seasonal cycle with an amplitude of about 4 ppm. At both seasonal and inter‐annual scales, we find differences in phase between and the local eddy covariance net ecosystem exchange (EC‐NEE), which is interpreted as an indicator of a decoupling between local and non‐local drivers of . In addition, we present how the 2015–2016 El Niño‐induced drought was captured by our atmospheric record as a positive 2σ anomaly in both the wet and dry season of 2016. Furthermore, we analyzed the observed seasonal cycle and inter‐annual variability of together with net ecosystem exchange (NEE) using a suite of modeled flux products representing biospheric and aquatic CO 2 exchange. We use both non‐optimized and optimized (i.e., resulting from atmospheric inverse modeling) NEE fluxes as input in an atmospheric transport model (STILT). The observed shape and amplitude of the seasonal cycle was captured neither by the simulations using the optimized fluxes nor by those using the diagnostic Vegetation and Photosynthesis Respiration Model (VPRM). We show that including the contribution of CO 2 from river evasion improves the simulated shape (not the magnitude) of the seasonal cycle when using a data‐driven non‐optimized NEE product (FLUXCOM). The simulated contribution from river evasion was found to be 25% of the seasonal cycle amplitude. Our study demonstrates the importance of the ATTO record to better understand the Amazon carbon cycle at various spatial and temporal scales.

Phylogenetic organization in the assimilation of chemically distinct substrates by soil bacteria - Chansotheary Dang; Jeth G.V. Walkup; Bruce A. Hungate; Rima B. Franklin; Egbert Schwartz; Ember M. Morrissey (Environmental Microbiology, 2022)
Summary Soils are among the most biodiverse habitats on earth and while the species composition of microbial communities can influence decomposition rates and pathways, the functional significance of many microbial species and phylogenetic groups remains unknown. If bacteria exhibit phylogenetic organization in their function, this could enable ecologically meaningful classification of bacterial clades. Here, we show non‐random phylogenetic organization in the rates of relative carbon assimilation for both rapidly mineralized substrates (amino acids and glucose) assimilated by many microbial taxa and slowly mineralized substrates (lipids and cellulose) assimilated by relatively few microbial taxa. When mapped onto bacterial phylogeny using ancestral character estimation this phylogenetic organization enabled the identification of clades involved in the decomposition of specific soil organic matter substrates. Phylogenetic organization in substrate assimilation could provide a basis for predicting the functional attributes of uncharacterized microbial taxa and understanding the significance of microbial community composition for soil organic matter decomposition.

The kappa-opioid receptor agonist, triazole 1.1, reduces oxycodone self-administration and enhances oxycodone-induced thermal antinociception in male rats - C. Austin Zamarripa; Tanya Pareek; Hayley M. Schrock; Thomas E. Prisinzano; Bruce E. Blough; Kenneth J. Sufka; Kevin B. Freeman (Psychopharmacology, 2021)

Distribution and diversity of alternate hosts of Maruca vitrata Fabricius in three West African countries - Prince Christopher Addae; Y. Anani Bruce; Iliyasu M. Utono; Mumuni Abudulai; Fousseni Traore; Mohammad F. Ishiyaku; Rabiu S. Adamu; Ahmed Seidu; Benoît J. Batieno; Onyekachi Francis Nwankwo; Malick N. Ba; Gloria A. Adazebra; et al. (International Journal of Tropical Insect Science, 2021)
The evolution of resistance to the Bacillus thuringiensis ( Bt ) toxins by insect pests is a major threat to Bt technology. However, the rate of resistance can be slowed with appropriate integrated insect resistance management (IRM) strategies. Surveys were conducted to identify alternate host species for Maruca vitrata (commonly called the legume pod borer or Maruca ) that could serve as refuges for Pod-Borer Resistant (PBR) cowpea in three West African countries (Ghana, Nigeria, and Burkina Faso). Survey sites included 25 in northern Ghana, 44 in northern Nigeria, and 52 in north-central and southwestern Burkina Faso. Alternate hosts of Maruca identified from plant species belonging to the Fabaceae family that showed signs of Maruca damage on cowpea tissues were collected and dissected. Larvae that were found during these dissections were reared to adult moths in the laboratory then identified to species. The alternate host plants including species of Crotolaria , Sesbania , Tephrosia , and Vigna were the most frequently encountered among sites and locations. Flowering and podding of these plants overlapped with flowering and podding of the nearby (~200 m) cowpea crop. Abundance of these wild hosts and overlapping flowering patterns with the cowpea crop in most locations have the potential to sustain ample numbers of Bt susceptible Maruca that will mate with possible resistant Maruca and deter resistance development. Further quantitative studies, however, are required from each location to determine if actual Maruca production from alternate hosts is sufficient for a PBR IRM strategy. If verified, this approach would be compatible with the high dose/refuge IRM strategy that includes alternate hosts and non- Bt crops as refuges.

Aluminum solubility in rutile (TiO2) - Christopher M. Hoff; E. Bruce Watson (Physics and Chemistry of Minerals, 2021)

Consistent Prevalence of Spondyloarthropathy Over 2300 Years: Ancient Egyptians and the Synchronic Baboon Catacomb - Bruce M. Rothschild (Evolutionary Biology, 2021)

Use of whole genome analysis to identify shared genomic variants across breeds in canine mitral valve disease - Brian Williams; Steven G. Friedenberg; Bruce W. Keene; Sandy P. Tou; Teresa C. DeFrancesco; Kathryn M. Meurs (Human Genetics, 2021)

The use of statistical methods to assess groundwater contamination in the Lower Tano river basin, Ghana, West Africa - Adwoba K. M. Edjah; Bruce Banoeng-Yakubo; Thomas Tetteh Akiti; Kwabena Doku-Amponsah; Anthony A. Duah; Enoch Sakyi-Yeboah; Joseph Valcory Kippo; Inusah Amadu; Kwabina Ibrahim (Environmental Monitoring and Assessment, 2021)

The second wave of earthworm invasions in North America: biology, environmental impacts, management and control of invasive jumping worms - Chih-Han Chang; Marie L. C. Bartz; George Brown; Mac A. Callaham; Erin K. Cameron; Andrea Dávalos; Annise Dobson; Josef H. Görres; Bradley M. Herrick; Hiroshi Ikeda; Samuel W. James; Marie R. Johnston; et al. (Biological Invasions, 2021)

An Ecosystem Approach to Wild Rice-Fish Cultivation - Nesar Ahmed; Shirley Thompson; Bruce Hardy; Giovanni M. Turchini (Reviews in Fisheries Science & Aquaculture, 2021)

Adenosine A2A receptor null chondrocyte transcriptome resembles that of human osteoarthritic chondrocytes - Cristina M. Castro; Carmen Corciulo; Benjamin Friedman; Zhi Li; Samson Jacob; David Fenyo; Bruce N. Cronstein (Purinergic Signalling, 2021)

Analysis of the P53N a Novel Protein Encoded on Chromosome 22q12.1-12.3 in Glioblastomas and Ependymomas Specimens - Bruce M. Frankel; David Cachia; Sunil J. Patel; Arabinda Das (Journal of Molecular Neuroscience, 2021)

Iron-withdrawing anti-infectives for new host-directed therapies based on iron dependence, the Achilles’ heel of antibiotic-resistant microbes - Bruce E. Holbein; M. Trisha C. Ang; David S. Allan; Wangxue Chen; Christian Lehmann (Environmental Chemistry Letters, 2021)

Pinpointing Drivers of Extirpation in Sea Snakes: A Synthesis of Evidence From Ashmore Reef - Ruchira Somaweera; Vinay Udyawer; Michael L. Guinea; Daniela M. Ceccarelli; Rohan H. Clarke; Michelle Glover; Mathew Hourston; John Keesing; Arne Redsted Rasmussen; Kate Sanders; Richard Shine; Damian P. Thomson; et al. (Frontiers in Marine Science, 2021)
Over the past decade, vertebrate populations globally have experienced significant declines in distribution and abundance. Understanding the reasons behind these population declines is the first step in implementing appropriate management responses to improve conservation outcomes. Uncovering drivers of extirpation events after the fact, however, requires a careful forensic approach to prevent similar declines elsewhere. The once abundant and species-rich sea snake fauna of Ashmore Reef Marine Park, in the Timor Sea, collapsed dramatically in the early 2000s. No such decline has occurred on surrounding reefs. We synthesise the evidence for this collapse and the subsequent slow recovery and evaluate the plausibility of potential drivers for the declines, as well as provide evidence against certain explanations that have been proposed in the past. Our systematic review shows that of seven possible hypotheses considered, at least three are credible and require additional information: (1) stochastic environmental events may have increased the snakes’ susceptibility to pathogens, (2) a resurgence in the abundance of top predators may have induced a localised change in trophic structure, and (3) an acute increase in local boat traffic may have had negative physical impacts. One or more of these factors, possibly acting in combination with as yet other unidentified factors, is the most plausible explanation for the precipitous decline in sea snake populations observed. Based on this position, we identify future research directions with a focus on addressing critical gaps in knowledge to inform and prioritise future management actions.

An island‐hopping bird reveals how founder events shape genome‐wide divergence - Ashley T. Sendell‐Price; Kristen C. Ruegg; Bruce C. Robertson; Sonya M. Clegg (Molecular Ecology, 2021)
When populations colonize new areas, both strong selection and strong drift can be experienced due to novel environments and small founding populations, respectively. Empirical studies have predominantly focused on the phenotype when assessing the role of selection, and limited neutral‐loci when assessing founder‐induced loss of diversity. Consequently, the extent to which processes interact to influence evolutionary trajectories is difficult to assess. Genomic‐level approaches provide the opportunity to simultaneously consider these processes. Here, we examine the roles of selection and drift in shaping genomic diversity and divergence in historically documented sequential island colonizations by the silvereye ( Zosterops lateralis ). We provide the first empirical demonstration of the rapid appearance of highly diverged genomic regions following population founding, the position of which are highly idiosyncratic. As these regions rarely contained loci putatively under selection, it is most likely that these differences arise via the stochastic nature of the founding process. However, selection is required to explain rapid evolution of larger body size in insular silvereyes. Reconciling our genomic data with these phenotypic patterns suggests there may be many genomic routes to the island phenotype, which vary across populations. Finally, we show that accelerated divergence associated with multiple founding steps is the product of genome‐wide rather than localized differences, and that diversity erodes due to loss of rare alleles. However, even multiple founder events do not result in divergence and diversity levels seen in evolutionary older subspecies, and therefore do not provide a shortcut to speciation as proposed by founder‐effect speciation models.

Assessment of Flavobacterium psychrophilum ‐associated mortality in Atlantic salmon ( Salmo salar ) and brook trout ( Salvelinus fontinalis ) - Timothy J. Bruce; Jie Ma; Evan M. Jones; Brent M. Vuglar; Luke P. Oliver; Christopher Knupp; Thomas P. Loch; Kenneth D. Cain (Journal of Fish Diseases, 2021)
Salmonid diseases caused by infections of Flavobacterium psychrophilum , the causative agent of bacterial coldwater disease, remain difficult to manage as novel, pathogenic strains continue to emerge in aquaculture settings globally. To date, much of the research regarding treatment options and vaccine development has focused on rainbow trout ( Oncorhynchus mykiss ), but other inland‐reared salmonids are also impacted by this Gram‐negative bacterium. As such, Atlantic salmon ( Salmo salar ) and brook trout ( Salvelinus fontinalis ) were injection‐challenged with a variety of previously reported F. psychrophilum strains isolated from disease diagnostic cases in salmonids, as well as a standard and well‐studied F. psychrophilum strain (CSF 259–93) known to be virulent in rainbow trout. In three separate virulence assessments (Trials A, B and C), strains US063 (isolated from lake trout; Salvelinus namaycush ) and US149 (isolated from Atlantic salmon) caused a significantly higher cumulative per cent mortality (CPM) relative to other strains in Atlantic salmon ( p p =.008) and B (CPM 96% ± 2.3% vs. 81.33% ± 4.8%, p =.014). Trial C used a lower dose (1.86 × 10 8 CFU/mL) for US149, resulting in a lower mortality (78.67% ± 9.33%) relative to Trials A and B. CSF259‐93 did not cause significant mortality in any trials. In brook trout, the strain 03–179 (originally isolated from steelhead trout; Oncorhynchus mykiss ) was significantly more virulent than any other (CPM 100% ± 0%, p F. psychrophilum virulence testing in Atlantic salmon and brook trout, demonstrating the high virulence of US063 and US149 for these salmonid species. This information is applicable for the development of therapeutics and vaccines against F . psychrophilum infections and demonstrates the reproducibility of the experimental challenge model.

Correction to: The Downstream Impacts of Hydropower Dams and Indigenous and Local Knowledge: Examples from the Peace–Athabasca, Mekong, and Amazon - Ian G. Baird; Renato A. M. Silvano; Brenda Parlee; Mark Poesch; Bruce Maclean; Art Napoleon; Melody Lepine; Gustavo Hallwass (Environmental Management, 2021)

The Downstream Impacts of Hydropower Dams and Indigenous and Local Knowledge: Examples from the Peace–Athabasca, Mekong, and Amazon - Ian G. Baird; Renato A. M. Silvano; Brenda Parlee; Mark Poesch; Bruce Maclean; Art Napoleon; Melody Lepine; Gustavo Hallwass (Environmental Management, 2021)

Do integrated landscape approaches moderate climate impacts on livelihoods? A review of the evidence from agricultural landscapes - John M. A. Duncan; Bryan Boruff; Eloise M. Biggs; Billy T. Haworth; Nathan Wales; Eleanor Bruce (Regional Environmental Change, 2021)

Susan Lynn Williams: the Life of an Exceptional Scholar, Leader, and Friend (1951–2018) - William C. Dennison; Matthew E. S. Bracken; Maria Brown; John F. Bruno; James T. Carlton; Robert C. Carpenter; Tim J. B. Carruthers; Megan N. Dethier; Carlos M. Duarte; Thomas R. Fisher; James W. Fourqurean; Richard K. Grosberg; et al. (Estuaries and Coasts, 2021)
Susan Lynn Williams (1951–2018) was an exceptional marine ecologist whose research focused broadly on the ecology of benthic nearshore environments dominated by seagrasses, seaweeds, and coral reefs. She took an empirical approach founded in techniques of physiological ecology. Susan was committed to applying her research results to ocean management through outreach to decision-makers and resource managers. Susan’s career included research throughout the USA in tropical, temperate, and polar regions, but she specialized in tropical marine ecology. Susan’s scholarship, leadership, and friendship touched many people, leading to this multi-authored paper. Susan’s scholarship was multi-faceted, and she excelled in scientific discovery, integration of scientific results, application of science for conservation, and teaching, especially as a mentor to undergraduate and graduate students and postdoctoral scholars. Susan served in a variety of leadership positions throughout her career. She embodied all facets of leadership; leading by example, listening to others, committing to the “long haul,” maintaining trust, and creating a platform for all to shine. Susan was an important role model for women in science. Susan was also a loyal friend, maintaining friendships for many decades. Susan loved cooking and entertaining with friends. This paper provides an overview of the accomplishments of Susan in the broad categories of scholarship, leadership, and friendship.

Grasping at digitalisation: turning imagination into fact in the sugarcane farming community - Simon J. Fielke; Bruce M. Taylor; Emma Jakku; Martijn Mooij; Cara Stitzlein; Aysha Fleming; Peter J. Thorburn; Anthony J. Webster; Aaron Davis; Maria P. Vilas (Sustainability Science, 2021)
Nutrient runoff from catchments that drain into the Great Barrier Reef (GBR) is a significant source of stress for this World Heritage Area. An alliance of collaborative on-ground water quality monitoring (Project 25) and technologically driven digital application development (Digiscape GBR) projects were formulated to provide data that highlighted the contribution of a network of Australian sugar cane farmers, amongst other sources, to nutrient runoff. This environmental data and subsequent information were extended to the farming community through scientist-led feedback sessions and the development of specialised digital technology (1622™WQ) that help build an understanding of the nutrient movements, in this case nitrogen, such that farmers might think about and eventually act to alter their fertilizer application practices. This paper reflects on a socio-environmental sustainability challenge that emerged during this case study, by utilising the nascent concept of digi-grasping. We highlight the importance of the entire agricultural knowledge and advice network being part of an innovation journey to increase the utility of digital agricultural technologies developed to increase overall sustainability. We develop the digi-MAST analytical framework, which explores modes of being and doing in the digital world, ranging from ‘the everyday mystery of the digital world (M)’, through digital ‘awareness (A)’, digitally ‘sparked’ being/s (S), and finally the ability of individuals and/or groups to ‘transform (T)’ utilising digital technologies and human imaginations. Our digi-MAST framework allows us to compare agricultural actors, in this case, to understand present modes of digi-grasping to help determine the resources and actions likely to be required to achieve impact from the development of various forms of digital technological research outputs.

Late Neanderthal short-term and specialized occupations at the Abri du Maras (South-East France, level 4.1, MIS 3) - Marie-Hélène Moncel; M. Gema Chacón; Delphine Vettese; Marie-Agnès Courty; Camille Daujeard; Aleix Eixea; Paul Fernandes; Ethel Allué; Bruce Hardy; Florent Rivals; Philippe Béarez; Rosalia Gallotti; et al. (Archaeological and Anthropological Sciences, 2021)

Warrumbungle Volcano: facies architecture and evolution of a complex shield volcano - K. F. Bull; A. L. Troedson; S. Bodorkos; P. L. Blevin; M. C. Bruce; K. Waltenberg (Australian Journal of Earth Sciences, 2021)

Acute after-school screen time in children decreases impulse control and activation toward high-calorie food stimuli in brain regions related to reward and attention - Mary Efraim; C. Brock Kirwan; Nathan M. Muncy; Larry A. Tucker; Sunku Kwon; Bruce W. Bailey (Brain Imaging and Behavior, 2021)

Persistent COVID-19-associated neurocognitive symptoms in non-hospitalized patients - Joanna Hellmuth; T. Allen Barnett; Breton M. Asken; J. Daniel Kelly; Leonel Torres; Melanie L. Stephens; Bryan Greenhouse; Jeffrey N. Martin; Felicia C. Chow; Steven G. Deeks; Meredith Greene; Bruce L. Miller; et al. (Journal of NeuroVirology, 2021)
As cases of coronavirus disease 2019 (COVID-19) mount worldwide, attention is needed on potential long-term neurologic impacts for the majority of patients who experience mild to moderate illness managed as outpatients. To date, there has not been discussion of persistent neurocognitive deficits in patients with milder COVID-19. We present two cases of non-hospitalized patients recovering from COVID-19 with persistent neurocognitive symptoms. Commonly used cognitive screens were normal, while more detailed testing revealed working memory and executive functioning deficits. An observational cohort study of individuals recovering from COVID-19 (14 or more days following symptom onset) identified that among the first 100 individuals enrolled, 14 were non-hospitalized patients reporting persistent cognitive issues. These 14 participants had a median age of 39 years (interquartile range: 35–56), and cognitive symptoms were present for at least a median of 98 days (interquartile range: 71–120 following acute COVID-19 symptoms); no participants with follow-up evaluation reported symptom resolution. We discuss potential mechanisms to be explored in future studies, including direct viral effects, indirect consequences of immune activation, and immune dysregulation causing auto-antibody production.

Vascular plant extinction in the continental United States and Canada - Wesley M. Knapp; Anne Frances; Reed Noss; Robert F. C. Naczi; Alan Weakley; George D. Gann; Bruce G. Baldwin; James Miller; Patrick McIntyre; Brent D. Mishler; Gerry Moore; Richard G. Olmstead; et al. (Conservation Biology, 2021)
Extinction rates are expected to increase during the Anthropocene. Current extinction rates of plants and many animals remain unknown. We quantified extinctions among the vascular flora of the continental United States and Canada since European settlement. We compiled data on apparently extinct species by querying plant conservation databases, searching the literature, and vetting the resulting list with botanical experts. Because taxonomic opinion varies widely, we developed an index of taxonomic uncertainty (ITU). The ITU ranges from A to F, with A indicating unanimous taxonomic recognition and F indicating taxonomic recognition by only a single author. The ITU allowed us to rigorously evaluate extinction rates. Our data suggest that 51 species and 14 infraspecific taxa, representing 33 families and 49 genera of vascular plants, have become extinct in our study area since European settlement. Seven of these taxa exist in cultivation but are extinct in the wild. Most extinctions occurred in the west, but this outcome may reflect the timing of botanical exploration relative to settlement. Sixty‐four percent of extinct plants were single‐site endemics, and many occurred outside recognized biodiversity hotspots. Given the paucity of plant surveys in many areas, particularly prior to European settlement, the actual extinction rate of vascular plants is undoubtedly much higher than indicated here.

DeepNeuro: an open-source deep learning toolbox for neuroimaging - Andrew Beers; James Brown; Ken Chang; Katharina Hoebel; Jay Patel; K. Ina Ly; Sara M. Tolaney; Priscilla Brastianos; Bruce Rosen; Elizabeth R. Gerstner; Jayashree Kalpathy-Cramer (Neuroinformatics, 2021)

Summer Ichthyoplankton Assemblage Diversity Within a Southeastern United States Estuary - Bruce W. Pfirrmann; Matthew E. Kimball; Marvin M. Mace; Brendan D. Turley (Estuaries and Coasts, 2021)

Learning from failure at the science–policy interface for climate action in agriculture - Dhanush Dinesh; Dries Hegger; Joost Vervoort; Bruce M. Campbell; Peter P. J. Driessen (Mitigation and Adaptation Strategies for Global Change, 2021)
Science–policy engagement efforts to accelerate climate action in agricultural systems are key to enable the sector to contribute to climate and food security goals. However, lessons to improve science–policy engagement efforts in this context mostly come from successful efforts and are limited in terms of empirical scope. Moreover, lessons have not been generated systematically from failed science–policy engagement efforts. Such analysis using lessons from failure management can improve or even transform the efficacy of efforts. To address this knowledge gap, we examined challenges and failures faced in science–policy engagement efforts of the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS). We developed an explanatory framework inspired by Cash et al.’s criteria for successful knowledge systems for sustainable development: credibility, salience, and legitimacy, complemented with insights from the wider literature. Using this framework in a survey, we identified factors which explain failure. To effectively manage these factors, we propose a novel approach for researchers working at the science–policy interface to fail intelligently, which involves planning for failure, minimizing risks, effective design, making failures visible, and learning from failures. This approach needs to be complemented by actions at the knowledge system level to create an enabling environment for science–policy interfaces.

The psychoactive aminoalkylbenzofuran derivatives, 5-APB and 6-APB, mimic the effects of 3,4-methylenedioxyamphetamine (MDA) on monoamine transmission in male rats - Simon D. Brandt; Hailey M. Walters; John S. Partilla; Bruce E. Blough; Pierce V. Kavanagh; Michael H. Baumann (Psychopharmacology, 2020)

Negative Food Effect of Danirixin: Use of PBPK Modelling to Explore the Effect of Formulation and Meal Type on Clinical PK - Richard S. Lloyd; Martin I. Hingle; Jackie C. Bloomer; Stephen J. Charles; James M. Butler; Alan Paul; Xiaofeng Zhu; Bruce Miller; Donald D’Amico; Alison Donald; Ruth Tal-Singer; Claire Ambery (Pharmaceutical Research, 2020)

Assessing the Eutrophic Susceptibility of New Zealand Estuaries - David R. Plew; John R. Zeldis; Bruce D. Dudley; Amy L. Whitehead; Leigh M. Stevens; Barry M. Robertson; Ben P. Robertson (Estuaries and Coasts, 2020)
We developed a method to predict the susceptibility of New Zealand estuaries to eutrophication. This method predicts macroalgae and phytoplankton responses to potential nutrient concentrations and flushing times, obtained nationally from simple dilution models, a GIS land-use model and physical estuary properties. Macroalgal response was based on an empirically derived relationship between potential nitrogen concentrations and an established macroalgal index (EQR) and phytoplankton response using an analytical growth model. Intertidal area was used to determine which primary producer was likely to lead to eutrophic conditions within estuaries. We calculated the eutrophication susceptibility of 399 New Zealand estuaries and assigned them to susceptibility bands A (lowest expected impact) to D (highest expected impact). Twenty-seven percent of New Zealand estuaries have high or very high eutrophication susceptibilities (band C or D), mostly (63% of band C and D) due to macroalgae. The physical properties of estuaries strongly influence susceptibility to macroalgae or phytoplankton blooms, and estuaries with similar physical properties cluster spatially around New Zealand’s coasts. As a result, regional patterns in susceptibility are apparent due to a combination of estuary types and land use patterns. The few areas in New Zealand with consistently low estuary eutrophication susceptibilities are either undeveloped or have estuaries with short flushing times, low intertidal area and/or minimal tidal influx. Estuaries with conditions favourable for macroalgae are most at risk. Our approach provides estuary-integrated susceptibility scores likely to be of use as a regional or national screening tool to prioritise more in-depth estuary assessments, to evaluate likely responses to altered nutrient loading regimes and assist in developing management strategies for estuaries.

Enhanced Fe3+ binding through cooperativity of 3-hydroxypyridin-4-one groups within a linear co-polymer: wrapping effect leading to superior antimicrobial activity - Roger Gumbau-Brisa; M. Trisha C. Ang; Bruce E. Holbein; Matthias Bierenstiel (BioMetals, 2020)

COSORE: A community database for continuous soil respiration and other soil‐atmosphere greenhouse gas flux data - Ben Bond‐Lamberty; Danielle S. Christianson; Avni Malhotra; Stephanie C. Pennington; Debjani Sihi; Amir AghaKouchak; Hassan Anjileli; M. Altaf Arain; Juan J. Armesto; Samaneh Ashraf; Mioko Ataka; Dennis Baldocchi; et al. (Global Change Biology, 2020)
Globally, soils store two to three times as much carbon as currently resides in the atmosphere, and it is critical to understand how soil greenhouse gas (GHG) emissions and uptake will respond to ongoing climate change. In particular, the soil‐to‐atmosphere CO 2 flux, commonly though imprecisely termed soil respiration ( R S ), is one of the largest carbon fluxes in the Earth system. An increasing number of high‐frequency R S measurements (typically, from an automated system with hourly sampling) have been made over the last two decades; an increasing number of methane measurements are being made with such systems as well. Such high frequency data are an invaluable resource for understanding GHG fluxes, but lack a central database or repository. Here we describe the lightweight, open‐source COSORE (COntinuous SOil REspiration) database and software, that focuses on automated, continuous and long‐term GHG flux datasets, and is intended to serve as a community resource for earth sciences, climate change syntheses and model evaluation. Contributed datasets are mapped to a single, consistent standard, with metadata on contributors, geographic location, measurement conditions and ancillary data. The design emphasizes the importance of reproducibility, scientific transparency and open access to data. While being oriented towards continuously measured R S , the database design accommodates other soil‐atmosphere measurements (e.g. ecosystem respiration, chamber‐measured net ecosystem exchange, methane fluxes) as well as experimental treatments (heterotrophic only, etc.). We give brief examples of the types of analyses possible using this new community resource and describe its accompanying R software package.

Salinity and inundation effects on productivity of brackish tidal marsh plants in the San Francisco Bay-Delta Estuary - Christopher N. Janousek; Bruce D. Dugger; Brandon M. Drucker; Karen M. Thorne (Hydrobiologia, 2020)

Spatiotemporal Patterns of Mineral and Organic Matter Deposition Across Two San Francisco Bay-Delta Tidal Marshes - Kevin J. Buffington; Christopher N. Janousek; Karen M. Thorne; Bruce D. Dugger (Wetlands, 2020)

Modeling Mixed Vascular and Alzheimer’s Dementia Using Focal Subcortical Ischemic Stroke in Human ApoE4-TR:5XFAD Transgenic Mice - Eric Y. Hayden; Julia M. Huang; Malena Charreton; Stefanie M. Nunez; Jennifer N. Putman; Bruce Teter; Jason T. Lee; Andrew Welch; Sally Frautschy; Gregory Cole; Edmond Teng; Jason D. Hinman (Translational Stroke Research, 2020)

Opioid-Associated Hearing Loss: A 20-Year Review from the New Jersey Poison Center - Alexander M. Mozeika; Bruce E. Ruck; Lewis S. Nelson; Diane P. Calello (Journal of Medical Toxicology, 2020)

Comparative demography of commercially important species of coral grouper, Plectropomus leopardus and P. laevis , from Australia's great barrier reef and Coral Sea marine parks - Samuel D. Payet; Jake R. Lowe; Bruce D. Mapstone; Morgan S. Pratchett; Tane H. Sinclair‐Taylor; Brett M. Taylor; Peter A. Waldie; Hugo B. Harrison (Journal of Fish Biology, 2020)
Understanding the spatial and environmental variation in demographic processes of fisheries target species, such as coral grouper (Genus: Plectropomus ), is important for establishing effective management and conservation strategies. Herein we compare the demography of Plectropomus leopardus and P. laevis between Australia's Great Barrier Reef Marine Park (GBRMP), which has been subject to sustained and extensive fishing pressure, and the oceanic atolls of Australia's Coral Sea Marine Park (CSMP), where there is very limited fishing for reef fishes. Coral grouper length‐at‐age data from contemporary and historical otolith collections across 9.4 degrees of latitude showed little difference in lifetime growth between GBRMP and CSMP regions. Plectropomus laevis populations in GBRMP reefs had significantly higher rates of total mortality than populations in the CSMP. Mean maximum lengths and mean maximum ages of P. laevis were also smaller in the GBRMP than in the CSMP, even when considering populations sampled within GBRMP no‐take marine reserves (NTMRs). Plectropomus leopardus , individuals were on average smaller on fished reefs than NTMRs in the GBRMP, but all other aspects of demography were broadly similar between regions despite the negligible levels of fishing pressure in the CSMP. Similarities between regions in growth profiles and length‐at‐age comparisons of P. laevis and P. leopardus suggest that the environmental differences between the CSMP and the GBRMP may not have significant impacts on lifetime growth. Our results show that fishing may have influenced the demography of coral grouper on the GBR, particularly for the slower growing and longer lived species, P. laevis .

Reconsidering humaneness - Jordan O. Hampton; Penny M. Fisher; Bruce Warburton (Conservation Biology, 2020)
Animal welfare is increasingly important in the understanding of how human activity affects wildlife, but the conservation community is still grappling with meaningful terminology when communicating this aspect of their work. One example is the use of the terms “humane” and “inhumane.” These terms are used in scientific contexts, but they also have legal and social definitions. Without reference to a defined technical standard, describing an action or outcome as humane (or inhumane) constrains science communication because the terms have variable definitions; establish a binary (something is either humane or inhumane); and imply underlying values reflecting a moral prescription. Invoking the term “humane,” and especially the strong antithesis “inhumane,” can infer a normative judgment of how animals ought to be treated (humane) or ought not to be treated (inhumane). The consequences of applying this terminology are not just academic. Publicizing certain practices as humane can create blurred lines around contentious animal welfare questions and, perhaps intentionally, defer scrutiny of actual welfare outcomes. Labeling other practices as inhumane can be used cynically to erode their public support. We suggest that, if this normative language is used in science, it should always be accompanied by a clear, contextual definition of what is meant by humane.

Analysis of P78: A Novel Cytoplasmic Membrane-Associated Protein Encoded on Chromosome 19q13.3 in Glioma Specimens - Bruce M. Frankel; David Cachia; Sunil J. Patel; Arabinda Das (Journal of Molecular Neuroscience, 2020)

Cyanide Contamination of the Puyango-Tumbes River Caused by Artisanal Gold Mining in Portovelo-Zaruma, Ecuador - Bruce G. Marshall; Marcello M. Veiga; Henrique A. M. da Silva; Jean Remy Davée Guimarães (Current Environmental Health Reports, 2020)

Exploring movement patterns and changing distributions of baleen whales in the western North Atlantic using a decade of passive acoustic data - Genevieve E. Davis; Mark F. Baumgartner; Peter J. Corkeron; Joel Bell; Catherine Berchok; Julianne M. Bonnell; Jacqueline Bort Thornton; Solange Brault; Gary A. Buchanan; Danielle M. Cholewiak; Christopher W. Clark; Julien Delarue; et al. (Global Change Biology, 2020)
Six baleen whale species are found in the temperate western North Atlantic Ocean, with limited information existing on the distribution and movement patterns for most. There is mounting evidence of distributional shifts in many species, including marine mammals, likely because of climate‐driven changes in ocean temperature and circulation. Previous acoustic studies examined the occurrence of minke ( Balaenoptera acutorostrata ) and North Atlantic right whales (NARW; Eubalaena glacialis ). This study assesses the acoustic presence of humpback ( Megaptera novaeangliae ), sei ( B. borealis ), fin ( B. physalus ), and blue whales ( B. musculus ) over a decade, based on daily detections of their vocalizations. Data collected from 2004 to 2014 on 281 bottom‐mounted recorders, totaling 35,033 days, were processed using automated detection software and screened for each species' presence. A published study on NARW acoustics revealed significant changes in occurrence patterns between the periods of 2004–2010 and 2011–2014; therefore, these same time periods were examined here. All four species were present from the Southeast United States to Greenland; humpback whales were also present in the Caribbean. All species occurred throughout all regions in the winter, suggesting that baleen whales are widely distributed during these months. Each of the species showed significant changes in acoustic occurrence after 2010. Similar to NARWs, sei whales had higher acoustic occurrence in mid‐Atlantic regions after 2010. Fin, blue, and sei whales were more frequently detected in the northern latitudes of the study area after 2010. Despite this general northward shift, all four species were detected less on the Scotian Shelf area after 2010, matching documented shifts in prey availability in this region. A decade of acoustic observations have shown important distributional changes over the range of baleen whales, mirroring known climatic shifts and identifying new habitats that will require further protection from anthropogenic threats like fixed fishing gear, shipping, and noise pollution.

Fitness, independent of physical activity is associated with cerebral blood flow in adults at risk for Alzheimer’s disease - Ryan J. Dougherty; Elizabeth A. Boots; Jacob B. Lindheimer; Aaron J. Stegner; Stephanie Van Riper; Dorothy F. Edwards; Catherine L. Gallagher; Cynthia M. Carlsson; Howard A. Rowley; Barbara B. Bendlin; Sanjay Asthana; Bruce P. Hermann; et al. (Brain Imaging and Behavior, 2020)

Description and distribution of Desmacella hyalina sp. nov. (Porifera, Desmacellidae), a new cryptic demosponge in glass sponge reefs from the western coast of Canada - Lauren K. Law; Henry M. Reiswig; Bruce S. Ott; Neil McDaniel; Amanda S. Kahn; Keenan C. Guillas; Curtis Dinn; Sally P. Leys (Marine Biodiversity, 2020)

Isolation and experimental challenge of cultured burbot ( Lota lota maculosa ) with Flavobacterium columnare and Aeromonas sp. isolates - Timothy J. Bruce; Jie Ma; Luke P. Oliver; Evan M. Jones; Benjamin R. LaFrentz; Kenneth D. Cain (Journal of Fish Diseases, 2020)
Burbot ( Lota lota maculosa ) are a potential new species for commercial aquaculture. As burbot culture expands, there is a need to further define pathogen susceptibility and characterize aspects of the burbot immune response in an effort to assess fish health. A recent clinical diagnostic case from juvenile burbot reared at a commercial production facility resulted in the isolation and identification of Flavobacterium columnare along with several Aeromonas spp. The F. columnare isolate was assigned to genetic group 1 via multiplex PCR, a genetic group commonly associated with columnaris disease cases in rainbow trout ( Oncorhynchus mykiss ). Virulence of the F. columnare isolate was assessed in vivo in both juvenile burbot and rainbow trout. Additionally, several of the Aeromonas sp. case isolates were identified via sequencing (16S rRNA, gyrB and rpoD ) and a putative A . sobria isolate (BI‐3) was used to challenge burbot, along with a known virulent Aeromonas sp. (A141), but BI‐3 was not found to be virulent. Burbot were refractory to F. columnare when challenged by immersion, and it is likely that this is a secondary pathogen for burbot. Although refractory in burbot, the identified F. columnare isolate (BI‐1) was found to be virulent in rainbow trout.

Effects of body size on estimation of mammalian area requirements - Michael J. Noonan; Christen H. Fleming; Marlee A. Tucker; Roland Kays; Autumn‐Lynn Harrison; Margaret C. Crofoot; Briana Abrahms; Susan C. Alberts; Abdullahi H. Ali; Jeanne Altmann; Pamela Castro Antunes; Nina Attias; et al. (Conservation Biology, 2020)
Accurately quantifying species’ area requirements is a prerequisite for effective area‐based conservation. This typically involves collecting tracking data on species of interest and then conducting home‐range analyses. Problematically, autocorrelation in tracking data can result in space needs being severely underestimated. Based on the previous work, we hypothesized the magnitude of underestimation varies with body mass, a relationship that could have serious conservation implications. To evaluate this hypothesis for terrestrial mammals, we estimated home‐range areas with global positioning system (GPS) locations from 757 individuals across 61 globally distributed mammalian species with body masses ranging from 0.4 to 4000 kg. We then applied block cross‐validation to quantify bias in empirical home‐range estimates. Area requirements of mammals 1, meaning the scaling of the relationship changed substantially at the upper end of the mass spectrum.

Neurochemical and behavioral comparisons of contingent and non-contingent methamphetamine exposure following binge or yoked long-access self-administration paradigms - Catherine A. Schweppe; Caitlin Burzynski; Subramaniam Jayanthi; Bruce Ladenheim; Jean Lud Cadet; Eliot L. Gardner; Zheng-Xiong Xi; Henriette van Praag; Amy Hauck Newman; Thomas M. Keck (Psychopharmacology, 2020)

Haplotype diversity underlying quantitative traits in Canadian soybean breeding germplasm - Robert W. Bruce; Davoud Torkamaneh; Christopher M. Grainger; François Belzile; Milad Eskandari; Istvan Rajcan (Theoretical and Applied Genetics, 2020)

Inflammation resolution: a dual-pronged approach to averting cytokine storms in COVID-19? - Dipak Panigrahy; Molly M. Gilligan; Sui Huang; Allison Gartung; Irene Cortés-Puch; Patricia J. Sime; Richard P. Phipps; Charles N. Serhan; Bruce D. Hammock (Cancer and Metastasis Reviews, 2020)

On the distinction of pollen grains of early varieties of Hordeum from Glyceria species: addressing the early cereal cultivation problem in palynology - Bruce M. Albert; James B. Innes (Palynology, 2020)

A novel tissue culture model for evaluating the effect of aging on stem cell fate in adult microvascular networks - Mohammad S. Azimi; Jessica M. Motherwell; Maria Dutreil; Ryan L. Fishel; Matthew Nice; Nicholas A. Hodges; Bruce A. Bunnell; Adam Katz; Walter L. Murfee (GeroScience, 2020)

Age-related murine hippocampal CA1 laminae oxidative stress measured in vivo by QUEnch-assiSTed (QUEST) MRI: impact of isoflurane anesthesia - Bruce A. Berkowitz; Robert H. Podolsky; Karen Lins Childers; Alexander Gow; Brandy L. Schneider; Scott C. Lloyd; Kelly E. Bosse; Alana C. Conti; Robin Roberts; Ali M. Berri; Emma Graffice; Kenan Sinan; et al. (GeroScience, 2020)
Age-related impairments in spatial learning and memory often precede non-familial neurodegenerative disease. Ex vivo studies suggest that physiologic age-related oxidative stress in hippocampus area CA1 may contribute to prodromal spatial disorientation and to morbidity. Yet, conventional blood or cerebrospinal fluid assays appear insufficient for early detection or management of oxidative stress within CA1 sub-regions in vivo. Here, we address this biomarker problem using a non-invasive MRI index of CA1 laminae oxidative stress based on reduction in R1 (= 1/T1) after anti-oxidant administration. An R1 reduction reflects quenching of continuous and excessive production of endogenous paramagnetic free radicals. Careful motion-correction image acquisition, and avoiding repeated exposure to isoflurane, facilitates detection of hippocampus CA1 laminae oxidative stress with QUEnch-assiSTed (QUEST) MRI. Intriguingly, age- and isoflurane-related oxidative stress is localized to the stratum lacunosum of the CA1 region. Our data raise the possibility of using QUEST MRI and FDA-approved anti-oxidants to remediate spatial disorientation and later neurodegeneration with age in animals and humans.

Myocardial adaptability in young and older-aged sea-level habitants sojourning at Mt Kilimanjaro: are cardiac compensatory limits reached in older trekkers? - Glenn M. Stewart; Courtney M. Wheatley-Guy; Norman R. Morris; Kirsten E. Coffman; Jan Stepanek; Alex R. Carlson; Amine Issa; Michael A. Schmidt; Bruce D. Johnson (European Journal of Applied Physiology, 2020)

Behavioural and Electrophysiological Responses of Female Anopheles gambiae Mosquitoes to Volatiles from a Mango Bait - Felician C. Meza; Joe M. Roberts; Islam S. Sobhy; Fredros O. Okumu; Frederic Tripet; Toby J. A. Bruce (Journal of Chemical Ecology, 2020)
Attractive Toxic Sugar Baits (ATSB) are used in a “lure-and-kill” approach for management of the malaria vector Anopheles gambiae , but the active chemicals were previously unknown. Here we collected volatiles from a mango, Mangifera indica , juice bait which is used in ATSBs in Tanzania and tested mosquito responses. In a Y-tube olfactometer, female mosquitoes were attracted to the mango volatiles collected 24–48 h, 48–72 h and 72–96 h after preparing the bait but volatiles collected at 96–120 h were no longer attractive. Volatile analysis revealed emission of 23 compounds in different chemical classes including alcohols, aldehydes, alkanes, benzenoids, monoterpenes, sesquiterpenes and oxygenated terpenes. Coupled GC-electroantennogram (GC-EAG) recordings from the antennae of An. gambiae showed robust responses to 4 compounds: humulene, ( E )-caryophyllene, terpinolene and myrcene. In olfactometer bioassays, mosquitoes were attracted to humulene and terpinolene. ( E )-caryophyllene was marginally attractive while myrcene elicited an avoidance response with female mosquitoes. A blend of humulene, ( E )-caryophyllene and terpinolene was highly attractive to females ( P < 0.001) when tested against a solvent blank. Furthermore, there was no preference when this synthetic blend was offered as a choice against the natural sample. Our study has identified the key compounds from mango juice baits that attract An. gambiae and this information may help to improve the ATSBs currently used against malaria vectors.

Chemical Mediation of Oviposition by Anopheles Mosquitoes: a Push-Pull System Driven by Volatiles Associated with Larval Stages - Bruce Schoelitsz; Victor Mwingira; Leonard E. G. Mboera; Hans Beijleveld; Constantianus J. M. Koenraadt; Jeroen Spitzen; Joop J. A. van Loon; Willem Takken (Journal of Chemical Ecology, 2020)
The oviposition behavior of mosquitoes is mediated by chemical cues. In the malaria mosquito Anopheles gambiae , conspecific larvae produce infochemicals that affect this behavior. Emanations from first instar larvae proved strongly attractive to gravid females, while those from fourth instars caused oviposition deterrence, suggesting that larval developmental stage affected the oviposition choice of the female mosquito. We examined the nature of these chemicals by headspace collection of emanations of water in which larvae of different stages were developing. Four chemicals with putative effects on oviposition behavior were identified: dimethyldisulfide (DMDS) and dimethyltrisulfide (DMTS) were identified in emanations from water containing fourth instars; nonane and 2,4-pentanedione (2,4-PD) were identified in emanations from water containing both first and fourth instars. Dual-choice oviposition studies with these compounds were done in the laboratory and in semi-field experiments in Tanzania. In the laboratory, DMDS and DMTS were associated with oviposition-deterrent effects, while results with nonane and 2,4-PD were inconclusive. In further studies DMDS and DMTS evoked egg retention, while with nonane and 2,4-PD 88% and 100% of female mosquitoes, respectively, laid eggs. In dual-choice semi-field trials DMDS and DMTS caused oviposition deterrence, while nonane and 2,4-PD evoked attraction, inducing females to lay more eggs in bowls containing these compounds compared to the controls. We conclude that oviposition of An. gambiae is mediated by these four infochemicals associated with conspecific larvae, eliciting either attraction or deterrence. High levels of egg retention occurred when females were exposed to chemicals associated with fourth instar larvae.

Mode of silver clearance following 28-day inhalation exposure to silver nanoparticles determined from lung burden assessment including post-exposure observation periods - Mi Seong Jo; Jin Kwon Kim; Younghun Kim; Hoi Pin Kim; Hee Sang Kim; Kangho Ahn; Ji Hyun Lee; Elaine M. Faustman; Mary Gulumian; Bruce Kelman; Il Je Yu (Archives of Toxicology, 2020)

Non-native vascular flora of the Arctic: Taxonomic richness, distribution and pathways - Pawel Wasowicz; Alexander N. Sennikov; Kristine B. Westergaard; Katie Spellman; Matthew Carlson; Lynn J. Gillespie; Jeffery M. Saarela; Steven S. Seefeldt; Bruce Bennett; Christian Bay; Stefanie Ickert-Bond; Henry Väre (Ambio, 2020)

Monetizing the Value of Measurements of Equilibrium Climate Sensitivity Using the Social Cost of Carbon - Roger M. Cooke; Alexander Golub; Bruce Wielicki; Martin Mlynczak; David Young; Rosemary Rallo Baize (Environmental Modeling & Assessment, 2020)

Fire affects the taxonomic and functional composition of soil microbial communities, with cascading effects on grassland ecosystem functioning - Sihang Yang; Qiaoshu Zheng; Yunfeng Yang; Mengting Yuan; Xingyu Ma; Nona R. Chiariello; Kathryn M. Docherty; Christopher B. Field; Jessica L. M. Gutknecht; Bruce A. Hungate; Audrey Niboyet; Xavier Le Roux; et al. (Global Change Biology, 2020)
Fire is a crucial event regulating the structure and functioning of many ecosystems. Yet few studies have focused on how fire affects taxonomic and functional diversities of soil microbial communities, along with changes in plant communities and soil carbon (C) and nitrogen (N) dynamics. Here, we analyze these effects in a grassland ecosystem 9 months after an experimental fire at the Jasper Ridge Global Change Experiment site in California, USA. Fire altered soil microbial communities considerably, with community assembly process analysis showing that environmental selection pressure was higher in burned sites. However, a small subset of highly connected taxa was able to withstand the disturbance. In addition, fire decreased the relative abundances of most functional genes associated with C degradation and N cycling, implicating a slowdown of microbial processes linked to soil C and N dynamics. In contrast, fire stimulated above‐ and belowground plant growth, likely enhancing plant–microbe competition for soil inorganic N, which was reduced by a factor of about 2. To synthesize those findings, we performed structural equation modeling, which showed that plants but not microbial communities were responsible for significantly higher soil respiration rates in burned sites. Together, our results demonstrate that fire ‘reboots’ the grassland ecosystem by differentially regulating plant and soil microbial communities, leading to significant changes in soil C and N dynamics.

Limitations of trait‐based approaches for stressor assessment: The case of freshwater invertebrates and climate drivers - Anna T. Hamilton; Ralf B. Schäfer; Matthew I. Pyne; Bruce Chessman; Karan Kakouei; Kate S. Boersma; Piet F. M. Verdonschot; Ralf C. M. Verdonschot; Meryl Mims; Kieran Khamis; Britta Bierwagen; Jen Stamp (Global Change Biology, 2020)
The appeal of trait‐based approaches for assessing environmental vulnerabilities arises from the potential insight they provide into the mechanisms underlying the changes in populations and community structure. Traits can provide ecologically based explanations for observed responses to environmental changes, along with predictive power gained by developing relationships between traits and environmental variables. Despite these potential benefits, questions remain regarding the utility and limitations of these approaches, which we explore focusing on the following questions: (a) How reliable are predictions of biotic responses to changing conditions based on single trait–environment relationships? (b) What factors constrain detection of single trait–environment relationships, and how can they be addressed? (c) Can we use information on meta‐community processes to reveal conditions when assumptions underlying trait‐based studies are not met? We address these questions by reviewing published literature on aquatic invertebrate communities from stream ecosystems. Our findings help to define factors that influence the successful application of trait‐based approaches in addressing the complex, multifaceted effects of changing climate conditions on hydrologic and thermal regimes in stream ecosystems. Key conclusions are that observed relationships between traits and environmental stressors are often inconsistent with predefined hypotheses derived from current trait‐based thinking, particularly related to single trait–environment relationships. Factors that can influence findings of trait‐based assessments include intercorrelations of among traits and among environmental variables, spatial scale, strength of biotic interactions, intensity of habitat disturbance, degree of abiotic stress, and methods of trait characterization. Several recommendations are made for practice and further study to address these concerns, including using phylogenetic relatedness to address intercorrelation. With proper consideration of these issues, trait‐based assessment of organismal vulnerability to environmental changes can become a useful tool to conserve threatened populations into the future.

Synthesis of novel α-glucans with potential health benefits through controlled glucose release in the human gastrointestinal tract - Joana Gangoiti; Sarah F. Corwin; Lisa M. Lamothe; Christina Vafiadi; Bruce R. Hamaker; Lubbert Dijkhuizen (Critical Reviews in Food Science and Nutrition, 2020)

Aerosol Pirfenidone Pharmacokinetics after Inhaled Delivery in Sheep: a Viable Approach to Treating Idiopathic Pulmonary Fibrosis - Lisa M Kaminskas; Cornelia B Landersdorfer; Robert J Bischof; Nathania Leong; Jibriil Ibrahim; Andrew N Davies; Stephen Pham; Steven Beck; A. Bruce Montgomery; Mark W Surber (Pharmaceutical Research, 2020)

The impact of different approaches to exposure assessment on understanding non-malignant respiratory disease risk in taconite miners - Nnaemeka U. Odo; Jeffrey H. Mandel; Bruce H. Alexander; David M. Perlman; Richard F. MacLehose; Gurumurthy Ramachandran; Andrew D. Ryan; Yuan Shao (International Archives of Occupational and Environmental Health, 2020)

Multilocus phylogeny of a cryptic radiation of Afrotropical long‐fingered bats (Chiroptera, Miniopteridae) - Terrence C. Demos; Paul W. Webala; Holly L. Lutz; Julian C. Kerbis Peterhans; Steven M. Goodman; Natalia Cortés‐Delgado; Michael Bartonjo; Bruce D. Patterson (Zoologica Scripta, 2020)
The Old World bat family Miniopteridae comprises only the genus Miniopterus , which includes 20 currently recognized species from the Afrotropical realm and 15 species from Eurasia and Australasia. Since 2003, the number of recognized Miniopterus species has grown from 19 to 35, with most newly described species endemic to Madagascar and the Comoros Archipelago. We investigated genetic variation, phylogenetic relationships and clade membership in Miniopterus focusing on Afrotropical taxa. We generated mitochondrial cytochrome‐ b (cyt‐ b ) and nuclear intron data (five genes) from 352 vouchered individuals collected at 78 georeferenced localities. Including 99 additional mitochondrial sequences from GenBank, we analysed a total of 25 recognized species. Mitochondrial genetic distances among cyt‐ b ‐supported clades averaged 9.3%, representing as many as five undescribed species. Multilocus coalescent delimitation strongly supported the genetic isolation of eight of nine tested unnamed clades. A large number of sampled clades in sub‐Saharan Africa are distributed wholly or partly in East Africa (nine of 13 clades), suggesting that Miniopterus diversity has been grossly underestimated. Although 25 of 27 cyt‐ b and 23 of 25 nuclear gene tree lineages from the Afrotropics were strongly supported as monophyletic, a majority of deep nodes were poorly resolved in phylogenetic analyses. Long terminal branches subtending short backbone internodes in the phylogenetic analyses suggest a rapid radiation model of diversification. This hypothesis needs to be tested using more phylogenetically informative data.

Digital camera monitoring of recreational fishing effort: Applications and challenges - Bruce W. Hartill; Stephen M. Taylor; Krystle Keller; Marc Simon Weltersbach (Fish and Fisheries, 2020)
The growing awareness of the impact that recreational fishers can have on fish stocks has highlighted the paucity of information used to inform their management. Most of the available information on the scale and nature of recreational catch and effort has come from intermittent and labour‐intensive surveys that provide fragmented insights into often highly variable fisheries. Digital cameras offer a more cost‐effective means of continuously monitoring trends in recreational fishing effort, and it is surprising that greater use of this approach has not been made to date given its widespread use in other contexts. We share lessons learnt from four early adopter studies in New Zealand, Australia and Germany, where digital cameras have been used to monitor recreational fishing effort. Many of the challenges that we have encountered and overcome were initially unforeseen, and we suggest solutions and strategies to address these issues. We conclude that all aspects of a camera‐based monitoring system should be considered from the outset, to optimize the utility and value of the information they provide over the long term. Aspects to consider include the location and configuration of a camera system, ensuring service continuity, image quality, data storage, image interpretation and ultimately the analysis of any data collected. Robustly designed digital camera monitoring systems can be used to gain greater insight into recreational fishery dynamics, leading to more informed, responsive and effective fisheries management.

Mutations in sorghum SBEIIb and SSIIa affect alkali spreading value, starch composition, thermal properties and flour viscosity - Stefanie Griebel; Richard P. Westerman; Adedayo Adeyanju; Charles Addo-Quaye; Bruce A. Craig; Clifford F. Weil; Suzanne M. Cunningham; Bhavesh Patel; Osvaldo H. Campanella; Mitchell R. Tuinstra (Theoretical and Applied Genetics, 2019)
Key message Seven novel alleles of SBEIIb and one allele of SSIIa co-segregated with the ASV phenotype and contributed to distinct starch quality traits important for food-processing applications. Abstract Sorghum is an important food crop for millions of people in Africa and Asia. Whole-genome re-sequencing of sorghum EMS mutants exhibiting an alkali spreading value (ASV) phenotype revealed candidate SNPs in Sobic.004G163700 and Sobic.010G093400 . Comparative genomics identified Sobic.010G093400 as a starch synthase IIa and Sobic.004G163700 as a starch branching enzyme IIb . Segregation analyses showed that mutations in Sobic.010G093400 or Sobic.004G163700 co-segregated with the ASV phenotype. Mutants in SSIIa exhibited no change in amylose content but expressed lower final viscosity and lower starch gelatinization temperature (GT) than starches from non-mutant plants. The sbeIIb mutants exhibited significantly higher amylose levels and starch GT and lower viscosity compared to non-mutant starches and ssIIa mutants. Mutations in SBEIIb had a dosage-dependent effect on amylose content. Double mutants of sbeIIb and ssIIa resembled their sbeIIb parent in amylose content, starch thermal properties and viscosity profiles. These variants will provide opportunities to produce sorghum varieties with modified starch end-use qualities important for the beer brewing and baking industries and specialty foods for humans with diabetes.

S100B and its association with HIV-associated neurocognitive disorders - Nath Limpruttidham; Brooks I. Mitchell; Kalpana J. Kallianpur; Beau K. Nakamoto; Scott A. Souza; Bruce Shiramizu; Lishomwa C. Ndhlovu; Dominic C. Chow; Cecilia M. Shikuma (Journal of NeuroVirology, 2019)

Molasses Grass Induces Direct and Indirect Defense Responses in Neighbouring Maize Plants - Tigist A. Tolosa; Amanuel Tamiru; Charles A. O. Midega; Johnnie Van Den Berg; Michael A. Birkett; Christine M. Woodcock; Toby J. A. Bruce; Segenet Kelemu; John A. Pickett; Zeyaur R. Khan (Journal of Chemical Ecology, 2019)

Persistence of an endangered native duck, feral mallards, and multiple hybrid swarms across the main Hawaiian Islands - Caitlin P. Wells; Philip Lavretsky; Michael D. Sorenson; Jeffrey L. Peters; Jeffrey M. DaCosta; Stephen Turnbull; Kimberly J. Uyehara; Christopher P. Malachowski; Bruce D. Dugger; John M. Eadie; Andrew Engilis (Molecular Ecology, 2019)
Interspecific hybridization is recognized as an important process in the evolutionary dynamics of both speciation and the reversal of speciation. However, our understanding of the spatial and temporal patterns of hybridization that erode versus promote species boundaries is incomplete. The endangered, endemic koloa maoli (or Hawaiian duck, Anas wyvilliana ) is thought to be threatened with genetic extinction through ongoing hybridization with an introduced congener, the feral mallard ( A. platyrhynchos ). We investigated spatial and temporal variation in hybrid prevalence in populations throughout the main Hawaiian Islands, using genomic data to characterize population structure of koloa, quantify the extent of hybridization, and compare hybrid proportions over time. To accomplish this, we genotyped 3,308 double‐digest restriction‐site‐associated DNA (ddRAD) loci in 425 putative koloa, mallards, and hybrids from populations across the main Hawaiian Islands. We found that despite a population decline in the last century, koloa genetic diversity is high. There were few hybrids on the island of Kauaʻi, home to the largest population of koloa. By contrast, we report that sampled populations outside of Kauaʻi can now be characterized as hybrid swarms, in that all individuals sampled were of mixed koloa × mallard ancestry. Further, there is some evidence that these swarms are stable over time. These findings demonstrate spatial variation in the extent and consequences of interspecific hybridization, and highlight how islands or island‐like systems with small population sizes may be especially prone to genetic extinction when met with a congener that is not reproductively isolated.

Rainfall-related natural disasters in the Northeast of Brazil as a response to ocean-atmosphere interaction - Bruce Kelly N. Silva; Ana Cleide B. Amorim; Claudio M. S. Silva; Paulo S. Lucio; Lara M. Barbosa (Theoretical and Applied Climatology, 2019)

Anatomical structure associated with vegetative growth variation in macadamia - Benjamin D. Toft; Mobashwer M. Alam; Bruce L. Topp (Plant and Soil, 2019)

A cofactor consumption screen identifies promising NfsB family nitroreductases for dinitrotoluene remediation - Elsie M. Williams; Abigail V. Sharrock; Elizabeth L. Rylott; Neil C. Bruce; Joanna K. MacKichan; David F. Ackerley (Biotechnology Letters, 2019)

Multiyear monitoring of survival following mitigation‐driven translocation of a long‐lived threatened reptile - Brett G. Dickson; Rick D. Scherer; Amanda M. Kissel; Bryan P. Wallace; Kathryn M. Langin; Miranda E. Gray; Amanda F. Scheib; Bruce Weise (Conservation Biology, 2019)
Translocation is used by managers to mitigate the negative impacts of development on species. Moving individuals to a new location is challenging, and many translocation attempts have failed. Robust, posttranslocation monitoring is therefore important for evaluating effects of translocation on target species. We evaluated the efficacy of a translocation designed to mitigate the effects of a utility‐scale solar energy project on the U.S. federally listed Mojave desert tortoise ( Gopherus agassizii ). The species is a long‐lived reptile threatened by a variety of factors, including habitat loss due to renewable energy development in the Mojave Desert and portions of the Colorado Desert in southern California (southwestern United States). We translocated 58 individual tortoises away from the project's construction site and intensively monitored them over 5 years (2012–2017). We monitored these individuals and tortoises located in the translocation release area (resident tortoises; n = 112) and control tortoises ( n = 149) in a nearby location. We used our tortoise encounter data and known‐fate survival models to estimate annual and cumulative survival. Translocated tortoises in each of 2 size classes (120–160 mm, >160 mm) did not survive at lower rates than resident and control tortoises over the study period. For models with different sets of biotic and abiotic covariates, annual and cumulative estimates of survival were always >0.87 and >0.56, respectively. Larger tortoises tended to have higher survival, but translocated tortoises were not differentially affected by the covariates used to model variation in survival. Based on these findings, our translocation design and study protocols could inform other translocation projects for desert species. Our case study highlights the benefits of combining rigorous scientific monitoring with well‐designed, mitigation‐driven management actions to reduce the negative effects of development on species of conservation concern.

Global in situ Observations of Essential Climate and Ocean Variables at the Air–Sea Interface - Luca R. Centurioni; Jon Turton; Rick Lumpkin; Lancelot Braasch; Gary Brassington; Yi Chao; Etienne Charpentier; Zhaohui Chen; Gary Corlett; Kathleen Dohan; Craig Donlon; Champika Gallage; et al. (Frontiers in Marine Science, 2019)

Transcriptome Analysis Reveals That Naphthenic Acids Perturb Gene Networks Related to Metabolic Processes, Membrane Integrity, and Gut Function in Silurana (Xenopus) tropicalis Embryos - Juan Manuel Gutierrez-Villagomez; Christopher J. Martyniuk; Lei Xing; Valerie S. Langlois; Bruce D. Pauli; Jules M. Blais; Vance L. Trudeau (Frontiers in Marine Science, 2019)

Ocean Observations to Improve Our Understanding, Modeling, and Forecasting of Subseasonal-to-Seasonal Variability - Aneesh C. Subramanian; Magdalena A. Balmaseda; Luca Centurioni; Rajib Chattopadhyay; Bruce D. Cornuelle; Charlotte DeMott; Maria Flatau; Yosuke Fujii; Donata Giglio; Sarah T. Gille; Thomas M. Hamill; Harry Hendon; et al. (Frontiers in Marine Science, 2019)

SMART Cables for Observing the Global Ocean: Science and Implementation - Bruce M. Howe; Brian K. Arbic; Jérome Aucan; Christopher R. Barnes; Nigel Bayliff; Nathan Becker; Rhett Butler; Laurie Doyle; Shane Elipot; Gregory C. Johnson; Felix Landerer; Stephen Lentz; et al. (Frontiers in Marine Science, 2019)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Observing the Oceans Acoustically - Bruce M. Howe; Jennifer Miksis-Olds; Eric Rehm; Hanne Sagen; Peter F. Worcester; Georgios Haralabus (Frontiers in Marine Science, 2019)

The effects of tree spacing regime and tree species composition on mineral nutrient composition of cocoa beans and canarium nuts in 8-year-old cocoa plantations - Shahla Hosseini-Bai; Stephen J. Trueman; Tio Nevenimo; Godfrey Hannet; Bruce Randall; Helen M. Wallace (Environmental Science and Pollution Research, 2019)

A new image classification approach for mapping coral density in State of Kuwait using high spatial resolution satellite images - M. Gholoum; D. Bruce; S. Alhazeem (International Journal of Remote Sensing, 2019)

Correction Factors for δ18O-Derived Global Sea Surface Temperature Reconstructions From Diagenetically Altered Intervals of Coral Skeletal Density Banding - Mayandi Sivaguru; Kyle W. Fouke; Lauren Todorov; Michael J. Kingsford; Kaitlyn E. Fouke; Jeffrey M. Trop; Bruce W. Fouke (Frontiers in Marine Science, 2019)

Runoff from glacier ice and seasonal snow in High Asia: separating melt water sources in river flow - Richard L. Armstrong; Karl Rittger; Mary J. Brodzik; Adina Racoviteanu; Andrew P. Barrett; Siri-Jodha Singh Khalsa; Bruce Raup; Alice F. Hill; Alia L. Khan; Alana M. Wilson; Rijan Bhakta Kayastha; Florence Fetterer; et al. (Regional Environmental Change, 2019)

Global Observing Needs in the Deep Ocean - Lisa A. Levin; Brian J. Bett; Andrew R. Gates; Patrick Heimbach; Bruce M. Howe; Felix Janssen; Andrea McCurdy; Henry A. Ruhl; Paul Snelgrove; Karen I. Stocks; David Bailey; Simone Baumann-Pickering; et al. (Frontiers in Marine Science, 2019)

A missense variant in the titin gene in Doberman pinscher dogs with familial dilated cardiomyopathy and sudden cardiac death - Kathryn M. Meurs; Steven G. Friedenberg; Justin Kolb; Chandra Saripalli; Paola Tonino; Kathleen Woodruff; Natasha J. Olby; Bruce W. Keene; Darcy B. Adin; Oriana L. Yost; Teresa C. DeFrancesco; Sunshine Lahmers; et al. (Human Genetics, 2019)

Elevated cerebrospinal fluid Galectin-9 is associated with central nervous system immune activation and poor cognitive performance in older HIV-infected individuals - Thomas A. Premeaux; Michelle L. D’Antoni; Mohamed Abdel-Mohsen; Satish K. Pillai; Kalpana J. Kallianpur; Beau K. Nakamoto; Melissa Agsalda-Garcia; Bruce Shiramizu; Cecilia M. Shikuma; Magnus Gisslén; Richard W. Price; Victor Valcour; et al. (Journal of NeuroVirology, 2019)

DNA metabarcoding—Need for robust experimental designs to draw sound ecological conclusions - Lucie Zinger; Aurélie Bonin; Inger G. Alsos; Miklós Bálint; Holly Bik; Frédéric Boyer; Anthony A. Chariton; Simon Creer; Eric Coissac; Bruce E. Deagle; Marta De Barba; Ian A. Dickie; et al. (Molecular Ecology, 2019)

The North Atlantic Aerosol and Marine Ecosystem Study (NAAMES): Science Motive and Mission Overview - Michael J. Behrenfeld; Richard H. Moore; Chris A. Hostetler; Jason Graff; Peter Gaube; Lynn M. Russell; Gao Chen; Scott C. Doney; Stephen Giovannoni; Hongyu Liu; Christopher Proctor; Luis M. Bolaños; et al. (Frontiers in Marine Science, 2019)

Synthesis of Ocean Observations Using Data Assimilation for Operational, Real-Time and Reanalysis Systems: A More Complete Picture of the State of the Ocean - Andrew M. Moore; Matthew J. Martin; Santha Akella; Hernan G. Arango; Magdalena Balmaseda; Laurent Bertino; Stefano Ciavatta; Bruce Cornuelle; Jim Cummings; Sergey Frolov; Pierre Lermusiaux; Paolo Oddo; et al. (Frontiers in Marine Science, 2019)

Putting It All Together: Adding Value to the Global Ocean and Climate Observing Systems With Complete Self-Consistent Ocean State and Parameter Estimates - Patrick Heimbach; Ichiro Fukumori; Christopher N. Hill; Rui M. Ponte; Detlef Stammer; Carl Wunsch; Jean-Michel Campin; Bruce Cornuelle; Ian Fenty; Gaël Forget; Armin Köhl; Matthew Mazloff; et al. (Frontiers in Marine Science, 2019)

The dopamine, serotonin and norepinephrine releasing activities of a series of methcathinone analogs in male rat brain synaptosomes - Bruce E. Blough; Ann M. Decker; Antonio Landavazo; Ojas A. Namjoshi; John S. Partilla; Michael H. Baumann; Richard B. Rothman (Psychopharmacology, 2019)

Description of a new species of Aethycteron Suriano & Beverley-Burton, 1982 (Monogenea: Ancyrocephalidae) on the gills of the rare striated darter, Etheostoma striatulum Page & Braasch (Perciformes: Percidae), from the Duck River, Tennessee, USA - Kara M. Million; Bruce W. Stallsmith (Systematic Parasitology, 2019)

Characterization of water chemistry in some communities of the Lower Tano river basin, Ghana, West Africa - A. K. M. Edjah; Bruce Banoeng-Yakubo; T. T. Akiti; Barbara Stenni; Giuliano Dreossi; K. Doku-Amponsah (Arabian Journal of Geosciences, 2019)

Spatiotemporal remote sensing of ecosystem change and causation across Alaska - Neal J. Pastick; M. Torre Jorgenson; Scott J. Goetz; Benjamin M. Jones; Bruce K. Wylie; Burke J. Minsley; Hélène Genet; Joseph F. Knight; David K. Swanson; Janet C. Jorgenson (Global Change Biology, 2019)
Contemporary climate change in Alaska has resulted in amplified rates of press and pulse disturbances that drive ecosystem change with significant consequences for socio‐environmental systems. Despite the vulnerability of Arctic and boreal landscapes to change, little has been done to characterize landscape change and associated drivers across northern high‐latitude ecosystems. Here we characterize the historical sensitivity of Alaska's ecosystems to environmental change and anthropogenic disturbances using expert knowledge, remote sensing data, and spatiotemporal analyses and modeling. Time‐series analysis of moderate—and high‐resolution imagery was used to characterize land‐ and water‐surface dynamics across Alaska. Some 430,000 interpretations of ecological and geomorphological change were made using historical air photos and satellite imagery, and corroborate land‐surface greening, browning, and wetness/moisture trend parameters derived from peak‐growing season Landsat imagery acquired from 1984 to 2015. The time series of change metrics, together with climatic data and maps of landscape characteristics, were incorporated into a modeling framework for mapping and understanding of drivers of change throughout Alaska. According to our analysis, approximately 13% (~174,000 ± 8700 km 2 ) of Alaska has experienced directional change in the last 32 years (±95% confidence intervals). At the ecoregions level, substantial increases in remotely sensed vegetation productivity were most pronounced in western and northern foothills of Alaska, which is explained by vegetation growth associated with increasing air temperatures. Significant browning trends were largely the result of recent wildfires in interior Alaska, but browning trends are also driven by increases in evaporative demand and surface‐water gains that have predominately occurred over warming permafrost landscapes. Increased rates of photosynthetic activity are associated with stabilization and recovery processes following wildfire, timber harvesting, insect damage, thermokarst, glacial retreat, and lake infilling and drainage events. Our results fill a critical gap in the understanding of historical and potential future trajectories of change in northern high‐latitude regions.

Seasonal Loading and Concentration Patterns for Fecal Bacteroidales qPCR Markers and Relationships to Water Quality Parameters at Baseflow - M. A. Stallard; S. Winesett; M. Scopel; M. Bruce; F. C. Bailey (Water, Air, & Soil Pollution, 2019)

The digging dynamics of ant tunnels: movement, encounters, and nest space - A. I. Bruce; A. Pérez-Escudero; T. J. Czaczkes; M. Burd (Insectes Sociaux, 2019)

Leveraging linkage evidence to identify low-frequency and rare variants on 16p13 associated with blood pressure using TOPMed whole genome sequencing data - Karen Y. He; Xiaoyin Li; Tanika N. Kelly; Jingjing Liang; Brian E. Cade; Themistocles L. Assimes; Lewis C. Becker; Amber L. Beitelshees; Adam P. Bress; Yen-Pei Christy Chang; Yii-Der Ida Chen; Paul S. de Vries; et al. (Human Genetics, 2019)

Understanding the evolving phenotype of vascular complications in telomere biology disorders - Cecilia Higgs; Yanick J. Crow; Denise M. Adams; Emmanuel Chang; Don Hayes; Utz Herbig; James N. Huang; Ryan Himes; Kunal Jajoo; F. Brad Johnson; Susan D. Reynolds; Yoshihiro Yonekawa; et al. (Angiogenesis, 2019)

Future Research Directions on the “Elusive” White Shark - Charlie Huveneers; Kirin Apps; Edgar E. Becerril-García; Barry Bruce; Paul A. Butcher; Aaron B. Carlisle; Taylor K. Chapple; Heather M. Christiansen; Geremy Cliff; Tobey H. Curtis; Toby S. Daly-Engel; Heidi Dewar; et al. (Frontiers in Marine Science, 2018)

MicroRNA Expression Levels Are Altered in the Cerebrospinal Fluid of Patients with Young-Onset Alzheimer’s Disease - Paul M. McKeever; Raphael Schneider; Foad Taghdiri; Anna Weichert; Namita Multani; Robert A. Brown; Adam L. Boxer; Anna Karydas; Bruce Miller; Janice Robertson; Maria Carmela Tartaglia (Molecular Neurobiology, 2018)

Cratons, kimberlites and diamonds: selected papers of the 11th International Kimberlite Conference - Thomas Stachel; D. Graham Pearson; Andrea Giuliani; Casey M. Hetman; Jaroslav (Jarek) Jakubec; Philip E. Janney; Bruce A. Kjarsgaard; Alan F. Kobussen; Jingao Liu; Oded Navon; Roberta Rudnick; David B. Snyder; et al. (Mineralogy and Petrology, 2018)

Geochronology, classification and mantle source characteristics of kimberlites and related rocks from the Rae Craton, Melville Peninsula, Nunavut, Canada - Chiranjeeb Sarkar; Bruce A. Kjarsgaard; D. Graham Pearson; Larry M. Heaman; Andrew J. Locock; John P. Armstrong (Mineralogy and Petrology, 2018)

Probabilistic reasoning about measurements of equilibrium climate sensitivity: combining disparate lines of evidence - Roger M Cooke; Bruce Wielicki (Climatic Change, 2018)

Tundra Trait Team: A database of plant traits spanning the tundra biome - Anne D. Bjorkman; Isla H. Myers‐Smith; Sarah C. Elmendorf; Signe Normand; Haydn J. D. Thomas; Juha M. Alatalo; Heather Alexander; Alba Anadon‐Rosell; Sandra Angers‐Blondin; Yang Bai; Gaurav Baruah; Mariska te Beest; et al. (Global Ecology and Biogeography, 2018)
Motivation The Tundra Trait Team (TTT) database includes field‐based measurements of key traits related to plant form and function at multiple sites across the tundra biome. This dataset can be used to address theoretical questions about plant strategy and trade‐offs, trait–environment relationships and environmental filtering, and trait variation across spatial scales, to validate satellite data, and to inform Earth system model parameters. Main types of variable contained The database contains 91,970 measurements of 18 plant traits. The most frequently measured traits (> 1,000 observations each) include plant height, leaf area, specific leaf area, leaf fresh and dry mass, leaf dry matter content, leaf nitrogen, carbon and phosphorus content, leaf C:N and N:P, seed mass, and stem specific density. Spatial location and grain Measurements were collected in tundra habitats in both the Northern and Southern Hemispheres, including Arctic sites in Alaska, Canada, Greenland, Fennoscandia and Siberia, alpine sites in the European Alps, Colorado Rockies, Caucasus, Ural Mountains, Pyrenees, Australian Alps, and Central Otago Mountains (New Zealand), and sub‐Antarctic Marion Island. More than 99% of observations are georeferenced. Time period and grain All data were collected between 1964 and 2018. A small number of sites have repeated trait measurements at two or more time periods. Major taxa and level of measurement Trait measurements were made on 978 terrestrial vascular plant species growing in tundra habitats. Most observations are on individuals (86%), while the remainder represent plot or site means or maximums per species. Software format csv file and GitHub repository with data cleaning scripts in R; contribution to TRY plant trait database ( www.try-db.org ) to be included in the next version release.

Probability discounting of treatment decisions in multiple sclerosis: associations with disease knowledge, neuropsychiatric status, and adherence - Jared M. Bruce; Amanda S. Bruce; Sharon Lynch; Joanie Thelen; Seung-Lark Lim; Julia Smith; Delwyn Catley; Derek D. Reed; David P. Jarmolowicz (Psychopharmacology, 2018)

Spondyloarthropathy in vertebrae of the aquatic Cretaceous snake Lunaophis aquaticus, and its first recognition in modern snakes - Adriana María Albino; Bruce Rothschild; Jorge D. Carrillo-Briceño; James M. Neenan (The Science of Nature, 2018)

The inter-tester repeatability of a model for analysing elbow flexion-extension during overhead sporting movements - Denny J. M. Wells; Cyril J. Donnelly; Bruce C. Elliott; Kane J. Middleton; Jacqueline A. Alderson (Medical & Biological Engineering & Computing, 2018)

Feasibility of Providing Web-Based Information to Breast Cancer Patients Prior to a Surgical Consult - Jordan G. Bruce; Jennifer L. Tucholka; Nicole M. Steffens; Jane E. Mahoney; Heather B. Neuman (Journal of Cancer Education, 2018)

Production of membrane proteins for characterisation of their pheromone-sensing and antimicrobial resistance functions - Aalishaa A. Azam; Jean M. Kinder; G. Nasir Khan; Ade Alase; Pikyee Ma; Yang Liu; James R. Ault; Peter J. F. Henderson; Babur Z. Chowdhry; Bruce D. Alexander; Stephen E. Harding; Mary K. Phillips-Jones (European Biophysics Journal, 2018)

Temperature mediates the impact of non-native rainbow trout on native freshwater fishes in South Africa’s Cape Fold Ecoregion - Jeremy M. Shelton; Olaf L. F. Weyl; Karen J. Esler; Bruce R. Paxton; N. Dean Impson; Helen F. Dallas (Biological Invasions, 2018)

Publisher Correction to: Background invertebrate herbivory on dwarf birch (Betula glandulosa-nana complex) increases with temperature and precipitation across the tundra biome - Isabel C. Barrio; Elin Lindén; Mariska Te Beest; Johan Olofsson; Adrian Rocha; Eeva M. Soininen; Juha M. Alatalo; Tommi Andersson; Ashley Asmus; Julia Boike; Kari Anne Bråthen; John P. Bryant; et al. (Polar Biology, 2018)

Erratum to: Roads to interdisciplinarity – working at the nexus among food systems, nutrition and health - F. Picchioni; E. Aurino; L. Aleksandrowicz; M. Bruce; S. Chesterman; P. Dominguez-Salas; Z. Gersten; S. Kalamatianou; C. Turner; J. Yates (Food Security, 2018)

Comparison of base-line and chemical-induced transcriptomic responses in HepaRG and RPTEC/TERT1 cells using TempO-Seq - Alice Limonciel; Gamze Ates; Giada Carta; Anja Wilmes; Manfred Watzele; Peter J. Shepard; Harper C. VanSteenhouse; Bruce Seligmann; Joanne M. Yeakley; Bob van de Water; Mathieu Vinken; Paul Jennings (Archives of Toxicology, 2018)

Limited support for the “abundant centre” hypothesis in birds along a tropical elevational gradient: implications for the fate of lowland tropical species in a warmer future - Benjamin G. Freeman; Bruce M. Beehler (Journal of Biogeography, 2018)
Aim Since Darwin, ecologists have assumed that species tend to be abundant in the centre of their geographic distributions and rare at their range edges. We test two predictions of this abundant centre hypothesis: (a) that species are common in the centre of their range and rare at the edges and (b) that empirical distributions along environmental gradients are well described by symmetric bell‐shaped curves. Location A reef‐to‐ridgetop elevational gradient in the Yopno–Urawa–Som Conservation Area ( YUS CA ) on the Huon Peninsula in Papua New Guinea. Taxon Birds. Methods We use mist net capture rates to quantify species’ abundances as a function of range position, then fit a series of models with different shapes, including symmetric curves, to species’ empirical abundance distributions. Results Species peak abundances were located near species’ low elevation range edges, high elevation range edges and everywhere in between. Real abundance distributions were fit well by symmetric curves in fewer than half of the species we analysed. Most lowland species have high abundances at their low elevation margin near sea level. Main conclusions We find only limited support for the abundant centre hypothesis. Most lowland species appear to currently occupy a “truncated” realized niche, suggesting that they will be able to persist at low elevations even as temperatures increase and that lowland biotic attrition is unlikely. In addition to analyses, we present (a) a full species list for the 256 species recorded thus far within the YUS CA , with elevational limits for all forest species and (b) the raw data from our extensive mist net surveys. This information provides valuable baseline data that can be used by future biodiversity scientists to evaluate the changes in the YUS avifauna and will be generally useful to biodiversity scientists studying tropical elevational gradients.

The DRD2 Taq1A A1 Allele May Magnify the Risk of Alzheimer’s in Aging African-Americans - Kenneth Blum; Rajendra D. Badgaiyan; Georgia M. Dunston; David Baron; Edward J. Modestino; Thomas McLaughlin; Bruce Steinberg; Mark S. Gold; Marjorie C. Gondré-Lewis (Molecular Neurobiology, 2018)

Variability of sun‐induced chlorophyll fluorescence according to stand age‐related processes in a managed loblolly pine forest - Roberto Colombo; Marco Celesti; Remo Bianchi; Petya K. E. Campbell; Sergio Cogliati; Bruce D. Cook; Lawrence A. Corp; Alexander Damm; Jean‐Christophe Domec; Luis Guanter; Tommaso Julitta; Elizabeth M. Middleton; et al. (Global Change Biology, 2018)
Leaf fluorescence can be used to track plant development and stress, and is considered the most direct measurement of photosynthetic activity available from remote sensing techniques. Red and far‐red sun‐induced chlorophyll fluorescence ( SIF ) maps were generated from high spatial resolution images collected with the HyPlant airborne spectrometer over even‐aged loblolly pine plantations in North Carolina (United States). Canopy fluorescence yield (i.e., the fluorescence flux normalized by the light absorbed) in the red and far‐red peaks was computed. This quantifies the fluorescence emission efficiencies that are more directly linked to canopy function compared to SIF radiances. Fluorescence fluxes and yields were investigated in relation to tree age to infer new insights on the potential of those measurements in better describing ecosystem processes. The results showed that red fluorescence yield varies with stand age. Young stands exhibited a nearly twofold higher red fluorescence yield than mature forest plantations, while the far‐red fluorescence yield remained constant. We interpreted this finding in a context of photosynthetic stomatal limitation in aging loblolly pine stands. Current and future satellite missions provide global datasets of SIF at coarse spatial resolution, resulting in intrapixel mixture effects, which could be a confounding factor for fluorescence signal interpretation. To mitigate this effect, we propose a surrogate of the fluorescence yield, namely the Canopy Cover Fluorescence Index ( CCFI ) that accounts for the spatial variability in canopy structure by exploiting the vegetation fractional cover. It was found that spatial aggregation tended to mask the effective relationships, while the CCFI was still able to maintain this link. This study is a first attempt in interpreting the fluorescence variability in aging forest stands and it may open new perspectives in understanding long‐term forest dynamics in response to future climatic conditions from remote sensing of SIF .

Experimental Detritus Manipulations Unite Surface and Cave Stream Ecosystems Along a Common Energy Gradient - Michael P. Venarsky; Jonathan P. Benstead; Alexander D. Huryn; Brock M. Huntsman; Jennifer W. Edmonds; Robert H. Findlay; J. Bruce Wallace (Ecosystems, 2018)

Therapeutic Applications for Adipose-Derived Stem Cells in Wound Healing and Tissue Engineering - Michelle E. McCarthy; Theodore A. Brown; Joanna Bukowska; Bruce A. Bunnell; Trivia Frazier; Xiying Wu; Jeffrey M. Gimble (Current Stem Cell Reports, 2018)

Petrology, geochemistry and a probable late Cambrian age for harzburgites of the Coolac Serpentinite, New South Wales, Australia - M. C. Bruce (Australian Journal of Earth Sciences, 2018)

Frontiers in alley cropping: Transformative solutions for temperate agriculture - Kevin J. Wolz; Sarah T. Lovell; Bruce E. Branham; William C. Eddy; Keefe Keeley; Ronald S. Revord; Michelle M. Wander; Wendy H. Yang; Evan H. DeLucia (Global Change Biology, 2018)
Annual row crops dominate agriculture around the world and have considerable negative environmental impacts, including significant greenhouse gas emissions. Transformative land‐use solutions are necessary to mitigate climate change and restore critical ecosystem services. Alley cropping ( AC )—the integration of trees with crops—is an agroforestry practice that has been studied as a transformative, multifunctional land‐use solution. In the temperate zone, AC has strong potential for climate change mitigation through direct emissions reductions and increases in land‐use efficiency via overyielding compared to trees and crops grown separately. In addition, AC provides climate change adaptation potential and ecological benefits by buffering alley crops to weather extremes, diversifying income to hedge financial risk, increasing biodiversity, reducing soil erosion, and improving nutrient‐ and water‐use efficiency. The scope of temperate AC research and application has been largely limited to simple systems that combine one timber tree species with an annual grain. We propose two frontiers in temperate AC that expand this scope and could transform its climate‐related benefits: (i) diversification via woody polyculture and (ii) expanded use of tree crops for food and fodder. While AC is ready now for implementation on marginal lands, we discuss key considerations that could enhance the scalability of the two proposed frontiers and catalyze widespread adoption.

Recreational sea fishing in Europe in a global context—Participation rates, fishing effort, expenditure, and implications for monitoring and assessment - Kieran Hyder; Marc Simon Weltersbach; Mike Armstrong; Keno Ferter; Bryony Townhill; Anssi Ahvonen; Robert Arlinghaus; Andrei Baikov; Manuel Bellanger; Janis Birzaks; Trude Borch; Giulia Cambie; et al. (Fish and Fisheries, 2018)
Marine recreational fishing ( MRF ) is a high‐participation activity with large economic value and social benefits globally, and it impacts on some fish stocks. Although reporting MRF catches is a European Union legislative requirement, estimates are only available for some countries. Here, data on numbers of fishers, participation rates, days fished, expenditures, and catches of two widely targeted species were synthesized to provide European estimates of MRF and placed in the global context. Uncertainty assessment was not possible due to incomplete knowledge of error distributions; instead, a semi‐quantitative bias assessment was made. There were an estimated 8.7 million European recreational sea fishers corresponding to a participation rate of 1.6%. An estimated 77.6 million days were fished, and expenditure was €5.9 billion annually. There were higher participation, numbers of fishers, days fished and expenditure in the Atlantic than the Mediterranean, but the Mediterranean estimates were generally less robust. Comparisons with other regions showed that European MRF participation rates and expenditure were in the mid‐range, with higher participation in Oceania and the United States, higher expenditure in the United States, and lower participation and expenditure in South America and Africa. For both northern European sea bass ( Dicentrarchus labrax , Moronidae) and western Baltic cod ( Gadus morhua , Gadidae) stocks, MRF represented 27% of the total removals. This study highlights the importance of MRF and the need for bespoke, regular and statistically sound data collection to underpin European fisheries management. Solutions are proposed for future MRF data collection in Europe and other regions to support sustainable fisheries management.

Taxonomic patterns in the nitrogen assimilation of soil prokaryotes - Ember M. Morrissey; Rebecca L. Mau; Egbert Schwartz; Benjamin J. Koch; Michaela Hayer; Bruce A. Hungate (Environmental Microbiology, 2018)
Summary Nitrogen (N) is frequently a limiting nutrient in soil; its availability can govern ecosystem functions such as primary production and decomposition. Assimilation of N by microorganisms impacts the availability of N in soil. Despite its established ecological significance, the contributions of microbial taxa to N assimilation are unknown. Here we measure N uptake and use by microbial phylotypes and taxonomic groups within a diverse assemblage of soil microbes through quantitative stable isotope probing (qSIP) with 15 N. Following incubation with 15 , distinct patterns of 15 N assimilation among taxonomic groups were observed. For instance, glucose addition stimulated 15 N assimilation in most members of Actinobacteria and Proteobacteria but generally decreased 15 N use by Firmicutes and Bacteriodetes. While is considered a preferred and universal source of N to prokaryotes, the majority (> 80%) of N assimilation in our soils could be attributed to a handful of active orders. Characterizing N assimilation of taxonomic groups with 15 N qSIP may provide a basis for understanding how microbial community composition influences N availability in the environment.

Effects of plant species on stream bacterial communities via leachate from leaf litter - Adam S. Wymore; Elena Salpas; Giorgio Casaburi; Cindy M. Liu; Lance B. Price; Bruce A. Hungate; William H. McDowell; Jane C. Marks (Hydrobiologia, 2018)

Feminization of Male Brown Treesnake Methyl Ketone Expression via Steroid Hormone Manipulation - M. Rockwell Parker; Saumya M. Patel; Jennifer E. Zachry; Bruce A. Kimball (Journal of Chemical Ecology, 2018)

Estimating carbon and showing impacts of drought using satellite data in regression-tree models - Stephen P. Boyte; Bruce K. Wylie; Daniel M. Howard; Devendra Dahal; Tagir Gilmanov (International Journal of Remote Sensing, 2018)

Assessment of wound healing of tagged gray ( Eschrichtius robustus ) and blue ( Balaenoptera musculus ) whales in the eastern North Pacific using long‐term series of photographs - Stephanie A. Norman; Kiirsten R. Flynn; Alexandre N. Zerbini; Frances M. D. Gulland; Michael J. Moore; Stephen Raverty; David S. Rotstein; Bruce R. Mate; Craig Hayslip; Diane Gendron; Richard Sears; Annie B. Douglas; et al. (Marine Mammal Science, 2018)
Tags have been used to examine migration routes and habitat use of large whales for >40 yr, however, evaluation of tag wound healing has largely been short‐term, anecdotal or generalized. This study developed methods for systematic photographic assessment of long‐term external consequences of tag placement, to determine potential differences in wound healing between species and tag types and thus advise future tagging efforts to possibly minimize undesirable side effects. Tag site appearance and healing characteristics were evaluated by two reviewers and a time series evaluated by five veterinarians from photographs during 995 postdeployment encounters with 34 gray and 63 blue whales tagged in the North Pacific. Blue whale resightings were less frequent, but spanned a longer time period due to earlier tag deployments than the more frequent gray whale follow‐up observations. Swelling occurred in 74% of reencountered gray whales, with the highest frequency 6 mo postdeployment. Swellings were common in blue whales with early tag designs but rare with current models. Depressions occurred in 82% of gray and 71% of blue whales. This study demonstrates the value of follow‐up studies of tagged animals and systematic scoring of photographs to quantitatively compare tag response.

Integrated ecological–economic fisheries models—Evaluation, review and challenges for implementation - J Rasmus Nielsen; Eric Thunberg; Daniel S Holland; Jorn O Schmidt; Elizabeth A Fulton; Francois Bastardie; Andre E Punt; Icarus Allen; Heleen Bartelings; Michel Bertignac; Eckhard Bethke; Sieme Bossier; et al. (Fish and Fisheries, 2018)
Marine ecosystems evolve under many interconnected and area‐specific pressures. To fulfil society's intensifying and diversifying needs while ensuring ecologically sustainable development, more effective marine spatial planning and broader‐scope management of marine resources is necessary. Integrated ecological–economic fisheries models ( IEEFM s) of marine systems are needed to evaluate impacts and sustainability of potential management actions and understand, and anticipate ecological, economic and social dynamics at a range of scales from local to national and regional. To make these models most effective, it is important to determine how model characteristics and methods of communicating results influence the model implementation, the nature of the advice that can be provided and the impact on decisions taken by managers. This article presents a global review and comparative evaluation of 35 IEEFM s applied to marine fisheries and marine ecosystem resources to identify the characteristics that determine their usefulness, effectiveness and implementation. The focus is on fully integrated models that allow for feedbacks between ecological and human processes although not all the models reviewed achieve that. Modellers must invest more time to make models user friendly and to participate in management fora where models and model results can be explained and discussed. Such involvement is beneficial to all parties, leading to improvement of mo‐dels and more effective implementation of advice, but demands substantial resources which must be built into the governance process. It takes time to develop effective processes for using IEEFM s requiring a long‐term commitment to integrating multidisciplinary modelling advice into management decision‐making.

Defining ecologically relevant scales for spatial protection with long‐term data on an endangered seabird and local prey availability - Richard B. Sherley; Philna Botha; Les G. Underhill; Peter G. Ryan; Danie van Zyl; Andrew C. Cockcroft; Robert J.M. Crawford; Bruce M. Dyer; Timothée R. Cook (Conservation Biology, 2017)
Human activities are important drivers of marine ecosystem functioning. However, separating the synergistic effects of fishing and environmental variability on the prey base of nontarget predators is difficult, often because prey availability estimates on appropriate scales are lacking. Understanding how prey abundance at different spatial scales links to population change can help integrate the needs of nontarget predators into fisheries management by defining ecologically relevant areas for spatial protection. We investigated the local population response (number of breeders) of the Bank Cormorant ( Phalacrocorax neglectus ), a range‐restricted endangered seabird, to the availability of its prey, the heavily fished west coast rock lobster ( Jasus lalandii ). Using Bayesian state‐space modeled cormorant counts at 3 colonies, 22 years of fisheries‐independent data on local lobster abundance, and generalized additive modeling, we determined the spatial scale pertinent to these relationships in areas with different lobster availability. Cormorant numbers responded positively to lobster availability in the regions with intermediate and high abundance but not where regime shifts and fishing pressure had depleted lobster stocks. The relationships were strongest when lobsters 20–30 km offshore of the colony were considered, a distance greater than the Bank Cormorant's foraging range when breeding, and may have been influenced by prey availability for nonbreeding birds, prey switching, or prey ecology. Our results highlight the importance of considering the scale of ecological relationships in marine spatial planning and suggest that designing spatial protection around focal species can benefit marine predators across their full life cycle. We propose the precautionary implementation of small‐scale marine protected areas, followed by robust assessment and adaptive‐management, to confirm population‐level benefits for the cormorants, their prey, and the wider ecosystem, without negative impacts on local fisheries.

Assessing the Functional Limitations of Lipids and Fatty Acids for Diet Determination: The Importance of Tissue Type, Quantity, and Quality - Lauren Meyer; Heidi Pethybridge; Peter D. Nichols; Crystal Beckmann; Barry D. Bruce; Jonathan M. Werry; Charlie Huveneers (Frontiers in Marine Science, 2017)

Background invertebrate herbivory on dwarf birch (Betula glandulosa-nana complex) increases with temperature and precipitation across the tundra biome - Isabel C. Barrio; Elin Lindén; Mariska Te Beest; Johan Olofsson; Adrian Rocha; Eeva M. Soininen; Juha M. Alatalo; Tommi Andersson; Ashley Asmus; Julia Boike; Kari Anne Bråthen; John P. Bryant; et al. (Polar Biology, 2017)

Inundation, Vegetation, and Sediment Effects on Litter Decomposition in Pacific Coast Tidal Marshes - Christopher N. Janousek; Kevin J. Buffington; Glenn R. Guntenspergen; Karen M. Thorne; Bruce D. Dugger; John Y. Takekawa (Ecosystems, 2017)

The ecology and management of mammal invasions in forests - A. David M. Latham; Bruce Warburton; Andrea E. Byrom; Roger P. Pech (Biological Invasions, 2017)

Regional and seasonal variability in planktonic photosynthesis and planktonic community respiration in Amazon floodplain lakes - Bruce R. Forsberg; John M. Melack; Jeffrey E. Richey; Tania P. Pimentel (Hydrobiologia, 2017)

Plumage aberrations in Macaroni Penguins Eudyptes chrysolophus at sub-Antarctic Marion Island - Tegan Carpenter-Kling; Bruce M. Dyer; Azwainewi B. Makhado; Pierre A. Pistorius (Polar Biology, 2017)

The signature of human pressure history on the biogeography of body mass in tetrapods - Giovanni Rapacciuolo; Julie Marin; Gabriel C. Costa; Matthew R. Helmus; Jocelyn E. Behm; Thomas M. Brooks; S. Blair Hedges; Volker C. Radeloff; Bruce E. Young; Catherine H. Graham (Global Ecology and Biogeography, 2017)
Aim Examining the biogeography of body size is crucial for understanding how animal communities are assembled and maintained. In tetrapods, body size varies predictably with temperature, moisture, productivity seasonality and topographical complexity. Although millennial‐scale human pressures are known to have led to the extinction of primarily large‐bodied tetrapods, human pressure history is often ignored in studies of body size that focus on extant species. Here, we analyse 11,377 tetrapod species of the Western Hemisphere to test whether millennial‐scale human pressures have left an imprint on contemporary body mass distributions throughout the tetrapod clade. Location Western Hemisphere. Time period Contemporary. Major taxa studied Tetrapods (birds, mammals, amphibians and reptiles). Methods We mapped the distribution of assemblage‐level median tetrapod body mass at a resolution of 110 km across the Western Hemisphere. We then generated multivariate models of median body mass as a function of temperature, moisture, productivity seasonality and topographical complexity, as well as two variables capturing the history of human population density and human‐induced land conversion over the past 12,000 years. We controlled for both spatial and phylogenetic autocorrelation effects on body mass–environment relationships. Results Human pressures explain a small but significant portion of geographical variation in median body mass that cannot be explained by ecological constraints alone. Overall, the median body mass of tetrapod assemblages is lower than expected in areas with a longer history of high human population density and land conversion, but there are important differences among tetrapod classes. Main conclusions At this broad scale, the effect of human pressure history on tetrapod body mass is low relative to that of ecology. However, ignoring spatial variation in the history of human pressure is likely to lead to bias in studies of the present‐day functional composition of tetrapod assemblages, at least in areas that have long been influenced by humans.

Are fluvial islands “real” islands for arboreal mammals? Uncovering the effect of patch size under the species–area relationship - Rafael M. Rabelo; Júlio César Bicca‐Marques; Susan Aragón; Bruce Walker Nelson (Journal of Biogeography, 2017)
Aim We tested the “habitat amount hypothesis”, which predicts that the effect of patch size on number of species results from a “sample area effect” rather than an “island effect”. Specifically, we (1) compared parameters of the species–area relationship ( SAR ) of arboreal mammals in forested fluvial islands and continuous forest, and (2) separated the effects of island size and of landscape‐scale habitat amount on species richness. Location Middle‐Solimões River region, Central Amazon. Methods We surveyed arboreal mammals along line‐transects on 15 fluvial floodplain islands and nine transects in continuous floodplain forest. Transect length varied according to island size. Transects of similar length were established in continuous forest. We used power transformed (log‐log) models to construct a SAR for the set of island transects and another SAR for the set of continuous forest transects. We compared slope and intercept between the two SAR s using ANCOVA . We used multiple regressions to separate the effects of island size and of habitat amount on the rarefied number of species across multiple spatial scales (500–6,000 m). Results The two species–area curves showed similar slopes, but the intercept was lower for islands. Multiple regressions showed the best fit at the 5,500 m spatial scale. At this scale, habitat amount predicted species richness, whereas island size did not. Main conclusions We conclude that the apparent effect of patch size on the number of species may be simply due to the sample area effect and that no island effect operates on this patchy system. Accordingly, island size per se does not increase the number of species at a sample site. Fluvial islands should not be treated as “real” islands from the island biogeography perspective. In sum, we found support for the habitat amount hypothesis for predicting the richness of arboreal mammals on fluvial islands.

Microtubule-Targeting Agents Eribulin and Paclitaxel Differentially Affect Neuronal Cell Bodies in Chemotherapy-Induced Peripheral Neuropathy - Sarah J. Benbow; Krystyna M. Wozniak; Bridget Kulesh; April Savage; Barbara S. Slusher; Bruce A. Littlefield; Mary Ann Jordan; Leslie Wilson; Stuart C. Feinstein (Neurotoxicity Research, 2017)

Evaluation of synthetic oviposition stimulants to enhance egg collection of the oriental fruit fly, Bactrocera dorsalis (Diptera: Tephritidae) - P. D. Kamala Jayanthi; Vivek Kempraj; Ravindra M. Aurade; Toby J. A. Bruce (Journal of Pest Science, 2017)

Stiffness of Protease Sensitive and Cell Adhesive PEG Hydrogels Promotes Neovascularization In Vivo - Ryan M. Schweller; Zi Jun Wu; Bruce Klitzman; Jennifer L. West (Annals of Biomedical Engineering, 2017)

Genetic Variants of Microtubule Actin Cross-linking Factor 1 (MACF1) Confer Risk for Parkinson’s Disease - Xin Wang; Nuomin Li; Nian Xiong; Qi You; Jie Li; Jinlong Yu; Hong Qing; Tao Wang; Heather J. Cordell; Ole Isacson; Jeffery M. Vance; Eden R. Martin; et al. (Molecular Neurobiology, 2017)

Measuring the effectiveness of landscape approaches to conservation and development - Jeffrey A. Sayer; Chris Margules; Agni K. Boedhihartono; Terry Sunderland; James D. Langston; James Reed; Rebecca Riggs; Louise E. Buck; Bruce M. Campbell; Koen Kusters; Chris Elliott; Peter A. Minang; et al. (Sustainability Science, 2017)

Unusual intraosseous fossilized soft tissues from the Middle Triassic Nothosaurus bone - Dawid Surmik; Bruce M. Rothschild; Roman Pawlicki (The Science of Nature, 2017)

Quantifying food web interactions in the North Pacific – a data-based approach - Patricia A. Livingston; Kerim Aydin; Troy W. Buckley; Geoffrey M. Lang; Mei-Sun Yang; Bruce S. Miller (Environmental Biology of Fishes, 2017)

Demographic Drivers of Aboveground Biomass Dynamics During Secondary Succession in Neotropical Dry and Wet Forests - Danaë M. A. Rozendaal; Robin L. Chazdon; Felipe Arreola-Villa; Patricia Balvanera; Tony V. Bentos; Juan M. Dupuy; J. Luis Hernández-Stefanoni; Catarina C. Jakovac; Edwin E. Lebrija-Trejos; Madelon Lohbeck; Miguel Martínez-Ramos; Paulo E. S. Massoca; et al. (Ecosystems, 2017)

Vascular Coupling System for End-to-End Anastomosis: An In Vivo Pilot Case Report - Huizhong Li; Bruce Gale; Jill Shea; Himanshu Sant; Christi M. Terry; Jay Agarwal (Cardiovascular Engineering and Technology, 2017)

Exposure to a diet high in fat attenuates dendritic spine density in the medial prefrontal cortex - Paige M. Dingess; Rebecca A. Darling; E. Kurt Dolence; Bruce W. Culver; Travis E. Brown (Brain Structure and Function, 2017)

Roads to interdisciplinarity – working at the nexus among food systems, nutrition and health - F. Picchioni; E. Aurino; L. Aleksandrowicz; M. Bruce; S. Chesterman; P. Dominguez-Salas; Z. Gersten; S. Kalamatianou; C. Turner; J. Yates (Food Security, 2017)

HPLC-MS Analysis of Lichen-Derived Metabolites in the Life Stages of Crambidia cephalica (Grote & Robinson) - Timothy J. Anderson; David L. Wagner; Bruce R. Cooper; Megan E. McCarty; Jennifer M. Zaspel (Journal of Chemical Ecology, 2017)

Electrophysiological and behavioral responses of female African rice gall midge, Orseolia oryzivora Harris and Gagné, to host plant volatiles - Emmanuel O. Ogah; Lesley E. Smart; Christine M. Woodcock; John C. Caulfield; Michael A. Birkett; John A. Pickett; Francis E. Nwilene; Toby J. Bruce (Journal of Chemical Ecology, 2017)

Long‐term declines in an intertidal foundation species parallel shifts in community composition - Cascade J. B. Sorte; Victoria E. Davidson; Marcus C. Franklin; Kylla M. Benes; Meredith M. Doellman; Ron J. Etter; Robyn E. Hannigan; Jane Lubchenco; Bruce A. Menge (Global Change Biology, 2017)
The earth is in the midst of a biodiversity crisis, and projections indicate continuing and accelerating rates of global changes. Future alterations in communities and ecosystems may be precipitated by changes in the abundance of strongly interacting species, whose disappearance can lead to profound changes in abundance of other species, including an increase in extinction rate for some. Nearshore coastal communities are often dependent on the habitat and food resources provided by foundational plant (e.g., kelp) and animal (e.g., shellfish) species. We quantified changes in the abundance of the blue mussel ( M ytilus edulis ), a foundation species known to influence diversity and productivity of intertidal habitats, over the past 40 years in the Gulf of Maine, USA , one of the fastest warming regions in the global ocean. Using consistent survey methods, we compared contemporary population sizes to historical data from sites spanning >400 km. The results of these comparisons showed that blue mussels have declined in the Gulf of Maine by >60% (range: 29–100%) at the site level since the earliest benchmarks in the 1970s. At the same time as mussels declined, community composition shifted: at the four sites with historical community data, the sessile community became increasingly algal dominated. Contemporary (2013–2014) surveys across 20 sites showed that sessile species richness was positively correlated to mussel abundance in mid to high intertidal zones. These results suggest that declines in a critical foundation species may have already impacted the intertidal community. To inform future conservation efforts, we provide a database of historical and contemporary baselines of mussel population abundance and dynamics in the Gulf of Maine. Our results underscore the importance of anticipating not only changes in diversity but also changes in the abundance and identity of component species, as strong interactors like foundation species have the potential to drive cascading community shifts.

Managing the nitrogen cycle to reduce greenhouse gas emissions from crop production and biofuel expansion - Stephen M. Ogle; Bruce A. McCarl; Justin Baker; Stephen J. Del Grosso; Paul R. Adler; Keith Paustian; William J. Parton (Mitigation and Adaptation Strategies for Global Change, 2016)

Reducing emissions from agriculture to meet the 2 °C target - Eva Wollenberg; Meryl Richards; Pete Smith; Petr Havlík; Michael Obersteiner; Francesco N. Tubiello; Martin Herold; Pierre Gerber; Sarah Carter; Andrew Reisinger; Detlef P. van Vuuren; Amy Dickie; et al. (Global Change Biology, 2016)
More than 100 countries pledged to reduce agricultural greenhouse gas ( GHG ) emissions in the 2015 Paris Agreement of the United Nations Framework Convention on Climate Change. Yet technical information about how much mitigation is needed in the sector vs. how much is feasible remains poor. We identify a preliminary global target for reducing emissions from agriculture of ~1 Gt CO 2 e yr −1 by 2030 to limit warming in 2100 to 2 °C above pre‐industrial levels. Yet plausible agricultural development pathways with mitigation cobenefits deliver only 21–40% of needed mitigation. The target indicates that more transformative technical and policy options will be needed, such as methane inhibitors and finance for new practices. A more comprehensive target for the 2 °C limit should be developed to include soil carbon and agriculture‐related mitigation options. Excluding agricultural emissions from mitigation targets and plans will increase the cost of mitigation in other sectors or reduce the feasibility of meeting the 2 °C limit.

Associations between the pink wormfish, Microdesmus longipinnis (Weymouth), and the ghost shrimp, Lepidophthalmus louisianensis (Schmitt), in artificial burrows - Andrew M. Savage; Bruce E. Felgenhauer (Environmental Biology of Fishes, 2016)

Diffusive methane fluxes from Negro, Solimões and Madeira rivers and fringing lakes in the Amazon basin - Pedro M. Barbosa; John M. Melack; Vinicius F. Farjalla; João Henrique F. Amaral; Vinicius Scofield; Bruce R. Forsberg (Limnology and Oceanography, 2016)
The first extensive set of measurements of methane concentrations and fluxes for the Negro River and its major tributaries combined with complementary data for the Solimões and Madeira rivers and several tributaries are presented and their temporal and spatial variations examined. Fluxes were measured using floating chambers, and dissolved CH 4 concentrations were measured by the headspace technique. In the Solimões basin, tributaries had higher fluxes when water levels were low; no statistical difference among periods for lakes and the main stem river was observed. In the Negro basin, rivers had higher fluxes with greater variations among rivers during high water than during low water based on fluxes calculated from the concentration gradient and modelled gas transfer coefficients. We estimate a regional methane emission of 0.31 Tg C yr −1 for large river channels in the lowland Amazon basin.

Walking through the statistical black boxes of plant breeding - Alencar Xavier; William M. Muir; Bruce Craig; Katy Martin Rainey (Theoretical and Applied Genetics, 2016)

Magma decompression rates during explosive eruptions of Kīlauea volcano, Hawaii, recorded by melt embayments - David J. Ferguson; Helge M. Gonnermann; Philipp Ruprecht; Terry Plank; Erik H. Hauri; Bruce F. Houghton; Donald A. Swanson (Bulletin of Volcanology, 2016)

First histological examination of a neoplastic lesion from a free‐swimming white shark, Carcharodon carcharias L. - C Huveneers; S Klebe; A Fox; B Bruce; R Robbins; J D Borucinska; R Jones; M Z Michael (Journal of Fish Diseases, 2016)

Prioritization of knowledge‐needs to achieve best practices for bottom trawling in relation to seabed habitats - Michel J Kaiser; Ray Hilborn; Simon Jennings; Ricky Amaroso; Michael Andersen; Kris Balliet; Eric Barratt; Odd A Bergstad; Stephen Bishop; Jodi L Bostrom; Catherine Boyd; Eduardo A Bruce; et al. (Fish and Fisheries, 2016)
Management and technical approaches that achieve a sustainable level of fish production while at the same time minimizing or limiting the wider ecological effects caused through fishing gear contact with the seabed might be considered to be ‘best practice’. To identify future knowledge‐needs that would help to support a transition towards the adoption of best practices for trawling, a prioritization exercise was undertaken with a group of 39 practitioners from the seafood industry and management, and 13 research scientists who have an active research interest in bottom‐trawl and dredge fisheries. A list of 108 knowledge‐needs related to trawl and dredge fisheries was developed in conjunction with an ‘expert task force’. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge‐need. The top 25 knowledge‐needs are presented, as scored separately by practitioners and scientists. There was considerable consistency in the priorities identified by these two groups. The top priority knowledge‐need to improve current understanding on the distribution and extent of different habitat types also reinforced the concomitant need for the provision and access to data on the spatial and temporal distribution of all forms of towed bottom‐fishing activities. Many of the other top 25 knowledge‐needs concerned the evaluation of different management approaches or implementation of different fishing practices, particularly those that explore trade‐offs between effects of bottom trawling on biodiversity and ecosystem services and the benefits of fish production as food.

The invasive annual cheatgrass releases more nitrogen than crested wheatgrass through root exudation and senescence - Kendalynn A. Morris; John M. Stark; Bruce Bugbee; Jeanette M. Norton (Oecologia, 2016)

Recurrence of progressive multifocal leukoencephalopathy despite immune recovery in two HIV seropositive individuals - Kate M. Crossley; Shruti Agnihotri; Joga Chaganti; Michael L. Rodriguez; Leon Patrick McNally; Nagagopal Venna; Sarah E. Turbett; Matthew Gutman; Adrienne Morey; Igor J. Koralnik; Bruce J. Brew (Journal of NeuroVirology, 2016)

Human‐mediated extirpation of the unique Chatham Islands sea lion and implications for the conservation management of remaining New Zealand sea lion populations - Nicolas J. Rawlence; Catherine J. Collins; Christian N. K. Anderson; Justin J. Maxwell; Ian W. G. Smith; Bruce C. Robertson; Michael Knapp; Katherine Ann Horsburgh; Jo‐Ann L. Stanton; R. Paul Scofield; Alan J. D. Tennyson; Elizabeth A. Matisoo‐Smith; et al. (Molecular Ecology, 2016)
While terrestrial megafaunal extinctions have been well characterized worldwide, our understanding of declines in marine megafauna remains limited. Here, we use ancient DNA analyses of prehistoric ( AD ) sea lion specimens from New Zealand's isolated Chatham Islands to assess the demographic impacts of human settlement. These data suggest there was a large population of sea lions, unique to the Chatham Islands, at the time of Polynesian settlement. This distinct mitochondrial lineage became rapidly extinct within 200 years due to overhunting, paralleling the extirpation of a similarly large endemic mainland population. Whole mitogenomic analyses confirm substantial intraspecific diversity among prehistoric lineages. Demographic models suggest that even low harvest rates would likely have driven rapid extinction of these lineages. This study indicates that surviving Phocarctos populations are remnants of a once diverse and widespread sea lion assemblage, highlighting dramatic human impacts on endemic marine biodiversity. Our findings also suggest that Phocarctos bycatch in commercial fisheries may contribute to the ongoing population decline.

On the Differentiation of Foveal and Peripheral Early Visual Evoked Potentials - Bruce C. Hansen; Andrew M. Haun; Aaron P. Johnson; Dave Ellemberg (Brain Topography, 2016)

Interacting environmental mosaics drive geographic variation in mussel performance and predation vulnerability - Kristy J. Kroeker; Eric Sanford; Jeremy M. Rose; Carol A. Blanchette; Francis Chan; Francisco P. Chavez; Brian Gaylord; Brian Helmuth; Tessa M. Hill; Gretchen E. Hofmann; Margaret A. McManus; Bruce A. Menge; et al. (Ecology Letters, 2016)
Although theory suggests geographic variation in species' performance is determined by multiple niche parameters, little consideration has been given to the spatial structure of interacting stressors that may shape local and regional vulnerability to global change. Here, we use spatially explicit mosaics of carbonate chemistry, food availability and temperature spanning 1280 km of coastline to test whether persistent, overlapping environmental mosaics mediate the growth and predation vulnerability of a critical foundation species, the mussel Mytilus californianus . We find growth was highest and predation vulnerability was lowest in dynamic environments with frequent exposure to low pH seawater and consistent food. In contrast, growth was lowest and predation vulnerability highest when exposure to low pH seawater was decoupled from high food availability, or in exceptionally warm locations. These results illustrate how interactions among multiple drivers can cause unexpected, yet persistent geographic mosaics of species performance, interactions and vulnerability to environmental change.

The natural expression of individual differences in self-reported level of response to alcohol during ecologically assessed drinking episodes - Constantine J. Trela; Thomas M. Piasecki; Bruce D. Bartholow; Andrew C. Heath; Kenneth J. Sher (Psychopharmacology, 2016)

Liposome size and charge optimization for intraarterial delivery to gliomas - Shailendra Joshi; Johann R. N. Cooke; Darren K. W. Chan; Jason A. Ellis; Shaolie S. Hossain; Rajinder P. Singh-Moon; Mei Wang; Irving J. Bigio; Jeffrey N. Bruce; Robert M. Straubinger (Drug Delivery and Translational Research, 2016)

Projections of climate change effects on discharge and inundation in the Amazon basin - Mino Viana Sorribas; Rodrigo C. D. Paiva; John M. Melack; Juan Martin Bravo; Charles Jones; Leila Carvalho; Edward Beighley; Bruce Forsberg; Marcos Heil Costa (Climatic Change, 2016)

The Economic Impact for Farm Injury in Minnesota, 2004–2010 - Adrienne M. K. Landsteiner; Patricia M. McGovern; John A. Nyman; Bruce H. Alexander; Paula G. Lindgren; Allan N. Williams (Journal of Agromedicine, 2016)

Life cycle assessment capacity roadmap (section 1): decision-making support using LCA - Lise Laurin; Ben Amor; Till M. Bachmann; Jane Bare; Christoph Koffler; Serge Genest; Philipp Preiss; Jason Pierce; Barclay Satterfield; Bruce Vigon (The International Journal of Life Cycle Assessment, 2016)

Separate and joint effects of alcohol and caffeine on conflict monitoring and adaptation - Kira Bailey; Michael T. Amlung; David H. Morris; Mason H. Price; Curtis Von Gunten; Denis M. McCarthy; Bruce D. Bartholow (Psychopharmacology, 2016)

Population genomics of the filarial nematode parasite Wuchereria bancrofti from mosquitoes - Scott T. Small; Lisa J. Reimer; Daniel J. Tisch; Christopher L. King; Bruce M. Christensen; Peter M. Siba; James W. Kazura; David Serre; Peter A. Zimmerman (Molecular Ecology, 2016)
Wuchereria bancrofti is a parasitic nematode and the primary cause of lymphatic filariasis – a disease specific to humans. W. bancrofti currently infects over 90 million people throughout the tropics and has been acknowledged by the world health organization as a vulnerable parasite. Current research has focused primarily on the clinical manifestations of disease and little is known about the evolutionary history of W. bancrofti . To improve upon knowledge of the evolutionary history of W. bancrofti , we whole genome sequenced 13 W. bancrofti larvae. We circumvent many of the difficulties of multiple infections by sampling larvae directly from mosquitoes that were experimentally inoculated with infected blood. To begin, we used whole genome data to reconstruct the historical population size. Our results support a history of fluctuating population sizes that can be correlated with human migration and fluctuating mosquito abundances. Next, we reconstructed the putative pedigree of W. bancrofti worms within an infection using the kinship coefficient. We deduced that there are full‐sib and half‐sib relationships residing within the same larval cohort. Through combined analysis of the mitochondrial and nuclear genomes we concluded that this is likely a results of polyandrous mating, the first time reported for W. bancrofti . Lastly, we scanned the genomes for signatures of natural selection. Annotation of putative selected regions identified proteins that may have aided in a parasitic life style or may have evolved to protect against current drug treatments. We discuss our results in the greater context of understanding the biology of an animal with a unique life history and ecology.

Puberty and testosterone shape the corticospinal tract during male adolescence - Melissa M. Pangelinan; Gabriel Leonard; Michel Perron; G. Bruce Pike; Louis Richer; Suzanne Veillette; Zdenka Pausova; Tomáš Paus (Brain Structure and Function, 2016)

Adaptation of the ToxRTool to Assess the Reliability of Toxicology Studies Conducted with Genetically Modified Crops and Implications for Future Safety Testing - Michael S. Koch; John M. DeSesso; Amy Lavin Williams; Suzanne Michalek; Bruce Hammond (Critical Reviews in Food Science and Nutrition, 2016)

Estimating Symbiont Abundances and Gill Surface Areas in Specimens of the Hydrothermal Vent Mussel Bathymodiolus puteoserpentis Maintained in Pressure Vessels - Sébastien Duperron; Adrien Quiles; Kamil M. Szafranski; Nelly Léger; Bruce Shillito (Frontiers in Marine Science, 2016)

Effects of Paclitaxel and Eribulin in Mouse Sciatic Nerve: A Microtubule-Based Rationale for the Differential Induction of Chemotherapy-Induced Peripheral Neuropathy - Sarah J. Benbow; Brett M. Cook; Jack Reifert; Krystyna M. Wozniak; Barbara S. Slusher; Bruce A. Littlefield; Leslie Wilson; Mary Ann Jordan; Stuart C. Feinstein (Neurotoxicity Research, 2016)

Agri-health research: what have we learned and where do we go next? - Fiorella Picchioni; Lukasz Aleksandrowicz; Mieghan M. Bruce; Soledad Cuevas; Paula Dominguez-Salas; Lili Jia; Mehroosh Tak (Food Security, 2016)

A population pharmacokinetic model for R- and S-citalopram and desmethylcitalopram in Alzheimer’s disease patients with agitation - Ayman Akil; Robert R. Bies; Bruce G. Pollock; Dimitrios Avramopoulos; D. P. Devanand; Jacobo E. Mintzer; Anton P. Porsteinsson; Lon S. Schneider; Daniel Weintraub; Jerome Yesavage; David M. Shade; Constantine G. Lyketsos (Journal of Pharmacokinetics and Pharmacodynamics, 2016)

ZmGOLS2, a target of transcription factor ZmDREB2A, offers similar protection against abiotic stress as ZmDREB2A - Lei Gu; Yumin Zhang; Mingshuai Zhang; Tao Li; Lynnette M. A. Dirk; Bruce Downie; Tianyong Zhao (Plant Molecular Biology, 2016)

MiR-126 Regulates Growth Factor Activities and Vulnerability to Toxic Insult in Neurons - Woori Kim; Haneul Noh; Yenarae Lee; Jeha Jeon; Arthi Shanmugavadivu; Donna L. McPhie; Kwang-Soo Kim; Bruce M. Cohen; Hyemyung Seo; Kai C. Sonntag (Molecular Neurobiology, 2016)

Interdependence of DNA mismatch repair proteins MLH1 and MSH2 in apoptosis in human colorectal carcinoma cell lines - Samar Hassen; Akhtar A. Ali; Surya P. Kilaparty; Qudes A. Al-Anbaky; Waqar Majeed; Bruce M. Boman; Jeremy Z. Fields; Nawab Ali (Molecular and Cellular Biochemistry, 2016)

The Wolbachia WO bacteriophage proteome in the Aedes albopictus C/wStr1 cell line: evidence for lytic activity? - Gerald D. Baldridge; Todd W. Markowski; Bruce A. Witthuhn; LeeAnn Higgins; Abigail S. Baldridge; Ann M. Fallon (In Vitro Cellular & Developmental Biology - Animal, 2016)

Mosaic composition of ribA and wspB genes flanking the virB8-D4 operon in the Wolbachia supergroup B-strain, wStr - Gerald D. Baldridge; Yang Grace Li; Bruce A. Witthuhn; LeeAnn Higgins; Todd W. Markowski; Abigail S. Baldridge; Ann M. Fallon (Archives of Microbiology, 2016)

Uncertainty estimation for operational ocean forecast products—a multi-model ensemble for the North Sea and the Baltic Sea - Inga Golbeck; Xin Li; Frank Janssen; Thorger Brüning; Jacob W. Nielsen; Vibeke Huess; Johan Söderkvist; Bjarne Büchmann; Simo-Matti Siiriä; Olga Vähä-Piikkiö; Bruce Hackett; Nils M. Kristensen; et al. (Ocean Dynamics, 2015)

Participation in cognitively-stimulating activities is associated with brain structure and cognitive function in preclinical Alzheimer’s disease - Stephanie A. Schultz; Jordan Larson; Jennifer Oh; Rebecca Koscik; Maritza N. Dowling; Catherine L. Gallagher; Cynthia M. Carlsson; Howard A. Rowley; Barbara B. Bendlin; Sanjay Asthana; Bruce P. Hermann; Sterling C. Johnson; et al. (Brain Imaging and Behavior, 2015)

Posteromedial hyperactivation during episodic recognition among people with memory decline: findings from the WRAP study - Christopher R. Nicholas; Ozioma C. Okonkwo; Barbara B. Bendlin; Jennifer M. Oh; Sanjay Asthana; Howard A. Rowley; Bruce Hermann; Mark A. Sager; Sterling C. Johnson (Brain Imaging and Behavior, 2015)

Exploring, exploiting and evolving diversity of aquatic ecosystem models: a community perspective - Annette B. G. Janssen; George B. Arhonditsis; Arthur Beusen; Karsten Bolding; Louise Bruce; Jorn Bruggeman; Raoul-Marie Couture; Andrea S. Downing; J. Alex Elliott; Marieke A. Frassl; Gideon Gal; Daan J. Gerla; et al. (Aquatic Ecology, 2015)

Exercise training reduces the flesh firmness of juvenile hāpuku ( Polyprion oxygeneios ) with a hypertrophic reduction in muscle fibre density - JR Khan; S Pether; M Bruce; SP Walker; Y Hemar; NA Herbert (New Zealand Journal of Marine and Freshwater Research, 2015)
Consumers base the organoleptic quality of fish on factors such as texture, which can be altered by exercise. The effect of exercise on the fillet firmness of hāpuku ( Polyprion oxygeneios ) was investigated to determine whether exercise would yield a firmer and more desirable product. To achieve this, the firmness and muscle fibre density (MFD) of fillets from fish exercised for 8 weeks at 0.0, 0.75 or 1.5 body lengths/second (BL s −1 ) was assessed. Firmness was significantly lower in the 0.75 BL s −1 and 1.5 BL s −1 exercised fish than the 0.0 BL s −1 group. MFD was also significantly lower in the exercise treatments. This is explained by an increase in the median fibre size with exercise implying that exercise stimulated muscle fibre hypertrophy, leading to lowered MFD. Assuming that firmer flesh is perceived to be more desirable, exercise may have little value in the production of hāpuku.

Holding-time and method comparisons for the analysis of fecal-indicator bacteria in groundwater - Rebecca N. Bushon; Amie M. G. Brady; Bruce D. Lindsey (Environmental Monitoring and Assessment, 2015)

Identifying craniofacial features associated with prenatal exposure to androgens and testing their relationship with brain development - Klára Marečková; Mallar M. Chakravarty; Claire Lawrence; Gabriel Leonard; Daniel Perusse; Michel Perron; Bruce G. Pike; Louis Richer; Suzanne Veillette; Zdenka Pausova; Tomáš Paus (Brain Structure and Function, 2015)

Incidence Rates and Trend of Serious Farm-Related Injury in Minnesota, 2000–2011 - Adrienne M. K. Landsteiner; Patricia M. McGovern; Bruce H. Alexander; Paula G. Lindgren; Allan N. Williams (Journal of Agromedicine, 2015)

Current strategies for mutation detection in phenotype-driven screens utilising next generation sequencing - Michelle M. Simon; Eva Marie Y. Moresco; Katherine R. Bull; Saumya Kumar; Ann-Marie Mallon; Bruce Beutler; Paul K. Potter (Mammalian Genome, 2015)

Performance of digital screening mammography in a population-based cohort of black and white women - Louise M. Henderson; Thad Benefield; Sarah J. Nyante; Mary W. Marsh; Mikael Anne Greenwood-Hickman; Bruce F. Schroeder (Cancer Causes & Control, 2015)

Land use and management change under climate change adaptation and mitigation strategies: a U.S. case study - Jianhong E. Mu; Anne M. Wein; Bruce A. McCarl (Mitigation and Adaptation Strategies for Global Change, 2015)

Climate change turns up the heat on vertebrate pest control - A. David M. Latham; M. Cecilia Latham; Ellen Cieraad; Daniel M. Tompkins; Bruce Warburton (Biological Invasions, 2015)

Molecular biomarkers for chronological age in animal ecology - Simon N. Jarman; Andrea M. Polanowski; Cassandra E. Faux; Jooke Robbins; Ricardo De Paoli‐Iseppi; Mark Bravington; Bruce E. Deagle (Molecular Ecology, 2015)
The chronological age of an individual animal predicts many of its biological characteristics, and these in turn influence population‐level ecological processes. Animal age information can therefore be valuable in ecological research, but many species have no external features that allow age to be reliably determined. Molecular age biomarkers provide a potential solution to this problem. Research in this area of molecular ecology has so far focused on a limited range of age biomarkers. The most commonly tested molecular age biomarker is change in average telomere length, which predicts age well in a small number of species and tissues, but performs poorly in many other situations. Epigenetic regulation of gene expression has recently been shown to cause age‐related modifications to DNA and to cause changes in abundance of several RNA types throughout animal lifespans. Age biomarkers based on these epigenetic changes, and other new DNA ‐based assays, have already been applied to model organisms, humans and a limited number of wild animals. There is clear potential to apply these marker types more widely in ecological studies. For many species, these new approaches will produce age estimates where this was previously impractical. They will also enable age information to be gathered in cross‐sectional studies and expand the range of demographic characteristics that can be quantified with molecular methods. We describe the range of molecular age biomarkers that have been investigated to date and suggest approaches for developing the newer marker types as age assays in nonmodel animal species.

Gene Expression of Secale cereale (Fall Rye) Grown in Petroleum Hydrocarbon (PHC) Impacted Soil With and Without Plant Growth-Promoting Rhizobacteria (PGPR), Pseudomonas putida - Jolanta Gurska; Bernard R. Glick; Bruce M. Greenberg (Water, Air, & Soil Pollution, 2015)

Cardiorespiratory fitness is associated with brain structure, cognition, and mood in a middle-aged cohort at risk for Alzheimer’s disease - Elizabeth A. Boots; Stephanie A. Schultz; Jennifer M. Oh; Jordan Larson; Dorothy Edwards; Dane Cook; Rebecca L. Koscik; Maritza N. Dowling; Catherine L. Gallagher; Cynthia M. Carlsson; Howard A. Rowley; Barbara B. Bendlin; et al. (Brain Imaging and Behavior, 2015)

Diverse phenotypic consequences of mutations affecting the C-terminus of FLNA - Margriet van Kogelenberg; Alice R. Clark; Zandra Jenkins; Tim Morgan; Ananda Anandan; Gregory M. Sawyer; Matthew Edwards; Tracy Dudding; Tessa Homfray; Bruce Castle; John Tolmie; Fiona Stewart; et al. (Journal of Molecular Medicine, 2015)

The response of Ω-loop D dynamics to truncation of trimethyllysine 72 of yeast iso-1-cytochrome c depends on the nature of loop deformation - Levi J. McClelland; Sean M. Seagraves; Md. Khurshid Alam Khan; Melisa M. Cherney; Swati Bandi; Justin E. Culbertson; Bruce E. Bowler (JBIC Journal of Biological Inorganic Chemistry, 2015)

Toll-like receptor diversity in 10 threatened bird species: relationship with microsatellite heterozygosity - Catherine E. Grueber; Gabrielle J. Knafler; Tania M. King; Alistair M. Senior; Stefanie Grosser; Bruce Robertson; Kerry A. Weston; Patricia Brekke; Christian L. W. Harris; Ian G. Jamieson (Conservation Genetics, 2015)

Reliability of negative BOLD in ipsilateral sensorimotor areas during unimanual task activity - Keith M. McGregor; Atchar Sudhyadhom; Joe Nocera; Ari Seff; Bruce Crosson; Andrew J. Butler (Brain Imaging and Behavior, 2015)

Tephra fallout hazards at Quito International Airport (Ecuador) - Alain C. M. Volentik; Bruce F. Houghton (Bulletin of Volcanology, 2015)

Projected changes in wildlife habitats in Arctic natural areas of northwest Alaska - Bruce G. Marcot; M. Torre Jorgenson; James P. Lawler; Colleen M. Handel; Anthony R. DeGange (Climatic Change, 2015)

Animal-Related Activities as Risk Factors for Injuries Among Youth on Agricultural Operations - Andrew D. Ryan; Susan G. Gerberich; Bruce H. Alexander; Colleen M. Renier (Journal of Agromedicine, 2015)

Denitrification kinetics in biomass- and biochar-amended soils of different landscape positions - Rajesh Chintala; Rachel K Owen; Thomas E Schumacher; Kurt A Spokas; Louis M McDonald; Sandeep Kumar; David E Clay; Douglas D Malo; Bruce Bleakley (Environmental Science and Pollution Research, 2015)

Association between tobacco use and the upper gastrointestinal microbiome among Chinese men - Emily Vogtmann; Roberto Flores; Guoqin Yu; Neal D. Freedman; Jianxin Shi; Mitchell H. Gail; Bruce A. Dye; Guo-Qing Wang; Vanja Klepac-Ceraj; Bruce J. Paster; Wen-Qiang Wei; Hui-Qin Guo; et al. (Cancer Causes & Control, 2015)

Responses of Parasitoids to Volatiles Induced by Chilo partellus Oviposition on Teosinte, a Wild Ancestor of Maize - Daniel M. Mutyambai; Toby J. A. Bruce; Charles A. O. Midega; Christine M. Woodcock; John C. Caulfield; Johnnie Van Den Berg; John A. Pickett; Zeyaur R. Khan (Journal of Chemical Ecology, 2015)

Surface decontamination of plant tissue explants with chlorine dioxide gas - Bhawana; Jeannie M. Stubblefield; Anthony L. Newsome; A. Bruce Cahoon (In Vitro Cellular & Developmental Biology - Plant, 2015)

Closely Related Tree Species Differentially Influence the Transfer of Carbon and Nitrogen from Leaf Litter Up the Aquatic Food Web - Zacchaeus G. Compson; Bruce A. Hungate; George W. Koch; Steve C. Hart; Jesse M. Maestas; Kenneth J. Adams; Thomas G. Whitham; Jane C. Marks (Ecosystems, 2015)

On the Micrometeorology of the Southern Great Plains. 2: Turbulence Statistics - Bruce B. Hicks; W. R. Pendergrass; C. A. Vogel; R. N. Keener; S. M. Leyton (Boundary-Layer Meteorology, 2015)

Astrocyte glycogen as an emergency fuel under conditions of glucose deprivation or intense neural activity - Angus M. Brown; Bruce R. Ransom (Metabolic Brain Disease, 2015)

Polycyclic aromatic hydrocarbons (PAHs) in Crassostrea rhizophorae and Cathorops spixii from the Caroni Swamp, Trinidad, West Indies - La Daana K. Kanhai; Judith F. Gobin; Denise M. Beckles; Bruce Lauckner; Azad Mohammed (Environmental Science and Pollution Research, 2015)

Reducing greenhouse gas emissions, water use, and grain arsenic levels in rice systems - Bruce A. Linquist; Merle M. Anders; Maria Arlene A. Adviento‐Borbe; Rufus L. Chaney; L. Lanier Nalley; Eliete F.F. da Rosa; Chris van Kessel (Global Change Biology, 2015)
Agriculture is faced with the challenge of providing healthy food for a growing population at minimal environmental cost. Rice ( Oryza sativa ), the staple crop for the largest number of people on earth, is grown under flooded soil conditions and uses more water and has higher greenhouse gas ( GHG ) emissions than most crops. The objective of this study was to test the hypothesis that alternate wetting and drying ( AWD – flooding the soil and then allowing to dry down before being reflooded) water management practices will maintain grain yields and concurrently reduce water use, greenhouse gas emissions and arsenic (As) levels in rice. Various treatments ranging in frequency and duration of AWD practices were evaluated at three locations over 2 years. Relative to the flooded control treatment and depending on the AWD treatment, yields were reduced by GWP of CH 4 and N 2 O emissions) reduced by 45–90%, and grain As concentrations reduced by up to 64%. In general, as the severity of AWD increased by allowing the soil to dry out more between flood events, yields declined while the other benefits increased. The reduction in GWP was mostly attributed to a reduction in CH 4 emissions as changes in N 2 O emissions were minimal among treatments. When AWD was practiced early in the growing season followed by flooding for remainder of season, similar yields as the flooded control were obtained but reduced water use (18%), GWP (45%) and yield‐scaled GWP (45%); although grain As concentrations were similar or higher. This highlights that multiple environmental benefits can be realized without sacrificing yield but there may be trade‐offs to consider. Importantly, adoption of these practices will require that they are economically attractive and can be adapted to field scales.

Phoma stem canker disease on oilseed rape (Brassica napus) in China is caused by Leptosphaeria biglobosa ‘brassicae’ - Ze Liu; Akinwunmi O. Latunde-Dada; Avice M. Hall; Bruce D. L. Fitt (European Journal of Plant Pathology, 2014)

Paternal intake of folate and vitamins B6 and B12 before conception and risk of childhood acute lymphoblastic leukemia - Helen D. Bailey; Margaret Miller; Kathryn R. Greenop; Carol Bower; John Attia; Glenn M. Marshall; Bruce K. Armstrong; Elizabeth Milne (Cancer Causes & Control, 2014)

Treatment intensification with maraviroc (CCR5 antagonist) leads to declines in CD16-expressing monocytes in cART-suppressed chronic HIV-infected subjects and is associated with improvements in neurocognitive test performance: implications for HIV-associated neurocognitive disease (HAND) - Lishomwa C. Ndhlovu; Tracie Umaki; Glen M. Chew; Dominic C. Chow; Melissa Agsalda; Kalpana J. Kallianpur; Robert Paul; Guangxiang Zhang; Erika Ho; Nancy Hanks; Beau Nakamoto; Bruce T. Shiramizu; et al. (Journal of NeuroVirology, 2014)

Genetic variability among populations of Fusicladium species from different host trees and geographic locations in the USA - Chunxian Chen; Clive H. Bock; Phillip M. Brannen; James E. Adaskaveg; Mike W. Hotchkiss; Marin T. Brewer; Bruce W. Wood (Mycological Progress, 2014)

The miRNA23b-regulated signaling network as a key to cancer development—implications for translational research and therapeutics - Vignesh Viswanathan; Jeremy Fields; Bruce M. Boman (Journal of Molecular Medicine, 2014)

Turnip mosaic virus: potential for crop losses in the grain belt of New South Wales, Australia - Mark W. Schwinghamer; Mark A. Schilg; John A. Walsh; Rodney W. Bambach; Rosa M. Cossu; Judith M. Bambridge; Tamrika L. Hind-Lanoiselet; Bruce E. McCorkell; Peter Cross (Australasian Plant Pathology, 2014)

Geochemical evidence for provenance of Ordovician cherts in southeastern Australia - M. C. Bruce; I. G. Percival (Australian Journal of Earth Sciences, 2014)

Interaction of psychoactive tryptamines with biogenic amine transporters and serotonin receptor subtypes - Bruce E. Blough; Antonio Landavazo; Ann M. Decker; John S. Partilla; Michael H. Baumann; Richard B. Rothman (Psychopharmacology, 2014)

Spatial–temporal structure of mixing interface turbulence at two large river confluences - Kory M. Konsoer; Bruce L. Rhoads (Environmental Fluid Mechanics, 2014)

Deciphering petrogenic processes using Pb isotope ratios from time-series samples at Bezymianny and Klyuchevskoy volcanoes, Central Kamchatka Depression - Theresa M. Kayzar; Bruce K. Nelson; Olivier Bachmann; Ann M. Bauer; Pavel E. Izbekov (Contributions to Mineralogy and Petrology, 2014)

Combining genetic data to identify relatedness among founders in a genetically depauperate parrot, the Kakapo (Strigops habroptilus) - Laura M. Bergner; Ian G. Jamieson; Bruce C. Robertson (Conservation Genetics, 2014)

Assessment of genetic structure among eastern North Pacific gray whales on their feeding grounds - Aimée R. Lang; John Calambokidis; Jonathan Scordino; Victoria L. Pease; Amber Klimek; Vladimir N. Burkanov; Pat Gearin; Dennis I. Litovka; Kelly M. Robertson; Bruce R. Mate; Jeff K. Jacobsen; Barbara L. Taylor (Marine Mammal Science, 2014)
Although most eastern North Pacific (ENP) gray whales feed in the Bering, Beaufort, and Chukchi Seas during summer and fall, a small number of individuals, referred to as the Pacific Coast Feeding Group (PCFG), show intra‐ and interseasonal fidelity to feeding areas from northern California through southeastern Alaska. We used both mitochondrial DNA (mtDNA) and 12 microsatellite markers to assess whether stock structure exists among feeding grounds used by ENP gray whales. Significant mtDNA differentiation was found when samples representing the PCFG ( n = 71) were compared with samples ( n = 103) collected from animals feeding further north ( F ST = 0.012 , P = 0.0045). No significant nuclear differences were detected. These results indicate that matrilineal fidelity plays a role in creating structure among feeding grounds but suggests that individuals from different feeding areas may interbreed. Haplotype diversities were similar between strata ( h PCFG = 0.945, h N orthern = 0.952), which, in combination with the low level of mtDNA differentiation identified, suggested that some immigration into the PCFG could be occurring. These results are important in evaluating the management of ENP gray whales, especially in light of the Makah Tribe's proposal to resume whaling in an area of the Washington coast utilized by both PCFG and migrating whales.

Improved allometric models to estimate the aboveground biomass of tropical trees - Jérôme Chave; Maxime Réjou‐Méchain; Alberto Búrquez; Emmanuel Chidumayo; Matthew S. Colgan; Welington B.C. Delitti; Alvaro Duque; Tron Eid; Philip M. Fearnside; Rosa C. Goodman; Matieu Henry; Angelina Martínez‐Yrízar; et al. (Global Change Biology, 2014)
Terrestrial carbon stock mapping is important for the successful implementation of climate change mitigation policies. Its accuracy depends on the availability of reliable allometric models to infer oven‐dry aboveground biomass of trees from census data. The degree of uncertainty associated with previously published pantropical aboveground biomass allometries is large. We analyzed a global database of directly harvested trees at 58 sites, spanning a wide range of climatic conditions and vegetation types (4004 trees ≥ 5 cm trunk diameter). When trunk diameter, total tree height, and wood specific gravity were included in the aboveground biomass model as covariates, a single model was found to hold across tropical vegetation types, with no detectable effect of region or environmental factors. The mean percent bias and variance of this model was only slightly higher than that of locally fitted models. Wood specific gravity was an important predictor of aboveground biomass, especially when including a much broader range of vegetation types than previous studies. The generic tree diameter–height relationship depended linearly on a bioclimatic stress variable E , which compounds indices of temperature variability, precipitation variability, and drought intensity. For cases in which total tree height is unavailable for aboveground biomass estimation, a pantropical model incorporating wood density, trunk diameter, and the variable E outperformed previously published models without height. However, to minimize bias, the development of locally derived diameter–height relationships is advised whenever possible. Both new allometric models should contribute to improve the accuracy of biomass assessment protocols in tropical vegetation types, and to advancing our understanding of architectural and evolutionary constraints on woody plant development.

Developing yellowtail kingfish ( Seriola lalandi ) and hāpuku ( Polyprion oxygeneios ) for New Zealand aquaculture - JE Symonds; SP Walker; S Pether; Y Gublin; D McQueen; A King; GW Irvine; AN Setiawan; JA Forsythe; M Bruce (New Zealand Journal of Marine and Freshwater Research, 2014)
Two high value species, yellowtail kingfish ( Seriola lalandi ) and hāpuku (groper, Polyprion oxygeneios ), have been identified as suitable new candidates for New Zealand aquaculture. This paper reviews the research by NIWA and collaborators conducted to test the biological, technological and economic feasibility of farming these two species. NIWA now has the capability to produce sufficient kingfish fingerlings per year to meet the needs of the early stages of an industry. Advances in hāpuku aquaculture have also been significant, from spawning in captivity through to the selection of juveniles for improved growth. Recently, the first spawning of captive hāpuku F1 broodstock and production of F2 eggs, larvae and juveniles was achieved. Although hāpuku larval survival remains variable, the ability to close the life cycle, and the availability of domesticated broodstock, provide a significant step forward and increase the chances of this species being commercially farmed.

HOX genes and their role in the development of human cancers - Seema Bhatlekar; Jeremy Z. Fields; Bruce M. Boman (Journal of Molecular Medicine, 2014)

Characterization of the DYX2 locus on chromosome 6p22 with reading disability, language impairment, and IQ - John D. Eicher; Natalie R. Powers; Laura L. Miller; Kathryn L. Mueller; Sara Mascheretti; Cecilia Marino; Erik G. Willcutt; John C. DeFries; Richard K. Olson; Shelley D. Smith; Bruce F. Pennington; J. Bruce Tomblin; et al. (Human Genetics, 2014)

Temperature dependence of an estuarine harmful algal bloom: Resolving interannual variability in bloom dynamics using a degree‐day approach - David K. Ralston; Bruce A. Keafer; Michael L. Brosnahan; Donald M. Anderson (Limnology and Oceanography, 2014)
Observations of harmful algal blooms (HABs) of the dinoflagellate Alexandrium fundyense in an estuary over multiple years were used to assess drivers of their spatial and temporal variability. Nauset Estuary on Cape Cod, Massachusetts has a recurrent, self‐seeding A. fundyense population that produces paralytic shellfish poisoning toxins and leads to nearly annual closure to shellfishing. Weekly surveys of the entire estuary were made in 3 of 4 consecutive years, with surveys of a subembayment during the intervening year. Major A. fundyense blooms were observed all 4 yr, with maximum concentrations > 10 6 cells L −1 . Concentrations were greatest in three salt ponds at the distal edges of the estuary. The bloom timing varied among the salt ponds and among years, although the blooms had similar durations and maximum cell concentrations. Nutrient concentrations did not correlate with the growth of the bloom, but differences in water temperature among years and ponds were significant. Net growth rates inferred from the surveys were similar to those from laboratory experiments, and increased linearly with temperature. A growing degree‐day calculation was used to account for effects of interannual variability and spatial gradients in water temperature on population development. The approach collapsed variability in the timing of bloom onset, development, and termination across years and among ponds, suggesting that this relatively simple metric could be used as an early‐warning indicator for HABs in Nauset and similar areas with localized, self‐seeding blooms.

Δ9-Tetrahydrocannabinol Treatment During Human Monocyte Differentiation Reduces Macrophage Susceptibility to HIV-1 Infection - Julie C. Williams; Sofia Appelberg; Bruce A. Goldberger; Thomas W. Klein; John W. Sleasman; Maureen M. Goodenow (Journal of Neuroimmune Pharmacology, 2014)

Ground water contamination with 238U, 234U, 235U, 226Ra and 210Pb from past uranium mining: cove wash, Arizona - Kenya Moore Dias da Cunha; Helenes Henderson; Bruce M. Thomson; Adam A. Hecht (Environmental Geochemistry and Health, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

HIV-associated neurocognitive disorder in Australia: a case of a high-functioning and optimally treated cohort and implications for international neuroHIV research - Lucette A. Cysique; Robert K. Heaton; Jody Kamminga; Tammy Lane; Thomas M. Gates; Danielle M. Moore; Emma Hubner; Andrew Carr; Bruce J. Brew (Journal of NeuroVirology, 2014)

H alomonas sulfidaeris ‐dominated microbial community inhabits a 1.8 km‐deep subsurface C ambrian S andstone reservoir - Yiran Dong; Charu Gupta Kumar; Nicholas Chia; Pan‐Jun Kim; Philip A. Miller; Nathan D. Price; Isaac K. O. Cann; Theodore M. Flynn; Robert A. Sanford; Ivan G. Krapac; Randall A. Locke; Pei‐Ying Hong; et al. (Environmental Microbiology, 2014)
Summary A low‐diversity microbial community, dominated by the γ ‐proteobacterium H alomonas sulfidaeris , was detected in samples of warm saline formation porewater collected from the C ambrian Mt. S imon S andstone in the I llinois B asin of the N orth A merican M idcontinent (1.8 km/5872 ft burial depth, 50° C , pH 8, 181 bars pressure). These highly porous and permeable quartz arenite sandstones are directly analogous to reservoirs around the world targeted for large‐scale hydrocarbon extraction, as well as subsurface gas and carbon storage. A new downhole low‐contamination subsurface sampling probe was used to collect in situ formation water samples for microbial environmental metagenomic analyses. Multiple lines of evidence suggest that this H . sulfidaeris ‐dominated subsurface microbial community is indigenous and not derived from drilling mud microbial contamination. Data to support this includes V 1‐ V 3 pyrosequencing of formation water and drilling mud, as well as comparison with previously published microbial analyses of drilling muds in other sites. Metabolic pathway reconstruction, constrained by the geology, geochemistry and present‐day environmental conditions of the Mt . S imon S andstone, implies that H . sulfidaeris ‐dominated subsurface microbial community may utilize iron and nitrogen metabolisms and extensively recycle indigenous nutrients and substrates. The presence of aromatic compound metabolic pathways suggests this microbial community can readily adapt to and survive subsurface hydrocarbon migration.

Seasonal patterns in microbial communities inhabiting the hot springs of T engchong, Y unnan Province, C hina - Brandon R. Briggs; Eoin L. Brodie; Lauren M. Tom; Hailiang Dong; Hongchen Jiang; Qiuyuan Huang; Shang Wang; Weiguo Hou; Geng Wu; Liuquin Huang; Brian P. Hedlund; Chuanlun Zhang; et al. (Environmental Microbiology, 2014)
Summary Studies focusing on seasonal dynamics of microbial communities in terrestrial and marine environments are common; however, little is known about seasonal dynamics in high‐temperature environments. Thus, our objective was to document the seasonal dynamics of both the physicochemical conditions and the microbial communities inhabiting hot springs in T engchong County, Y unnan Province, C hina. The PhyloChip microarray detected 4882 operational taxonomic units ( OTUs ) within 79 bacterial phylum‐level groups and 113 OTUs within 20 archaeal phylum‐level groups, which are additional 54 bacterial phyla and 11 archaeal phyla to those that were previously described using pyrosequencing. Monsoon samples ( J une 2011) showed increased concentrations of potassium, total organic carbon, ammonium, calcium, sodium and total nitrogen, and decreased ferrous iron relative to the dry season ( J anuary 2011). At the same time, the highly ordered microbial communities present in J anuary gave way to poorly ordered communities in J une, characterized by higher richness of B acteria , including microbes related to mesophiles. These seasonal changes in geochemistry and community structure are likely due to high rainfall influx during the monsoon season and indicate that seasonal dynamics occurs in high‐temperature environments experiencing significant changes in seasonal recharge. Thus, geothermal environments are not isolated from the surrounding environment and seasonality affects microbial ecology.

Swimming capabilities of stoats and the threat to inshore sanctuaries - Carolyn M. King; Andrew Veale; Bruce Patty; Lisa Hayward (Biological Invasions, 2014)

Invasion trajectory of alien trees: the role of introduction pathway and planting history - Jason E. Donaldson; Cang Hui; David M. Richardson; Mark P. Robertson; Bruce L. Webber; John R.U. Wilson (Global Change Biology, 2014)
Global change is driving a massive rearrangement of the world's biota. Trajectories of distributional shifts are shaped by species traits, the recipient environment and driving forces with many of the driving forces directly due to human activities. The relative importance of each in determining the distributions of introduced species is poorly understood. We consider 11 Australian Acacia species introduced to South Africa for different reasons (commercial forestry, dune stabilization and ornamentation) to determine how features of the introduction pathway have shaped their invasion history. Projections from species distribution models ( SDM s) were developed to assess how the reason for introduction influences the similarity between climatic envelopes in native and alien ranges. A lattice model for an idealized invasion was developed to assess the relative contribution of intrinsic traits and introduction dynamics on the abundance and extent over the course of simulated invasions. SDM s show that alien populations of ornamental species in South Africa occupy substantially different climate space from their native ranges, whereas species introduced for forestry occupy a similar climate space in native and introduced ranges. This may partly explain the slow spread rates observed for some alien ornamental plants. Such mismatches are likely to become less pronounced with the current drive towards ‘eco gardens’ resulting in more introductions of ornamental species with a close climate match between native and newly introduced regions. The results from the lattice model showed that the conditions associated with the introduction pathway (especially introduction pressure) dominate early invasion dynamics. The placement of introduction foci in urban areas limited the extent and abundance of invasive populations. Features of introduction events appear to initially mask the influence of intrinsic species traits on invasions and help to explain the relative success of species introduced for different purposes. Introduction dynamics therefore can have long‐lasting influences on the outcomes of species redistributions, and must be explicitly considered in management plans.

Optimizing rice yields while minimizing yield‐scaled global warming potential - Cameron M. Pittelkow; Maria A. Adviento‐Borbe; Chris van Kessel; James E. Hill; Bruce A. Linquist (Global Change Biology, 2014)
To meet growing global food demand with limited land and reduced environmental impact, agricultural greenhouse gas ( GHG ) emissions are increasingly evaluated with respect to crop productivity, i.e., on a yield‐scaled as opposed to area basis. Here, we compiled available field data on CH 4 and N 2 O emissions from rice production systems to test the hypothesis that in response to fertilizer nitrogen (N) addition, yield‐scaled global warming potential ( GWP ) will be minimized at N rates that maximize yields. Within each study, yield N surplus was calculated to estimate deficit or excess N application rates with respect to the optimal N rate (defined as the N rate at which maximum yield was achieved). Relationships between yield N surplus and GHG emissions were assessed using linear and nonlinear mixed‐effects models. Results indicate that yields increased in response to increasing N surplus when moving from deficit to optimal N rates. At N rates contributing to a yield N surplus, N 2 O and yield‐scaled N 2 O emissions increased exponentially. In contrast, CH 4 emissions were not impacted by N inputs. Accordingly, yield‐scaled CH 4 emissions decreased with N addition. Overall, yield‐scaled GWP was minimized at optimal N rates, decreasing by 21% compared to treatments without N addition. These results are unique compared to aerobic cropping systems in which N 2 O emissions are the primary contributor to GWP , meaning yield‐scaled GWP may not necessarily decrease for aerobic crops when yields are optimized by N fertilizer addition. Balancing gains in agricultural productivity with climate change concerns, this work supports the concept that high rice yields can be achieved with minimal yield‐scaled GWP through optimal N application rates. Moreover, additional improvements in N use efficiency may further reduce yield‐scaled GWP , thereby strengthening the economic and environmental sustainability of rice systems.

Bringing it all together: researcher dialogue to improve synthesis in regional climate adaptation in South-East Queensland, Australia - Bruce M. Taylor; Ryan R. J. McAllister (Regional Environmental Change, 2014)

Long‐Range Movement of Humpback Whales and Their Overlap with Anthropogenic Activity in the South Atlantic Ocean - HOWARD C. ROSENBAUM; SARA M. MAXWELL; FRANCINE KERSHAW; BRUCE MATE (Conservation Biology, 2014)
Humpback whales (Megaptera novaeangliae) are managed by the International Whaling Commission as 7 primary populations that breed in the tropics and migrate to 6 feeding areas around the Antarctic. There is little information on individual movements within breeding areas or migratory connections to feeding grounds. We sought to better understand humpback whale habitat use and movements at breeding areas off West Africa, and during the annual migration to Antarctic feeding areas. We also assessed potential overlap between whale habitat and anthropogenic activities. We used Argos satellite‐monitored radio tags to collect data on 13 animals off Gabon, a primary humpback whale breeding area. We quantified habitat use for 3 cohorts of whales and used a state‐space model to determine transitions in the movement behavior of individuals. We developed a spatial metric of overlap between whale habitat and models of cumulative human activities, including oil platforms, toxicants, and shipping. We detected strong heterogeneity in movement behavior over time that is consistent with previous genetic evidence of multiple populations in the region. Breeding areas for humpback whales in the eastern Atlantic were extensive and extended north of Gabon late in the breeding season. We also observed, for the first time, direct migration between West Africa and sub‐Antarctic feeding areas. Potential overlap of whale habitat with human activities was the highest in exclusive economic zones close to shore, particularly in areas used by both individual whales and the hydrocarbon industry. Whales potentially overlapped with different activities during each stage of their migration, which makes it difficult to implement mitigation measures over their entire range. Our results and existing population‐level data may inform delimitation of populations and actions to mitigate potential threats to whales as part of local, regional, and international management of highly migratory marine species . Cuantificación de los Movimientos de Gran Amplitud y el Traslape Potencial con Actividad Antropogénica y las Ballenas Jorobadas en el Océano Atlántico Sur

Metals in sediments and mangrove oysters (Crassostrea rhizophorae) from the Caroni Swamp, Trinidad - La Daana K. Kanhai; Judith F. Gobin; Denise M. Beckles; Bruce Lauckner; Azad Mohammed (Environmental Monitoring and Assessment, 2014)

Specific Volatile Compounds from Mango Elicit Oviposition in Gravid Bactrocera dorsalis Females - Pagadala D. Kamala Jayanthi; Vivek Kempraj; Ravindra M. Aurade; Ravindra K. Venkataramanappa; Bakthavatsalam Nandagopal; Abraham Verghese; Toby J. A. Bruce (Journal of Chemical Ecology, 2014)

A standardized set of metrics to assess and monitor tree invasions - John R. U. Wilson; Paul Caplat; Ian A. Dickie; Cang Hui; Bruce D. Maxwell; Martin A. Nuñez; Aníbal Pauchard; Marcel Rejmánek; David M. Richardson; Mark P. Robertson; Dian Spear; Bruce L. Webber; et al. (Biological Invasions, 2014)

Land cover changes and their biogeophysical effects on climate - Rezaul Mahmood; Roger A. Pielke; Kenneth G. Hubbard; Dev Niyogi; Paul A. Dirmeyer; Clive McAlpine; Andrew M. Carleton; Robert Hale; Samuel Gameda; Adriana Beltrán‐Przekurat; Bruce Baker; Richard McNider; et al. (International Journal of Climatology, 2014)
Land cover changes ( LCCs ) play an important role in the climate system. Research over recent decades highlights the impacts of these changes on atmospheric temperature, humidity, cloud cover, circulation, and precipitation. These impacts range from the local‐ and regional‐scale to sub‐continental and global‐scale. It has been found that the impacts of regional‐scale LCC in one area may also be manifested in other parts of the world as a climatic teleconnection. In light of these findings, this article provides an overview and synthesis of some of the most notable types of LCC and their impacts on climate. These LCC types include agriculture, deforestation and afforestation, desertification, and urbanization. In addition, this article provides a discussion on challenges to, and future research directions in, assessing the climatic impacts of LCC .

Genetic and morphometric evidence on a G alápagos I sland exposes founder effects and diversification in the first‐known (truly) feral western dog population - Sini E. M. Reponen; Sarah K. Brown; Bruce D. Barnett; Benjamin N. Sacks (Molecular Ecology, 2014)
Domesticated animals that revert to a wild state can become invasive and significantly impact native biodiversity. Although dogs can be problematic locally, only the A ustralasian dingo is known to occur in isolation from humans. Western dogs have experienced more intense artificial selection, which potentially limits their invasiveness. However, feral dogs eradicated from I sabela I sland, G alápagos in the 1980s could be the first‐known exception. We used DNA and morphometric data from 92 of these dogs to test the hypotheses that (i) these dogs persisted independently of humans for up to a century and a half since descending from a handful of dogs introduced in the early 1800s, vs. (ii) similarly to other western feral dog populations, they reflected continuous recruitment of strays from human settlements on a portion of the Island. We detected one dominant maternal lineage and one dominant paternal lineage shared by the three subpopulations, along with low autosomal genetic diversity, consistent with the hypothesized common origins from a small founder population. Genetic diversity patterns among the three island subpopulations were consistent with stepping‐stone founder effects, while morphometric differentiation suggested rapid phenotypic divergence, possibly due to drift and reinforced by selection corresponding to distinct microclimates and habitats on I sabela. Despite the continued presence of free‐ranging dogs in the vicinity of settlements on I sabela and other G alápagos I slands, feral populations have not reestablished in remote areas since the 1980s, emphasizing the rarity of conditions necessary for feralization of modern western dogs.

Trampling Impacts on Thermotolerant Vegetation of Geothermal Areas in New Zealand - Bruce R. Burns; Jonet Ward; Theresa M. Downs (Environmental Management, 2013)

Feasibility and potential role of ferumoxytol-enhanced neuroimaging in HIV-associated neurocognitive disorder - Beau K. Nakamoto; Cecilia M. Shikuma; Debra Ogata-Arakaki; Tracie Umaki; Edward A. Neuwelt; Bruce T. Shiramizu; Dominic C. Chow; Nisha I. Parikh; Kalpana J. Kallianpur; Bronwyn E. Hamilton (Journal of NeuroVirology, 2013)

The Response of Pediatric Ribs to Quasi-static Loading: Mechanical Properties and Microstructure - Amanda M. Agnew; Kevin Moorhouse; Yun-Seok Kang; Bruce R. Donnelly; Kiel Pfefferle; Angela X. Manning; Alan S. Litsky; Rod Herriott; Mahmoud Abdel-Rasoul; John H. Bolte (Annals of Biomedical Engineering, 2013)

Evaluation of spatio-temporal variations in chlorophyll- a in Lake Naivasha, Kenya: remote-sensing approach - Jane Ndungu; Bruce C. Monger; Denie C.M. Augustijn; Suzanne J.M.H. Hulscher; Nzula Kitaka; Jude M. Mathooko (International Journal of Remote Sensing, 2013)

The effects of cage-diving activities on the fine-scale swimming behaviour and space use of white sharks - Charlie Huveneers; Paul J. Rogers; Crystal Beckmann; Jayson M. Semmens; Barry D. Bruce; Laurent Seuront (Marine Biology, 2013)

Probabilistic accounting of uncertainty in forecasts of species distributions under climate change - Seth J. Wenger; Nicholas A. Som; Daniel C. Dauwalter; Daniel J. Isaak; Helen M. Neville; Charles H. Luce; Jason B. Dunham; Michael K. Young; Kurt D. Fausch; Bruce E. Rieman (Global Change Biology, 2013)
Forecasts of species distributions under future climates are inherently uncertain, but there have been few attempts to describe this uncertainty comprehensively in a probabilistic manner. We developed a Monte Carlo approach that accounts for uncertainty within generalized linear regression models (parameter uncertainty and residual error), uncertainty among competing models (model uncertainty), and uncertainty in future climate conditions (climate uncertainty) to produce site‐specific frequency distributions of occurrence probabilities across a species' range. We illustrated the method by forecasting suitable habitat for bull trout ( Salvelinus confluentus ) in the Interior Columbia River Basin, USA , under recent and projected 2040s and 2080s climate conditions. The 95% interval of total suitable habitat under recent conditions was estimated at 30.1–42.5 thousand km; this was predicted to decline to 0.5–7.9 thousand km by the 2080s. Projections for the 2080s showed that the great majority of stream segments would be unsuitable with high certainty, regardless of the climate data set or bull trout model employed. The largest contributor to uncertainty in total suitable habitat was climate uncertainty, followed by parameter uncertainty and model uncertainty. Our approach makes it possible to calculate a full distribution of possible outcomes for a species, and permits ready graphical display of uncertainty for individual locations and of total habitat.

Underlying causes of yield spatial variability and potential for precision management in rice systems - Maegen B. Simmonds; Richard E. Plant; José M. Peña-Barragán; Chris van Kessel; Jim Hill; Bruce A. Linquist (Precision Agriculture, 2013)

Neuropathy-Inducing Effects of Eribulin Mesylate Versus Paclitaxel in Mice with Preexisting Neuropathy - Krystyna M. Wozniak; Ying Wu; Mohamed H. Farah; Bruce A. Littlefield; Kenichi Nomoto; Barbara S. Slusher (Neurotoxicity Research, 2013)

Priority research questions for the UK food system - John S. I. Ingram; Hugh L. Wright; Lucy Foster; Timothy Aldred; David Barling; Tim G. Benton; Paul M. Berryman; Charles S. Bestwick; Alice Bows-Larkin; Tim F. Brocklehurst; Judith Buttriss; John Casey; et al. (Food Security, 2013)
The rise of food security up international political, societal and academic agendas has led to increasing interest in novel means of improving primary food production and reducing waste. There are however, also many ‘post-farm gate’ activities that are critical to food security, including processing, packaging, distributing, retailing, cooking and consuming. These activities all affect a range of important food security elements, notably availability, affordability and other aspects of access, nutrition and safety. Addressing the challenge of universal food security, in the context of a number of other policy goals (e.g. social, economic and environmental sustainability), is of keen interest to a range of UK stakeholders but requires an up-to-date evidence base and continuous innovation. An exercise was therefore conducted, under the auspices of the UK Global Food Security Programme, to identify priority research questions with a focus on the UK food system (though the outcomes may be broadly applicable to other developed nations). Emphasis was placed on incorporating a wide range of perspectives (‘world views’) from different stakeholder groups: policy, private sector, non-governmental organisations, advocacy groups and academia. A total of 456 individuals submitted 820 questions from which 100 were selected by a process of online voting and a three-stage workshop voting exercise. These 100 final questions were sorted into 10 themes and the ‘top’ question for each theme identified by a further voting exercise. This step also allowed four different stakeholder groups to select the top 7–8 questions from their perspectives. Results of these voting exercises are presented. It is clear from the wide range of questions prioritised in this exercise that the different stakeholder groups identified specific research needs on a range of post-farm gate activities and food security outcomes. Evidence needs related to food affordability, nutrition and food safety (all key elements of food security) featured highly in the exercise. While there were some questions relating to climate impacts on production, other important topics for food security (e.g. trade, transport, preference and cultural needs) were not viewed as strongly by the participants.

The ovine newborn and human foetal intervertebral disc contain perlecan and aggrecan variably substituted with native 7D4 CS sulphation motif: spatiotemporal immunolocalisation and co-distribution with Notch-1 in the human foetal disc - Cindy Shu; Clare Hughes; Susan M. Smith; Margaret M. Smith; Anthony Hayes; Bruce Caterson; Christopher B. Little; James Melrose (Glycoconjugate Journal, 2013)

Reliable, verifiable and efficient monitoring of biodiversity via metabarcoding - Yinqiu Ji; Louise Ashton; Scott M. Pedley; David P. Edwards; Yong Tang; Akihiro Nakamura; Roger Kitching; Paul M. Dolman; Paul Woodcock; Felicity A. Edwards; Trond H. Larsen; Wayne W. Hsu; et al. (Ecology Letters, 2013)
To manage and conserve biodiversity, one must know what is being lost, where, and why, as well as which remedies are likely to be most effective. Metabarcoding technology can characterise the species compositions of mass samples of eukaryotes or of environmental DNA . Here, we validate metabarcoding by testing it against three high‐quality standard data sets that were collected in Malaysia (tropical), China (subtropical) and the United Kingdom (temperate) and that comprised 55,813 arthropod and bird specimens identified to species level with the expenditure of 2,505 person‐hours of taxonomic expertise. The metabarcode and standard data sets exhibit statistically correlated alpha‐ and beta‐diversities, and the two data sets produce similar policy conclusions for two conservation applications: restoration ecology and systematic conservation planning. Compared with standard biodiversity data sets, metabarcoded samples are taxonomically more comprehensive, many times quicker to produce, less reliant on taxonomic expertise and auditable by third parties, which is essential for dispute resolution.

Raman spectroscopic documentation of Oligocene bladder stone - Bruce M. Rothschild; Larry D. Martin; Brendan Anderson; Alison Olcott Marshall; Craig P. Marshall (The Science of Nature, 2013)

Adaptation to climate change: changes in farmland use and stocking rate in the U.S. - Jianhong E. Mu; Bruce A. McCarl; Anne M. Wein (Mitigation and Adaptation Strategies for Global Change, 2013)

The MCIC Collection: A Shared Repository of Multi-Modal, Multi-Site Brain Image Data from a Clinical Investigation of Schizophrenia - Randy L. Gollub; Jody M. Shoemaker; Margaret D. King; Tonya White; Stefan Ehrlich; Scott R. Sponheim; Vincent P. Clark; Jessica A. Turner; Bryon A. Mueller; Vince Magnotta; Daniel O’Leary; Beng C. Ho; et al. (Neuroinformatics, 2013)

A proposed mechanism for the observed ontogenetic improvement in the hearing ability of hapuka (Polyprion oxygeneios) - P. E. Caiger; J. C. Montgomery; M. Bruce; J. Lu; C. A. Radford (Journal of Comparative Physiology A, 2013)

Systematics of spiny‐backed treefrogs ( H ylidae: O steocephalus ): an A mazonian puzzle - Karl‐Heinz Jungfer; Julián Faivovich; José M. Padial; Santiago Castroviejo‐Fisher; Mariana M. Lyra; Bianca V. M. Berneck; Patricia P. Iglesias; Philippe J. R. Kok; Ross D. MacCulloch; Miguel T. Rodrigues; Vanessa K. Verdade; Claudia P. Torres Gastello; et al. (Zoologica Scripta, 2013)
Spiny‐backed tree frogs of the genus O steocephalus are conspicuous components of the tropical wet forests of the A mazon and the G uiana S hield. Here, we revise the phylogenetic relationships of O steocephalus and its sister group T epuihyla , using up to 6134 bp of DNA sequences of nine mitochondrial and one nuclear gene for 338 specimens from eight countries and 218 localities, representing 89% of the 28 currently recognized nominal species. Our phylogenetic analyses reveal (i) the paraphyly of O steocephalus with respect to T epuihyla , (ii) the placement of ‘ H yla’ warreni as sister to T epuihyla , (iii) the non‐monophyly of several currently recognized species within O steocephalus and (iv) the presence of low ( O . taurinus and O . oophagus ) for the 16 S gene fragment used in amphibian DNA barcoding. We propose a new taxonomy, securing the monophyly of O steocephalus and T epuihyla by rearranging and redefining the content of both genera and also erect a new genus for the sister group of O steocephalus . The colouration of newly metamorphosed individuals is proposed as a morphological synapomorphy for O steocephalus . We recognize and define five monophyletic species groups within O steocephalus , synonymize three species of O steocephalus ( O . germani , O . phasmatus and O . vilmae ) and three species of T epuihyla ( T . celsae , T . galani and T . talbergae ) and reallocate three species ( H yla helenae to O steocephalus , O . exophthalmus to T epuihyla and O . pearsoni to D ryaderces gen. n.). Furthermore, we flag nine putative new species (an increase to 138% of the current diversity). We conclude that species numbers are largely underestimated, with most hidden diversity centred on widespread and polymorphic nominal species. The evolutionary origin of breeding strategies within O steocephalus is discussed in the light of this new phylogenetic hypothesis, and a novel type of amplexus (gular amplexus) is described.

Quantifying the production of dissolved organic nitrogen in headwater streams using 15 N tracer additions - Laura T. Johnson; Jennifer L. Tank; Robert O. Hall, Jr.; Patrick J. Mulholland; Stephen K. Hamilton; H. Maurice Valett; Jackson R. Webster; Melody J. Bernot; William H. McDowell; Bruce J. Peterson; Suzanne M. Thomas (Limnology and Oceanography, 2013)
Most nitrogen (N) assimilation in lake and marine ecosystems is often subsequently released via autochthonous dissolved organic nitrogen (DON) production, but autochthonous DON production has yet to be quantified in flowing waters. We measured in‐stream DON production following 24 h 15 N‐nitrate () tracer additions in 36 headwater streams, a subset of sites from the second Lotic Intersite Nitrogen eXperiment. Streams were located in five North American ecoregions and drained basins dominated by native vegetation, agriculture, or urban land use. Using a two‐compartment model, we could quantify DON production in 15 streams as a function of DO 15 N derived from 15 N tracer in biomass compartments. The streams with detectable DON production had higher % modified land use (agriculture + urban) in their basins than did streams with undetectable DON production. Median DON production represented 8% of total uptake when we used N biomass estimates based on N assimilated over 1 d (measured directly from the 15 N additions). Median DON production was 17% of total uptake when we used N assimilated over 42 d (extrapolated from previous 15 N tracer studies). Variation in DON production was positively correlated with ecosystem respiration, indicating that stream heterotrophy may influence DON production. In‐stream DON production was similar in magnitude to stream denitrification and nitrification, indicating that the production of autochthonous DON can represent a substantial transformation of stream N. Our results confirm that headwater streams can quickly convert inorganic N into organic forms, although the ultimate fate of DON remains unclear.

Remote climate forcing of decadal‐scale regime shifts in Northwest Atlantic shelf ecosystems - Charles H. Greene; Erin Meyer-Gutbrod; Bruce C. Monger; Louise P. McGarry; Andrew J. Pershing; Igor M. Belkin; Paula S. Fratantoni; David G. Mountain; Robert S. Pickart; Andrey Proshutinsky; Rubao Ji; James J. Bisagni; et al. (Limnology and Oceanography, 2013)
Decadal‐scale regime shifts in Northwest Atlantic shelf ecosystems can be remotely forced by climate‐associated atmosphere‐ocean interactions in the North Atlantic and Arctic Ocean Basins. This remote climate forcing is mediated primarily by basin‐ and hemispheric‐scale changes in ocean circulation. We review and synthesize results from process‐oriented field studies and retrospective analyses of time‐series data to document the linkages between climate, ocean circulation, and ecosystem dynamics. Bottom‐up forcing associated with climate plays a prominent role in the dynamics of these ecosystems, comparable in importance to that of top‐down forcing associated with commercial fishing. A broad perspective, one encompassing the effects of basin‐ and hemispheric‐scale climate processes on marine ecosystems, will be critical to the sustainable management of marine living resources in the Northwest Atlantic.

Associations of serum 25-hydroxyvitamin D with overall and breast cancer–specific mortality in a multiethnic cohort of breast cancer survivors - Adriana Villaseñor; Rachel Ballard-Barbash; Anita Ambs; Leslie Bernstein; Kathy Baumgartner; Richard Baumgartner; Cornelia M. Ulrich; Bruce W. Hollis; Anne McTiernan; Marian L. Neuhouser (Cancer Causes & Control, 2013)

Direct and Indirect Plant Defenses are not Suppressed by Endosymbionts of a Specialist Root Herbivore - Christelle A. M. Robert; Daniel L. Frank; Kristen A. Leach; Ted C. J. Turlings; Bruce E. Hibbard; Matthias Erb (Journal of Chemical Ecology, 2013)

Directional genomic hybridization for chromosomal inversion discovery and detection - F. Andrew Ray; Erin Zimmerman; Bruce Robinson; Michael N. Cornforth; Joel S. Bedford; Edwin H. Goodwin; Susan M. Bailey (Chromosome Research, 2013)

Phylogeography and adaptation genetics of stickleback from the H aida G waii archipelago revealed using genome‐wide single nucleotide polymorphism genotyping - Bruce E. Deagle; Felicity C. Jones; Devin M. Absher; David M. Kingsley; Thomas E. Reimchen (Molecular Ecology, 2013)
Threespine stickleback populations are model systems for studying adaptive evolution and the underlying genetics. In lakes on the H aida G waii archipelago (off western C anada), stickleback have undergone a remarkable local radiation and show phenotypic diversity matching that seen throughout the species distribution. To provide a historical context for this radiation, we surveyed genetic variation at >1000 single nucleotide polymorphism ( SNP ) loci in stickleback from over 100 populations. SNP s included markers evenly distributed throughout genome and candidate SNP s tagging adaptive genomic regions. Based on evenly distributed SNP s, the phylogeographic pattern differs substantially from the disjunct pattern previously observed between two highly divergent mt DNA lineages. The SNP tree instead shows extensive within watershed population clustering and different watersheds separated by short branches deep in the tree. These data are consistent with separate colonizations of most watersheds, despite underlying genetic connections between some independent drainages. This supports previous suppositions that morphological diversity observed between watersheds has been shaped independently, with populations exhibiting complete loss of lateral plates and giant size each occurring in several distinct clades. Throughout the archipelago, we see repeated selection of SNP s tagging candidate freshwater adaptive variants at several genomic regions differentiated between marine–freshwater populations on a global scale (e.g. EDA , Na/K ATP ase ). In estuarine sites, both marine and freshwater allelic variants were commonly detected. We also found typically marine alleles present in a few freshwater lakes, especially those with completely plated morphology. These results provide a general model for postglacial colonization of freshwater habitat by sticklebacks and illustrate the tremendous potential of genome‐wide SNP data sets hold for resolving patterns and processes underlying recent adaptive divergences.

Prescription drug dispensing profiles for one million children: a population-based analysis - Tingting Zhang; M. Anne Smith; Pat G. Camp; Salomah Shajari; Stuart M. MacLeod; Bruce C. Carleton (European Journal of Clinical Pharmacology, 2013)

Mobile receivers: releasing the mooring to ‘see’ where fish go - Sean A. Hayes; Nicole M. Teutschel; Cyril J. Michel; Cory Champagne; Patrick W. Robinson; Melinda Fowler; Tina Yack; David K. Mellinger; Samantha Simmons; Daniel P. Costa; R. Bruce MacFarlane (Environmental Biology of Fishes, 2013)

Global NeuroAIDS Roundtable - Jeymohan Joseph; Cristian L. Achim; Michael J. Boivin; Bruce J. Brew; David B. Clifford; Deborah A. Colosi; Ronald J. Ellis; Robert K. Heaton; Amadou Gallo-Diop; Igor Grant; Georgette D. Kanmogne; Mahendra Kumar; et al. (Journal of NeuroVirology, 2013)

Relating vesicle shapes in pyroclasts to eruption styles - Pranabendu Moitra; Helge M. Gonnermann; Bruce F. Houghton; Thomas Giachetti (Bulletin of Volcanology, 2013)

Genome-wide study identifies two loci associated with lung function decline in mild to moderate COPD - Nadia N. Hansel; Ingo Ruczinski; Nicholas Rafaels; Don D. Sin; Denise Daley; Alla Malinina; Lili Huang; Andrew Sandford; Tanda Murray; Yoonhee Kim; Candelaria Vergara; Susan R. Heckbert; et al. (Human Genetics, 2013)

Smoking, variation in N-acetyltransferase 1 (NAT1) and 2 (NAT2), and risk of non-Hodgkin lymphoma: a pooled analysis within the InterLymph consortium - Todd M. Gibson; Karin E. Smedby; Christine F. Skibola; David W. Hein; Susan L. Slager; Silvia de Sanjosé; Claire M. Vajdic; Yawei Zhang; Brian C.-H. Chiu; Sophia S. Wang; Henrik Hjalgrim; Alexandra Nieters; et al. (Cancer Causes & Control, 2013)

Association of time-dependent changes in mu opioid receptor mRNA, but not BDNF, TrkB, or MeCP2 mRNA and protein expression in the rat nucleus accumbens with incubation of heroin craving - Florence R. M. Theberge; Charles L. Pickens; Evan Goldart; Sanya Fanous; Bruce T. Hope; Qing-Rong Liu; Yavin Shaham (Psychopharmacology, 2012)

A Statistically Based Acute Ischemia Detection Algorithm Suitable for an Implantable Device - Bruce Hopenfeld; M. Sasha John; Tim A. Fischell; Steven R. Johnson (Annals of Biomedical Engineering, 2012)

Crop classification modelling using remote sensing and environmental data in the Greater Platte River Basin, USA - Daniel M. Howard; Bruce K. Wylie; Larry L. Tieszen (International Journal of Remote Sensing, 2012)

Trade-Offs Between Biodiversity Conservation and Economic Development in Five Tropical Forest Landscapes - Marieke Sandker; Manuel Ruiz-Perez; Bruce M. Campbell (Environmental Management, 2012)

Vertebrate metacommunity structure along an extensive elevational gradient in the tropics: a comparison of bats, rodents and birds - Steven J. Presley; Laura M. Cisneros; Bruce D. Patterson; Michael R. Willig (Global Ecology and Biogeography, 2012)
Aim We evaluated the structure of metacommunities for each of three vertebrate orders (Chiroptera, Rodentia and Passeriformes) along an extensive elevational gradient. Using elevation as a proxy for variation in abiotic characteristics and the known elevational distributions of habitat types, we assessed the extent to which variation in those factors may structure each metacommunity based on taxon‐specific characteristics. Location Manu Biosphere Reserve in the Peruvian Andes. Methods Metacommunity structure is an emergent property of a set of species distributions across geographic or environmental gradients. We analysed elements of metacommunity structure (coherence, range turnover and range boundary clumping) to determine the best‐fit structure for each metacommunity along an elevational gradient comprising 13 250‐m elevational intervals and 58 species of rodent, 92 species of bat or 586 species of passerine. Results For each taxon, the environmental gradient along which the metacommunity was structured was highly correlated with elevation. Clementsian structure (i.e. groups of species replacing other such groups along the gradient) characterized rodents, with a group of species that was characteristic of rain forests and a group of species that was characteristic of higher elevation habitats (i.e. above 1500 m). Distributions of bats were strongly nested, with more montane communities comprising subsets of species at lower elevations. The structure of the passerine metacommunity was complex and most consistent with a quasi‐Clementsian structure. Main conclusions Each metacommunity exhibited a different structure along the same elevational gradient, and each structure can be accounted for by taxon‐specific responses to local environmental factors that vary predictably with elevation. The structures of rodent and bird metacommunities suggest species sorting associated with habitat specializations, whereas structure of the bat metacommunity is probably moulded by a combination of species‐specific tolerances to increasingly cold, low‐productivity environs of higher elevations and the diversity and abundance of food resources associated with particular habitat types.

Critical difference applied to exercise-induced oxidative stress: the dilemma of distinguishing biological from statistical change - Gareth W. Davison; Tony Ashton; Jane McEneny; Ian S. Young; Bruce Davies; Damian M. Bailey (Journal of Physiology and Biochemistry, 2012)

Genome-wide association analysis of circulating vitamin D levels in children with asthma - Jessica Lasky-Su; Nancy Lange; John M. Brehm; Amy Damask; Manuel Soto-Quiros; Lydiana Avila; Juan C. Celedón; Glorisa Canino; Michelle M. Cloutier; Bruce W. Hollis; Scott T. Weiss; Augusto A. Litonjua (Human Genetics, 2012)

Chondroitin sulphate and heparan sulphate sulphation motifs and their proteoglycans are involved in articular cartilage formation during human foetal knee joint development - James Melrose; Marc D. Isaacs; Susan M. Smith; Clare E. Hughes; Christopher B. Little; Bruce Caterson; Anthony J. Hayes (Histochemistry and Cell Biology, 2012)

Groundwater quality in some Voltaian and Birimian aquifers in northern Ghana—application of mulitvariate statistical methods and geographic information systems - Sandow Mark Yidana; Bruce Banoeng-Yakubo; Abdul-Samed Aliou; Thomas M. Akabzaa (Hydrological Sciences Journal, 2012)

Geomorphic and stratigraphic evidence for an unusual tsunami or storm a few centuries ago at Anegada, British Virgin Islands - Brian F. Atwater; Uri S. ten Brink; Mark Buckley; Robert S. Halley; Bruce E. Jaffe; Alberto M. López-Venegas; Eduard G. Reinhardt; Maritia P. Tuttle; Steve Watt; Yong Wei (Natural Hazards, 2012)

Comparison of techniques used to count single-celled viable phytoplankton - Mia K. Steinberg; Matthew R. First; Edward J. Lemieux; Lisa A. Drake; Bruce N. Nelson; David M. Kulis; Donald M. Anderson; Nicholas A. Welschmeyer; Penny R. Herring (Journal of Applied Phycology, 2012)

A splice site mutation in a gene encoding for PDK4, a mitochondrial protein, is associated with the development of dilated cardiomyopathy in the Doberman pinscher - Kathryn M. Meurs; Sunshine Lahmers; Bruce W. Keene; Stephen N. White; Mark A. Oyama; Evan Mauceli; Kerstin Lindblad-Toh (Human Genetics, 2012)

A comment on: ‘TitaniQ under pressure: the effect of pressure and temperature on the solubility of Ti in quartz’, by Jay B. Thomas, E. Bruce Watson, Frank S. Spear, Philip T. Shemella, Saroj K. Nayak and Antonio Lanzirotti - Colin J. N. Wilson; Terry M. Seward; Aidan S. R. Allan; Bruce L. A. Charlier; Léa Bello (Contributions to Mineralogy and Petrology, 2012)

Erratum to: Acquisition of cocaine self-administration in male Sprague–Dawley rats: effects of cocaine dose but not initial locomotor response to cocaine - Bruce H. Mandt; Nickie L. Johnston; Nancy R. Zahniser; Richard M. Allen (Psychopharmacology, 2012)

Motor map reliability and aging: a TMS/fMRI study - Keith M. McGregor; Haley Carpenter; Erin Kleim; Atchar Sudhyadhom; Keith D. White; Andrew J. Butler; Jeffrey Kleim; Bruce Crosson (Experimental Brain Research, 2012)

Performance and energy costs associated with scaling infrared heater arrays for warming field plots from 1 to 100 m - Bruce A. Kimball; Matthew M. Conley; Keith F. Lewin (Theoretical and Applied Climatology, 2012)

Effect of the Mammalian Arginase Inhibitor 2(S)-Amino-6-Boronohexanoic Acid on Bacillus anthracis Arginase - Pei Tsai; Guan-Liang Cao; Bruce Tomczuk; Peter D. Suzdak; Alan S. Cross; Paul Shapiro; Gerald M. Rosen (Current Microbiology, 2012)

Isolation and Identification of Host Cues from Mango, Mangifera indica, That Attract Gravid Female Oriental Fruit fly, Bactrocera dorsalis - Pagadala D. Kamala Jayanthi; Christine M. Woodcock; John Caulfield; Michael A. Birkett; Toby J. A. Bruce (Journal of Chemical Ecology, 2012)

Exercise intensity and oxygen uptake kinetics in African-American and Caucasian women - Nicola Lai; Fatima Tolentino-Silva; Melita M. Nasca; Marco A. Silva; L. Bruce Gladden; Marco E. Cabrera (European Journal of Applied Physiology, 2012)

Oviposition Induced Volatile Emissions from African Smallholder Farmers’ Maize Varieties - Amanuel Tamiru; Toby J. A. Bruce; Charles A. O. Midega; Christine M. Woodcock; Michael A. Birkett; John A. Pickett; Zeyaur R. Khan (Journal of Chemical Ecology, 2012)

Acquisition of cocaine self-administration in male Sprague–Dawley rats: effects of cocaine dose but not initial locomotor response to cocaine - Bruce H. Mandt; Nickie L. Johnston; Nancy R. Zahniser; Richard M. Allen (Psychopharmacology, 2012)

Canine models of Duchenne muscular dystrophy and their use in therapeutic strategies - Joe N. Kornegay; Janet R. Bogan; Daniel J. Bogan; Martin K. Childers; Juan Li; Peter Nghiem; David A. Detwiler; C. Aaron Larsen; Robert W. Grange; Ratna K. Bhavaraju-Sanka; Sandra Tou; Bruce P. Keene; et al. (Mammalian Genome, 2012)

Aberrant crypt foci as predictors of colorectal neoplasia on repeat colonoscopy - Joseph C. Anderson; Helen Swede; Tarun Rustagi; Petr Protiva; Devon Pleau; Bruce M. Brenner; Thiruchandurai V. Rajan; Christopher D. Heinen; Joel B. Levine; Daniel W. Rosenberg (Cancer Causes & Control, 2012)

In situ tensile fracture toughness of surficial cohesive marine sediments - Bruce D. Johnson; Mark A. Barry; Bernard P. Boudreau; Peter A. Jumars; Kelly M. Dorgan (Geo-Marine Letters, 2012)

An Overview of Three Promising Mechanical, Optical, and Biochemical Engineering Approaches to Improve Selective Photothermolysis of Refractory Port Wine Stains - Guillermo Aguilar; Bernard Choi; Mans Broekgaarden; Owen Yang; Bruce Yang; Pedram Ghasri; Jennifer K. Chen; Rick Bezemer; J. Stuart Nelson; Anne Margreet van Drooge; Albert Wolkerstorfer; Kristen M. Kelly; et al. (Annals of Biomedical Engineering, 2012)

Bodyweight and other correlates of symptom-detected breast cancers in a population offered screening - Anne Kricker; Tracey DiSipio; Jennifer Stone; Chris Goumas; Jane E. Armes; Dorota M. Gertig; Bruce K. Armstrong (Cancer Causes & Control, 2012)

Web 2.0 collaborations address uncertainty in climate reconstructions of the past millennium - David Morrill Anderson; Bruce A. Bauer; Charles R. Buckner; Edward Gille; Wendy S. Gross; Michael Hartman; Carrie Morrill; Anju M. Shah; Eugene R. Wahl (Earth Science Informatics, 2011)

Multiple Effects of Changes in Arctic Snow Cover - Terry V. Callaghan; Margareta Johansson; Ross D. Brown; Pavel Ya. Groisman; Niklas Labba; Vladimir Radionov; Raymond S. Bradley; Sylvie Blangy; Olga N. Bulygina; Torben R. Christensen; Jonathan E. Colman; Richard L. H. Essery; et al. (Ambio, 2011)

Spatiotemporal trends of mercury in walleye and largemouth bass from the Laurentian Great Lakes Region - Bruce A. Monson; David F. Staples; Satyendra P. Bhavsar; Thomas M. Holsen; Candy S. Schrank; Sara K. Moses; Daryl J. McGoldrick; Sean M. Backus; Kathryn A. Williams (Ecotoxicology, 2011)

Outreach Programs, Peer Pressure, and Common Sense: What Motivates Homeowners to Mitigate Wildfire Risk? - Sarah M. McCaffrey; Melanie Stidham; Eric Toman; Bruce Shindler (Environmental Management, 2011)

Phylogenetic analysis of Gaeumannomyces graminis varieties based on sequence insertions in the small subunit rDNA - Hanafy M. Fouly; Osman Radwan; S. Bruce Martin; Henry T. Wilkinson (Australasian Plant Pathology, 2011)

On the coupling between vegetation and the atmosphere - Isabella M. Angelini; Michael Garstang; Robert E. Davis; Bruce Hayden; David R. Fitzjarrald; David R. Legates; Steven Greco; Stephen Macko; Vickie Connors (Theoretical and Applied Climatology, 2011)

Diving patterns of female macaroni penguins breeding on Marion Island, South Africa - Lorien Pichegru; Yan Ropert-Coudert; Akiko Kato; Akinori Takahashi; Bruce M. Dyer; Peter G. Ryan (Polar Biology, 2011)

Submarine hydrothermal activity and gold-rich mineralization at Brothers Volcano, Kermadec Arc, New Zealand - Cornel E. J. de Ronde; Gary J. Massoth; David A. Butterfield; Bruce W. Christenson; Junichiro Ishibashi; Robert G. Ditchburn; Mark D. Hannington; Robert L. Brathwaite; John E. Lupton; Vadim S. Kamenetsky; Ian J. Graham; Georg F. Zellmer; et al. (Mineralium Deposita, 2011)

The role of granites in volcanic-hosted massive sulphide ore-forming systems: an assessment of magmatic–hydrothermal contributions - David L. Huston; Jorge M. R. S. Relvas; J. Bruce Gemmell; Susan Drieberg (Mineralium Deposita, 2011)

Structured decision making as a proactive approach to dealing with sea level rise in Florida - Julien Martin; Paul L. Fackler; James D. Nichols; Bruce C. Lubow; Mitchell J. Eaton; Michael C. Runge; Bradley M. Stith; Catherine A. Langtimm (Climatic Change, 2011)

Identification of Semiochemicals Released by Cotton, Gossypium hirsutum, Upon Infestation by the Cotton Aphid, Aphis gossypii - Mahabaleshwar Hegde; Janser N. Oliveira; Joao G. da Costa; Ervino Bleicher; Antonio E. G. Santana; Toby J. A. Bruce; John Caulfield; Sarah Y. Dewhirst; Christine M. Woodcock; John A. Pickett; Michael A. Birkett (Journal of Chemical Ecology, 2011)

Osteomyelitis in a Paleozoic reptile: ancient evidence for bacterial infection and its evolutionary significance - Robert R. Reisz; Diane M. Scott; Bruce R. Pynn; Sean P. Modesto (The Science of Nature, 2011)

CD-1 and Balb/cJ mice do not show enduring antidepressant-like effects of ketamine in tests of acute antidepressant efficacy - Anita J. Bechtholt-Gompf; Karen L. Smith; Catherine S. John; Hannah H. Kang; William A. Carlezon; Bruce M. Cohen; Dost Öngür (Psychopharmacology, 2011)

Subcortical brain atrophy persists even in HAART-regulated HIV disease - James T. Becker; Joanne Sanders; Sarah K. Madsen; Ann Ragin; Lawrence Kingsley; Victoria Maruca; Bruce Cohen; Karl Goodkin; Eileen Martin; Eric N. Miller; Ned Sacktor; Jeffery R. Alger; et al. (Brain Imaging and Behavior, 2011)

Remote sensing classification of grass seed cropping practices in western Oregon - George W. Mueller-Warrant; Gerald W. Whittaker; Stephen M. Griffith; Gary M. Banowetz; Bruce D. Dugger; Tiffany S. Garcia; Guillermo Giannico; Kathryn L. Boyer; Brenda C. McComb (International Journal of Remote Sensing, 2011)

Classifying the Hydrologic Function of Prairie Potholes with Remote Sensing and GIS - Jennifer Rover; Chris K. Wright; Ned H. Euliss; David M. Mushet; Bruce K. Wylie (Wetlands, 2011)

Lack of effect of sublingual salvinorin A, a naturally occurring kappa opioid, in humans: a placebo-controlled trial - John E. Mendelson; Jeremy R. Coyle; Juan Carlos Lopez; Matthew J. Baggott; Keith Flower; E. Thomas Everhart; Thomas A. Munro; Gantt P. Galloway; Bruce M. Cohen (Psychopharmacology, 2011)

Spatial Frequency Domain Imaging of Intrinsic Optical Property Contrast in a Mouse Model of Alzheimer’s Disease - Alexander J. Lin; Maya A. Koike; Kim N. Green; Jae G. Kim; Amaan Mazhar; Tyler B. Rice; Frank M. LaFerla; Bruce J. Tromberg (Annals of Biomedical Engineering, 2011)

The Role of Botanic Gardens in the Science and Practice of Ecological Restoration - KATE A. HARDWICK; PEGGY FIEDLER; LYNDON C. LEE; BRUCE PAVLIK; RICHARD J. HOBBS; JAMES ARONSON; MARTIN BIDARTONDO; ERIC BLACK; DAVID COATES; MATTHEW I. DAWS; KINGSLEY DIXON; STEPHEN ELLIOTT; et al. (Conservation Biology, 2011)
Many of the skills and resources associated with botanic gardens and arboreta, including plant taxonomy, horticulture, and seed bank management, are fundamental to ecological restoration efforts, yet few of the world's botanic gardens are involved in the science or practice of restoration. Thus, we examined the potential role of botanic gardens in these emerging fields. We believe a reorientation of certain existing institutional strengths, such as plant‐based research and knowledge transfer, would enable many more botanic gardens worldwide to provide effective science‐based support to restoration efforts. We recommend botanic gardens widen research to include ecosystems as well as species, increase involvement in practical restoration projects and training practitioners, and serve as information hubs for data archiving and exchange.

Subarachnoid Hemorrhage Induces Gliosis and Increased Expression of the Pro-inflammatory Cytokine High Mobility Group Box 1 Protein - Kentaro Murakami; Masayo Koide; Travis M. Dumont; Sheila R. Russell; Bruce I. Tranmer; George C. Wellman (Translational Stroke Research, 2011)

Data sharing and retrieval using OAI-PMH - Ranjeet Devarakonda; Giri Palanisamy; James M. Green; Bruce E. Wilson (Earth Science Informatics, 2011)

Seasonality and depth distribution of a mesopelagic foraminifer, Hastigerinella digitata , in Monterey Bay, California - Pincelli M. Hull; Karen J. Osborn; Richard D. Norris; Bruce H. Robison (Limnology and Oceanography, 2011)
We investigated the habitat depth and population dynamics of mesopelagic foraminifera in Monterey Bay, California, using 12 yr of video surveys and specimens from live collections. The water column over Monterey Canyon continuously supports two distinct species of mesopelagic foraminifera, Hastigerinella digitata and a previously unknown species referred to as Hastigerina sp., with H. digitata dominating the planktonic foraminiferal assemblage at mesopelagic depths. H. digitata populations live within a narrow depth horizon that lies above the core of the regional oxygen minimum zone at a depth of 280–358 m and O 2 concentrations of 1–1.3 mL L −1 . Our observations provide a modern calibration for understanding fossil digitate planktonic foraminifera. We observed numerous copepods in various stages of ingestion on the spines of H. digitata and a conspicuous lack of detritus attached to the spine network, providing support for the hypothesis that H. digitata is an obligate carnivore. H. digitata populations did not show the strong two‐phase seasonality that characterizes the population dynamics of many mesopelagic species that live above the Monterey Canyon, although H. digitata was generally more abundant in cooler waters on seasonal and interannual timescales.

Coordinated approaches to quantify long‐term ecosystem dynamics in response to global change - YIQI LUO; JERRY MELILLO; SHULI NIU; CLAUS BEIER; JAMES S. CLARK; AIMÉE T. CLASSEN; ERIC DAVIDSON; JEFFREY S. DUKES; R. DAVE EVANS; CHRISTOPHER B. FIELD; CLAUDIA I. CZIMCZIK; MICHAEL KELLER; et al. (Global Change Biology, 2011)
Many serious ecosystem consequences of climate change will take decades or even centuries to emerge. Long‐term ecological responses to global change are strongly regulated by slow processes, such as changes in species composition, carbon dynamics in soil and by long‐lived plants, and accumulation of nutrient capitals. Understanding and predicting these processes require experiments on decadal time scales. But decadal experiments by themselves may not be adequate because many of the slow processes have characteristic time scales much longer than experiments can be maintained. This article promotes a coordinated approach that combines long‐term, large‐scale global change experiments with process studies and modeling. Long‐term global change manipulative experiments, especially in high‐priority ecosystems such as tropical forests and high‐latitude regions, are essential to maximize information gain concerning future states of the earth system. The long‐term experiments should be conducted in tandem with complementary process studies, such as those using model ecosystems, species replacements, laboratory incubations, isotope tracers, and greenhouse facilities. Models are essential to assimilate data from long‐term experiments and process studies together with information from long‐term observations, surveys, and space‐for‐time studies along environmental and biological gradients. Future research programs with coordinated long‐term experiments, process studies, and modeling have the potential to be the most effective strategy to gain the best information on long‐term ecosystem dynamics in response to global change.

Clostridium perfringens bacteriophages ΦCP39O and ΦCP26F: genomic organization and proteomic analysis of the virions - Bruce S. Seal; Derrick E. Fouts; Mustafa Simmons; Johnna K. Garrish; Robin L. Kuntz; Rebekah Woolsey; Kathleen M. Schegg; Andrew M. Kropinski; Hans-W. Ackermann; Gregory R. Siragusa (Archives of Virology, 2011)

Two respiratory enzyme systems in Campylobacter jejuni NCTC 11168 contribute to growth on l ‐lactate - Marie T. Thomas; Mark Shepherd; Robert K. Poole; Arnoud H. M. van Vliet; David J. Kelly; Bruce M. Pearson (Environmental Microbiology, 2011)
Summary Campylobacter jejuni , a major food‐borne intestinal pathogen, preferentially utilizes a few specific amino acids and some organic acids such as pyruvate and l ‐ and d ‐lactate as carbon sources, which may be important for growth in the avian and mammalian gut. Here, we identify the enzymatic basis for C. jejuni growth on l ‐lactate. Despite the presence of an annotated gene for a fermentative lactate dehydrogenase ( cj1167 ), no evidence for lactate excretion could be obtained in C. jejuni NCTC 11168, and inactivation of the cj1167 gene did not affect growth on lactate as carbon source. Instead, l ‐lactate utilization in C. jejuni NCTC 11168 was found to proceed via two novel NAD‐independent l ‐LDHs; a non‐flavin iron–sulfur containing three subunit membrane‐associated enzyme (Cj0075c‐73c), and a flavin and iron–sulfur containing membrane‐associated oxidoreductase (Cj1585c). Both enzymes contribute to growth on l ‐lactate, as single mutants in each system grew as well as wild‐type on this substrate, while a cj0075c cj1585c double mutant showed no l ‐lactate oxidase activity and did not utilize or grow on l ‐lactate; d ‐lactate‐dependent growth was unaffected. Orthologues of Cj0075c‐73c (LldEFG/LutABC) and Cj1585c (Dld‐II) were recently shown to represent two novel families of l ‐ and d ‐lactate oxidases; this is the first report of a bacterium where both enzymes are involved in l ‐lactate utilization only. The cj0075c‐73c genes are located directly downstream of a putative lactate transporter gene ( cj0076c, lctP ), which was also shown to be specific for l ‐lactate. The avian and mammalian gut environment contains dense populations of obligate anaerobes that excrete lactate; our data indicate that C. jejuni is well equipped to use l ‐ and d ‐lactate as both electron‐donor and carbon source.

Patterns of ancestry and genetic diversity in reintroduced populations of the slimy sculpin: implications for conservation - David D. Huff; Loren M. Miller; Bruce Vondracek (Conservation Genetics, 2010)

Electrophysiological and Behavioral Responses of Sorghum Shoot Fly, Atherigona soccata, to Sorghum Volatiles - Poluru G. Padmaja; Christine M. Woodcock; Toby J. A. Bruce (Journal of Chemical Ecology, 2010)

Polymorphisms in oxidative stress and inflammation pathway genes, low-dose ionizing radiation, and the risk of breast cancer among US radiologic technologists - Sara J. Schonfeld; Parveen Bhatti; Elizabeth E. Brown; Martha S. Linet; Steven L. Simon; Robert M. Weinstock; Amy A. Hutchinson; Marilyn Stovall; Dale L. Preston; Bruce H. Alexander; Michele M. Doody; Alice J. Sigurdson (Cancer Causes & Control, 2010)

Cold weather and the potential range of invasive Burmese pythons - Michael L. Avery; Richard M. Engeman; Kandy L. Keacher; John S. Humphrey; William E. Bruce; Tom C. Mathies; Richard E. Mauldin (Biological Invasions, 2010)

Nutrient enrichment differentially affects body sizes of primary consumers and predators in a detritus‐based stream - John M. Davis; Amy D. Rosemond; Susan L. Eggert; Wyatt F. Cross; J. Bruce Wallace (Limnology and Oceanography, 2010)
We assessed how a 5‐yr nutrient enrichment affected the responses of different size classes of primary consumers and predators in a detritus‐based headwater stream. We hypothesized that alterations in detritus availability because of enrichment would decrease the abundance and biomass of large‐bodied consumers. In contrast, we found that 2 yr of enrichment increased the biomass and abundance of all consumers regardless of body size. Furthermore, during the fourth and fifth year of enrichment, the abundance and biomass of largebodied primary consumers continued to increase, while small‐bodied primary consumers returned to pretreatment levels. The size structure of a dominant primary consumer ( Pycnopsyche spp.) also shifted during the 5‐yr enrichment: its average and maximum individual body size increased in the treatment stream compared with the reference stream. Positive enrichment effects also occurred on small‐bodied predators, but not on large‐bodied predators. Thus, enrichment increased prey body size, but these positive effects on large prey did not propagate up to higher trophic levels to affect large predators. Because consumer body size can be an important species‐specific trait determining population dynamics and ecosystem processes, these observed shifts in consumer size distributions suggest a potentially important pathway for global increases in nutrient enrichment to alter stream structure and function.

An examination of aspartate decarboxylase and glutamate decarboxylase activity in mosquitoes - Graham Richardson; Haizhen Ding; Tom Rocheleau; George Mayhew; Erin Reddy; Qian Han; Bruce M. Christensen; Jianyong Li (Molecular Biology Reports, 2010)

Patterns of mussel recruitment in southern Africa: a caution about using artificial substrata to approximate natural recruitment - Kathleen E. Reaugh-Flower; George M. Branch; Jean M. Harris; Christopher D. McQuaid; Bronwen Currie; Arthur Dye; Bruce Robertson (Marine Biology, 2010)

Mapping Human and Social Dimensions of Conservation Opportunity for the Scheduling of Conservation Action on Private Land - ANDREW T. KNIGHT; RICHARD M. COWLING; MARK DIFFORD; BRUCE M. CAMPBELL (Conservation Biology, 2010)
Spatial prioritization techniques are applied in conservation‐planning initiatives to allocate conservation resources. Although typically they are based on ecological data (e.g., species, habitats, ecological processes), increasingly they also include nonecological data, mostly on the vulnerability of valued features and economic costs of implementation. Nevertheless, the effectiveness of conservation actions implemented through conservation‐planning initiatives is a function of the human and social dimensions of social‐ecological systems, such as stakeholders’ willingness and capacity to participate. We assessed human and social factors hypothesized to define opportunities for implementing effective conservation action by individual land managers (those responsible for making day‐to‐day decisions on land use) and mapped these to schedule implementation of a private land conservation program. We surveyed 48 land managers who owned 301 land parcels in the Makana Municipality of the Eastern Cape province in South Africa. Psychometric statistical and cluster analyses were applied to the interview data so as to map human and social factors of conservation opportunity across a landscape of regional conservation importance. Four groups of landowners were identified, in rank order, for a phased implementation process. Furthermore, using psychometric statistical techniques, we reduced the number of interview questions from 165 to 45, which is a preliminary step toward developing surrogates for human and social factors that can be developed rapidly and complemented with measures of conservation value, vulnerability, and economic cost to more‐effectively schedule conservation actions. This work provides conservation and land management professionals direction on where and how implementation of local‐scale conservation should be undertaken to ensure it is feasible.

The Kynurenine Pathway and Inflammation in Amyotrophic Lateral Sclerosis - Yiquan Chen; Roger Stankovic; Karen M. Cullen; Vincent Meininger; Brett Garner; Sarah Coggan; Ross Grant; Bruce J. Brew; Gilles J. Guillemin (Neurotoxicity Research, 2010)

Differential Regulation of Calcium-Activated Potassium Channels by Dynamic Intracellular Calcium Signals - Joanne E. Millership; Caroline Heard; Ian M. Fearon; Jason I. E. Bruce (The Journal of Membrane Biology, 2010)

Role of kappa-opioid receptors in the effects of salvinorin A and ketamine on attention in rats - Christina L. Nemeth; Tracie A. Paine; Joseph E. Rittiner; Cécile Béguin; F. Ivy Carroll; Bryan L. Roth; Bruce M. Cohen; William A. Carlezon (Psychopharmacology, 2010)

Mercury: reusable metadata management, data discovery and access system - Ranjeet Devarakonda; Giriprakash Palanisamy; Bruce E. Wilson; James M. Green (Earth Science Informatics, 2010)

Phylogeography of Leiopelma hochstetteri reveals strong genetic structure and suggests new conservation priorities - Antoine Fouquet; David M. Green; Bruce Waldman; Julia H. Bowsher; Katherine P. McBride; Neil J. Gemmell (Conservation Genetics, 2010)

Peptide Interfacial Biomaterials Improve Endothelial Cell Adhesion and Spreading on Synthetic Polyglycolic Acid Materials - Xin Huang; Stefan Zauscher; Bruce Klitzman; George A. Truskey; William M. Reichert; Daniel J. Kenan; Mark W. Grinstaff (Annals of Biomedical Engineering, 2010)

Characterisation of bacteria in ascites—reporting the potential of culture-independent, molecular analysis - G. B. Rogers; L. E. Russell; P. G. Preston; P. Marsh; J. E. Collins; J. Saunders; J. Sutton; D. Fine; K. D. Bruce; M. Wright (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Effects of seasonality and resource limitation on organic matter turnover by Chironomidae (Diptera) in southern Appalachian headwater streams - Angela M. Romito; Susan L. Eggert; Jeffrey M. Diez; J. Bruce Wallace (Limnology and Oceanography, 2010)
Despite their high abundance, secondary production, and known reliance on detrital material, the role of chironomids (Diptera) in fine particulate organic matter (FPOM) dynamics has not been well quantified. We conducted field trials using fluorescent pigment markers to estimate seasonal rates of consumption, annual secondary production, assimilation efficiency (AE), and FPOM turnover for non‐Tanypodinae chironomids in two similar, southern Appalachian, headwater streams. An ecosystem‐level experimental manipulation of detrital inputs in one study stream allowed for a unique assessment of turnover in reference, resource‐limited, and resource‐recovery systems. Seasonality had a significant effect on larval gut‐passage time (GPT), with faster GPT at higher temperatures. Mean GPT ranged from 39 min (summer) to 67 min (winter). Mean annual FPOM turnover was reduced in the resource‐limited stream (5.5 kg ash‐free dry weight per year; 12% of mean annual FPOM export) compared to the reference stream (46 kg yr −1 ; 74% of mean export). Following 4 yr of resource recovery, FPOM turnover increased to 24 kg ash‐free dry wt yr −1 (16% of export) but remained lower than levels measured in the reference stream (53 kg ash‐free dry wt yr −1 ; 20% of export). Chironomid contribution to FPOM turnover was much higher in low vs. high discharge conditions (74% in low discharge vs. 20% in high discharge). Assimilation efficiency was estimated to be low in all systems (1.7–2.5%). Chironomids turned over a large portion of FPOM available to them, suggesting that turnover by the entire collector community in forested headwater systems may be much higher than expected.

Modelling the bacterial communities associated with cystic fibrosis lung infections - T. Spasenovski; M. P. Carroll; A. K. Lilley; M. S. Payne; K. D. Bruce (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Association between cervical dysplasia and human papillomavirus in HIV seropositive women from Johannesburg South Africa - Cynthia Firnhaber; Hoa Van Le; Audrey Pettifor; Doreen Schulze; Pam Michelow; Ian M. Sanne; David A. Lewis; Anna-Lise Williamson; Bruce Allan; Sophia Williams; Allen Rinas; Simon Levin; et al. (Cancer Causes & Control, 2010)

Responses of soil nitrogen cycling to the interactive effects of elevated CO2 and inorganic N supply - Audrey Niboyet; Laure Barthes; Bruce A. Hungate; Xavier Le Roux; Juliette M. G. Bloor; Annick Ambroise; Sandrine Fontaine; Peter M. Price; Paul W. Leadley (Plant and Soil, 2010)

The Open AUC Project - Helmut Cölfen; Thomas M. Laue; Wendel Wohlleben; Kristian Schilling; Engin Karabudak; Bradley W. Langhorst; Emre Brookes; Bruce Dubbs; Dan Zollars; Mattia Rocco; Borries Demeler (European Biophysics Journal, 2010)

Identification and characterization of a highly virulent triple reassortant H1N1 swine influenza virus in the United States - Wenjun Ma; Amy L. Vincent; Kelly M. Lager; Bruce H. Janke; Steven C. Henry; Raymond R. R. Rowland; Richard A. Hesse; Jürgen A. Richt (Virus Genes, 2010)

Time course of changes in immuneoendocrine markers following an international rugby game - Brian Cunniffe; Andrew J. Hore; Dean M. Whitcombe; Ken P. Jones; Julien S. Baker; Bruce Davies (European Journal of Applied Physiology, 2010)

Policy Development for Biodiversity Offsets: A Review of Offset Frameworks - Bruce A. McKenney; Joseph M. Kiesecker (Environmental Management, 2010)

KATP channel Kir6.2 E23K variant overrepresented in human heart failure is associated with impaired exercise stress response - Santiago Reyes; Sungjo Park; Bruce D. Johnson; Andre Terzic; Timothy M. Olson (Human Genetics, 2009)

Age-Related Changes in Motor Control During Unimanual Movements - Keith M. McGregor; Jason G. Craggs; Michelle L. Benjamin; Bruce Crosson; Keith D. White (Brain Imaging and Behavior, 2009)

Risks of shifting baselines highlighted by anecdotal accounts of New Zealand's snapper ( Pagrus auratus ) fishery - Darren M. Parsons; Mark A. Morrison; Alison B. MacDiarmid; Bruce Stirling; Phillip Cleaver; Ian W.G. Smith; Maria Butcher (New Zealand Journal of Marine and Freshwater Research, 2009)
Anecdotal data sources may constitute an important component of the information available about an exploited species, as record keeping may not have occurred until after exploitation began. Here, we aimed to fill any gaps in the exploitative history of the sparid snapper ( Pagrus auratus ), using social and historical research methods. Social research consisted of interviews with recreational fishers, focusing on the most and largest snapper they had caught. In addition, the diary‐logs of two recreational fishers were analysed. Historical research consisted of investigation of old books, photos, archives and unpublished sources unconventional to fishery science. Interviews with fishers demonstrated no or weak trends in snapper abundance or size, and were likely impeded by a lack of ability to detect change in a fish stock that may still be considered abundant. The fishers’ perception of change, however, largely reflected recent experiences (last c. 10 years), when biomass is understood to have increased, and mostly did not consider experiences before the 1980s. Alternatively, diary‐logs of fisher catch rates produced a pattern that matched formal stock assessments of snapper biomass, suggesting declines in abundance up until the 1990s and an increase in biomass after that time. Historical research, although more qualitative, had the ability to investigate periods where formal records were not kept and described a fishery vastly different from the current one. Snapper were easily caught, in great abundance and in unusual locations. Localised depletion of snapper was first noticed in the early 20th century, despite spectacular catches of snapper occurring after that time. Snapper behaviour was also likely different, with visual sightings of snapper by onlookers a common occurrence. Although predictions from stock assessment models are consistent with that of the anecdotes listed here (i.e., high biomass in the past), these anecdotes are valuable as they explain lost biomass in a perspective meaningful to all. This perspective may be valuable for managers trying to consider the non‐financial value of a shared fishery but, if unrecognised, represents a shifting baseline.

Influence of landscape restoration and degradation on storm surge and waves in southern Louisiana - Ty V. Wamsley; Mary A. Cialone; Jane M. Smith; Bruce A. Ebersole; Alison S. Grzegorzewski (Natural Hazards, 2009)

Change in zooxanthellae and mucocyte tissue density as an adaptive response to environmental stress by the coral, Montastraea annularis - Alan M. Piggot; Bruce W. Fouke; Mayandi Sivaguru; Robert A. Sanford; H. Rex Gaskins (Marine Biology, 2009)

Land-Use and Land-Cover Dynamics in the Central Rift Valley of Ethiopia - Efrem Garedew; Mats Sandewall; Ulf Söderberg; Bruce M. Campbell (Environmental Management, 2009)

Characterization of a newly emerged genetic cluster of H1N1 and H1N2 swine influenza virus in the United States - Amy L. Vincent; Wenjun Ma; Kelly M. Lager; Marie R. Gramer; Juergen A. Richt; Bruce H. Janke (Virus Genes, 2009)

Exploring the effectiveness of integrated conservation and development interventions in a Central African forest landscape - Marieke Sandker; Bruce M. Campbell; Zacharie Nzooh; Terry Sunderland; Victor Amougou; Louis Defo; Jeffrey Sayer (Biodiversity and Conservation, 2009)

Oligomerization of membrane-bound Bcl-2 is involved in its pore formation induced by tBid - Jun Peng; Jingzhen Ding; Chibing Tan; Bruce Baggenstoss; Zhi Zhang; Suzanne M. Lapolla; Jialing Lin (Apoptosis, 2009)

Proteasome activity in a naïve mosquito cell line infected with Wolbachia pipientis wAlbB - Ann M. Fallon; Bruce A. Witthuhn (In Vitro Cellular & Developmental Biology - Animal, 2009)

Sub-micron scale distributions of trace elements in zircon - Amy E. Hofmann; John W. Valley; E. Bruce Watson; Aaron J. Cavosie; John M. Eiler (Contributions to Mineralogy and Petrology, 2009)

The genome of Polaromonas naphthalenivorans strain CJ2, isolated from coal tar‐contaminated sediment, reveals physiological and metabolic versatility and evolution through extensive horizontal gene transfer - Jane M. Yagi; David Sims; Thomas Brettin; David Bruce; Eugene L. Madsen (Environmental Microbiology, 2009)
Summary We analysed the genome of the aromatic hydrocarbon‐degrading, facultatively chemolithotrophic betaproteobacterium, Polaromonas naphthalenivorans strain CJ2. Recent work has increasingly shown that Polaromonas species are prevalent in a variety of pristine oligotrophic environments, as well as polluted habitats. Besides a circular chromosome of 4.4 Mb, strain CJ2 carries eight plasmids ranging from 353 to 6.4 kb in size. Overall, the genome is predicted to encode 4929 proteins. Comparisons of DNA sequences at the individual gene, gene cluster and whole‐genome scales revealed strong trends in shared heredity between strain CJ2 and other members of the Comamonadaceae and Burkholderiaceae . blastp analyses of protein coding sequences across strain CJ2's genome showed that genetic commonalities with other betaproteobacteria diminished significantly in strain CJ2's plasmids compared with the chromosome, especially for the smallest ones. Broad trends in nucleotide characteristics (GC content, GC skew, Karlin signature difference) showed at least six anomalous regions in the chromosome, indicating alteration of genome architecture via horizontal gene transfer. Detailed analysis of one of these anomalous regions (96 kb in size, containing the nag ‐like naphthalene catabolic operon) indicates that the fragment's insertion site was within a putative MiaB‐like tRNA‐modifying enzyme coding sequence. The mosaic nature of strain CJ2's genome was further emphasized by the presence of 309 mobile genetic elements scattered throughout the genome, including 131 predicted transposase genes, 178 phage‐related genes, and representatives of 12 families of insertion elements. A total of three different terminal oxidase genes were found (putative cytochrome aa 3 ‐type oxidase, cytochrome cbb 3 ‐type oxidase and cytochrome bd ‐type quinol oxidase), suggesting adaptation by strain CJ2 to variable aerobic and microaerobic conditions. Sequence‐suggested abilities of strain CJ2 to carry out nitrogen fixation and grow on the aromatic compounds, biphenyl and benzoate, were experimentally verified. These new phenotypes and genotypes set the stage for gaining additional insights into the physiology and biochemistry contributing to strain CJ2's fitness in its native habitat, contaminated sediment.

Semiochemicals used in Host Location by the Coffee berry Borer, Hypothenemus hampei - Esayas Mendesil; Toby J. A. Bruce; Christine M. Woodcock; John C. Caulfield; Emiru Seyoum; John A. Pickett (Journal of Chemical Ecology, 2009)

Evidence for developmental plasticity in response to demographic variation in nature - Michael M. Kasumovic; Matthew J. Bruce; Marie E. Herberstein; Maydianne C. B. Andrade (Ecology, 2009)
Adaptive developmental plasticity has been demonstrated across a number of taxa in response to variables such as photoperiod, resource abundance, and predator presence. Demographics also vary temporally and spatially within populations, but few studies have examined the possibility that developmental plasticity in response to changes in these variables can alter phenotypic distributions. Plastic responses to variable population density and sex ratio may play an important role in explaining phenotypic variation in nature. In this study, we examine two species of spiders ( Nephila plumipes and Argiope keyserlingi ) to examine whether there is evidence that males alter their development in response to demographics in natural populations. We studied spiders in which developing males can use pheromones as a cue of the density of conspecific males and females. We used published information about the mating systems and life history of each species to make predictions about expected patterns of plasticity in development time and correlated changes in adult body size in response to demographic variation. Within each species, male size and mass were positively correlated with the density of males but negatively correlated with the density of females, and as predicted, this was true only when calculated at spatial scales relevant to selection in each species. In contrast, seasonal variation in photoperiod could not explain measured variance in male size. Our results support the idea that developmental plasticity in response to demographics has a significant effect on phenotypic distributions in natural populations. Our results suggest that a proportion of variation in male phenotypes could be explained as a plasticity‐mediated evolutionary response to variation in population demographics rather than as a physiological response to resource abundance and/or photoperiod.

Encouraging the Move Towards Predictive Population Models for the Obese Using Propofol as a Motivating Example - Sarah C. McLeay; Glynn A. Morrish; Carl M. Kirkpatrick; Bruce Green (Pharmaceutical Research, 2009)

Lung-to-lung circulation times during exercise in heart failure - Norman R. Morris; Eric M. Snyder; Kenneth C. Beck; Bruce D. Johnson (European Journal of Applied Physiology, 2009)

The effects of sildenafil and acetazolamide on breathing efficiency and ventilatory control during hypoxic exercise - Sophie Lalande; Eric M. Snyder; Thomas P. Olson; Minelle L. Hulsebus; Marek Orban; Virend K. Somers; Bruce D. Johnson; Robert P. Frantz (European Journal of Applied Physiology, 2009)

Number of aberrant crypt foci associated with adiposity and IGF1 bioavailability - Helen Swede; Thomas E. Rohan; Herbert Yu; Joseph C. Anderson; Richard G. Stevens; Jane Brokaw; Joel Levine; Bruce M. Brenner; Carl D. Malchoff; Valerie B. Duffy; Devon C. Pleau; Daniel W. Rosenberg (Cancer Causes & Control, 2009)

Wood duck duckling mortality and habitat implications in floodplain systems - J. Brian Davis; Bruce D. Leopold; Richard M. Kaminski; Robert R. Cox (Wetlands, 2009)

Neurodegeneration and Ageing in the HAART Era - Bruce J. Brew; S. M. Crowe; A. Landay; Lucette A. Cysique; Gilles Guillemin (Journal of Neuroimmune Pharmacology, 2009)

Trophic linkages between periphyton and grazing macroinvertebrates in rivers with different levels of catchment development - Bruce C. Chessman; Douglas P. Westhorpe; Simon M. Mitrovic; Lorraine Hardwick (Hydrobiologia, 2009)

Techniques to study nephron function: microscopy and imaging - Bruce A. Molitoris; Ruben M. Sandoval (Pflügers Archiv - European Journal of Physiology, 2009)

Nitrate removal in stream ecosystems measured by 15N addition experiments: Total uptake - Robert O. Hall; Jennifer L. Tank; Daniel J. Sobota; Patrick J. Mulholland; Jonathan M. O'Brien; Walter K. Dodds; Jackson R. Webster; H. Maurice Valett; Geoffrey C. Poole; Bruce J. Peterson; Judy L. Meyer; William H. McDowell; et al. (Limnology and Oceanography, 2009)
We measured uptake length of 15 NO 3 − in 72 streams in eight regions across the United States and Puerto Rico to develop quantitative predictive models on controls of NO 3 − uptake length. As part of the Lotic Intersite Nitrogen eXperiment II project, we chose nine streams in each region corresponding to natural (reference), suburban‐urban, and agricultural land uses. Study streams spanned a range of human land use to maximize variation in NO 3 − concentration, geomorphology, and metabolism. We tested a causal model predicting controls on NO 3 − uptake length using structural equation modeling. The model included concomitant measurements of ecosystem metabolism, hydraulic parameters, and nitrogen concentration. We compared this structural equation model to multiple regression models which included additional biotic, catchment, and riparian variables. The structural equation model explained 79% of the variation in log uptake length ( S Wtot ). Uptake length increased with specific discharge ( Q/w ) and increasing NO 3 − concentrations, showing a loss in removal efficiency in streams with high NO 3 − concentration. Uptake lengths shortened with increasing gross primary production, suggesting autotrophic assimilation dominated NO 3 − removal. The fraction of catchment area as agriculture and suburban‐urban land use weakly predicted NO 3 − uptake in bivariate regression, and did improve prediction in a set of multiple regression models. Adding land use to the structural equation model showed that land use indirectly affected NO 3 − uptake lengths via directly increasing both gross primary production and NO 3 − concentration. Gross primary production shortened S Wtot , while increasing NO 3 − lengthened S Wtot resulting in no net effect of land use on NO 3 − removal.

Nitrate removal in stream ecosystems measured by 15N addition experiments: Denitrification - Patrick J. Mulholland; Robert O. Hall; Daniel J. Sobota; Walter K. Dodds; Stuart E. G. Findlay; Nancy B. Grimm; Stephen K. Hamilton; William H. McDowell; Jonathan M. O'Brien; Jennifer L. Tank; Linda R. Ashkenas; Lee W. Cooper; et al. (Limnology and Oceanography, 2009)
We measured denitrification rates using a field 15 NO 3 − tracer‐addition approach in a large, cross‐site study of nitrate uptake in reference, agricultural, and suburban‐urban streams. We measured denitrification rates in 49 of 72 streams studied. Uptake length due to denitrification ( S Wden n) ranged from 89 m to 184 km (median of 9050 m) and there were no significant differences among regions or land‐use categories, likely because of the wide range of conditions within each region and land use. N 2 production rates far exceeded N 2 O production rates in all streams. The fraction of total NO 3 − removal from water due to denitrification ranged from 0.5% to 100% among streams (median of 16%), and was related to NH 4 + concentration and ecosystem respiration rate (ER). Multivariate approaches showed that the most important factors controlling S Wden were specific discharge (discharge / width) and NO 3 − concentration (positive effects), and ER and transient storage zones (negative effects). The relationship between areal denitrification rate ( U den ) and NO 3 − concentration indicated a partial saturation effect. A power function with an exponent of 0.5 described this relationship better than a Michaelis‐Menten equation. Although U den increased with increasing NO 3 − concentration, the efficiency of NO 3 − removal from water via denitrification declined, resulting in a smaller proportion of streamwater NO 3 − load removed over a given length of stream. Regional differences in stream denitrification rates were small relative to the proximate factors of NO 3 − concentration and ecosystem respiration rate, and land use was an important but indirect control on denitrification in streams, primarily via its effect on NO 3 − concentration.

Feeding behavior of the ctenophore Thalassocalyce inconstans: revision of anatomy of the order Thalassocalycida - Holly F. Swift; William M. Hamner; Bruce H. Robison; Laurence P. Madin (Marine Biology, 2009)

Informative study designs to identify true parameter–covariate relationships - Phey Yen Han; Carl M. J. Kirkpatrick; Bruce Green (Journal of Pharmacokinetics and Pharmacodynamics, 2009)

Possible impacts of anthropogenic and natural aerosols on Australian climate: a review - Leon D. Rotstayn; Melita D. Keywood; Bruce W. Forgan; Albert J. Gabric; Ian E. Galbally; John L. Gras; Ashok K. Luhar; Grant H. McTainsh; Ross M. Mitchell; Stuart A. Young (International Journal of Climatology, 2009)
A review is presented of the aerosol–climate interaction with specific focus on the Australian region. The uncertainties associated with this interaction are much larger than those associated with greenhouse gases or other forcing agents, and are currently a major obstacle in climate‐change research. However, new research suggests that aerosol effects are of comparable importance to greenhouse gases as a driver of recent climate trends in the Southern Hemisphere, including Australia. A significant new result from climate modelling is that anthropogenic aerosol over Asia affects meridional temperature gradients and atmospheric circulation, and may have caused an increase in rainfall over north‐western Australia. Global ocean circulation provides another mechanism whereby aerosol changes in the Northern Hemisphere can affect climate in the Southern Hemisphere, suggesting an urgent need for further targeted studies using coupled ocean‐atmosphere global climate models. To better model climate variability and climate change in the Australian region, more research is needed into the sources of aerosol and their precursors, their atmospheric distributions and transformations, and how to incorporate these processes robustly in global climate models (GCMs). The following priorities are suggested for further research in Australia linking aerosol observations and modelling: natural aerosol over the Southern Ocean, tropical biomass‐burning aerosol in Indonesia and Australia, secondary organic aerosol (SOA) from volatile organic compounds (VOCs), wind‐blown dust and modulation of rainfall by anthropogenic aerosol. Copyright © 2008 Royal Meteorological Society

Clinical Characteristics and Outcomes in Patients with Pulmonary Blastomycosis - Doug Kralt; Bruce Light; Mary Cheang; Tracy MacNair; Lyle Wiebe; Bill Limerick; Pete Sarsfield; Greg Hammond; Kerry MacDonald; Elly Trepman; John M. Embil (Mycopathologia, 2009)

Biological flora of New Zealand 11. Eleocharis sphacelata , kuta, paopao, bamboo spike sedge - Mieke M. Kapa; Bruce D. Clarkson (New Zealand Journal of Botany, 2009)
information relevant to the ecology and morphology of Eleocharis sphacelata (Cyperaceae) available through published and unpublished sources is assembled and reviewed. Eleocharis sphacelata is a freshwater wetland sedge found growing at the edge of lake margins, swamps, lagoons, and bogs within New Zealand, australia, and papua New Guinea. it is a perennial rhizomatous herb, with tall green cylindrical culms rising from submerged rhizomes generally buried under water in aerobic soils. a tendency to dominate the deepwater margins makes E. sphacelata crucial to the ecology of this habitat as a source of food, shelter, and protection for invertebrates, birds, and fish. Eleocharis sphacelata is commonly named giant spike‐rush, kuta, or paopao. Māori have traditionally used the plant for clothing and warm coverings within whare (houses). Recent interest comes from its use in restoration plantings and constructed wetlands.

The conservation (protected area) status of New Zealand's indigenous grasslands: An update - Alan F. Mark; Pascale Michel; Katharine J. M. Dickinson; Bruce McLennan (New Zealand Journal of Botany, 2009)
The conservation (protected area) status of New Zealand's indigenous grasslands has been updated to December 2007, from the previous analysis of September 2002, to contribute to a global assessment and conservation initiative for the world's temperate grasslands. Only in the South Island rangeland geographic area has there been a substantial increase in the formally protected area of indigenous grasslands. These areas are mainly at the higher altitudes and associated with government's continued review of high country leasehold tenures. The area formally protected has increased from 12.8 to 15.4% of the original baseline (1840) grassland area of 82 436 km 2 over this period, but low to mid‐altitude systems continue to be poorly protected and are undergoing rapid land transformation.

The Role of Vasoactive Intestinal Peptide (VIP) in Megakaryocyte Proliferation - Chaneun Nam; Adam J. Case; Bruce S. Hostager; M. Sue O’Dorisio (Journal of Molecular Neuroscience, 2009)

Vulnerability of Rehabilitated Agricultural Production Systems to Invasion by Nontarget Plant Species - Sara G. Baer; David M. Engle; Johannes M. H. Knops; Kenneth A. Langeland; Bruce D. Maxwell; Fabian D. Menalled; Amy J. Symstad (Environmental Management, 2009)

The aggregating behaviour of Argiope radon, with special reference to web decorations - Dinesh Rao; Malcolm Webster; Astrid M. Heiling; Matthew J. Bruce; Marie E. Herberstein (Journal of Ethology, 2009)

Individual differences in cocaine-induced locomotor activity in male Sprague–Dawley rats and their acquisition of and motivation to self-administer cocaine - Bruce H. Mandt; Susan Schenk; Nancy R. Zahniser; Richard M. Allen (Psychopharmacology, 2008)

Genomic differences between Campylobacter jejuni isolates identify surface membrane and flagellar function gene products potentially important for colonizing the chicken intestine - Kelli L. Hiett; Alain Stintzi; Tracy M. Andacht; Robin L. Kuntz; Bruce S. Seal (Functional & Integrative Genomics, 2008)

Adoptive immunotherapy: good habits instilled at youth have long-term benefits - Chrystal M. Paulos; Megan M. Suhoski; Gabriela Plesa; Tianying Jiang; Samik Basu; Tatiana N. Golovina; Shuguang Jiang; Nicole A. Aqui; Daniel J. Powell; Bruce L. Levine; Richard G. Carroll; James L. Riley; et al. (Immunologic Research, 2008)

Decompression syndrome and the evolution of deep diving physiology in the Cetacea - Brian Lee Beatty; Bruce M. Rothschild (The Science of Nature, 2008)

Phylogeny of the Rodent Genus Isothrix (Hystricognathi, Echimyidae) and its Diversification in Amazonia and the Eastern Andes - Bruce D. Patterson; Paúl M. Velazco (Journal of Mammalian Evolution, 2008)

Influence of sildenafil on lung diffusion during exposure to acute hypoxia at rest and during exercise in healthy humans - Eric M. Snyder; Thomas P. Olson; Bruce D. Johnson; Robert P. Frantz (European Journal of Applied Physiology, 2008)

Oyster Predation by Black Drum Varies Spatially and Seasonally - Kenneth M. Brown; Gerald J. George; Gary W. Peterson; Bruce A. Thompson; James H. Cowan (Estuaries and Coasts, 2008)

Dispersal of wetland plant seeds by mallards: Influence of gut passage on recovery, retention, and germination - Chanpen Wongsriphuek; Bruce D. Dugger; Anne M. Bartuszevige (Wetlands, 2008)

Vitamin D insufficiency among African-Americans in the southeastern United States: implications for cancer disparities (United States) - Kathleen M. Egan; Lisa B. Signorello; Heather M. Munro; Margaret K. Hargreaves; Bruce W. Hollis; William J. Blot (Cancer Causes & Control, 2008)

SWAT.nz: New-Zeland-based “Sand Waves and Turbulence” experimental programme - Stephen E. Coleman; Vladimir I. Nikora; Bruce W. Melville; Derek G. Goring; Thomas M. Dougal Clunie; Heide Friedrich (Acta Geophysica, 2008)

Knowing But Not Doing: Selecting Priority Conservation Areas and the Research–Implementation Gap - ANDREW T. KNIGHT; RICHARD M. COWLING; MATHIEU ROUGET; ANDREW BALMFORD; AMANDA T. LOMBARD; BRUCE M. CAMPBELL (Conservation Biology, 2008)
Conservation assessment is a rapidly evolving discipline whose stated goal is the design of networks of protected areas that represent and ensure the persistence of nature (i.e., species, habitats, and environmental processes) by separating priority areas from the activities that degrade or destroy them. Nevertheless, despite a burgeoning scientific literature that ever refines these techniques for allocating conservation resources, it is widely believed that conservation assessments are rarely translated into actions that actually conserve nature. We reviewed the conservation assessment literature in peer‐reviewed journals and conducted survey questionnaires of the authors of these studies. Two‐thirds of conservation assessments published in the peer‐reviewed scientific literature do not deliver conservation action, primarily because most researchers never plan for implementation. This research–implementation gap between conservation science and real‐world action is a genuine phenomenon and is a specific example of the “knowing–doing gap” that is widely recognized in management science. Given the woefully inadequate resources allocated for conservation, our findings raise questions over the utility of conservation assessment science, as currently practiced, to provide useful, pragmatic solutions to conservation planning problems. A reevaluation of the conceptual and operational basis of conservation planning research is urgently required. We recommend the following actions for beginning a process for bridging the research–implementation gap in conservation planning: (1) acknowledge the research–implementation gap is real, (2) source research questions from practitioners, (3) situate research within a broader conservation planning model, (4) expand the social dimension of conservation assessments, (5) support conservation plans with transdisciplinary social learning institutions, (6) reward academics for societal engagement and implementation, and (7) train students in skills for “doing” conservation.

How Drugs Interact with Transporters: SGLT1 as a Model - Donald D. F. Loo; Bruce A. Hirayama; Monica Sala-Rabanal; Ernest M. Wright (The Journal of Membrane Biology, 2008)

Investigations of the temporal variation of cyanobacterial and other phytoplanktonic cells at the offtake of a large reservoir, and their survival following passage through it - Timothy Ingleton; Tsuyoshi Kobayashi; Brian Sanderson; Ronald Patra; Catriona M. O. Macinnis-Ng; Bruce Hindmarsh; Lee Clifford Bowling (Hydrobiologia, 2008)

Visual search and foraging compared in a large-scale search task - Alastair D. Smith; Bruce M. Hood; Iain D. Gilchrist (Cognitive Processing, 2008)

ATP Dependence of Na+-Driven Cl–HCO3 Exchange in Squid Axons - Bruce A. Davis; Emilia M. Hogan; John M. Russell; Walter F. Boron (The Journal of Membrane Biology, 2008)

15 N enrichment as an integrator of the effects of C and N on microbial metabolism and ecosystem function - Paul Dijkstra; Corinne M. LaViolette; Jeffrey S. Coyle; Richard R. Doucett; Egbert Schwartz; Stephen C. Hart; Bruce A. Hungate (Ecology Letters, 2008)
Organic carbon (C) and nitrogen (N) are essential for heterotrophic soil microorganisms, and their bioavailability strongly influences ecosystem C and N cycling. We show here that the natural 15 N abundance of the soil microbial biomass is affected by both the availability of C and N and ecosystem N processing. Microbial 15 N enrichment correlated negatively with the C : N ratio of the soil soluble fraction and positively with net N mineralization for ecosystems spanning semiarid, temperate and tropical climates, grassland and forests, and over four million years of ecosystem development. In addition, during soil incubation, large increases in microbial 15 N enrichment corresponded to high net N mineralization rates. These results support the idea that the N isotope composition of an organism is determined by the balance between N assimilation and dissimilation. Thus, 15 N enrichment of the soil microbial biomass integrates the effects of C and N availability on microbial metabolism and ecosystem processes.

Epithelial Barrier Modulation by a Channel Forming Peptide - Suma Somasekharan; Robert Brandt; Takeo Iwamoto; John M. Tomich; Bruce D. Schultz (The Journal of Membrane Biology, 2008)

Early Life Stress on Brain Structure and Function Across the Lifespan: A Preliminary Study - Donna L. Seckfort; Robert Paul; Stuart M. Grieve; Brian Vandenberg; Richard A. Bryant; Leanne M. Williams; C. Richard Clark; Ronald A. Cohen; Steven Bruce; Evian Gordon (Brain Imaging and Behavior, 2008)

New geologic, fluid inclusion and stable isotope studies on the controversial Igarapé Bahia Cu–Au deposit, Carajás Province, Brazil - Ana M. Dreher; Roberto P. Xavier; Bruce E. Taylor; Sérgio L. Martini (Mineralium Deposita, 2008)

Blowing Smoke in Yellowstone: Air Quality Impacts of Oversnow Motorized Recreation in the Park - David D. Shively; Bruce M. C. Pape; Richard N. Mower; Yong Zhou; Rachel Russo; Barkley C. Sive (Environmental Management, 2008)

Using Light-Use and Production Efficiency Models to Predict Photosynthesis and Net Carbon Exchange During Forest Canopy Disturbance - Bruce D. Cook; Paul V. Bolstad; Jonathan G. Martin; Faith Ann Heinsch; Kenneth J. Davis; Weiguo Wang; Ankur R. Desai; Ron M. Teclaw (Ecosystems, 2008)

Southernmost occurrence of the slender tuna, Allothunnus fallai, off Tierra del Fuego, South Atlantic Ocean - Bruce B. Collette; Juan M. Díaz de Astarloa (Ichthyological Research, 2008)

Infrared heater arrays for warming ecosystem field plots - BRUCE A. KIMBALL; MATTHEW M. CONLEY; SHIPING WANG; XINGWU LIN; CAIYUN LUO; JACK MORGAN; DAVID SMITH (Global Change Biology, 2008)
There is a need for methodology to warm open‐field plots in order to study the likely effects of global warming on ecosystems in the future. Herein, we describe the development of arrays of more powerful and efficient infrared heaters with ceramic heating elements. By tilting the heaters at 45° from horizontal and combining six of them in a hexagonal array, good uniformity of warming was achieved across 3‐m‐diameter plots. Moreover, there do not appear to be obstacles (other than financial) to scaling to larger plots. The efficiency [ η h (%); thermal radiation out per electrical energy in] of these heaters was higher than that of the heaters used in most previous infrared heater experiments and can be described by: η h = 10 + 25exp(− 0.17 u ), where u is wind speed at 2 m height (m s − 1 ). Graphs are presented to estimate operating costs from degrees of warming, two types of plant canopy, and site windiness. Four such arrays were deployed over plots of grass at Haibei, Qinghai, China and another at Cheyenne, Wyoming, USA, along with corresponding reference plots with dummy heaters. Proportional integral derivative systems with infrared thermometers to sense canopy temperatures of the heated and reference plots were used to control the heater outputs. Over month‐long periods at both sites, about 75% of canopy temperature observations were within 0.5 °C of the set‐point temperature differences between heated and reference plots. Electrical power consumption per 3‐m‐diameter plot averaged 58 and 80 kW h day − 1 for Haibei and Cheyenne, respectively. However, the desired temperature differences were set lower at Haibei (1.2 °C daytime, 1.7 °C night) than Cheyenne (1.5 °C daytime, 3.0 °C night), and Cheyenne is a windier site. Thus, we conclude that these hexagonal arrays of ceramic infrared heaters can be a successful temperature free‐air‐controlled enhancement (T‐FACE) system for warming ecosystem field plots.

Integrating Agricultural Landscapes with Biodiversity Conservation in the Mesoamerican Hotspot - CELIA A. HARVEY; OLIVER KOMAR; ROBIN CHAZDON; BRUCE G. FERGUSON; BRYAN FINEGAN; DANIEL M. GRIFFITH; MIGUEL MARTÍNEZ‐RAMOS; HELDA MORALES; RONALD NIGH; LORENA SOTO‐PINTO; MICHIEL VAN BREUGEL; MARK WISHNIE (Conservation Biology, 2008)

Nuclear, chloroplast, and mitochondrial transcript abundance along a maize leaf developmental gradient - A. Bruce Cahoon; Elizabeth M. Takacs; Richard M. Sharpe; David B. Stern (Plant Molecular Biology, 2008)

Vertical tectonics of the High Plateau region, Manihiki Plateau, Western Pacific, from seismic stratigraphy - Huirong-Anita Ai; Joann M. Stock; Robert Clayton; Bruce Luyendyk (Marine Geophysical Research, 2008)

Development of blooms of Cyclotella meneghiniana and Nitzschia spp. (Bacillariophyceae) in a shallow river and estimation of effective suppression flows - Simon M. Mitrovic; Bruce C. Chessman; Alec Davie; Estelle L. Avery; Natasha Ryan (Hydrobiologia, 2008)

Feasibility of Multi-site Clinical Structural Neuroimaging Studies of Aging Using Legacy Data - Christine Fennema-Notestine; Anthony C. Gamst; Brian T. Quinn; Jenni Pacheco; Terry L. Jernigan; Leon Thal; Randy Buckner; Ron Killiany; Deborah Blacker; Anders M. Dale; Bruce Fischl; Brad Dickerson; et al. (Neuroinformatics, 2007)

Biological flora of New Zealand 10. Phormium tenax , harakeke, New Zealand flax - Priscilla M. Wehi; Bruce D. Clarkson (New Zealand Journal of Botany, 2007)
We review the biosystematics, chemistry, phenology, ecology, and cultural and economic uses of Phormium tenax , a widespread iconic New Zealand monocotyledon. Phormium tenax is endemic to New Zealand, Norfolk Island, and the Chatham Islands, and is distinguished from the sole other member of the genus, P. cookianum , by its erect trigonous seed capsules and red flowers, despite incomplete barriers to hybridisation. Flowers produce abundant nectar and are bird pollinated. Seed is orthodox and tolerates drying, while chilling overcomes dormancy. Rich, well‐drained alluvial and organic soils encourage abundant growth in P. tenax but prolonged flooding and drought reduce growth and survival. Lack of tolerance to both frost and low mean annual temperatures distinguish its environmental niche from that of P. cookianum , but further research is required to characterise these differences more accurately. Phormium tenax is a significant component of vegetation on coastal cliffs, slopes, and dunelands; in estuarine shrublands; and lake margin and freshwater communities. Wide morphological variation in Phormium has led to cultivar development by Maori for weaving and by horticulturalists for ornamental garden use. Phormium tenax is important in many ecological communities as a food source, and is often used in restoration and revegetation plantings.

One-carbon metabolism gene polymorphisms and risk of non-Hodgkin lymphoma in Australia - Kyoung-Mu Lee; Qing Lan; Anne Kricker; Mark P. Purdue; Andrew E. Grulich; Claire M. Vajdic; Jennifer Turner; Denise Whitby; Daehee Kang; Stephen Chanock; Nathaniel Rothman; Bruce K. Armstrong (Human Genetics, 2007)

IL-6 gene variation is associated with IL-6 and C-reactive protein levels but not cardiovascular outcomes in the Cardiovascular Health Study - Jeremy D. Walston; M. Daniele Fallin; Mary Cushman; Leslie Lange; Bruce Psaty; Nancy Jenny; Warren Browner; Russell Tracy; Peter Durda; Alex Reiner (Human Genetics, 2007)

Right ventricular function with hypoxic exercise: effects of sildenafil - Jesper Kjaergaard; Eric M. Snyder; Christian Hassager; Thomas P. Olson; Jae K. Oh; Bruce D. Johnson; Robert P. Frantz (European Journal of Applied Physiology, 2007)

A spatial analysis of indigenous cover patterns and implications for ecological restoration in urban centres, New Zealand - Bruce D. Clarkson; Priscilla M. Wehi; Lars K. Brabyn (Urban Ecosystems, 2007)

Tephrabase: tephrochronology and the development of a centralised European database - Anthony J. Newton; Andrew J. Dugmore; Bruce M. Gittings (Journal of Quaternary Science, 2007)
Tephrabase was launched on the World Wide Web in 1995 as a tool for tephrochronological research. In order to facilitate the identification, correlation and dating of tephra deposits, this database may be interrogated through multiple routes, including by source volcano, date, location, and tephra chemistry; datasets include stratigraphy, geochemistry, chronology and spatial information. Currently all the European data refer to Late Quaternary Icelandic‐sourced tephras, post‐12 k yr BP. The sites (62) where the tephra deposits are found include Iceland, the United Kingdom, Ireland, the Faroe Islands, Sweden and Russia. In addition, there are also data on tephra layers in central Mexico. Use of Tephrabase highlights the importance of selected geochemical data, but this has to be used with care as major element characteristics alone do not always produce unique definitions for single tephra deposits. For the most accurate results multiple criteria must be used. Tephrabase can be found at http://www.tephrabase.org . Copyright © 2007 John Wiley & Sons, Ltd.

Occupational exposure to ionizing and non-ionizing radiation and risk of non-Hodgkin lymphoma - Ken K. Karipidis; Geza Benke; Malcolm R. Sim; Timo Kauppinen; Anne Kricker; Ann Maree Hughes; Andrew E. Grulich; Claire M. Vajdic; John Kaldor; Bruce Armstrong; Lin Fritschi (International Archives of Occupational and Environmental Health, 2007)

Soil organic matter effects on plant available and water soluble phosphorus - Tsutomu Ohno; Bruce R. Hoskins; M. Susan Erich (Biology and Fertility of Soils, 2007)

Relating plant and pathogen development to optimise fungicide control of phoma stem canker (Leptosphaeria maculans) on winter oilseed rape (Brassica napus) - Julie M. Steed; Andreas Baierl; Bruce D. L. Fitt (European Journal of Plant Pathology, 2007)

Selenium and Metal Concentrations in Waterbird Eggs and Chicks at Agassiz National Wildlife Refuge, Minnesota - Thomas W. Custer; Christine M. Custer; Bruce A. Eichhorst; David Warburton (Archives of Environmental Contamination and Toxicology, 2007)

Functional MRI of Language in Aphasia: A Review of the Literature and the Methodological Challenges - Bruce Crosson; Keith McGregor; Kaundinya S. Gopinath; Tim W. Conway; Michelle Benjamin; Yu-Ling Chang; Anna Bacon Moore; Anastasia M. Raymer; Richard W. Briggs; Megan G. Sherod; Christina E. Wierenga; Keith D. White (Neuropsychology Review, 2007)

The floral volatile, methyl benzoate, from snapdragon (Antirrhinum majus) triggers phytotoxic effects in Arabidopsis thaliana - Jun-ichiro Horiuchi; Dayakar V. Badri; Bruce A. Kimball; Florence Negre; Natalia Dudareva; Mark W. Paschke; Jorge M. Vivanco (Planta, 2007)

Coral microbial communities, zooxanthellae and mucus along gradients of seawater depth and coastal pollution - James S. Klaus; Ingmar Janse; Jeffrey M. Heikoop; Robert A. Sanford; Bruce W. Fouke (Environmental Microbiology, 2007)
Summary The high incidence of coral disease in shallow coastal marine environments suggests seawater depth and coastal pollution have an impact on the microbial communities inhabiting healthy coral tissues. A study was undertaken to determine how bacterial communities inhabiting tissues of the coral Montastraea annularis change at 5 m, 10 m and 20 m water depth in varying proximity to the urban centre and seaport of Willemstad, Curaçao, Netherlands Antilles. Analyses of terminal restriction fragment length polymorphisms (TRFLP) of 16S rRNA gene sequences show significant differences in bacterial communities of polluted and control localities only at the shallowest seawater depth. Furthermore, distinct differences in bacterial communities were found with increasing water depth. Comparisons of TRFLP peaks with sequenced clone libraries indicate the black band disease cyanobacterium clone CD1C11 is common and most abundant on healthy corals in less than 10 m water depth. Similarly, sequences belonging to a previously unrecognized group of likely phototrophic bacteria, herein referred to as CAB‐I, were also more common in shallow water. To assess the influence of environmental and physiologic factors on bacterial community structure, canonical correspondence analysis was performed using explanatory variables associated with: (i) light availability; (ii) seawater pollution; (iii) coral mucus composition; (iv) the community structure of symbiotic algae; and (v) the photosynthetic activity of symbiotic algae. Eleven per cent of the variation in bacterial communities was accounted for by covariation with these variables; the most important being photosynthetically active radiation (sunlight) and the coral uptake of sewage‐derived compounds as recorded by the δ 15 N of coral tissue.

Expression of the cytoskeleton linker protein ezrin in human cancers - Benjamin Bruce; Gaurav Khanna; Ling Ren; Goran Landberg; Karin Jirström; Charles Powell; Alain Borczuk; Evan T. Keller; Kirk J. Wojno; Paul Meltzer; Kristin Baird; Andrea McClatchey; et al. (Clinical & Experimental Metastasis, 2007)

Physical activity and endometrial cancer risk: a review of the current evidence, biologic mechanisms and the quality of physical activity assessment methods - Anne E. Cust; Bruce K. Armstrong; Christine M. Friedenreich; Nadia Slimani; Adrian Bauman (Cancer Causes & Control, 2007)

(11Z,13E)-Hexadecadien-1-yl Acetate: Sex Pheromone of the Grass Webworm Herpetogramma licarsisalis—Identification, Synthesis, and Field Bioassays - Andrew R. Gibb; D. Max Suckling; Ashraf M. El-Sayed; Björn Bohman; C. Rikard Unelius; Jennifer J. Dymock; Michelle L. Larsen; Bruce E. Willoughby (Journal of Chemical Ecology, 2007)

Domestic Sewage and Oil Spills in Streams: Effects on Edaphic Invertebrates in Flooded Forest, Manaus, Amazonas, Brazil - Sheyla R. M. Couceiro; Neusa Hamada; Ruth L. M. Ferreira; Bruce R. Forsberg; Jéferson O. da Silva (Water, Air, & Soil Pollution, 2007)

Etiologic Subtypes of Attention-Deficit/Hyperactivity Disorder: Brain Imaging, Molecular Genetic and Environmental Factors and the Dopamine Hypothesis - James M. Swanson; Marcel Kinsbourne; Joel Nigg; Bruce Lanphear; Gerry A. Stefanatos; Nora Volkow; Eric Taylor; B. J. Casey; F. Xavier Castellanos; Pathik D. Wadhwa (Neuropsychology Review, 2007)

Effects of elevated plasma tryptophan on brain activation associated with the Stroop task - Rhian M. Morgan; Allyson M. M. Parry; Ricardo M. Arida; Paul M. Matthews; Bruce Davies; Linda M. Castell (Psychopharmacology, 2007)

Retrotransposons and Tandem Repeat Sequences in the Nuclear Genomes of Cryptomonad Algae - Hameed Khan; Catherine Kozera; Bruce A. Curtis; Jillian Tarrant Bussey; Stan Theophilou; Sharen Bowman; John M. Archibald (Journal of Molecular Evolution, 2007)

Tsunami Warnings: Understanding in Hawai‘i - Chris E. Gregg; Bruce F. Houghton; Douglas Paton; David M. Johnston; Donald A. Swanson; Brian S. Yanagi (Natural Hazards, 2007)

Deforestation and sewage effects on aquatic macroinvertebrates in urban streams in Manaus, Amazonas, Brazil - Sheyla R. M. Couceiro; Neusa Hamada; Sérgio L. B. Luz; Bruce R. Forsberg; Tânia Pena Pimentel (Hydrobiologia, 2007)

Taxonomic Considerations in Listing Subspecies Under the U.S. Endangered Species Act - SUSAN M. HAIG; ERIK A. BEEVER; STEVEN M. CHAMBERS; HOPE M. DRAHEIM; BRUCE D. DUGGER; SUSIE DUNHAM; ELISE ELLIOTT‐SMITH; JOSEPH B. FONTAINE; DYLAN C. KESLER; BRIAN J. KNAUS; IARA F. LOPES; PETE LOSCHL; et al. (Conservation Biology, 2006)
The U.S. Endangered Species Act (ESA) allows listing of subspecies and other groupings below the rank of species. This provides the U.S. Fish and Wildlife Service and the National Marine Fisheries Service with a means to target the most critical unit in need of conservation. Although roughly one‐quarter of listed taxa are subspecies, these management agencies are hindered by uncertainties about taxonomic standards during listing or delisting activities. In a review of taxonomic publications and societies, we found few subspecies lists and none that stated standardized criteria for determining subspecific taxa. Lack of criteria is attributed to a centuries‐old debate over species and subspecies concepts. Nevertheless, the critical need to resolve this debate for ESA listings led us to propose that minimal biological criteria to define disjunct subspecies (legally or taxonomically) should include the discreteness and significance criteria of distinct population segments (as defined under the ESA). Our subspecies criteria are in stark contrast to that proposed by supporters of the phylogenetic species concept and provide a clear distinction between species and subspecies. Efforts to eliminate or reduce ambiguity associated with subspecies‐level classifications will assist with ESA listing decisions. Thus, we urge professional taxonomic societies to publish and periodically update peer‐reviewed species and subspecies lists. This effort must be paralleled throughout the world for efficient taxonomic conservation to take place.

The effect of 18 h of simulated high altitude on left ventricular function - Jesper Kjaergaard; Eric M. Snyder; Christian Hassager; Thomas P. Olson; Jae K. Oh; Bruce D. Johnson (European Journal of Applied Physiology, 2006)

Defoliation of Centaurea solstitialis Stimulates Compensatory Growth and Intensifies Negative Effects on Neighbors - Ragan M. Callaway; Judy Kim; Bruce E. Mahall (Biological Invasions, 2006)

Hyperdisease in the late Pleistocene: validation of an early 20th century hypothesis - Bruce M. Rothschild; Richard Laub (The Science of Nature, 2006)

Did ice-age bovids spread tuberculosis? - Bruce M. Rothschild; Larry D. Martin (The Science of Nature, 2006)

A northwest North American training set: distribution of freshwater midges in relation to air temperature and lake depth - Erin M. Barley; Ian R. Walker; Joshua Kurek; Les C. Cwynar; Rolf W. Mathewes; Konrad Gajewski; Bruce P. Finney (Journal of Paleolimnology, 2006)

Managing an Endangered Asian Bovid in an Australian National Park: The Role and Limitations of Ecological-Economic Models in Decision-Making - Barry W. Brook; David M. J. S. Bowman; Corey J. A. Bradshaw; Bruce M. Campbell; Peter J. Whitehead (Environmental Management, 2006)

Developmental components of large-scale search: evidence from children and individuals with partial genetic deletions - Alastair D. Smith; Iain D. Gilchrist; Bruce M. Hood; Annette Karmiloff-Smith (Cognitive Processing, 2006)

Plant–soil feedbacks and invasive spread - Jonathan M. Levine; Elizaveta Pachepsky; Bruce E. Kendall; Stephanie G. Yelenik; Janneke Hille Ris Lambers (Ecology Letters, 2006)
Plant invaders have been suggested to change soil microbial communities and biogeochemical cycling in ways that can feedback to benefit themselves. In this paper, we ask when do these feedbacks influence the spread of exotic plants. Because answering this question is empirically challenging, we show how ecological theory on ‘pushed’ and ‘pulled’ invasions can be used to examine the problem. We incorporate soil feedbacks into annual plant invasion models, derive the conditions under which such feedbacks affect spread, and support our approach with simulations. We show that in homogeneous landscapes, strong positive feedbacks can influence spreading velocity for annual invaders, but that empirically documented feedbacks are not strong enough to do so. Moreover, to influence spread, invaders must modify the soil environment over a spatial scale larger than is biologically realistic. Though unimportant for annual invader spread in our models, feedbacks do affect invader density and potential impact. We discuss how future research might consider the way landscape structure, dispersal patterns, and the time scales over which plant–soil feedbacks develop regulate the effects of such feedbacks on invader spread.

C-type natriuretic peptide and its receptor are downregulated in pulmonary epithelium following birth - Christopher A. D’Angelis; Peter A. Nickerson; Rita M. Ryan; Daniel D. Swartz; Bruce A. Holm (Histochemistry and Cell Biology, 2006)

Enhanced sucrose pellet consumption induced by benzodiazepine-type drugs in squirrel monkeys: role of GABAA receptor subtypes - Angela N. Duke; Donna M. Platt; James M. Cook; Shengming Huang; Wenyuan Yin; Bruce A. Mattingly; James K. Rowlett (Psychopharmacology, 2006)

Temporal and spatial appearance of wall polysaccharides during cellularization of barley (Hordeum vulgare) endosperm - Sarah M. Wilson; Rachel A. Burton; Monika S. Doblin; Bruce A. Stone; Edward J. Newbigin; Geoffrey B. Fincher; Antony Bacic (Planta, 2006)

Prey-mediated effects of transgenic canola on a beneficial, non-target, carabid beetle - Natalie Ferry; Evan A. Mulligan; C. Neal Stewart; Bruce E. Tabashnik; Gordon R. Port; Angharad M. R. Gatehouse (Transgenic Research, 2006)

Mortality Partitions and their Relevance to Research on Senescence - Bruce A. Carnes; Larry R. Holden; S. Jay Olshansky; M. Tarynn Witten; Jacob S. Siegel (Biogerontology, 2006)

Desmoid Tumors – a Characterization of Patients Seen at Mayo Clinic 1976–1999 - Taya Fallen; Marcia Wilson; Bruce Morlan; Noralane M Lindor (Familial Cancer, 2006)

RAAS polymorphisms alter the acute blood pressure response to aerobic exercise among men with hypertension - Bruce E. Blanchard; Gregory J. Tsongalis; Margaux A. Guidry; Lisa A. LaBelle; Michelle Poulin; Amy L. Taylor; Carl M. Maresh; Joseph Devaney; Paul D. Thompson; Linda S. Pescatello (European Journal of Applied Physiology, 2006)

An Operational Model for Implementing Conservation Action - ANDREW T. KNIGHT; RICHARD M. COWLING; BRUCE M. CAMPBELL (Conservation Biology, 2006)
The preoccupation of many conservation planners with the refinement of systematic assessment techniques has manifested an “implementation crisis” in conservation planning. This preoccupation has provided systematic assessments with well‐tested tools (e.g., area selection algorithms) and principles (e.g., representation, complementarity), but our understanding of these techniques currently far exceeds our ability to apply them effectively to pragmatic conservation problems. The science is informative about where one needs to do conservation, but silent on how to achieve it. Operational models, defined as simplified conceptualizations of processes for implementing conservation action at priority conservation areas, are essential for guiding conservation planning initiatives because they assist understanding of how these processes function. Operational models developed to date have largely been linear, simplistic, and focused on the systematic assessment of biological entities. Experience in the real world indicates that operational models for conducting conservation planning initiatives should explicitly complement a systematic conservation assessment with activities that empower individuals and institutions (enabling) and explicitly aim to secure conservation action (implementation). Specifically, implementing effective conservation action requires that systematic assessments be integrated functionally with a process for developing an implementation strategy and processes for stakeholder collaboration while maintaining a broad focus on the implementation of conservation action. A suite of hallmarks define effective operational models (e.g., stakeholder collaboration, links with land‐use planning, social learning, and action research). Greater development and testing of the practical application of operational models should lead to higher levels of effective implementation and alleviate the implementation crisis. Social learning institutions are essential for ensuring ongoing improvement in the development and application of operational models that deliver effective conservation action.

Growth Suppression of Canola through Wheat Stubble II. Investigating Impacts of Hypocotyl Elongation using Simulated Stubble - S. E. Bruce; M. H. Ryan; S. Hely; J. A. Kirkegaard; J. Pratley (Plant and Soil, 2006)

Land‐use impacts and water quality targets in the intensive dairying catchment of the Toenepi Stream, New Zealand - Robert J. Wilcock; Ross M. Monaghan; John M. Quinn; Alan M. Campbell; Bruce S. Thorrold; Maurice J. Duncan; Alec W. McGowan; Keith Betteridge (New Zealand Journal of Marine and Freshwater Research, 2006)
Water quality monitoring in Toenepi Stream, New Zealand, started in 1995 in a study of dairy farming influences on lowland stream quality and has continued since then with brief interruptions. Surveys have provided information about changes in farm and soil management practices as they relate to environmental sustainability. Although average water quality in Toenepi Stream has changed little during 1995–2004, there have been some notable improvements. Water clarity measured by black disc has improved from 0.6m to 1.5m, and median ammonia‐N and nitrate‐N concentrations have declined by 70% and 57%, respectively. The frequency and magnitude of extreme concentrations have declined—most notably for nitrogen (N) forms, which also had decreased mean values. Specific yields for suspended solids (SS) and phosphorus (P) forms in 2002–04 were 47–67% of 1995–97 values, mainly because of lower water yields. Reduced specific yields for N forms in 2002–04 (34–37% of 1995–97 yields) were also attributable to lower mean concentrations in stream water. Faecal bacteria concentrations have not abated and are on average 2–3 times recommended guideline values for contact recreation. Fewer dairy farms and an increased proportion irrigating dairyshed effluent to land, rather than discharging it to the stream via two‐pond systems, were likely causes of improvement in water quality. Water quality targets were developed for Toenepi Stream to achieve contact recreation criteria for the Piako River (downstream) and for intrinsic habitat values for Toenepi Stream. A range of mitigation measures has been formulated to meet these targets, but substantial uptake of sustainable farming practices is needed to improve water quality in Toenepi Stream.

Metallothionein-3 and neuronal nitric oxide synthase levels in brains from the Tg2576 mouse model of Alzheimer's disease - Bruce L. Martin; Abigail M. Tokheim; Patrick T. McCarthy; Brendan S. Doms; Andrew A. Davis; Ian M. Armitage (Molecular and Cellular Biochemistry, 2006)

Biological monitoring and surveillance results of Gulf War I veterans exposed to depleted uranium - Melissa A. McDiarmid; Susan M. Engelhardt; Marc Oliver; Patricia Gucer; P. David Wilson; Robert Kane; Michael Kabat; Bruce Kaup; Larry Anderson; Dennis Hoover; Lawrence Brown; Richard J. Albertini; et al. (International Archives of Occupational and Environmental Health, 2006)

Investments in Fuel Removals to Avoid Forest Fires Result in Substantial Benefits - C. Larry Mason; Bruce R. Lippke; Kevin W. Zobrist; Thomas D. Bloxton; Kevin R. Ceder; Jeffrey M. Comnick; James B. McCarter; Heather K. Rogers (Journal of Forestry, 2006)
Forest fuel reduction treatments are needed, as shown by the increased number and cost of devastating crown fires in overly dense forests. Although large trees can be removed for valuable products, the market value for the smaller logs may be less than the harvest and hauling charges, resulting in a net cost for thinning operations. However, failure to remove these small logs results in the retention of ladder fuels that support crown fires with destructive impacts to the forest landscape. A cost/benefit analysis broadened to include market and nonmarket considerations indicates that the negative impacts of crown fires are underestimated and that the benefits of government investments in fuel reductions are substantial.

Soil nematodes mediate positive interactions between legume plants and rhizobium bacteria - Jun-ichiro Horiuchi; Balakrishnan Prithiviraj; Harsh P. Bais; Bruce A. Kimball; Jorge M. Vivanco (Planta, 2005)

Possible modes of coral-reef development at Molokai, Hawaii, inferred from seismic-reflection profiling - Walter A. Barnhardt; Bruce M. Richmond; Eric E. Grossman; Patrick Hart (Geo-Marine Letters, 2005)

Development and Evaluation of a PCR Based Assay for Detection of the Toxic Dinoflagellate, Gymnodinium catenatum(Graham) in Ballast Water and Environmental Samples - Jawahar G. Patil; Rasanthi M. Gunasekera; Bruce E. Deagle; Nicholas J. Bax; Susan I. Blackburn (Biological Invasions, 2005)

Evidence for the Cd2+ Activation of the Aryl Sulfatase from Helix pomatia - Abigail M. Tokheim; Donna J. Spannaus-Martin; Bruce L. Martin (BioMetals, 2005)

Historical Evidence of Widespread Chytrid Infection in North American Amphibian Populations - MARTIN OUELLET; IGOR MIKAELIAN; BRUCE D. PAULI; JEAN RODRIGUE; DAVID M. GREEN (Conservation Biology, 2005)
Emerging infectious diseases may be contributing to the global decline of amphibian populations. In particular, chytridiomycosis, a cutaneous fungal infection of amphibians caused by the chytrid Batrachochytrium dendrobatidis , gained attention in the 1990s as an apparently new pathogen. This fungus has been implicated as the causative agent of widespread mortalities among wild amphibians in geographically disparate parts of the world. To investigate the global distribution, historical occurrence, and infectiousness of this pathogen, we examined 3371 postmetamorphic and adult amphibians collected between 1895 and 2001 from 25 countries for the presence of chytrid fungi in the epidermis. Cutaneous chytrid infection was diagnosed in 383 of 2931 (13.1%) specimens of 12 common amphibian species from five Canadian provinces and seven American states, including 30 of 69 locations examined in the St. Lawrence River Valley of Québec. Chytrids were observed in 7.0% (46/655) of the adults collected in the 1960s, the earliest cases being two green frogs ( Rana clamitans ) collected in 1961 from Saint‐Pierre‐de‐Wakefield, Québec. In recent studies, morbidity and mortality attributable to chytridiomycosis were not observed in infected amphibians from Québec despite a 17.8% (302/1698) prevalence of chytrid infection during the period 1990–2001. The prevalence of infection during this latter period was not statistically different when compared with the period 1960–1969. Epidermal chytrid infections were not observed in 440 amphibians examined from 23 other countries. In light of the fact that infection by B. dendrobatidis is widely distributed and apparently enzootic in seemingly healthy amphibians from eastern North America, lethal outbreaks of chytridiomycosis among amphibian populations appear to have complex causes and may be the result of underlying predisposing factors.

Differentiation of activated satellite cells in denervated muscle following single fusions in situ and in cell culture - Andrei B. Borisov; Eduard I. Dedkov; Bruce M. Carlson (Histochemistry and Cell Biology, 2005)

Risk of non-Hodgkin lymphoma associated with occupational exposure to solvents, metals, organic dusts and PCBs (Australia) - Lin Fritschi; Geza Benke; Ann M. Hughes; Anne Kricker; Claire M. Vajdic; Andrew Grulich; Jennifer Turner; Samuel Milliken; John Kaldor; Bruce K. Armstrong (Cancer Causes & Control, 2005)

On the Closing Sounds of a Mechanical Heart Valve - Changfu Wu; Bruce A. Herman; Stephen M. Retta; Laurence W. Grossman; Jia-Shing Liu; Ned H. C. Hwang (Annals of Biomedical Engineering, 2005)

Vertical distribution and diurnal migration patterns of Jasus edwardsii phyllosomas off the east coast of the North Island, New Zealand - Russell W. Bradford; Barry D. Bruce; Stephen M. Chiswell; John D. Booth; Andrew Jeffs; Simon Wotherspoon (New Zealand Journal of Marine and Freshwater Research, 2005)
The rock lobster Jasus edwardsii forms the basis of important fisheries in south‐eastern Australia and New Zealand. Their long pelagic larval phyllosoma phase (12–24 months) raises many questions as to how the larvae are retained and/or recruited into local populations. Recent attempts to model the dispersal of J. edwardsii phyllosoma have had mixed success at reconstructing settlement patterns. However, these models have either ignored vertical distribution or have used that of the western rock lobster, Panulirus cygnus. We report on the vertical distribution and migration of J. edwardsii phyllosomas, collected in March/April 2003 from the Wairarapa Eddy off the east coast of the North Island, New Zealand, and provide a model to describe their vertical distribution. J. edwardsii phyllosoma were primarily recorded within the upper 100 m over similar depth ranges to those reported for other palinurid and scyllarid species. Well‐defined changes in diel vertical distribution were restricted to late‐stage larvae. Mid‐stage phyllosomas were concentrated in the upper 20 m both day and night. Late‐stage phyllosomas were concentrated in the upper 20 m during the night, but they were absent from the upper 20 m during the day and distributed primarily between 20 and 100 m. Future modelling will benefit from using larval distribution and behaviour patterns specific to J. edwardsii.

Density-dependent effects on physical condition and reproduction in North American elk: an experimental test - Kelley M. Stewart; R. Terry. Bowyer; Brian L. Dick; Bruce K. Johnson; John G. Kie (Oecologia, 2005)

Patterns of ascospore release in relation to phoma stem canker epidemiology in England (Leptosphaeria maculans) and Poland (Leptosphaeria biglobosa) - Yong-Ju Huang; Bruce D. L. Fitt; Malgorzata Jedryczka; Sylwia Dakowska; Jonathan S. West; Peter Gladders; Julie M. Steed; Zi-Qin Li (European Journal of Plant Pathology, 2005)

Bacterial communities inhabiting the healthy tissues of two Caribbean reef corals: interspecific and spatial variation - James S. Klaus; Jorge Frias-Lopez; George T. Bonheyo; Jeffrey M. Heikoop; Bruce W. Fouke (Coral Reefs, 2005)

Specific Detection of Pacific Oyster (Crassostrea gigas) Larvae in Plankton Samples Using Nested Polymerase Chain Reaction - Jawahar G. Patil; Rasanthi M. Gunasekera; Bruce E. Deagle; Nicholas J. Bax (Marine Biotechnology, 2005)

Influence of Targets and Assessment Region Size on Perceived Conservation Priorities - David D. Diamond; C. Diane True; Taisia M. Gordon; Scott P. Sowa; Walter E. Foster; K. Bruce Jones (Environmental Management, 2005)

Estimating the complexity of bird song by using capture-recapture approaches from community ecology - Lszl Z. Garamszegi; Thorsten J. S. Balsby; Ben D. Bell; Marta Borowiec; Bruce E. Byers; Tudor Draganoiu; Marcel Eens; Wolfgang Forstmeier; Paolo Galeotti; Diego Gil; Leen Gorissen; Poul Hansen; et al. (Behavioral Ecology and Sociobiology, 2005)

Urea in the Tributaries of the Chesapeake and Coastal Bays of Maryland - Patricia M. Glibert; T. Mark Trice; Bruce Michael; Lois Lane (Water, Air, & Soil Pollution, 2005)

Estimated contribution of Atlantic Coastal loggerhead turtle nesting populations to offshore feeding aggregations - Mark A. Roberts; Christopher J. Anderson; Bruce Stender; Al Segars; J. David Whittaker; James M. Grady; Joseph M. Quattro (Conservation Genetics, 2005)

The Pseudorabies Virus Serine/Threonine Kinase Us3 Contains Mitochondrial, Nuclear and Membrane Localization Signals - Christine M. Calton; Jessica A. Randall; Melissa W. Adkins; Bruce W. Banfield (Virus Genes, 2004)

Community preparedness for lava flows from Mauna Loa and Hualālai volcanoes, Kona, Hawai‘i - Chris E. Gregg; Bruce F. Houghton; Douglas Paton; Donald A. Swanson; David M. Johnston (Bulletin of Volcanology, 2004)

Preliminary climatology and improved modelling of south Indian Ocean and Southern Ocean mid‐latitude cyclones - Bruce W. Buckley; Lance M. Leslie (International Journal of Climatology, 2004)
The intense mid‐latitude cyclones that traverse the southern waters of the Indian Ocean, between South Africa and southwestern Western Australia, are among the strongest depressions found anywhere in the world, outside tropical waters. Near‐surface winds that exceed storm force (i.e. 24 m/s or 48 knots), and central pressures of 960 hPa and lower, are relatively common for these systems. They pose a constant threat to both open ocean and coastal shipping, and regularly generate severe weather over the populated southwestern corner of Australia. Large ocean waves and swell produce extensive coastal inundation and erosion. There were two main aims in this study. The first aim was to develop a preliminary climatology of these intense mid‐latitude cyclones, for the region 20–60 °S, 30–130 °E. The climatology, which is the first that we are aware of for this notoriously data‐sparse region, is based largely upon satellite observations, particularly scatterometer data, and is supplemented by ship, buoy and all available land observations. The climatology revealed that, historically, the frequency and intensity of the mid‐latitude cyclones in this domain have been significantly underestimated. This underestimation has resulted in analyses that have serious flaws, and the resultant operational forecasts provided to the duty forecasters in the regional forecast centre located in Perth, Western Australia, are of highly variable quality. A number of other climatological features of these storms are discussed in this article. The second aim was to identify the factors that can contribute to a significant improvement in model forecasts of these storms. So far, there have been very few studies of explosively developing cyclones over this part of the world. Results are presented here from a series of high‐resolution numerical simulations of an intense cool season Southern Ocean cyclone that developed in 2003, using the HIRES numerical weather prediction model developed by L.M. Leslie. Here, we examine the sensitivity of the cyclone predictions to both model resolution and the initial analyses. The predicted variables of most interest are the central pressure, maximum sustained near‐surface wind speeds, extent of storm‐force winds, and the horizontal and vertical structure of the storm. Increased detail in the initial state is provided mainly by the assimilation into the archived global operational analyses of high‐resolution satellite‐derived data, including QuikSCAT scatterometer winds and sea‐surface temperatures. The combination of increased horizontal and vertical model resolution, and improved initial model states, was found to produce numerical forecasts with significantly more accurate wind speeds than those obtained from the coarser resolution operational models, which also did not have the benefits of all the additional data. Finally, areas of future research are outlined, including coupling the HIRES atmospheric model with ocean and wave models, to improve forecasts of the sea state, including wind wave heights, swell and storm surges. Copyright © 2004 Royal Meteorological Society

Seasonal changes in the distribution and abundance of benthic invertebrates in six headwater streams in central Florida - Bruce C. Cowell; Amy H. Remley; Diane M. Lynch (Hydrobiologia, 2004)

High-resolution Numerical Simulation of Flow Through a Highly Sinuous River Reach - José F. Rodriguez; Fabián A. Bombardelli; Marcelo H. García; Kelly M. Frothingham; Bruce L. Rhoads; Jorge D. Abad (Water Resources Management, 2004)

Regionalization of methane emissions in the Amazon Basin with microwave remote sensing - John M. Melack; Laura L. Hess; Mary Gastil; Bruce R. Forsberg; Stephen K. Hamilton; Ivan B.T. Lima; Evlyn M.L.M. Novo (Global Change Biology, 2004)
Wetlands of the Amazon River basin are globally significant sources of atmospheric methane. Satellite remote sensing (passive and active microwave) of the temporally varying extent of inundation and vegetation was combined with field measurements to calculate regional rates of methane emission for Amazonian wetlands. Monthly inundation areas for the fringing floodplains of the mainstem Solimões/Amazon River were derived from analysis of the 37 GHz polarization difference observed by the Scanning Multichannel Microwave Radiometer from 1979 to 1987. L‐band synthetic aperture radar data (Japanese Earth Resources Satellite‐1) were used to determine inundation and wetland vegetation for the Amazon basin ( −1 , with a standard deviation (SD) of the mean of 0.3 Tg C yr −1 ; 67% of this range in uncertainty is owed to the range in rates of methane emission and 33% is owed to uncertainty in the areal estimates of inundation and vegetative cover. Methane emission from a 1.77 million square kilometers area in the central basin had a mean of 6.8 Tg C yr −1 with a SD of 1.3 Tg C yr −1 . If extrapolated to the whole basin below the 500 m contour, approximately 22 Tg C yr −1 is emitted; this mean flux has a greenhouse warming potential of about 0.5 Pg C as CO 2 . Improvement of these regional estimates will require many more field measurements of methane emission, further examination of remotely sensed data for types of wetlands not represented in the central basin, and process‐based models of methane production and emission.

Effect of sub-chronic hydrocortisone on responses to amphetamine in normal male volunteers - Stuart Watson; Allan H. Young; Andrea J. Hearn; Margaret S. Smith; Bruce M. Owen; Peter Gallagher (Psychopharmacology, 2004)

Growth autocorrelation and animal size variation - Masami Fujiwara; Bruce E. Kendall; Roger M. Nisbet (Ecology Letters, 2004)
It has long been recognized that variability in animal size is affected by how individual growth rate is autocorrelated in time. Earlier studies have attributed the mechanism generating the autocorrelation primarily to size‐dependent growth rate and autocorrelation in resource abundance. All of these studies have shown that positive autocorrelation in individual growth rate always translates into increased variability in size. We show that energy reserves in individuals induce growth autocorrelation by acting like a low pass filter between the resource and the internal energy that is available for metabolism, growth and reproduction. However, the reserve also reduces the variance in growth rate. Consequently, reserve‐induced growth autocorrelation has relatively little effect on size variability in the population, contradicting existing ideas about the relationship between the growth autocorrelation and size variability.

An Upwelling Event at Onondaga Lake, NY: Characterization, Impact and Recurrence* - Steven W. Effler; Bruce A. Wagner; Susan M. O'Donnell; David A. Matthews; David M. O'Donnell; Rakesh K. Gelda; Carol M. Matthews; Edwin A. Cowen (Hydrobiologia, 2004)

Reliability and validity of the Biodex system 3 pro isokinetic dynamometer velocity, torque and position measurements - Tamara C. Valovich-mcLeod; Sandra J. Shultz; Bruce M. Gansneder; David H. Perrin; Joshua M. Drouin (European Journal of Applied Physiology, 2004)

Thermodynamic and metabolic effects on the scaling of production and population energy use - S. K. Morgan Ernest; Brian J. Enquist; James H. Brown; Eric L. Charnov; James F. Gillooly; Van M. Savage; Ethan P. White; Felisa A. Smith; Elizabeth A. Hadly; John P. Haskell; S. Kathleen Lyons; Brian A. Maurer; et al. (Ecology Letters, 2003)
Ecosystem properties result in part from the characteristics of individual organisms. How these individual traits scale to impact ecosystem‐level processes is currently unclear. Because metabolism is a fundamental process underlying many individual‐ and population‐level variables, it provides a mechanism for linking individual characteristics with large‐scale processes. Here we use metabolism and ecosystem thermodynamics to scale from physiology to individual biomass production and population‐level energy use. Temperature‐corrected rates of individual‐level biomass production show the same body‐size dependence across a wide range of aerobic eukaryotes, from unicellular organisms to mammals and vascular plants. Population‐level energy use for both mammals and plants are strongly influenced by both metabolism and thermodynamic constraints on energy exchange between trophic levels. Our results show that because metabolism is a fundamental trait of organisms, it not only provides a link between individual‐ and ecosystem‐level processes, but can also highlight other important factors constraining ecological structure and dynamics.

Estimating cotton evapotranspiration crop coefficients with a multispectral vegetation index - Douglas J. Hunsaker; Paul J. Pinter; Edward M. Barnes; Bruce A. Kimball (Irrigation Science, 2003)

The Effects of Spatial Scale of Climate Scenarios on Economic Assessments: An Example from U.S. Agriculture - Richard M. Adams; Bruce A. McCarl; Linda O. Mearns (Climatic Change, 2003)

A new view of K+-induced contraction in rat aorta: the role of Ca2+ binding - Gennadi M. Kravtsov; Iain C. Bruce; Tak Ming Wong; Chiu-Yin Kwan (Pflügers Archiv - European Journal of Physiology, 2003)

Strong conservation of the human NF2 locus based on sequence comparison in five species - Caisa M. Hansson; Haider Ali; Carl E. G. Bruder; Ingegerd Fransson; Sindy Kluge; Bjrn Andersson; Bruce A. Roe; Uwe Menzel; Jan P. Dumanski (Mammalian Genome, 2003)

Hemocyte-mediated phagocytosis and melanization in the mosquito Armigeres subalbatus following immune challenge by bacteria - Julin F. Hillyer; Shelley L. Schmidt; Bruce M. Christensen (Cell and Tissue Research, 2003)

Mineral-chemical studies of metamorphosed hydrothermal alteration in the Kristineberg volcanogenic massive sulfide district, Sweden - Mark D. Hannington; Ingrid M. Kjarsgaard; Alan G. Galley; Bruce Taylor (Mineralium Deposita, 2003)

Early onset of virus infection and up-regulation of cytokines in mice treated with cadmium and manganese - Pankaj Seth; Mirza M. Husain; Pratibha Gupta; Bruce A. Schoneboom; Franziska B. Grieder; Haresh Mani; Radha K. Maheshwari (BioMetals, 2003)

Edaphic races and phylogenetic taxa in the Lasthenia californica complex (Asteraceae: Heliantheae): an hypothesis of parallel evolution - Nishanta Rajakaruna; Bruce G. Baldwin; Raymund Chan; Andrée M. Desrochers; Bruce A. Bohm; Jeannette Whitton (Molecular Ecology, 2003)
Lasthenia californica sensu Ornduff consists of two races that differ in their flavonoid pigments and edaphic tolerances. Recent phylogenetic studies of Lasthenia have revealed that members of L . californica sensu Ornduff belong to two phylogenetic species. The relationship of the edaphic races to these new species and to each other is the focus of this study. Characterization of flavonoid profiles and phylogenetic placement of 33 populations demonstrates that races and phylogenetic taxa are not concordant, suggesting that one or both edaphic races evolved in parallel in the two clades. We hypothesize an edaphically linked ecological role for flavonoid differences that first revealed the existence of two races.

Post‐Agricultural Succession in El Petén, Guatemala - Bruce G. Ferguson; John Vandermeer; Helda Morales; Daniel M. Griffith (Conservation Biology, 2003)
We compared post‐agricultural succession across the range of farming activities practiced in Guatemala's northern lowlands: agroforestry, swidden, ranching, and input‐intensive monocultures. At 10 sites over 13 to 40 months we assessed the following characteristics of trees and shrubs that were>1 cm diameter at breast height: height, basal‐area accumulation, recruitment of all individuals and fleshy‐fruited individuals, and accumulation of all species and fleshy‐fruited species. Succession, as measured by all these response variables except height, was dramatically faster on agroforestry and swidden sites than on pastures or input‐intensive monocultures. Overall recruitment was faster for swiddens than for agroforests, but other response variables did not differ significantly between the two treatments. Regression results suggest that initial ground cover by herbs inhibited recruitment of woody colonists. The significant positive coefficient for initial basal area and the significant negative coefficient for distance from forest for accumulation of both fleshy‐fruited individuals and species are probably explained by the behavioral responses of seed‐dispersing animals. Our results suggest that the conservation strategy of discouraging swidden agriculture in favor of sedentary, input‐intensive agriculture to relieve pressure on old‐growth forest may be counterproductive over the long term.

Minisatellite DNA profiling detects lineages and parentage in the endangered kakapo (Strigops habroptilus) despite low microsatellite DNA variation - Hilary C. Miller; David M. Lambert; Craig D. Millar; Bruce C. Robertson; Edward O. Minot (Conservation Genetics, 2003)

Plants that protect ecosystems: a survey from California - Bruce M. Pavlik (Biodiversity and Conservation, 2003)

Hillslope Nutrient Dynamics Following Upland Riparian Vegetation Disturbance - J. Alan Yeakley; David C. Coleman; Bruce L. Haines; Brian D. Kloeppel; Judy L. Meyer; Wayne T. Swank; Barry W. Argo; James M. Deal; Sharon F. Taylor (Ecosystems, 2003)

MyoD and myogenin protein expression in skeletal muscles of senile rats - Eduard I. Dedkov; Tatiana Y. Kostrominova; Andrei B. Borisov; Bruce M. Carlson (Cell and Tissue Research, 2003)

Biochemical composition of three algal species proposed as food for captive freshwater mussels - Catherine M. Gatenby; David M. Orcutt; Daniel A. Kreeger; Bruce C. Parker; Vannessa A. Jones; Richard J. Neves (Journal of Applied Phycology, 2003)

Managing Troubled Data: Coastal Data Partnerships Smooth Data Integration - Stephen S. Hale; Anne Hale Miglarese; M. Patricia Bradley; Thomas J. Belton; Larry D. Cooper; Michael T. Frame; Christopher A. Friel; Linda M. Harwell; Robert E. King; William K. Michener; David T. Nicolson; Bruce G. Peterjohn (Environmental Monitoring and Assessment, 2003)

Ancient DNA gives green light to Galápagos Land Iguana repatriation - Bruce V. Hofkin; April Wright; Jennifer Altenbach; Kornelia Rassmann; Heidi M. Snell; Robert D. Miller; Anne C. Stone; Howard L. Snell (Conservation Genetics, 2003)

Mathematical modeling of precipitationand dissolution reactions in microbiological systems - Bruce E. Rittmann; James E. Banaszak; Jeanne M. VanBriesen; Donald T. Reed (Biodegradation, 2002)

Top-down control in a detritus-based food web: fish, shredders, and leaf breakdown - Carl R. Ruetz; Raymond M. Newman; Bruce Vondracek (Oecologia, 2002)

Reproductive ecology and the persistence of an endangered plant - Tina M. Carlsen; Erin K. Espeland; Bruce M. Pavlik (Biodiversity and Conservation, 2002)

Nitric oxide decreases the sensitivity of pulmonary endothelial cells to LPS-induced apoptosis in a zinc-dependent fashion - Zi-Lue Tang; Karla J. Wasserloos; Xianghong Liu; Molly S. Stitt; Ian J. Reynolds; Bruce R. Pitt; Claudette M. St. Croix (Molecular and Cellular Biochemistry, 2002)

Characterization of hemocytes from the yellow fever mosquito, Aedes aegypti - Julián F. Hillyer; Bruce M. Christensen (Histochemistry and Cell Biology, 2002)

Improved PCR-based Assays for Pre-symptomatic Diagnosis of Light Leaf Spot and Determination of Mating Type of Pyrenopeziza Brassicae on Winter Oilseed Rape - Simon J. Foster; Alison M. Ashby; Bruce D.L. Fitt (European Journal of Plant Pathology, 2002)

Avidin Expressed in Transgenic Tobacco Leaves Confers Resistance to Two Noctuid Pests, Helicoverpa Armigera and Spodoptera Litura - Elisabeth P.J. Burgess; Louise A. Malone; John T. Christeller; Melissa T. Lester; Colleen Murray; Bruce A. Philip; Margaret M. Phung; Emma L. Tregidga (Transgenic Research, 2002)

The Expression of a Mammalian Proteinase Inhibitor, Bovine Spleen Trypsin Inhibitor in Tobacco and its Effects on Helicoverpa armigera Larvae - John T. Christeller; Elisabeth P.J. Burgess; Valentina Mett; Heather S. Gatehouse; Ngaire P. Markwick; Colleen Murray; Louise A. Malone; Michelle A. Wright; Bruce A. Philip; Dianne Watt; Laurence N. Gatehouse; Gáabor L. Lövei; et al. (Transgenic Research, 2002)

Cluster of pulmonary blastomycosis in a rural community: Evidence for multiple high-risk environmental foci following a sustained period of diminished precipitation - Mary E. Proctor; Bruce S. Klein; Jeffrey M. Jones; Jeffrey P. Davis (Mycopathologia, 2002)

Characterisation of Acid Mine Drainage Using a Combination of Hydrometric, Chemical and Isotopic Analyses, Mary Murphy Mine, Colorado - Jennifer M. Hazen; Mark W. Williams; Bruce Stover; Mike Wireman (Environmental Geochemistry and Health, 2002)

A Multiscale Conceptual Framework for Integrated Ecogeomorphological Research to Support Stream Naturalization in the Agricultural Midwest - Kelly M. Frothingham; Bruce L. Rhoads; Edwin E. Herricks (Environmental Management, 2002)

Elevated atmospheric CO 2 stimulates aboveground biomass in a fire‐regenerated scrub‐oak ecosystem - Paul Dijkstra; Graham Hymus; Debra Colavito; David A. Vieglais; Christina M. Cundari; David P. Johnson; Bruce A. Hungate; C. ROSS Hinkle; Bert G. Drake (Global Change Biology, 2002)
The effect of elevated atmospheric CO 2 concentration ( C a ) on the aboveground biomass of three oak species, Quercus myrtifolia , Q. geminata , and Q. chapmanii , was estimated nondestructively using allometric relationships between stem diameter and aboveground biomass after four years of experimental treatment in a naturally fire‐regenerated scrub‐oak ecosystem. After burning a stand of scrub‐oak vegetation, re‐growing plants were exposed to either current ambient (379 µL L −1 CO 2 ) or elevated (704 µL L −1 CO 2 ) C a in 16 open‐top chambers over a four‐year period, and measurements of stem diameter were carried out annually on all oak shoots within each chamber. Elevated C a significantly increased aboveground biomass, expressed either per unit ground area or per shoot; elevated C a had no effect on shoot density. The relative effect of elevated C a on aboveground biomass increased each year of the study from 44% (May 96–Jan 97), to 55% (Jan 97–Jan 98), 66% (Jan 98–Jan 99), and 75% (Jan 99–Jan 00). The effect of elevated C a was species specific: elevated C a significantly increased aboveground biomass of the dominant species, Q. myrtifolia , and tended to increase aboveground biomass of Q. chapmanii , but had no effect on aboveground biomass of the subdominant, Q. geminata . These results show that rising atmospheric CO 2 has the potential to stimulate aboveground biomass production in ecosystems dominated by woody species, and that species‐specific growth responses could, in the long term, alter the composition of the scrub‐oak community.

Seasonal changes in respiration of halophytes in salt playas in the Great Basin, U.S.A. - Lyneen C. Harris; Bilquees Gul; M. Ajmal Khan; Lee D. Hansen; Bruce N. Smith (Wetlands Ecology and Management, 2001)

Afforestation of bottomland hardwoods in the Lower Mississippi Alluvial Valley: Status and trends - Stephen H. Schoenholtz; Jeremy P. James; Richard M. Kaminski; Bruce D. Leopold; Andrew W. Ezell (Wetlands, 2001)

Temporal records of δ13C and δ15N in North Pacific pinnipeds: inferences regarding environmental change and diet - Amy C. Hirons; Donald M. Schell; Bruce P. Finney (Oecologia, 2001)

Noninvasive Measurement of Acceleration at the Knee Joint in Patients with Rheumatoid Arthritis and Spondyloarthropathy of the Knee - Narender P. Reddy; Bruce M. Rothschild; Eon Verrall; Anand Joshi (Annals of Biomedical Engineering, 2001)

Primary productivity of planet earth: biological determinants and physical constraints in terrestrial and aquatic habitats - Richard J. Geider; Evan H. Delucia; Paul G. Falkowski; Adrien C. Finzi; J. Philip Grime; John Grace; Todd M. Kana; Julie La Roche; Stephen P. Long; Bruce A. Osborne; Trevor Platt; I. Colin Prentice; et al. (Global Change Biology, 2001)

Development of a prototype reporter-based assay for the evaluation of gap junctional intercellular communication - Ann J. Barbier; Bruce M. Baron (Biotechnology Letters, 2001)

WAKs: cell wall-associated kinases linking the cytoplasm to the extracellular matrix - Catherine M. Anderson; Tanya A. Wagner; Mireille Perret; Zheng-Hui He; Deze He; Bruce D. Kohorn (Plant Molecular Biology, 2001)

A pear-derived kairomone with pheromonal potency that attracts male and female codling moth, Cydia pomonella (L.) - Douglas M. Light; Alan L. Knight; Clive A. Henrick; Dayananda Rajapaska; Bill Lingren; Joseph C. Dickens; Katherine M. Reynolds; Ronald G. Buttery; Gloria Merrill; James Roitman; Bruce C. Campbell (The Science of Nature, 2001)

Hepatic over-expression of peroxisome proliferator activated receptor γ2 in the ob/ob mouse model of non‐insulin dependent diabetes mellitus - Roshanak Rahimian; Esther MasihKhan; Maggie Lo; Cornelis van Breemen; Bruce M. McManus; Gregory P. Dubé (Molecular and Cellular Biochemistry, 2001)

Late Pleistocene and Holocene slip rate of the Northern Wadi Araba fault, Dead Sea Transform, Jordan - Tina M. Niemi; Hongwei Zhang; Mohammad Atallah; J. Bruce J. Harrison (Journal of Seismology, 2001)

Deficit irrigation strategies using midday stem water potential in prune - Bruce D. Lampinen; Kenneth A. Shackel; Stephen M. Southwick; William H. Olson (Irrigation Science, 2001)

A Stream Visual Assessment Protocol (SVAP) for Riparian Landowners - Ronald Bjorkland; Catherine M. Pringle; Bruce Newton (Environmental Monitoring and Assessment, 2001)

Economic Implications of Potential ENSO Frequency and Strength Shifts - Chi-Chung Chen; Bruce A. McCarl; Richard M. Adams (Climatic Change, 2001)

Developing an Ecosystem Perspective from Experimental Monitoring Programs: II. Ecophysiological Responses of a Rare Geothermal Grass to Soil Water - Bruce M. Pavlik (Environmental Management, 2001)

Developing an Ecosystem Perspective from Experimental Monitoring Programs: I. Demographic Responses of a Rare Geothermal Grass to Soil Temperature - BRUCE M. PAVLIK; ANDREW ENBERG (Environmental Management, 2001)

The Sydney Hailstorm of April 14, 1999: Synoptic descriptionand numerical simulation - Bruce W. Buckley; Yuqing Wang; Lance M. Leslie (Meteorology and Atmospheric Physics, 2001)

Population Pharmacokinetic Modeling of Steady State Carbamazepine Clearance in Children, Adolescents, and Adults - David M. Reith; Wayne D. Hooper; John Parke; Bruce Charles (Journal of Pharmacokinetics and Pharmacodynamics, 2001)

Accelerated HER-2 degradation enhanced ovarian tumor recognition by CTL. Implications for tumor immunogenicity - Agapito Castilleja; Nancy E. Ward; Catherine A. O'Brian; Bruce Swearingen; Eric Swan; Michal A. Gillogly; James L. Murray; Andrzej P. Kudelka; David M. Gershenson; Constantin G. Ioannides (Molecular and Cellular Biochemistry, 2001)

Influence of stream size on ammonium and suspended particulate nitrogen processing - Wilfred M. Wollheim; Bruce J. Peterson; Linda A. Deegan; John E. Hobbie; Beth Hooker; William B. Bowden; Kenneth J. Edwardson; David B. Arscott; Anne E. Hershey; Jacques Finlay (Limnology and Oceanography, 2001)
We used 15 NH 4 tracer additions to determine travel distances of ammonium (NH4 ) and suspended particulate organic nitrogen (SPON) in six streams ranging from second to fifth order located within a single watershed on the North Slope of Alaska. Based on the distribution of 15 N stored in stream bottom compartments (primary producers or grazers), we estimated NH 4 travel lengths. We used a two‐compartment model to estimate the travel length of SPON based on the distribution of source 15 N on the stream bottom and SPO 15 N in the water column. Both NH 4 and SPON travel lengths (S w and S p , respectively) increased with discharge primarily due to changes in depth and velocity. Variation in the vertical mass transfer coefficient ( v f ) of both NH 4 and SPON did occur among the streams but was not related to stream size and was relatively small compared to the change in physical characteristics. Thus, in the Kuparuk watershed, physical gradients outweighed biological or chemical changes as controls on NH 4 and SPON travel length. The one exception was the Kuparuk fertilized reach, where phosphorus fertilization greatly increased biological activity and NH 4 processing compared to unaltered streams. Longitudinal gradients in major biological driving variables such as litter inputs, debris dams, and shading are absent in the Arctic, perhaps explaining the relatively uniform NH 4 ‐ v f . Watersheds in other biomes may show differing degrees of physical versus biological/chemical controls. A conceptual model is presented for comparing the relative strength of these controls among different watersheds. Strong relationships between discharge and travel length should greatly aid development of watershed models of nutrient dynamics.

Structure and function of the soil microbial community in microhabitats of a heavy metal polluted soil - E. Kandeler; D. Tscherko; K. D. Bruce; M. Stemmer; P. J. Hobbs; R. D. Bardgett; W. Amelung (Biology and Fertility of Soils, 2000)

Renewal-Process Approximation of a Stochastic Threshold Model for Electrical Neural Stimulation - Ian C. Bruce; Laurence S. Irlicht; Mark W. White; Stephen J. O'leary; Graeme M. Clark (Journal of Computational Neuroscience, 2000)

A Landscape Ecology Assessment of the Tensas River Basin - Daniel T. Heggem; Curtis M. Edmonds; Anne C. Neale; Lee Bice; K. Bruce Jones (Environmental Monitoring and Assessment, 2000)

Modeling Runoff Response to Land Cover and Rainfall Spatial Variability in Semi-Arid Watersheds - Mariano Hernandez; Scott N. Miller; David C. Goodrich; Bruce F. Goff; William G. Kepner; Curtis M. Edmonds; K. Bruce Jones (Environmental Monitoring and Assessment, 2000)

Summary of the MAIA Working Conference - M. Patricia Bradley; Barbara S. Brown; Stephen S. Hale; Frederick W. Kutz; Ronald B. Landy; R. Shedlock; R. Mangold; Alvin Morris; Walter Galloway; Jeffrey S. Rosen; R. Pepino; Bruce Wiersma (Environmental Monitoring and Assessment, 2000)

Analysis of nitrogen cycling in a forest stream during autumn using a 15 N‐tracer addition - Jennifer L. Tank; Judy L. Meyer; Diane M. Sanzone; Patrick J. Mulholland; Jackson R. Webster; Bruce J. Peterson; Wilfred M. Wollheim; Norman E. Leonard (Limnology and Oceanography, 2000)
We added 15 NH 4 Cl over 6 weeks to Upper Ball Creek, a second‐order deciduous forest stream in the Appalachian Mountains, to follow the uptake, spiraling, and fate of nitrogen in a stream food web during autumn. A priori predictions of N flow and retention were made using a simple food web mass balance model. Values of δ 15 N were determined for stream water ammonium, nitrate, dissolved organic nitrogen, and various compartments of the food web over time and distance and then compared to model predictions. Ammonium uptake lengths were shortest at the beginning of the tracer addition (28 m) and increased through time (day 20 = 82 m, day 41 = 94 m), and ammonium residence time in stream water ranged from 4 min on day 0 to 15 min on day 41. Whole‐stream ammonium uptake rates, determined from the decline in 15 NH 4 in water over the stream reach, decreased from 191 mg N m −2 d −1 on day 0 to 83.2 mg N m −2 d −1 on day 41. Temporal trends in the NH 4 mass transfer coefficient ( ν f ) were similar to uptake rates; ν f was highest on day 0 (7.4 × 10 −4 m s −1 ) and lower on days 20 and 41 (2.7 and 2.8 × 10 −4 m s −1 , respectively). Rates of nitrification were estimated to be very low throughout the tracer addition and accounted for 15 NH 4 uptake on day 0. It appears that most of the N in epilithon was actively cycling based on comparisons of 15 N in stream water and biomass at the end of the experiment. In contrast, for allochthonous organic matter, we found that microbial 15 N represented 69% of the label in wood, 20% in leaves, and 31% in fine benthic organic matter (FBOM). Despite higher δ 15 N values in primary producers, 15 NH 4 uptake rates per unit stream bottom area were generally lower in epilithon compared to the detrital compartments, a result of the lower biomass of epilithon. Turnover times were similar for epilithon (47 d), leaves (38 d), and FBOM (53 d) based on the decline in 15 N tracer over the first 28 d after the addition stopped. Incorporation of 15 N varied among biomass compartments involved in ammonium uptake from water. Primary producers were more highly labeled than allochthonous organic matter. Epilithon δ 15 N values were higher than leaves or FBOM, appeared to reach isotopic equilibrium by day 42, and followed model‐predicted trends. The grazing mayfly Stenonema was more highly labeled than the epilithon, which suggests selective feeding or assimilation of the more highly labeled algal‐bacterial portion of the epilithon. Leaves had very low δ 15 N values, and δ 15 N values for the shredding stonefly Tallaperla were close to model predictions and followed labeling in leaves. Total retention of 15 N at the end of the experiment by the nine largest biomass compartments within the study reach accounted for only 12.3% of added 15 N, with leaves and FBOM representing the largest portions. Export of 15 N by suspended particulate and dissolved N accounted for an additional 11% and 30% of added 15 N, respectively. Results from the 15 N‐tracer addition in Upper Ball Creek demonstrate the high ammonium demand associated with microbes colonizing leaf detritus and the resultant linkage to invertebrate shredders. In Upper Ball Creek in autumn, spiraling of NH 4 is very tight, NH 4 residence time in water is short, and uptake rates are very high. Analyses of N spiraling in unimpacted streams provide an ecological foundation for assessment of spiraling in high‐N streams.

The effect of elevated atmospheric carbon dioxide levels on soil bacterial communities - K. D. Bruce; T. H. Jones; T. M. Bezemer; L. J. Thompson; D. A. Ritchie (Global Change Biology, 2000)
Summary The effect of elevated carbon dioxide levels on total bacterial communities was studied in a series of controlled and replicated model terrestrial ecosystems over a period of 38 weeks. The bacterial community was profiled using Denaturing Gradient Gel Electrophoresis (DGGE) analysis of bacterial 16S rRNA gene fragments amplified by the Polymerase Chain Reaction from DNA extracted directly from soil. Bacterial community DGGE profiles provided three major findings: (i) there was a high degree of profile similarity after ≈ 12 weeks (one plant generation); (ii) whilst overall DGGE profile was maintained over the 38 weeks (three plant generations), the banding patterns became more diverse with time; (iii) DGGE data provided no evidence for a shift in bacterial community structure resulting from exposure of the ecosystem to an increased atmospheric CO 2 level.

Sudden temperature changes in the Sydney Basin: climatology and case studies during the Olympic months of September and October - Bruce W. Buckley; Lance M. Leslie (International Journal of Climatology, 2000)

Sudden temperature changes in the Sydney Basin: climatology and case studies during the Olympic months of September and October - Bruce W. Buckley; Lance M. Leslie (International Journal of Climatology, 2000)

Microsatellite primers for the kakapo (Strigops habroptilus) and their utility in other parrots - Bruce C. Robertson; Edward O. Minot; David M. Lambert (Conservation Genetics, 2000)

Expression of the soybean (Kunitz) trypsin inhibitor in transgenic tobacco: Effects on larval development of Spodoptera litura - Michael T. McManus; E.P.J. Burgess; Bruce Philip; Lyn M. Watson; W.A. Laing; Christine R. Voisey; Derek W.R. White (Transgenic Research, 1999)

Transport and Metabolic Characterization of Caco-2 Cells Expressing CYP3A4 and CYP3A4 Plus Oxidoreductase - Ming Hu; Yiqi Li; Christine M. Davitt; Shiew-Mei Huang; Kenneth Thummel; Bruce W. Penman; Charles L. Crespi (Pharmaceutical Research, 1999)

Modeling speciation effects on biodegradation in mixed metal/chelate systems - Jeanne M. VanBriesen; Bruce E. Rittmann (Biodegradation, 1999)

Molecular sexing of individual kakapo, Strigops habroptilus Aves, from faeces - Bruce C. Robertson; Edward O. Minot; David M. Lambert (Molecular Ecology, 1999)

Spectral resolution of low-energy chlorophylls in Photosystem I of Synechocystis sp. PCC 6803 through direct excitation - Erin M. Gill; Bruce P. Wittmershaus (Photosynthesis Research, 1999)

Avocado shoot culture, plantlet development and net CO2 assimilation in an ambient and CO2 enhanced environment - Witjaksono; Bruce A. Schaffer; Angel M. Colls; Richard E. Litz; Pamela A. Moon (In Vitro Cellular & Developmental Biology - Plant, 1999)

Using chlorophyll a fluorescence to detect the onset of anthracene photoinduced toxicity in Lemna gibba, and the mitigating effects of a commercial humic acid - Robert W. Gensemer; D. George Dixon; Bruce M. Greenberg (Limnology and Oceanography, 1999)
The influence of a commercial humic acid (Aldrich; AHA) on the development of anthracene photoinduced toxicity to the duckweed Lemna gibba was examined using both room‐ and low‐temperature (77°K) chlorophyll fluorescence assays. Plants were exposed to 2 mg liter ‐1 anthracene both with and without 6.2 mg liter ‐1 of AHA and grown under either visible light or simulated solar radiation that mimics the natural abundance of UV radiation. Exposure periods ranged from 1 to 48 h to examine temporal changes in chlorophyll degradation and chlorophyll a fluorescence induction in response to these light and HA treatments. The onset of anthracene photoinduced toxicity followed a definite sequence; chlorophyll a fluorescence induction parameters (F v /F m , and t ½ ) responded earliest to anthracene exposure, with observable chlorophyll degradation requiring up to 24 to 48 h. Of these, t ½ was the most sensitive, with significant inhibition apparent within 1 h of exposure. Throughout the entire 48‐h exposure, 6.2 mg liter ‐1 AHA ameliorated the photoinduced toxicity of anthracene, in terms of both chlorophyll degradation and F v /F m inhibition. In contrast, AHA delayed the complete inhibition of t ½ by only 1 to 24 h rather than permanently protecting the plants from anthracene damage to PS2. This suggests that AHA may slow, but not prevent, the entrance of either intact anthracene or its photooxidized byproducts under these exposure conditions.

Identification of genes within the Krd deletion on mouse Chromosome 19 - Weizhen Ji; Bruce Herron; Julie M. Jones; Nancy A. Jenkins; Debra J. Gilbert; Neal G. Copeland; Richard Swank; Lorraine Flaherty; Miriam H. Meisler (Mammalian Genome, 1999)

Symposia lectures - F. Parak; A. Ostermann; G. U. Nienhaus; Nobuo Niimura; William A. Eaton; Stephen J. Hagen; Eric R. Henry; James Hofrichter; Gouri Jas; Lisa Lapidus; Victor Muñoz; Chih-chen Wang; et al. (Journal of Biosciences, 1999)

Practical Real-Time Computing System for Biomedical Experiment Interface - David J. Christini; Kenneth M. Stein; Steven M. Markowitz; Bruce B. Lerman (Annals of Biomedical Engineering, 1999)

Ancient latitudinal gradients of C 3 /C 4 grasses interpreted from stable isotopes of New World Pleistocene horse ( Equus ) teeth - Bruce J Macfadden; Thure E Cerling; John M Harris; José Prado (Global Ecology and Biogeography, 1999)
Carbon and oxygen isotopic data are reported from 116 Pleistocene Equus teeth from sixty‐six localities in the New World ranging from 68°N (Alaska, Canada) to 35°S (Argentina). Equus species have been predominantly grazers, and as such, carbon isotopic values of their tooth enamel provide evidence of the Pleistocene distribution of C 3 and C 4 grasses. The carbon data presented here indicate a gradient (δ 13 C range of 10 parts/mil) in the relative proportion of C 3 and C 4 grasses between high latitude and equatorial Equus samples. The largest amount of change from C 3 to C 4 grasses during the Pleistocene occurred in the mid‐latitudes between about 30 to 40°. The oxygen data, which vary proportionately with temperature, indicate a latitudinal gradient (δ 18 O range of 20 parts/mil) between high‐latitude and equatorial Equus samples. The basic pattern of latitudinal gradients of C 3 /C 4 grass distribution and temperature as interpreted from these Pleistocene data is similar to the modern‐day. The use of stable isotopes of fossil herbivore teeth represents a new means to interpret Pleistocene climates and terrestrial ecology.

Distribution of edaphic‐endemic butterflies in the Sierra Nevada of California - Bruce R. Gervais*; Arthur M. Shapiro (Global Ecology and Biogeography, 1999)
Five edaphically‐restricted or ‐endemic butterflies, mostly associated with serpentine, are shown to be distributed in the western foothills of the Sierra Nevada in addition to their previously documented areas of occupancy in the California North Coast Ranges. Two species are absolutely limited by the edaphic restriction of their host plants, while the other three seemingly are not. The controversies concerning the origins of serpentine endemism in plants apply to butterflies as well. Long‐term relictualism can presumably apply only at the metapopulation level, not the local population level, due to the frequency of fire in these habitats. Development and habitat‐conversion trends pose a high risk to the long‐term survival of these species in the Sierra Nevada.

Synthesis of an iron(II)-braced proline-II tripod protein - Bassam M. Nakhle; Tracie L. Vestal; Matthew J. Saderholm; Bruce W. Erickson (International Journal of Peptide Research and Therapeutics, 1999)

Engineering of betabellin 15D: Copper(II)-induced folding of a fibrillar β-sandwich protein - Amareth Lim; Philippe A. Guy; Alexander M. Makhov; Matthew J. Saderholm; Mathias Kroll; Yibing Yan; Robert J. Anderegg; Jack D. Griffith; Bruce W. Erickson (International Journal of Peptide Research and Therapeutics, 1999)

Effects of Thinning and Nitrogen Fertilization on Sugars and Terpenes in Douglas-Fir Vascular Tissues: Implications for Black Bear Foraging - Bruce A. Kimball; Eric C. Turnblom; Dale L. Nolte; Doreen L. Griffin; Richard M. Engeman (Forest Science, 1998)
The chemical constituents of coniferous vascular tissues play a role in bear forage selection. In particular, bear foraging preferences are related to the concentrations of simple sugars (nonstructural carbohydrates) and terpenes in the forage. Analyses of vascular tissue samples from trees collected in test plots indicated that both thinning and fertilization caused the sugar concentration of vascular tissues in the lower bole to increase. However, these treatments had no effect on the concentrations of hydrocarbon monoterpenes, oxygenated monoterpenes, or sesquiterpenes. These results may explain the observations that black bears prefer to forage in thinned and fertilized stands. For. Sci. 44(4):599-602.

Thyroid function in lead smelter workers: absence of subacute or cumulative effects with moderate lead burdens - Cynthia Schumacher; C. Andrew Brodkin; Bruce Alexander; Mark Cullen; Petrie M. Rainey; Chris van Netten; Elaine Faustman; Harvey Checkoway (International Archives of Occupational and Environmental Health, 1998)

Vertebrate Herbivory on Eucalyptus—Identification of Specific Feeding Deterrents for Common Ringtail Possums (Pseudocheirus peregrinus) by Bioassay-Guided Fractionation of Eucalyptus ovata Foliage - David M. Pass; William J. Foley; Bruce Bowden (Journal of Chemical Ecology, 1998)

Cocaine decreases relative cerebral blood volume in humans: a dynamic susceptibility contrast magnetic resonance imaging study - M. J. Kaufman; Jonathan M. Levin; Luis C. Maas; Stephanie L. Rose; Scott E. Lukas; Jack H. Mendelson; Bruce M. Cohen; Perry F. Renshaw (Psychopharmacology, 1998)

Sequence Comparison of Avian Infectious Bronchitis Virus S1 Glycoproteins of the Florida Serotype and Five Variant Isolates from Georgia and California - Kristi M. Moore; Joyce D. Bennett; Bruce S. Seal; Mark W. Jackwood (Virus Genes, 1998)

The Value of Improved ENSO Prediction to U.S. Agriculture - Andrew R. Solow; Richard F. Adams; Kelly J. Bryant; David M. Legler; James J. O'Brien; Bruce A. McCarl; William Nayda; Rodney Weiher (Climatic Change, 1998)

Quantitative reverse transcriptase PCR to gauge increased protease-activated receptor 1 (PAR-1) mRNA copy numbers in thewobbler mutant mouse - Raymundo M. Salcedo; Barry W. Festoff; Bruce A. Citron (Journal of Molecular Neuroscience, 1998)

Calcium mobilization and protease-activated receptor cleavage after thrombin stimulation in motor neurons - Irina V. Smirnova; Suzanne Vamos; Thomas Wiegmann; Bruce A. Citron; Paul M. Arnold; Barry W. Festoff (Journal of Molecular Neuroscience, 1998)

Effects of Plant Identity and Chemical Constituents on the Efficacy of a Baculovirus Against Heliothis virescens - Kelli Hoover; Julie L. Yee; Christine M. Schultz; David M. Rocke; Bruce D. Hammock; Sean S. Duffey (Journal of Chemical Ecology, 1998)

Use of competitive dead-end inhibitors to determine the chemical mechanism of action of yeast alcohol dehydrogenase - Vladimir Leskovac; Svetlana Trivić; Bruce M. Anderson (Molecular and Cellular Biochemistry, 1998)

A comparative analysis of nested subset patterns of species composition - David H. Wright; Bruce D. Patterson; Greg M. Mikkelson; Alan Cutler; Wirt Atmar (Oecologia, 1997)

Land use effects on habitat, water quality, periphyton, and benthic invertebrates in Waikato, New Zealand, hill‐country streams - John M. Quinn; A. Bryce Cooper; Robert J. Davies‐Colley; J. Christopher Rutherford; R. Bruce Williamson (New Zealand Journal of Marine and Freshwater Research, 1997)
Water quality, habitat, and biota were compared during spring amongst c. 100 m reaches on 11 streams draining pasture, native (podocarp‐broadleaf) forest, and exotic pine forest established on pasture 15 years previously. Differences were greatest between the pasture and native forest streams. Only 1–3% of incident light reached native and pine forest streams whereas 30% reached pasture streams. Pasture streams had 2.2°C higher mean temperature than the native streams, and 5‐fold higher nitrate, 30‐fold higher algal biomass, and 11‐fold higher gross photosynthesis. Native streams were 60% wider than pasture, with pine streams intermediate. Pine and pasture streams had 3‐fold higher suspended solids and fine sediment stored in the streambed than native streams. Woody debris volume was 17‐fold greater in pine than pasture streams, with native streams intermediate. Invertebrate taxa richness did not differ between land uses. Community composition differed most between pasture and native forest, with pine forest streams intermediate. Invertebrate densities were 3‐fold higher in pasture than native streams, mainly because of more chironomids and snails, but mayflies, stoneflies, and caddisflies densities were 2–3‐fold higher in forest streams than pasture.

Breeding Objective for Plantation Eucalypts Grown for Production of Kraft Pulp - Bruce L. Greaves; Nuno M. G. Borralho; Carolyn A. Raymond (Forest Science, 1997)
A long-term production function for unbleached eucalypt kraft pulp, incorporating all growing, harvesting, transport, and pulping costs, and variable capital and operating costs, was used to determine the economic importance of standing volume, basic density, pulp yield, and stem form. The value of each trait to breeding was defined as the relative improvement toward the objective (of minimizing total pulp cost) for a given selection intensity when selecting for each trait individually. For genetic parameters typical of eucalypts, and with the aid of simulated first-geneneration eucalypt populations, density and standing volume were the most important traits, providing the greatest savings in total pulp cost. Combined selection using density and volume provided 95% of the gains possible from an index involving all traits (density, volume, pulp yield, and form). Selection for pulp yield alone provided only 53% of the savings possible from selection for density, and improvement in stem form had negligible effect on total pulp cost. For. Sci. 43(4):465-472.

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Eighteen new polymorphic markers in the multiple endocrine neoplasia type 1 (MEN1) region - Pachiappan Manickam; Siradanahalli C. Guru; Larisa V. Debelenko; Sunita K. Agarwal; Shodimu-Emmanuel Olufemi; Jane M. Weisemann; Mark S. Boguski; Judy S. Crabtree; Yingping Wang; Bruce A. Roe; Irina A. Lubensky; Zhengping Zhuang; et al. (Human Genetics, 1997)

zrp2: a novel maize gene whose mRNA accumulates in the root cortex and mature stems - Bruce M. Held; Isaac John; Huiquing Wang; Lathika Moragoda; T. Shamala Tirimanne; Eve Syrkin Wurtele; James T. Colbert* (Plant Molecular Biology, 1997)

The impact of seasonal alteration in the lipid composition of broodstock diets on egg quality in the European sea bass - J. M. Navas; M. Bruce; M. Thrush; B. M. Farndale; N. Bromage; S. Zanuy; M. Carrillo; J. G. Bell; J. Ramos (Journal of Fish Biology, 1997)
Groups of European sea bass Dicentrarchus labrax L., broodstock were fed two pelleted, lipid‐enriched diets [maize oil, low essential fatty acid (EFA) or fish oil, high EFA]. Those fed the high EFA diet for 12 months or only during vitellogenesis (September to February) with the low EFA diet fed for the remaining 6 months, showed improved egg quality and higher hatching rates when compared to two groups fed the high EFA diet during either previtel‐logenesis (February to September) or the spawning period (February to April). The higher quality eggs contained higher levels of total n‐3 fatty acids, including increased levels of both docosahexaenoic acid (DHA) and eicosapaentaenoic acid (EPA). High levels of triacylglycerol (TAG) were linked with the poorer quality eggs from those groups fed the low EFA diet during the period of vitellogenesis. The present work identifies vitellogenesis as the period in the maturation during which EFA are incorporated most effectively into the developing oocytes.

On the Issue of Functional Form Choice in Hedonic Price Functions: Further Evidence - John M. Halstead; Rachel A. Bouvier; Bruce E. Hansen (Environmental Management, 1997)

Recurrent wavefront morphologies: A method for quantifying the complexity of epicardial activation patterns - Jack M. Rogers; Masahiro Usui; Bruce H. KenKnight; Raymond E. Ideker; William M. Smith (Annals of Biomedical Engineering, 1997)

A quantitative framework for analyzing epicardial activation patterns during ventricular fibrillation - Jack M. Rogers; Masahiro Usui; Bruce H. KenKnight; Raymond E. Ideker; William M. Smith (Annals of Biomedical Engineering, 1997)

Disruption of the phosphate-starvation response of oilseed rape suspension cells by the fungicide phosphonate - M. Christian Carswell; Bruce R. Grant; William C. Plaxton (Planta, 1997)

Disruption of the phosphate-starvation response of oilseed rape suspension cells by the fungicide phosphonate - M. Christian Carswell; Bruce R. Grant; William C. Plaxton (Planta, 1997)

A family exhibiting heteroplasmy in the human mitochondrial DNA control region reveals both somatic mosaicism and pronounced segregation of mitotypes - M. R. Wilson; Deborah Polanskey; Jeri Replogle; Joseph A. DiZinno; Bruce Budowle (Human Genetics, 1997)

A candidate model for angelman syndrome in the mouse - Bruce M. Cattanach; J. A. Barr; C. V. Beechey; J. Martin; J. Noebels; J. Jones (Mammalian Genome, 1997)

Regulation of MMP-9 (92 kDa type IV collagenase/gelatinase B) expression in stromal cells of human giant cell tumor of bone - Velidi H. Rao; Rakesh K. Singh; Julia A. Bridge; James R. Neff; G. Bradley Schaefer; Duane C. Delimont; Christopher M. Dunn; Warren G Sanger; Bruce A. Buehler; Raymond Sawaya; Garth L. Nicolson; Jasti S. Rao (Clinical & Experimental Metastasis, 1997)

The coleoptile chloroplast: Distinct distribution of xanthophyll cycle pigments, and enrichment in Photosystem II - Jianxin Zhu; Stephen M. Gómez; Bruce T. Mawson; Xiangqun Jin; Eduardo Zeiger (Photosynthesis Research, 1997)

Isolation of normal human colonic mucosa: Comparison of methods - David M. Wildrick; Richard Roll; Patrice Lointier; Belle Quintanilla; David H. Nichols; Bruce M. Boman (In Vitro Cellular & Developmental Biology - Animal, 1997)

Chemical contamination and associated liver diseases in two species of fish from San Francisco Bay and Bodega Bay - CARLA M. Stehr; MARK S. Myers; DOUGLAS G. BURROWS; MARGARET M. Krahn; JAMES P. Meador; BRUCE B. McCAIN; USHA Varanasi (Ecotoxicology, 1997)

Effects of ionizing radiation on the adhesive interaction of human tumor and endothelial cells in vitro - Mohammad F. Kiani; Bruce M. Fenton; Lee Ann Sporn; Dietmar W. Siemann (Clinical & Experimental Metastasis, 1997)

A comparison between computer modeled bioaerosol dispersion and a bioaerosol field spray event - Lisa M. Ganio; A. J. Mohr; Bruce Lighthart (Aerobiologia, 1995)

Noninvasive acceleration measurements to characterize knee arthritis and chondromalacia - Narender P. Reddy; Bruce M. Rothschild; Mita Mandal; Vineet Gupta; Srikanth Suryanarayanan (Annals of Biomedical Engineering, 1995)

Artificial wind-gust liberation of microbial bioaerosols previously deposited on plants - Bruce Lighthart; Brenda T. Shaffer; Balkumar Marthi; Lisa M. Ganio (Aerobiologia, 1993)

The amplitudes of unit events in Limulus photoreceptors are modulated from an input that resembles the overall response - Norberto M. Grzywacz; Peter Hillman; Bruce W. Knight (Biological Cybernetics, 1992)

Response transfer functions of Limulus ventral photoreceptors: interpretation in terms of transduction mechanisms - Norberto M. Grzywacz; Peter Hillman; Bruce W. Knight (Biological Cybernetics, 1992)

Process control with adaptive range coding - Bruce E. Rosen; James M. Goodwin; Jacques J. Vidal (Biological Cybernetics, 1992)

Dynamic response of naphthalene biodegradation in a continuous flow soil slurry reactor - Philip M. DiGrazia; J. M. Henry King; James W. Blackburn; Bruce A. Applegate; Paul R. Bienkowski; Barry L. Hilton; G. S. Sayler (Biodegradation, 1991)

Single-dose toxicokinetics ofN-nitrosomethylethylamine andN-nitrosomethyl (2,2,2-trideuterioethyl)amine in the rat - Anthony J. Streeter; Raymond W. Nims; Lucy M. Anderson; Young-Hun Heur; Eric von Hofe; Paul Kleihues; Victor C. Nelson; Bruce A. Mico; Larry K. Keefer (Archives of Toxicology, 1990)

Properties of the phosphate and phosphite transport systems of Phytophthora palmivora - Julia M. Griffith; Louise A. Akins; Bruce R. Grant (Archives of Microbiology, 1989)

Effect of phosphate on the toxicity of phosphite in Phytophthora palmivora - Julia M. Griffith; Robert H. Smillie; Julie O. Niere; Bruce R. Grant (Archives of Microbiology, 1989)

CO2 control of the respiratory system: Plant dynamics and stability analysis - Ahmed ElHefnawy; Gerald M. Saidel; Eugene N. Bruce (Annals of Biomedical Engineering, 1988)

Calcium control of differentiation in Phytophthora palmivora - Julia M. Griffith; Joanne R. Iser; Bruce R. Grant (Archives of Microbiology, 1988)

Effects of changes in pulmonary perfusion and surface area on endothelial ace activity - Bruce R. Pitt; George Lister; Paul Davies; Lynne M. Reid (Annals of Biomedical Engineering, 1987)

Purification and properties of arylsulfatase B from high- and low-activity mouse strains - William L. Daniel; Berthie M. Ruoff; D. Bruce Thompson; Julius B. Gore (Biochemical Genetics, 1985)

Purification and properties of arylsulfatase B from high- and low-activity mouse strains - William L. Daniel; Berthie M. Ruoff; D. Bruce Thompson; Julius B. Gore (Biochemical Genetics, 1985)

Genetic and physiological parameters associated with cadmium toxicity in Drosophila melanogaster - Nelwyn T. Christie; M. W. Williams; K. Bruce Jacobson (Biochemical Genetics, 1985)

Effects of petroleum on feeding and mortality of the American oyster - Bruce M. S. Mahoney; George S. Noyes (Archives of Environmental Contamination and Toxicology, 1982)

In situ nitrogen (C2H2) fixation in lakes of southern Victoria Land, Antarctica - F. C. Thomas Allnutt; Bruce C. Parker; Kenneth G. Seaburg; George M. Simmons (Aquatic Ecology, 1981)

Microcirculatory model relating geometrical variation to changes in pressure and flow rate - Bruce M. Fenton; B. W. Zweifach (Annals of Biomedical Engineering, 1981)

s of papers presented at the 63rd annual PAA meeting - Jose L. Rueda; Donald Berrios; W. R. Amoros; H. A. Mendoza; Jose Gil Archuleta; Gene D. Easton; C. R. Brown; Doug Bruce; Elsa Camadro; S. J. Peloquin; J. R. Davis; W. B. Jones; et al. (American Journal of Potato Research, 1979)

Nitrogenase activity in Rhodopseudomonas sulfidophila - Bruce C. Kelley; Yves Jouanneau; Paulette M. Vignais (Archives of Microbiology, 1979)

Age-related changes associated with the induction of o-pyrocatechuic acid carboxylyase in Aspergillus ornatus - Bruce M. Spiegelman; Bradner W. Coursen (Archives of Microbiology, 1975)